Report on the socioeconomic, humanitarian and human rights situation in the PalmaAfungi-Mocímboa area (Cabo Delgado) - Rufin, Jean-Christophe; Glowacki, Ingrid (Total Energies, 2023)
Patrick Pouyanné, Chairman and CEO of TotalEnergies, entrusted Jean-Christophe Rufin in December 2022, on behalf of the partners of the Mozambique LNG project, with an independent mission to assess the humanitarian situation in the province of Cabo Delgado where the project is located. Jean-Christophe Rufin, a recognized expert in the field humanitarian action and human rights, has carried out several investigation field trips in Mozambique. TotalEnergies publishes his report as well as the action plan decided by Mozambique LNG partners based on the recommendations of the report. The report recalls that the conflict in the province of Cabo Delgado has origins pre-dating the gas development projects and finds its roots in multiple factors not related to Mozambique LNG. It assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. The report assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. It notes an improved humanitarian situation in the north of Cabo Delgado, in particular with the return of the populations displaced by the conflict to the town of Palma and to a lesser degree to the town of Mocímboa da Praia. The report highlights the execution quality of the actions undertaken by Mozambique LNG and their positive impact on the living conditions of local population. However it recommends the establishment of a dedicated structure with increased resources to further expand these programs and to integrate them into an ambitious and sustainable strategy of local development covering the whole province, and not only guided by the security of the project site. Regarding the populations affected by the development of the Afungi industrial site, Jean-Christophe Rufin recommends several avenues of improvements to finalize in the best conditions the implementation of the resettlement plan and ensure the compensation of affected persons in accordance with the best practices. These improvements relate in particular to the update of the inventories of the affected persons’ assets, the payment timeline of compensations, the provision of agricultural land and the access to fishing areas.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; conflict / conflito; displaced communities / comunidades deslocadas; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; infrastructure - energy / infrastrutura - energia; natural resources - gas / recursos naturais - gás; private sector / setor privado; security / segurança; social action / ação social

Os espaços de participação e de exercício da cidadania, na voz de líderes associativos da província de Cabo Delgado - Feijó, João (Observador Rural, 2023)
O texto descreve os obstáculos históricos ao desenvolvimento de organizações da sociedade civil (OSC) em Moçambique, que conheceram um cenário mais acolhedor na Constituição de 1990. Mecanismos de apoio à sociedade civil capacitaram líderes locais, tornando-os melhor conhecedores de dispositivos legais, capazes de reunir evidências e de exercer impacto junto das populações. Contudo, as organizações enfrentaram problemas internos, relacionados com a ausência de recursos financeiros, com a capacitação dos seus membros e com problemas de transparência e rotatividade. O sistema de ensino desenvolve poucas competências de cidadania activa e o Estado desconfia de iniciativas de consciencialização das populações em direitos fundamentais ou em mecanismos de participação cívica. A manutenção de uma cultura política de súbdito foi funcional à penetração do grande capital na exploração de recursos naturais. As OSC enfrentam obstáculos à participação, relacionados com a forte politização da sociedade, com a desconfiança governamental em relação ao escrutínio público, proibição de manifestações públicas e receio das suas lideranças, particularmente após o início do conflito armado. A proliferação de conflitos nas áreas da indústria extractiva e a inexistência de canais formais de participação e de acesso à justiça foram agudizaram tensões, habilmente capitalizadas por grupos violentos. A guerra dispersou os membros de OSC que timidamente floresciam nos vários distritos, retirando-lhes capacidade organizativa, de advocacia e pressão social. A chegada de organizações humanitárias internacionais em resposta à emergência pouco incluiu as associações locais, reproduzindo relações assistencialistas e de dependência. O texto demonstra a urgência de identificação de líderes locais, (re)capacitação das OSC e criação de fóruns de participação social, invertendo a crença de que a violência constitui a forma possível e legítima de participação.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - portuguese / português; authority / autoridade; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; governance / governação

Spaces for participation and exercise of citizenship, in the voice of associative leaders in the province of Cabo Delgado - Feijó, João (Observador Rural, 2023)
The text describes the historical obstacles to the development of civil society organizations (CSOs) in Mozambique, which experienced a more welcoming scenario in the 1990 Constitution. Mechanisms to support civil society empowered local leaders, making them better knowledgeable of legal provisions, capable of gathering evidence and making an impact on the population. However, the organizations faced internal problems, related to the lack of financial resources, the training of their members and problems of transparency and turnover. The education system develops few competencies of active citizenship, and the State is distrustful of initiatives to raise the awareness of the populations on fundamental rights or on mechanisms of civic participation. The maintenance of a political culture of subject has been functional to the penetration of big capital in the exploitation of natural resources. CSOs face obstacles to participation, related to the strong politicization of society, government distrust of public scrutiny, prohibition of public demonstrations and fear of their leadership, particularly after the beginning of the armed conflict. The spread of conflicts in extractive industry areas and the absence of formal channels for participation and access to justice intensified tensions, which were skilfully capitalized on by violent groups. The war dispersed the members of CSOs that were timidly flourishing in the various districts, taking away their organizational, advocacy and social pressure capacity. The arrival of international humanitarian organisations in response to the emergency included local associations, reproducing relations of assistance and dependency. The text demonstrates the urgency of identifying local leaders, (re)empowering CSOs and creating forums for social participation, reversing the belief that violence constitutes the possible and legitimate form of participation.
Keywords: *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; conflict / conflito; extractive industries / indústrias extractivas; security / segurança

Grievance Redress Mechanisms in the Health Sector in Mozambique - POTENCIAR (POTENCIAR, 2023)
Context: This research stemmed from learning and changes that occurred in the intervention strategy and budget of the POTENCIAR programme. In consultations and meetings between the Programme Management Unit (UGP) and various actors operating in this area, POTENCIAR’s partners identified — in a participatory and inclusive manner — the issue of grievance redress mechanisms as a problem that they can intervene on within the context of Pro-Accountability Initiatives (PAIs). Taking this perspective , POTENCIAR conceived the present research on mechanisms for complaining about and denouncing poor standards in maternity services. Objectives: The objective of this study was to understand the complaints and grievances management system available to users in the health sector. The insights gained from this study will subsequently feed back into revision s to POTENCIAR’s theory of change and theory of action. The research included mapping the flow of the complaint channel ling process; identifying the motives, capacities, and opportunities for the health authorities to implement the system of mechanisms for redressing complaints; an analysis of how the perspectives of users are perceived, considered, and rejected by health authorities; and, finally, an analysis of the extent to which existing grievance mechanisms are used, including the opportunities, capacities, and motivations for using them.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; governance / governação; health / saúde; mecanismos de reclamação / grievance redress mechanisms

Maps of JICA Major Projects - JICA (Japan International Cooperation Agency (JICA), 2022)
Maps of JICA Major Projects
Keywords: #Map / Mapa; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

Against the Odds: Action for Empowerment and Accountability in Challenging Contexts - Anderson, Colin; Gaventa, John; Edwards, Jenny; Joshi, Anuradha; Nampoothiri, Niranjan; Wilson, Emilie (Institute of Development Studies, 2022)
How and under what conditions does citizen-led social and political action contribute to empowerment and accountability? What are the strategies used, and with what outcomes, especially in settings which are democratically weak, politically fragile and affected by legacies of violence and conflict? The A4EA programme has explored these questions in Mozambique, Myanmar, Nigeria and Pakistan over five years between 2016-2021. This paper presents the key findings and policy and practice implications from this research across the themes of space for citizen action; citizen-governance relations; women’s political participation and collective action; citizen-led strategies for empowerment and accountability; and enabling citizen action. It also shares important lessons drawn from A4EA experience on conducting and communicating research in complex political contexts like these, and for research consortia. Whilst the research conclusions are drawn from A4EA’s four focus countries, in an increasingly fragile and authoritarian world, the findings are becoming pertinent for more and more contexts across the globe.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; civic space / espaço cívico; civil society / sociedade civil; conflict / conflito; governance / governação; mobilization / mobilização

Futuro do trabalho(ador) em Moçambique na era digital - Ali, Rosimina; Muianga, Carlos (Desafios para Moçambique 2022, 2022)
O presente artigo analisou como as formas de trabalho mediadas digitalmente têm vindo a (re)formular e a mudar a natureza do trabalho e que questões isso coloca para o futuro do trabalho(ador). A análise da estrutura do mercado de trabalho em Moçambique sugeriu que qualquer tratamento da forma como o trabalho tem sido afectado por dinâmicas socioeconómicas específicas não deve ignorar a dinâmica mais ampla do funcionamento da economia e da organização do trabalho de uma forma mais geral. As conclusões preliminares sugerem que, sob o actual modo de organização da produção, prestação de serviços e trabalho na economia da plataforma digital, os padrões de informalidade existentes são reproduzidos, incluindo a correspondente irregularidade e instabilidade do trabalho que têm caracterizado o padrão de crescimento prevalecente em Moçambique. Argumenta-se que o futuro dos trabalhadores na era digital depende da organização mais alargada das estruturas e relações socioeconómicas que moldam a natureza do trabalho, organicamente integrado em processos de acumulação de capital à escala global. As nossas conclusões destacam que as estruturas produtivas de Moçambique não têm sido capazes de gerar trabalho decente. Verificou-se que, embora o trabalho mediado digitalmente seja uma dinâmica algo inovadora que necessita de ser mais bem pesquisada no contexto de Moçambique, deve ser entendido como parte de uma preocupação global relacionada com a natureza do trabalho e a estrutura dos mercados de trabalho no País. Deste modo, o trabalho mediado digitalmente é transversal a várias esferas dos mercados de trabalho e da economia em geral. Tem havido alguns desafios importantes, assim como a necessidade de reflectir sobre opções de políticas para melhor os enfrentar. Um desafio é a necessidade de conceptualizar o trabalho “gig” no contexto da economia moçambicana e das suas estruturas dominantes, especialmente a estrutura do mercado de trabalho. Outro desafio é como pesquisamos esta dinâmica num contexto em que os dados sistemáticos sobre os diferentes tipos de trabalhadores “gig” são praticamente inexistentes. Por outro lado, a organização colectiva é fundamental. Por último, mas não menos importante, coloca-se a necessidade de reflectir sobre as opções em termos de políticas destinadas a regulamentar a economia digital e a dinâmica que lhe está associada. Estas devem ser informadas por um entendimento claro sobre a dinâmica no trabalho, que só uma pesquisa aprofundada poderia proporcionar. Esta pesquisa sobre formas de trabalho mediadas digitalmente constitui apenas um ponto de partida. As conclusões sugeriram a necessidade de proceder à definição dessa regulamentação, uma vez que têm vindo a surgir novas manifestações de trabalho e tensões sobre as relações laborais. O quadro regulamentar deve tomar em consideração a organização e as relações laborais, bem como as condições sociais do trabalho amplamente criadas, reformuladas ou reproduzidas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; informality / informalidade; society / sociedade

Descolonizar os estudos urbanos em África. Conflitos armados e sustentabilidade urbana em Cabo Delgado. - Amaral, Silvia (Desafios para Moçambique 2022, 2022)
Este projecto de investigação pretende, assim, humildemente, contribuir para a descolonização dos estudos urbanos em Moçambique e Portugal, e para a transmutação dos traumas da guerra em oportunidades de desenvolvimento sustentável e prosperidade urbana.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; conflict / conflito; politics / política

A aceleração da financeirização: respostas das instituições financeiras internacionais à pandemia da COVID-19 em Moçambique - Barroso, Edgar; Castel-Branco, Ruth; Monjane, Boaventura (Desafios para Moçambique 2022, 2022)
O estudo conclui que as IFI aproveitaram este momento de crise para acelerar a financeirização do desenvolvimento; porém, também ilustra a resistência tanto do Estado como da sociedade civil. Se essas formas de resistência podem ou não contribuir para a construção de um Estado desenvolvido robusto depende do poder dos movimentos sociais globalizados para reaver o controlo e sacá-lo das garras do capitalismo financeiro. A primeira secção situa as respostas políticas do FMI e do Banco Mundial à pandemia da covid-19, numa análise histórica. Em 1987, Moçambique embarcou no seu primeiro programa de ajustamento estrutural, liberalizando a economia e eliminando impostos e tarifas; privatizando serviços públicos, empresas e activos; e desregulando as protecções sobre o consumidor e o trabalho. Essas medidas resultaram em cortes maciços na despesa, austeridade e dívida pública. A dívida de Moçambique foi subsequentemente cancelada, mas o FMI continuou a controlar a sua economia através do Instrumento de Apoio às Políticas. Actualmente, o Banco Mundial financia projectos que rondam os 3,7 mil milhões de dólares, ou o equivalente ao orçamento anual de Moçambique. O sector agrícola representa 14% do investimento e a protecção social, 9%. A segunda secção demonstra como o Banco Mundial utilizou a pandemia da covid-19 para impor a sua agenda de protecção social de duas formas importantes. Em primeiro lugar, substituindo a ideia de direitos universais por concessões altamente selectivas, de curto prazo e residuais ao arrepio das causas na raiz da pobreza e da desigualdade. Segundo argumentavam, as necessidades de longo prazo poderiam ser abordadas mais eficazmente pela diversificação dos meios de subsistência e a incorporação dos agregados familiares em situação de pobreza nos mercados financeiros através do crédito e da dívida. Em segundo lugar, tentando financiar as transferências monetárias pela externalização de sistemas de pagamento a prestadores de serviços financeiros. Embora esses condicionalismos se tenham revelado impossíveis de implementar e o Governo tenha acabado por ter de internalizar o programa, todo esse fiasco teve um custo material e humano considerável para os Moçambicanos. A terceira secção explora a abordagem do Banco Mundial à agricultura. Apesar de reconhecer que Moçambique tem uma lei da terra progressista, há muito que o Banco Mundial faz pressão pela colateralização da terra, a incorporação dos agricultores em cadeias produtos de base globais e a expansão da agricultura de grande escala, orientada para o mercado. Contudo, como ilustra a destruição da indústria do caju, os resultados são muitas vezes contraditórios. Recentemente, o Banco Mundial reorientou o seu apoio para a agricultura de pequena escala, adoptando o projecto Sustenta. O apoio aos pequenos proprietários e agricultores camponeses tem-se articulado com a privatização e a colateralização da terra. Com efeito, o lançamento do Sustenta coincide com a revisão da própria lei da terra que tinham elogiado como sendo progressista. Como conclui o capítulo, a pandemia criou uma oportunidade para o Banco Mundial acelerar a financeirização pela instrumentalização de empréstimos e subvenções. Isto levou à tentativa de expropriação do Estado moçambicano e da sua população através da externalização das funções do Estado e da privatização dos activos do Estado. Não obstante, os momentos de crise criam janelas de oportunidade para reorientar a política e a acção no sentido da construção de um estado desenvolvido. O capítulo insta a uma maior articulação entre os movimentos sociais - sejam eles sedeados no lar, no campo, na esquina, ou na fábrica - para unir forças contra a onda de expropriações, exploração e neoliberalismo tardio. Além disso, apela a que se reanime o movimento da justiça global para que seja possível responsabilizar as instituições financeiras internacionais
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19

Avaliação do Impacto da Subcomponente Subsídio para Crianças dos 0 aos 2. Componente de Subsídio para Criança do Programa Subsídio Social Básico na Província de Nampula em Moçambique Relatório da Pesquisa Final (24 meses) - Bonilla, Juan; Castro-Zarzur, Rosa; Seidenfeld, David; Peterman, Amber; Bruckauf, Zlata (American Institutes for Research e UNICEF, 2022)
Este relatório fornece os resultados finais da avaliação do Subsídio para Criança 0-2 de Moçambique. O Subsídio Criança 0-2 é um subcomponente do Programa de Subsídio Social Básico (PSSB), um programa nacional liderado pelo Ministério de Gênero, Criança e Ação Social (MGCAS). A avaliação coincide com a fase de arranque da intervenção, que aconteceu até 2021 em quatro distritos seleccionados da província de Nampula. A intervenção segue uma metodologia de 'dinheiro e cuidado' e inclui três componentes: (1) transferências de dinheiro, (2) um pacote de comunicação para a mudança social e de comportamentos (CMSC) com ênfase em nutrição (3) uma gestão de casos em temas de proteção social para os mais vulneráveis. A intervenção visa reduzir a pobreza e a vulnerabilidade social, fornecendo transferências em dinheiro para as cuidadoras principais de crianças pequenas com o objetivo geral de reduzir a pobreza, melhorar o bem-estar infantil e promover o acesso a serviços sociais básicos. Além disso, o componente de cuidados da intervenção pretende abordar a proteção complexa e inter-relacionada, bem como os riscos sociais, econômicos e de saúde, que as famílias-alvo enfrentam. A intervenção começou a ser implementada em setembro de 2018, e esta avaliação fornece evidências críticas sobre sua eficácia para informar a melhor forma de expansão da intervenção.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Ilha de Moçambique; GD - Lalaua; GD - Mogincual; GD - Nacala-a-Velha; GP - Nampula; L - portuguese / português; health - maternal and child / saúde - materno-infantil; social protection / proteção social

Mulheres lutando contra o HIV/SIDA: cuidadoras de Moçambique - Casimiro, Isabel Maria; Fauré, Yves-A; Tembe, Carlota Mondlane; Mutisse, Luisa Chicamisse (Desafios para Moçambique 2022, 2022)
Moçambique é um país caracterizado por índices elevados de pobreza onde a prevalência do Vírus da Imunodeficiência Humana (HIV)/Síndrome da Imunodeficiência Adquirida (SIDA) é muito alta e a taxa de incidência ainda preocupante, e cujos meios de combate à doença são limitados e dependem, em parte, da ajuda externa. A súbita emergência e rápida expansão da covid-19, a partir do início de 2020, teve um impacto negativo nas condições de tratamento das PVHIV, que, de certa forma, sofreram uma dupla aflição. Os serviços de saúde essenciais foram afectados - prevenção, diagnóstico, tratamento, cuidados paliativos e reabilitativos, etc. - com efeitos graves nos doentes mais vulneráveis (crianças, idosos, pessoas que vivem com doenças crónicas). Com este estudo, pretendemos apresentar os resultados obtidos através da divulgação das iniciativas das mulheres junto às autoridades públicas, instituições nacionais e internacionais, agências de cooperação bilaterais, associações e ONGs moçambicanas e estrangeiras dedicadas de uma ou de outra forma à luta contra o HIV/SIDA. Finalmente, almejamos examinar as condições em que estas iniciativas poderiam ser integradas ou pelo menos aproximadas das Unidades Sanitárias que trabalham na área do HIV/SIDA.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; gender / género; health / saúde; society / sociedade

Estudando a economia a partir da análise das crises - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2022, 2022)
Este artigo argumenta que as crises económicas do capitalismo, que reflectem as suas contradições estruturais fundamentais, oferecem interessantes ângulos de análise para explorar e entender as dinâmicas, os limites, os paradoxos, a evolução e as tensões inerentes ao sistema capitalista de acumulação. Estudar a economia a partir das crises oferece-nos uma lente para entender a lógica do funcionamento da economia nos seus limites e as ligações entre os seus vários ciclos, enquanto nos proporciona uma perspectiva histórica privilegiada sobre as opções para a superação do modo capitalista de produção. A forma como crises são estudadas - como eventos atípicos e isolados, falhas de mercado, erros de política, características orgânicas de um sector (por exemplo, a tendência do sector financeiro para a especulação) ou como elementos estruturais do sistema de acumulação de capital - esclarece-nos não só sobre a capacidade de as teorias económicas explicarem uma crise ou outra, mas sobre o entendimento que têm e a clareza que conseguem gerar e comunicar sobre o funcionamento do modo capitalista de produção. O artigo está organizado em três partes, nomeadamente uma discussão geral sobre as crises do capitalismo, uma reflexão histórica sobre as crises do sistema capitalista em Moçambique e conclusões sobre crises e a superação do capitalismo.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico

Desafios para Moçambique - 2022 - Castel-Branco, Carlos Nuno; Ali, Rosimina; Chichava, Sérgio; Forquilha, Salvador; Muianga, Carlos (Instituto de Estudos Sociais e Económicos, 2022)
PARTE I – POLÍTICA Dinâmicas da migração e o desenvolvimento da insurgência jihadista no Norte de Moçambique / Salvador Forquilha e João Pereira Descolonizar os estudos urbanos em África: conflitos armados e sustentabilidade urbana em Cabo Delgado / Sílvia Amaral O desafio moçambicano da laicidade / Severino Ngoenha Policiamento democrático – desafios de implementação em Moçambique. Uma análise detalhada da formação para a profissionalização / Tina Lorizzo e Vanja Petrovic Influência das respostas interinstitucionais coordenadas a emergências e desastres de saúde pública na resposta nacional à COVID-19 em Moçambique: estudo de caso / Celso Inguane e Victor Zimba Transição energética e engajamento público em Moçambique / Crescêncio Pereira, Euclides Gonçalves, Salvador Forquilha, Alexander Shankland e Patta Scott-Villiers PARTE II – ECONOMIA Estudando a economia a partir da análise das crises / Carlos Nuno Castel-Branco Financeirização, afunilamento da base produtiva e acumulação de capital em Moçambique / Carlos Nuno Castel-Branco e Diogo Maia Trabalho na agro-indústria e reprodução social do trabalho em Moçambique: constradições no sistema de acumulação actual / Rosimina Ali e Sara Stevano A expansão da produção agrícula capitalista e a reprodução social da força de trabalho rural: contradições dentro da lógica de acumulação de capital em Moçambique / Carlos Muianga Classe política e processos de acumulação dinâmicos em torno do projecto sino-moçambicano de arroz no Baixo Limpopo 2005-2014 / Ana Sofia Ganho Crise ambiental, acumulação e subsidtência rural: extractivismo e a nova fronteira de acumulação no contexto de mudanças climáticas / Natacha Bruna PARTE III – SOCIEDADE Futuro do trabalho(ador) em Moçambique na era digital / Rosimina Ali e Carlos Muianga A questão do género sob uma perspectiva histórica, nas políticas de saúde em Moçambique / Carmeliza Rosário Mulheres a lutar contra o HIV/Sida: cuidadoras em Moçambique / Isabel Maria Casimiro, Yves-A. Fauré, Carlota Mondlane Tembe e Luisa Chicamisse Mutisse O conflito capital-vida e a precarização da vida: notas sobre o trabalho de cuidados domiciliários em Moçambique / Paula Machava Sujeitos sem história? Cidadania sexual, temporalidade e os desafios da pós-colonialidade em Moçambique / Caio Simões de Araújo PARTE IV – MOÇAMBIQUE NO MUNDO A aceleração da financeirização: respostas das instituições financeiras internacionais à pandemia da COVID-19 em Moçambique / Edgar Barroso, Ruth Castel-Branco e Boaventura Monjane Alternativas africanas ao desenvolvimento e ao impacto da globalização – notas críticas soltas / Carlos Nuno Castel-Branco Políticas fundiárias na África Ocidental: experiências recentes de participação de organizações camponesas e relevância para Moçambique / Thomas Patriota Crise económica, instituições financeiras e oportunidades para a mudança: o caso da BVM, Moçambique / Salim Cripton Valá As relações Brasil-África no contexto da pandemia da COVID-19: o caso de Moçambique / Danilo Marcondes
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Financeirização, especialização funilada da produção e acumulação e capital em Moçambique - Castel-Branco, Carlos Nuno; Maia, Diogo (Desafios para Moçambique 2022, 2022)
Neste artigo, define-se financeirização não só como um aumento na expansão e extensão do sector financeiro, mas também como a crescente subordinação da acumulação real — a produção de mais-valia — à acumulação fictícia, que consiste em créditos em papel sobre mais-valia ainda por produzir, mas comercializados nos mercados financeiros, assim como a integração da acumulação real no domínio do capital portador de juros (Ashman, Fine e Newman, 2011; Hilferding, 1981 [1910]; Marx, 1981 [1894]). Bens reais, tais como a terra, mineração, concessões, recursos energéticos e infra-estruturas, foram transformados em activos financeiros e negociados nos mercados financeiros globais, tornando, assim, a propriedade e o controlo sobre os recursos, a par da expectativa de futuros fluxos de receitas provenientes da extracção e da liberdade de os comercializar, o verdadeiro negócio no cerne da economia extractiva (Castel-Branco, 2017). As empresas investem nestes recursos e utilizam-nos como um instrumento destinado a mobilizar o financiamento internacional, e o Estado adapta as suas prioridades políticas com vista a garantir e proteger a propriedade privada e o controlo privado dos recursos estratégicos, promover expectativas e transacções de créditos sobre recursos e absorver custos e resgatar corporações — ou promete fazê-lo — caso os seus planos de negócios fracassem (Castel-Branco, 2020, 2022). Nestas condições, as empresas privadas seguem uma via de desenvolvimento afunilada, centrada nos sectores de elevadas rendas — o núcleo minero-energético da economia e das finanças —, num contexto em que a capacidade do Estado para alcançar objectivos sociais e económicos mais abrangentes é significativamente reduzida. Entretanto, os mercados financeiros internacionais expandem a sua influência na estratégia e políticas das empresas públicas e privadas, incentivando a dívida em períodos de expansão e aproveitando-se das crises de dívida que se seguem — especulando contra as expectativas de incumprimento, aumentando as taxas de prémio sobre a dívida e sobre novos empréstimos e trocando a dívida por activos reais e por benefícios em matéria de políticas (ibid.). O artigo está organizado em três secções principais: a análise da transição da acumulação de capital centrada no Estado para a acumulação privada, que explora as ligações entre a primarização e a financeirização em Moçambique, e como estas se relacionam com a criação, no passado, da burguesia nacional segundo uma via neoliberal. As duas últimas secções oferecem uma análise mais específica e evidência empírica da dinâmica da primarização e da financeirização, discutindo como se relacionam com as vagas de expropriação do Estado, que foram respostas políticas e estratégicas públicas às tensões e crises que surgiram na busca de criar a burguesia nacional-capitalista.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico

Sujeitos sem história? Cidadania sexual, temporalidade e os desafios da pós-colonialidade em Moçambique - de Araújo, Caio Simões (Desafios para Moçambique 2022, 2022)
Neste artigo, propus-me analisar a complexa relação entre histórias queer, direitos sexuais e a promessa de cidadania num contexto pós-colonial. Demonstrei que, embora muitas vezes imaginados como “sujeitos sem história”, fora do tempo, as pessoas LGBTQIA+ encontram estratégias de inclusão no tempo da nação, reivindicando um lugar de pertença e formulando, ao mesmo tempo, uma crítica da sua marginalização na sociedade e na política moçambicanas, onde não conseguem exercer a sua cidadania plena. Argumentei, também, que regimes temporais são cruciais nas dinâmicas de exclusão e inclusão LGBTQIA+ no País, particularmente nas práticas governativas temporais - na crono-política - utilizadas pelo estado no constante adiamento da efectivação dos direitos deste grupo minoritário. Ao situar, neste debate contemporâneo, as questões da produção da história e da possibilidade (e talvez a necessidade) de uma memória queer plural, pretendi explorar o que Maria Paula Meneses identificou como «a vida pública [da história]», sobretudo «numa situação em que as memórias do passado presente são matéria de contestação na vida quotidiana» (2020, p. 15). Neste sentido, mais do que procurar uma versão mais rigorosa, porque inclusiva, de uma história oficial, o meu objectivo foi o de abrir um caminho para «uma história construída num diálogo entre o passado, o presente, e o futuro» (ibidem). Um futuro pelo qual muitos dos sujeitos LGBTQIA+ esperam, e trabalham activamente para construir. Como afirmou Liloca, uma activista trans: «a mensagem que eu deixo: vamos continuar a trabalhar, a lutar pelo nosso Moçambique, pelo nosso reconhecimento [como] comunidade LGBT.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; society / sociedade

Dinâmicas da migração e o desenvolvimento da insurgência jihadista no norte de Moçambique - Forquilha, Salvador; Pereira, João (Desafios para Moçambique 2022, 2022)
As dinâmicas locais de migração, no Norte de Moçambique, constituem um ponto de entrada importante para a análise e compreensão do estabelecimento e desenvolvimento da insurgência jihadista. Com efeito, neste artigo, com base num extenso trabalho de campo, procurámos mostrar que o avanço da insurgência se serviu de dinâmicas de migração externa e interna, que alimentaram uma vasta rede de recrutamento dos Al-Shabaab, facilitada essencialmente pela porosidade da fronteira com a Tanzânia e pela actividade pesqueira nas ilhas ao largo de Cabo Delgado. A porosidade da fronteira com a Tanzânia está na origem de um forte movimento migratório associado ao garimpo ilegal. Esse movimento trouxe para o território nacional, por um lado, indivíduos ligados a círculos salafistas provenientes particularmente da Tanzânia, Quénia e Somália e, por outro lado, indivíduos provenientes de zonas de guerra (particularmente da República Democrática do Congo), com experiência militar e envolvidos em redes de crime organizado. Por sua vez, o movimento migratório interno de pescadores artesanais do litoral de Nampula para Cabo Delgado ganhou um novo impulso no contexto da insurgência no Norte de Moçambique, transformando-se num elemento importante no processo de recrutamento para as fileiras dos Al-Shabaab.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; displaced communities / comunidades deslocadas; politics / política

Relatório de Avaliação Intermédia da Estratégia Nacional de Segurança Social Básica (2016 2024) - Hodges, Anthony; Bischler, Jana (Oxford Policy Management, 2022)
O sub sistema de segurança social básica em Moçambique entrou numa nova fase do seu desenvolvimento, na sequência da aprovação da segunda Estratégia Nacional de Segurança Social Básica (ENSSB II), em 2016. A Estratégia articula-se em torno da missão global de construir um sistema de segurança social básica em prol da população pobre e vulnerável e de contribuir para o desenvolvimento humano e social do país. É estruturada em quatro eixos sendo eles: o reforço do consumo, da autonomia e da resiliência (Eixo 1), a melhoria da nutrição e do acesso aos serviços de saúde e de educação (Eixo 2), a prevenção e a resposta aos riscos sociais (Eixo 3) e o desenvolvimento institucional (Eixo 4). Na sequência foi elaborado um Plano Operacional para o período inicial de implementação de 2016 até 2019. A ENSSB II prevê a realização de uma avaliação intermédia. A avaliação foi realizada pela Oxford Policy Manangement (OPM) e financiada pela Organização Internacional do Trabalho (OIT) entre Junho e Outubro de 2021, com o objectivo de avaliar o grau da sua implementação durante o período de cinco anos compreendido entre Fevereiro de 2016 e Janeiro de 2021. Visava igualmente avaliar a eficiência e a eficácia na implementação da mesma, os factores que afectaram o grau e o ritmo de implementação e a sua relevância contínua num contexto em evolução. A realização da avaliação centrou-se numa fase de pesquisa com três componentes: uma revisão da literatura, entrevistas com os actores-chave ao nível central e missões aos níveis provincial e distrital para entrevistas e reuniões com grupos focais, incluindo com os beneficiários, nas províncias de Nampula, Sofala e Gaza, e abrangendo dois distritos (um urbano e outro rural) em cada província.
Keywords: #Policy Document / Documento de Política; *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - evaluation / avaliação; Social security / segurança social; social protection / proteção social

Manual de procedimentos do Programa Subsídio Social Básico (PSSB) - INAS - Instituto Nacional de Acção Social (2022)
O presente Manual de Procedimentos (MdP) apresenta a definição do Programa Subsídio Social Básico (PSSB), os objectivos, as componentes, os grupos-alvo, os critérios de elegibilidade, os tipos de benefícios, os mecanismos e frequência de pagamentos, a permanência de beneficiários no programa e formas de saída, a transferência de beneficiários entre componentes do programa, bem como o seu ciclo operacional. Para além dos Guiões práticos que oferecem descrições detalhadas de cada processo a ser desenvolvido por todos os actores da implementação do PSSB, o Manual tem como objectivo orientar aos intervenientes e uniformizar os procedimentos a adoptar na implementação do PSSB.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental

Influência das repostas interinstitucionais coordenadas a emergências e desastres de saúde pública na resposta nacional à COVID-19 em Moçambique: Estudo de caso. - Inguane, Celso; Zimba, Victor (Desafios para Moçambique 2022, 2022)
Moçambique articulou oportunamente uma resposta nacional coordenada à covid-19, com um comando claro dos níveis mais altos do Governo central, inicialmente conceptualizada pelo sector da saúde. A resposta seguiu um modelo aparentemente híbrido, baseado numa resposta humanitária rápida usada para enfrentar calamidades naturais e numa abordagem de saúde global usada para responder a eventos de saúde pública. Estas abordagens foram institucionalizadas no País ao longo de duas décadas, caracterizadas pela liderança normativa do Governo moçambicano e apoio logístico, técnico e financeiro dos parceiros de cooperação internacional, com participação limitada da sociedade civil e do empresariado local em processos de tomada de decisão sobre a concepção e implementação da resposta. Este padrão de participação ficou evidente no primeiro ano da resposta à covid-19, em Moçambique. Contudo, foi também notado como padrão da resposta global a surtos de doenças infecciosas, epidemias e pandemias entre 2002 e 2015, nos seguintes termos: «muito frequentemente, o envolvimento da comunidade tem sido uma consideração a posteriori — pouco investigado, deixado para depois até que seja demasiado tarde e implementado atabalhoadamente” (Sands, Mundaca-Shah, & Dzau, 2016). O primeiro ano da resposta à covid-19, em Moçambique, revelou igualmente a presença generalizada de múltiplos mecanismos de coordenação, profundamente permeados por competições institucionais, incluindo a coexistência de múltiplos sistemas de informação em saúde, de repositórios e protocolos que não alimentavam a rotina do sistema de informação em saúde de modo que informasse uma resposta eficaz e coordenada à covid-19. Atender a tais multiplicidades requer energia e recursos que se desviavam da gestão eficaz da resposta nacional à covid-19. A dispersa legislação nacional sobre saúde pública, que não tomou em conta as necessidades de quarentena e outras restrições ao movimento de pessoas exigidas pela resposta à covid-19, agravou estas multiplicidades. O vácuo que essa escassez criou foi preenchido por uma profusão legislativa, produzida no âmbito de um Estado de Emergência, eventualmente substituído por um Estado de Calamidade Pública. Tal contribuiu para restrições ao espaço cívico (Pereira, Forquilha, & Shankland, 2021), justificadas por lógicas de governação da saúde pública. Assim, o modelo utilizado para a coordenação do primeiro ano da resposta nacional à covid-19, em Moçambique, salienta a importância de uma complexa combinação de influências sociopolíticas e de saúde pública que moldam as respostas nacionais a emergências e desastres de saúde pública no País. Tais influências incluem a exposição a pandemias nos últimos anos (Tsuei, 2020), exposição a desastres naturais a longo-prazo (Moore, Eng, & Daniel, 2003) Mozambique suffered its worst flooding in almost 50 years: 699 people died and hundreds of thousands were displaced. Over 49 countries and 30 international non-governmental organisations provided humanitarian assistance. Coordination of disaster assistance is critical for effective humanitarian aid operations, but limited attention has been directed toward evaluating the system-wide structure of inter-organisational coordination during humanitarian operations. Network analysis methods were used to examine the structure of interorganisational relations among 65 non-governmental organisations (NGOs e a interesses institucionais locais e globais (Fassin, 2012), incluindo a secundarização do envolvimento comunitário, notado com um padrão global (Sands, Mundaca-Shah, & Dzau, 2016) também documentados em países de língua oficial portuguesa (LEIASS, 2020).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; politics / política

Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Polliciamento democrático: Desafios de implementação em Moçambique. Uma análise detalhada da formação para a profissionalização - Lorizzo, Tina; Petrovic, Vanja (Desafios para Moçambique 2022, 2022)
Moçambique introduziu um sistema democrático de governação após as primeiras eleições, em 1994. Antes disso, uma guerra civil de quase duas décadas teve um impacto devastador nas infra-estruturas, na economia, e num estado já por si fraco. A democracia, como disse Baker, teve de ser construída do zero e o policiamento precisou de ser completamente reformado e reorganizado, devido à sua natureza militar e organização durante os anos de conflito (Baker, 2003). Este artigo baseia-se no quadro conceptual de policiamento democrático desenvolvido por Muntingh et al. para compreender melhor o estado do policiamento em Moçambique e identificar os principais desafios para o policiamento democrático (Muntingh et al., 2021). Segundo Muntingh et al., (2021), o policiamento democrático refere-se à obediência da polícia ao Estado de direito, à responsabilização da polícia e à justiça processual por parte da polícia ao serviço do público. Muntingh et al. (2021), identificaram nove dimensões do policiamento democrático. Essas dimensões (Figura 1) estão relacionadas e, em certa medida, têm relações causais e hierárquicas, embora na prática sejam frequentemente interligadas e interdependentes e também se reforçam mutuamente. Como se mostra na Figura 1, as nove dimensões são: 1) conhecimento, 2) eficácia e eficiência, 3) ética e responsabilidade, 4) direitos humanos, 5) agente da polícia como cidadão, 6) objectividade, 7) responsabilidade, 8) empatia e 9) confiança. As primeiras cinco dimensões representam variáveis de entrada, o que significa que estas são aquelas cujos valores afectam a saída ou a resposta do sistema. Se forem positivas, produzirão resultados positivos (de objectividade, capacidade de resposta e empatia), conduzindo ao produto final, que é a confiança na polícia. O resultado procurado, que está directamente ligado à confiança, é a legitimidade da polícia. Portanto, o policiamento democrático corresponde à visão da polícia como uma autoridade legítima, que trabalha para um bem comum (Muntingh et al., 2021). A antítese do policiamento democrático é o policiamento de regime. Este protege governos e não cidadãos, responde a um regime e não ao povo, controla e não protege as populações, protege um grupo dominante e permanece separado das comunidades (ibid.). Com base neste quadro teórico, as reformas legais e o apoio obtido dos doadores são analisados abaixo com referência específica sobre a confiança da população na polícia e sobre as questões recorrentes pelas quais a Polícia tem sido criticada por organizações internacionais e nacionais.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; politics / política; security / segurança

O conflito capital-vida e a precarização da vida: notas sobre o trabalho de cuidados dominiliários em Maputo - Machava, Paula (Desafios para Moçambique 2022, 2022)
Numa sociedade que atravessa e é atravessada por várias crises (económica, climática, social, só para citar algumas), onde as mulheres, apesar de serem constitucionalmente iguais aos homens, continuam a ser as que menos privilégios têm, as que mais sofrem de várias formas de violência, são constantemente vitimizadas, são as menos alfabetizadas; neste capítulo, pretendo, a partir da noção de cuidados (Carrasco, 1991; Cunha, 2021; Orozco, 2012) analisar com as cuidadoras domiciliárias assalariadas da cidade de Maputo o paradigma económico neoliberal vigente em Moçambique. Embora ao longo do texto fale mais na primeira pessoa do singular, este texto resulta de uma co-autoria com as cuidadoras. Privadas do domínio da escrita, deram o seu contributo contando as suas experiências, existências, vivências enquanto mulheres e trabalhadoras de cuidados em Maputo. Ao fazê-lo, deram vida à oralidade, uma das principais características das sociedades africanas que a moderna ciência ocidental sempre tentou combater. Herdamos de um processo histórico de quase 500 anos uma visão colonial, capitalista e heteropatriarcal, que não só categoriza e hierarquiza os trabalhos, mas também exclui da acumulação outras economias que mesmo não produzindo directamente o lucro são essenciais para a produção e manutenção capitalista, porque geram, alimentam e cuidam da vida que serve ao processo de acumulação. Para desenvolver o assunto que me proponho abordar, divido o texto em três partes que se complementam. Na primeira, procuro explicitar, de forma breve, os conceitos em uso no texto. Na segunda, lanço um olhar feminista sobre o neoliberalismo em Moçambique, explorando o conflito entre a busca desmedida pelo lucro (suas manifestações, configurações, consequências) e os cuidados com a vida das moçambicanas e dos moçambicanos. Na terceira, analiso como o conflito afecta o trabalho de cuidados e, na quarta e última parte, apresento os anseios e sugestões das cuidadoras para uma vida cuidada e bem vivida.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; society / sociedade

As relações Brasil-África no contexto da pandemia da COVID-19. Cooperação com Moçambique - Marcondes, Danilo (Desafios para Moçambique 2022, 2022)
A pandemia da covid-19 rapidamente se impôs como um dos principais, se não o principal, tema de política internacional, no período entre 2020 e 2022. A pandemia exacerbou desafios já encontrados pela comunidade internacional, como as restrições de mobilidade, assim como o acesso desigual a medicamentos e vacinas. Em certos contextos autoritários, as iniciativas de lockdown e distanciamento também foram mobilizadas para restringir as liberdades civis e de organização política. Certas respostas à pandemia também reforçaram o populismo com a adopção de um discurso negacionista, anti ciência e contrário a instituições multilaterais como a Organização Mundial de Saúde (OMS). O relacionamento entre o Brasil e o continente africano, no contexto da covid-19, precisa ser entendido a partir desses desafios e dos impactos que os mesmos deixaram na política internacional. No mesmo período, em Janeiro de 2022, o início do mandato brasileiro como membro nãopermanente do Conselho de Segurança das Nações Unidas (CSNU) também reforça os laços e interesses mútuos de cooperação entre o Brasil e o continente africano. Historicamente, a presença do Brasil no CSNU, principalmente no período do imediato pós-Guerra Fria, foi utilizada a favor dos países africanos parceiros, principalmente Angola e Moçambique. Em contrapartida, a maioria dos países africanos, em especial os países lusófonos, votam recorrentemente a favor das candidaturas brasileiras ao CSNU (Ministério das Relações Exteriores, 2021a). De forma a contribuir para uma melhor compreensão das dinâmicas apresentadas acima, o presente capítulo está dividido nas seguintes secções: uma análise geral sobre o acompanhamento da evolução da pandemia da covid no continente africano por parte dos diplomatas brasileiros, seguida de uma discussão sobre a cooperação brasileira no context da pandemia, e de uma secção sobre a covid-19 e as relações Brasil-Moçambique. O capítulo termina com a apresentação da conclusão. A pesquisa é beneficiada pelo acesso à documentação diplomática brasileira disponível via legislação brasileira de acesso à informação. Os documentos diplomáticos consultados incluem mensagens trocadas entre as diferentes embaixadas brasileiras, em especial a Embaixada do Brasil em Maputo-Brasemb Maputo, localizadas no continente africano e a Secretaria de Estado das Relações Exteriores (SERE), em Brasília.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; south-south cooperation / cooperação sul-sul

O desafio moçambicano da laicidade - Ngoenha, Severino (Desafios para Moçambique 2022, 2022)
Urgem quatro acções para afirmar a laicidade e atenuar o fenómeno do extremismo no Norte de Moçambique: A) As madrassas não podem substituir a escola pública, e o trabalho religioso que nelas se realiza tem de ser vigiado pelo Estado para que não se transformem em centros de propagação de ódio e de contravalores, contrários à tolerância e ao nosso viver em comum. B) O Estado tem de saber quem são os líderes religiosos, qual é a sua formação ideológica e as tendências religiosas que defendem. A termo, deveria criar condições para que a formação teológica dos líderes se faça em Moçambique e nas universidades públicas — o que já acontece em outros países, nomeadamente na Alemanha e na França — para se certificar de uma adequação entre o ensino religioso e os valores da moçambicanidade. C) Contra a propaganda agressiva e extremista que se abate sobre as populações por via das redes sociais, o Estado deveria usar a televisão e as redes nacionais e regionais da rádio, vocacionados ao serviço público, para educação cívica constante sobre a laicidade, sublinhar repetidamente a necessidade do respeito pela vida comum, a tolerância, o que podia ser feito em colaboração com os Alimos, hoje presentes em todo o País. D) Por fim, urge a necessidade da presença do Estado nos lugares de conflito que, apesar de necessários, não se reduza aos polícias e militares. A melhor maneira de aproximar o Estado das populações seria transferir alguns poderes de soberania (com tudo o que acarretam consigo) para outras zonas do País, o que diminuiria o sentimento de ausência de Estado que favorece, sobremaneira, a penetração de toda a sorte de gangsters económicos, políticos e religiosos. Mas parece que a síndrome do Maputo-centrismo pesa excessivamente sobre as nossas lideranças políticas, independentemente da proveniência ou das reivindicações de origem e pertença… Contudo, a construção da laicidade é um processo a infieri que só se pode realizar através de uma colaboração activa entre todos aqueles — muçulmanos, cristãos, agnósticos, ateus — que acreditam e estão prontos a militar e defender os valores do pluralismo e da unidade — acima de todas as diferenças — sobre o qual está fundado, desde os primórdios, o nosso ideal de moçambicanidade
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; politics / política

Políticas fundiárias na África Ocidental. Experiências recentes de participação de organizações camponesas e relevância para Moçambique - Patriota, Thomas C (Desafios para Moçambique 2022, 2022)
Este artigo examinou processos participativos de política fundiária rural em que uma organização agrária regional, a ROPPA, visou abordar ao menos três desafios interrelacionados: i) a regulação da posse e das transferências de terra como parte de estratégias articuladas de integração regional; ii) esforços para assegurar a distribuição de terras através do reconhecimento formal e actualização das formas colectivas de posse da terra; iii) a garantia de formas de governança participativa da terra por meio de amplas consultas ao nível local vinculadas a processos de formulação de políticas ao nível nacional.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura

Transição energética e engajamento público em Moçambique - Pereira, Crescêncio; Gonçalves, Euclides; Forquilha, Salvador (Desafios para Moçambique 2022, 2022)
Este estudo mostrou que, para serem analiticamente mais produtivos, os conceitos de circulação global, como o de transição energética, precisam ser adaptados para dar conta de realidades específicas num mundo que, historicamente, tem produzido relações desiguais. No caso de Moçambique, a estratégia para a transição energética passa pela exploração do gás natural, mas esta abordagem tem como limitação as características da indústria extractiva que produz poucas oportunidades de desenvolvimento ao nível local e tem o potencial de produzir impactos ambientais e sociais nefastos. Pressupostos de noções como engajamento público ou participação pública devem também ter em conta os contextos onde são introduzidas, de forma inseri-las nas dinâmicas de poder local e capitalizá-las com as experiências positivas existentes. No caso de Moçambique, foi demonstrado que qualquer entendimento ou estratégia para um engajamento público para uma transição energética deve considerar os níveis de abertura do espaço cívico, das capacidades dos cidadãos e das organizações da sociedade civil, e de pobreza energética nas regiões de extracção de recursos naturais. Em regiões como o Norte de Moçambique, onde níveis baixos de cobertura da rede de energia eléctrica se combinam com múltiplas formas de pobreza, os cidadãos colocam os problemas associados à transição energética em segundo plano em favor das necessidades relativas ao desenvolvimento local. Este estudo sobre transição energética e engajamento público em Moçambique mostrou os desafios que os intervenientes do subsector do petróleo e gás têm para mobilizar e expandir o espaço de debate público sobre formas de avançar no processo de transição energética em Moçambique. Da experiência de engajamento público existente, identificámos os três principais espaços de interacção ao nível internacional, nacional/central e ao nível local. Estes espaços de engajamento seguem dinâmicas mais ou menos autónomas e com poucas interligações. Experiências de engajamento público de Moçambique e outras partes do mundo mostram que as estratégias com maior nível de sucesso reconhecem a necessidade de articulação entre o Governo, as organizações da sociedade civil e a responsabilidade social das empresas para garantir o envolvimento das comunidades, além das convencionais consultas que são realizadas em exercícios para a mitigação dos impactos dos projectos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; natural resources / recursos naturais; politics / política

A questão do género sob uma perspectiva histórica, nas políticas de saúde em Moçambique - Rosário, Carmeliza (Desafios para Moçambique 2022, 2022)
O presente capítulo é baseado numa revisão histórica das políticas sociais desenvolvidas em Moçambique. Dentre as políticas sociais do País, a saúde tem sido consistentemente um dos sectores privilegiados. Já durante o tempo colonial, apesar das políticas discriminatórias entre a população indígena e a colonial, a saúde sempre figurou como preocupação governativa, particularmente em benefício das populações trabalhadoras assalariadas, em detrimento das não assalariadas. Além disso, os aspectos discriminatórios estendiam-se também à priorização dos homens como força laboral e à visão das mulheres e crianças como dependentes, criando inclusivamente benefícios maiores para homens casados e cimentando a perspectiva do homem como provedor. Na análise que se segue, apresenta-se o percurso legislativo do sector de saúde e os ideais preconizados nesta legislação, com particular atenção para a mulher e a sua consideração na mesma. De seguida, apresenta-se a desconexão estrutural que se tem verificado, em relação aos ideais preconizados. Por fim, apresentam-se exemplos sobre como as políticas de outros sectores podem afectar o sector da saúde e produzir efeitos transformadores incluindo de impacto para a equidade de género. Para tal, argumenta-se que, pese embora os desafios que o País enfrenta, de crises recorrentes, falta de recursos e dependência pela ajuda externa, é necessário determinar o tipo de Estado que se quer, social ou mercantilista. Deve ainda ultrapassar-se a visão limitada da saúde da mulher relacionada com sexualidade e reprodução e do papel do homem na saúde como condutor ou repressor dessas funções da mulher.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; society / sociedade

Classes of working women in Mozambique: an integrated framework to understand working lives - Stevano, Sara (Review of International Political Economy, 2022)
Feminist political economy has illuminated the gendered dimensions of the globalisation of production. Whilst this literature provides essential insights on gendered exploitation in export-oriented industries, women’s work in localised labour markets in the Global South remains underexplored. This paper seeks to address this gap by putting into dialogue three bodies of literature – feminist political economy of globalisation, political economy of development in southern Africa and the social reproduction of the everyday. It proposes an integrated conceptual framework to analyse women’s working lives and applies it to northern Mozambique. It makes two key findings. First, the lives of those working in localised labour markets are shaped by global capitalism through extreme fragmentation of labour regimes forcing people into multiple precarious forms of work – a process that entails the appropriation of women’s productive and reproductive labour. Second, the imperatives of social reproduction shape employment trajectories and expose differentiation among working women, seen for example through gendered constraints to mobility, care obligations and contributions to ceremonies. The implications are that the analysis of women’s working lives needs to capture three key aspects: social differentiation among working women, temporal and spatial dynamics of the everyday and the centrality of the reproduction of the social.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; gender / género; labour regimes / regimes de trabalho; social protection / proteção social; social reproduction / reprodução social

Crise económica, instituições financeiras e oportunidades para a mudança: o caso da BVM, Moçambique - Valá, Salim Cripton (Desafios para Moçambique 2022, 2022)
Com este artigo pretende analisar-se a crise económica no País, como ela afectou as instituições financeiras, em particular a BVM, e a oportunidade de mudança que comporta para ampliar o escopo da BVM e o seu impacto no sistema financeiro e na economia moçambicana. Procurar-se-á compreender, especificamente: i) como se manifestou a crise económica, quais os seus efeitos, e como isso impactou no sistema financeiro, no mercado de capitais e no desempenho da BVM; ii) o percurso e desempenho institucional da BVM e aferir até que ponto está a cumprir com os objectivos que ditaram a sua criação; iii) de que forma a crise económica pode favorecer a introdução de mudanças e reformas nas instituições financeiras, e mais particularmente no mercado de capitais e na BVM, e; iv) apresentar as medidas e reformas a introduzir para incrementar o desempenho e o impacto do mercado de capitais e da BVM na dinamização do sistema financeiro e da economia moçambicana. Este documento parte do pressuposto de que momentos de crise económica, como o que se vive actualmente, são também oportunidades para encetar mudanças e reformas que contribuam para melhorar o desempenho, ampliar o impacto e garantir a sustentabilidade do mercado de capitais e da BVM, e as acções já em curso para inverterem a tendência económica prevalecente, porque são insuficientes e de alcance limitado, devem ser prosseguidas com vigor, arrojo e sentido inovativo, devendo igualmente ser diversificadas, aprofundadas e ser mais abrangentes.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico

Getting Real about Unknowns in Complex Policy Work - Andrews, Matt (Research on Improving Systems of Education (RISE), 2021)
As with all public policy work, education policies are demanding. Policy workers need to ‘know’ a lot—about the problems they are addressing, the people who need to be engaged, the promises they can make in response, the context they are working in, and the processes they will follow to implement. Most policy workers answer questions about such issues within the structures of plan and control processes used to devise budgets and projects. These structures limit their knowledge gathering, organization and sense-making activities to up-front planning activities, and even though sophisticated tools like Theories of Change suggest planners ‘know’ all that is needed for policy success, they often do not. Policies are often fraught with ‘unknowns’ that cannot be captured in passive planning processes and thus repeatedly undermine even the best laid plans. Through a novel strategy that asks how much one knows about the answers to 25 essential policy questions, and an application to recent education policy interventions in Mozambique, this paper shows that it is possible to get real about unknowns in policy work. Just recognizing these unknowns exist—and understanding why they do and what kind of challenge they pose to policy workers—can help promote a more modest and realistic approach to doing complex policy work.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); education / educação; government policy / politica governamental

Monitoria comunitária independente ao PASD-PE COVID-19. Segunda Fase - Maputo e Namaacha - Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS) (Plataforma da Sociedade Civil Moçambicana para a Protecção Social (PSC-PS), 2021)
Os principais resultados da monitoria realizada em Montepuez destacaram a necessidade de: • Fortalecimento de mecanismos comunitários de participação e reforço do diálogo social entre comunidades e governo local; • Maior apropriação dos programas de protecção social básica por parte das comunidades e a necessidade de atribuir mais voz e protagonismo dos beneficiários sobre os serviços sociais prestados a nível destes programas; • Melhor comunicação e disseminação de informação estratégica sobre os programas de protecção social junto às comunidades, incluindo mais clareza sobre critérios de elegibilidade, valor dos benefícios, periodicidade e duração; • Maior mobilização social com vista a promover comunidades mais informadas e capacitadas para reivindicar os seus direitos sociais básicos; • Reforço de mecanismos de reclamações e queixas (clareza sobre como acessá-los); • Maior apoio para facilitação do acesso dos beneficiários aos pagamentos, em particular aqueles que precisam de auxílio para utilização dos telefones a partir dos quais recebem seus benefícios; • Ampliação dos métodos de pagamento para facilitar o acesso dos beneficiários às transferências.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Could Mozambique become a hydrogen hub? - Hanlon, Joseph (Mozambique News Reports & Clippings, 2021)
The proposal for the Mphanda Nkuwa dam 60 km downstream from Cahora Bassa, and using the same water to generate more electricity, is back on the table. The dam has been proposed since the colonial era, but there has never been a market for the electricity. Producing hydrogen would be the perfect market. In this special issue, we look at Mphanda Kkuwa and the potential for hydrogen.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GP - Tete; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

The role of integrated community case management projects in strengthening health systems: case study analysis in Ethiopia, Malawi and Mozambique - Story, William T; Pritchard, Susannah; Hejna, Emily; Olivas, Elijah; Sarriot, Eric (Health Policy and Planning, 2021)
Integrated community case management (iCCM) has now been implemented at scale globally. Literature to-date has focused primarily on the effectiveness of iCCM and the systems conditions required to sustain iCCM. In this study, we sought to explore opportunities taken and lost for strengthening health systems through successive iCCM programmes. We employed a systematic, embedded, multiple case study design for three countries—Ethiopia, Malawi and Mozambique—where Save the Children implemented iCCM programmes between 2009 and 2017. We used textual analysis to code 62 project documents on nine categories of functions of health systems using NVivo 11.0. The document review was supplemented by four key informant interviews. This study makes important contributions to the theoretical understanding of the role of projects in health systems strengthening by not only documenting evidence of systems strengthening in multi-year iCCM projects, but also emphasizing important deﬁciencies in systems strengthening efforts. Projects operated on a spectrum, ranging from gap-ﬁlling interventions, to support, to actual strengthening. While there were natural limits to the inﬂuence of a project on the health system, all successive projects found constructive opportunities to try to strengthen systems. Alignment with the Ministry of Health was not always static and simple, and ministries themselves have shown pluralism in their perspectives and orientations. We conclude that systems strengthening remains ‘everybody’s business’ and places demands for realism and transparency on government and the development architecture. While mid-size projects have limited decision space, there is value in better deﬁning where systems strengthening contributions can actually be made. Furthermore, systems strengthening is not solely about macro-level changes, as operational and efﬁciency gains at meso and micro levels can have value to the system. Claims of ‘systems strengthening’ are, however, bounded within the quality of evaluation and learning investments.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; health / saúde

Agrarian Change in Northern Mozambique: A ‘New’ Dimension of Research in Light of the Conflict and Violence in Cabo Delgado? - Muianga, Carlos (Informação sobre Desenvolvimento, Instituições e Análise Social, 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Transformação Agrária No Norte De Moçambique: Uma “Nova” Dimensão De Pesquisa À Luz Do Conflito E Violência Em Cabo Delgado? - Muianga, Carlos (Informação sobre Desenvolvimento, Instituições e Análise Social, 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Stemming the Insurrection in Mozambique’s Cabo Delgado (Africa Report N°303, 2021)
Principal Findings What’s new? Militant attacks and security force operations in Mozambique’s Cabo Delgado province have claimed nearly 3,000 lives, while displacing hundreds of thousands of people. Insecurity has prompted the suspension of a massive gas project. The Islamic State (ISIS) claims ties to the insurrection. Southern African governments are lobbying to send troops. Why did it happen? Mozambican militants have been motivated by grievances against a state that they see as delivering little for them, despite the development of major mineral and hydrocarbon deposits. Tanzanians and other foreigners have joined up, fuelling the insurrection. The country’s historically weak security forces have been unable to stem the onslaught. Why does it matter? Unaddressed, the insurrection could spread further, threatening national stability just as Mozambique is fulfilling a peace deal with the country’s main opposition group and heading into national elections in 2024. It could worsen instability along East Africa’s coast and present ISIS with a new front to exploit. What should be done? Maputo should accept targeted assistance for security operations to contain the insurrection, and avoid a heavy external deployment that could lead to a quagmire. Authorities should deploy aid to build trust with locals and open dialogue with militants. Regional governments should redouble law enforcement efforts to block transnational jihadist involvement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Conter a Insurreição em Cabo Delgado, Moçambique - International Crisis Group (Relatório África, 2021)
O que há de novo? Os ataques de militantes e as operações das forças de segurança na província moçambicana de Cabo Delgado já custaram praticamente 3000 vidas e deslocaram centenas de milhares de pessoas. A insegurança levou à suspensão de um gigantesco projeto de gás. O Estado Islâmico (ISIS) reivindica laços com a insurreição. Os governos do Sul de Africa estão a exercer pressão para o envio de tropas. Porque aconteceu? Os militantes moçambicanos foram motivados pelo descontentamento em relação a um estado que, do seu ponto de vista, pouco fez por eles, apesar do desenvolvimento de depósitos minerais e de hidrocarbonetos significativos. Tanzanianos e outros estrangeiros juntaram-se, alimentando a insurreição. As forças de segurança, historicamente fracas, foram incapazes de conter a ofensiva. Porque importa? Se não for tratada, a insurreição pode vir a alastrar-se, ameaçando a estabilidade nacional enquanto Moçambique está a alcançar um acordo de paz com o principal grupo de oposição do país e antes das eleições nacionais de 2024. A instabilidade ao longo da costa de Africa Oriental poderia piorar e fornecer ao ISIS uma nova frente a explorar. O que deve ser feito? Maputo deveria aceitar uma assistência direcionada para suas operações de segurança, a fim de conter a insurreição, e evitar uma mobilização externa forte, que poderia levar a uma estagnação. As autoridades deveriam fornecer assistência para construir uma relação de confiança com os habitantes locais e um diálogo aberto com os militantes. Os governos regionais deveriam redobrar seus esforços em matéria de aplicação da lei para impedir a implicação jihadista transnacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; innovation / inovação

Situação humanitária em Cabo Delgado: milhares de deslocados continuam sem assistência e apoio do Governo e das agências internacionais - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Mais de 30.500 pessoas que abandonaram as suas casas devido aos ataques terroristas na vila de Palma em Março último continuam a enfrentar dificuldades de alimentação e de abrigo nos centros de acolhimento. A maioria está no centro de trânsito de Pemba e outros nos campos de deslocados de Metuge. A Matriz de Monitoria de Deslocamentos da Organização Internacional para as Migrações (OIM) continua a registar a chegada diária de deslocados que fogem da insegurança no norte de Cabo Delgado. As autoridades governamentais e as agências humanitárias interromperam, há mais de um mês, as operações de salvamento de pessoas que estão concentradas na vila de reassentamento de Quitunda, a menos de 30 quilómetros da vila de Palma. Devido à insegurança, as agências humanitárias não estão a prestar apoio a milhares de pessoas que estão em Quitunda, nas proximidades do acampamento de Afungi.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Jovens de Gaza defendem que novo instrumento deve desburocratizar a obtenção de DUAT e combater a expropriação de terras pelas elites - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Falando em representação da Governadora da Província de Gaza, a Directora Provincial de Cultura e Turismo denunciou o velho problema de usurpação e acumulação de terra para fins de especulação latifundiária. Trata-se de uma prática comum em Moçambique em que as elites económicas e políticas se apropriam de terras valiosas e ficam à espera do melhor momento para fazer a transacção, preferencialmente com o capital estrangeiro. A representante da Governadora de Gaza disse que esta prática prejudica mais as mulheres que vivem nas zonas rurais por constituírem o grupo que mais usa a terra para a actividade agrícola. A Directora Provincial de Cultura e Turismo em Gaza saudou a iniciativa do CDD de auscultar a juventude sobre a revisão da Política Nacional de Terras, defendendo que, sendo a maioria da população, os jovens devem se apropriar do debate para influenciar a concepção de futuros instrumentos políticos e legais sobre o uso de terras.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Gaza; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

Jovens de Inhambane defendem que futura legislação deve estabelecer um prazo de até 15 dias para resposta ao pedido do DUAT - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Depois da cerimónia inaugural de quinta-feira na Província de Gaza, ontem, sexta-feira, 07 de Maio, foi a vez de Inhambane acolher o debate público no âmbito da auscultação de jovens sobre a revisão da Política Nacional de Terras. Falando na abertura da cerimónia, o Director dos Serviços Provinciais do Ambiente, em representação da Secretária de Estado da Província de Inhambane, defendeu que um dos desafios que a Inhambane enfrenta é o aumento do número de população perante um recurso terra que não é renovável, aliado aos desafios decorrentes das mudanças climáticas que demandam uma compensação da biodiversidade. O Director dos Serviços Provinciais do Ambiente de Inhambane falou também da emergência dos megaprojectos que, para o seu desenvolvimento, precisam do recurso terra. “A iniciativa do CDD de auscultar jovens sobre a revisão da Política Nacional de Terras constitui uma exaltação da cidadania. Todos nós, como moçambicanos, nas nossas comunidades, organizações, temos esta ímpar oportunidade de participar no melhoramento da nossa política de terras”.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; GP - Inhambane; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra; youth / juventude

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Rural Observer, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Provision and access to health services in Mozambique: An exploratory study on accountability and relations between health providers and users in Monapo district - Gonçalves, Euclides (POTENCIAR Programme, 2021)
This exploratory research set out to survey possible points of entry for POTENCIAR programme interventions and gather methodological insights for the ethnographic research component of the programme’s analytical strategy. It wil be used alongside other analytical studies undertaken by POTENCIAR (including the health sector analysis and the political economy analyses) to identify and design programme interventions. Following an inductive method, the team sought to assess the conditions and processes of health care provision and access from the perspective of health providers and residents in Monapo district in Nampula Province, northern Mozambique (POTENCIAR will implement its first PAI in Nampula province). To gain insights into accountability relations in the health sector, the team focused on the administrative and social institutions where health providers and users interact. The study asks the following question: From grounded perspectives of health providers and residents in Monapo district, what are the accountability issues in the provision and access to health services?
Keywords: *non-public; Ethnographic Studies; G - Mozambique / Moçambique; GD - Monapo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health / saúde

Observatory of Illicit Economies in Eastern and Southern Africa (Global Initiative Against Transnational and Organized Crime, 2021)
Illicit flows are a major part of the political and economic landscape of northern Mozambique. In South Africa, the trade in poached abalone and the trafficking of synthetic drug still remain joined today. The impact that heroin capsules have had in Durban in terms of violence, profitability and local demand for heroin. How illicit gold from South Sudan and the Democratic Republic of Congo flows through Uganda
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; conflict / conflito

Bispo de Pemba critica Nyusi: "Se eu fosse presidente, a minha presença seria outra. Estaria a falar de Cabo Delgado todos os dias" - Castro, Pedro Jorge (Moçambique para todos, 2021)
"Como é que um corrupto pode lutar contra si mesmo? É preciso uma espécie de revolução." As ameaças do governo. A guerra. E o deslocado que disparou contra insurgentes. Entrevista ao Bispo de Pemba.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - Pemba; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Total Suspends Mozambique LNG Temporarily on Security Threat - Francois De Beaupuy; Paul Burkhardt; Borges Nhamirre (Bloomberg.com, 2021)
French energy giant Total SE suspended its $20 billion liquefied natural gas project in Mozambique indefinitely due to an escalation of violence in the area, including a March attack by Islamic State-linked militants.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Vale moves to exit coal business - Argus Media (2021)
In its first step to exit the coal business, Brazilian mining firm Vale will acquire all stakes held by Japanese trading house Mitsui in the Moatize coal mine and Nacala corridor coal infrastructure in Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Financiamento da ADIN vai agravar a já insustentável dívida pública - Beula, Emídio (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Cenário Fiscal de Médio Prazo (CFMP 2022-2024), instrumento que marca o início do ciclo de planificação e orçamentação, avança cenários preocupantes em relação à evolução da dívida pública de Moçambique. Por exemplo, as projecções relativas às despesas públicas mostram que os encargos com a dívida pública, isto é, os pagamentos de juros relacionados com o serviço da dívida, passarão de 27.114,8 milhões de meticais em 2021 para 38.731,8 milhões de meticais em 2022, evidenciando um crescimento de cerca de 42,8%. Aliás, dados apresentados pelo CFMP indicam que a tendência deverá continuar crescente, pelo menos nos próximos três (3) anos, atingindo 44.734,2 milhões de meticais em 2024, o equivalente a uma subida de cerca de 65% em relação a 2021. Apesar dessas projecções, o Governo está a mobilizar um bilião de dólares para financiar as actividades da Agência de Desenvolvimento Integrado do Norte (ADIN) nas províncias de Cabo Delgado, Nampula e Niassa. O anúncio foi feito na semana passada pelo Ministro da Agricultura e Desenvolvimento Rural, Celso Correia, o governante responsável pela tutela administrativa da instituição. A mobilização do financiamento é feita antes mesmo da aprovação do plano estratégico da ADIN, denominado Estratégia Resiliente do Desenvolvimento Integrado do Norte. O documento ainda está em consulta pública nas três províncias onde serão implementados os projectos da agência de desenvolvimento da região norte.
Keywords: ADIN (Agency for Integrated Development of the North); G - Mozambique / Moçambique; G - north / norte; L - portuguese / português

Mozambique - Update, Cabo Delgado Situation, 2 (ReliefWeb, 2021)
English Situation Report on Mozambique about Coordination, Protection and Human Rights, Epidemic and more; published on 21 Apr 2021 by UNHCR
Keywords: G - Mozambique / Moçambique; L - english / inglês

Cabo Ligado 45 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Following the rise of Islamist group al-Shabab in Cabo Delgado - Marie Toulemonde (The Africa Report.com, 2021)
A visual explanation of how Mozambique’s islamist group al-Shabab has grown over the years in the northern Cabo Delgado province.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; extractive industries / indústrias extractivas

An overview of foreign security involvement in Mozambique (defenceWeb, 2021)
A number of private security companies, foreign governments and militaries have become involved in Mozambique in its fight against the insurgency in Cabo Delgado, but the Mozambican government has so far largely limited external involvement. Nevertheless, there are a number of companies and countries providing security and security assistance to Mozambique. Private military contractors Russian […]
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Cabo Ligado 44 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Some hid in the sea’: Islamist attack on Mozambique town a turning point in Africa’s ignored war - Cotterill, Joseph (Financial Times, 2021)
French group Total suspends work at gas plant near Palma despite authorities’ claims order has been restored
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Hunger spreading as Mozambique crisis reaches tipping point - Marima, Tendai (AlJezeera, 2021)
Thousands of people shelter in displacement camps with limited food supplies across Cabo Delgado following Palma attack.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Fechando a lacuna da protecção social na velhice: simulações dos efeitos de uma pensão para cobertura universal de velhice em Moçambique - Cunamizana, Imarciana; Muianga, Marcos; Zunguze, Celso (Ministry of Finance - Moçambique Government, 2021)
Esta nota de política apresenta as principais conclusões na sequência da aplicação do modelo MOZMOD de microsimulação de benefícios fiscais para estimar o impacto na redução da pobreza e da desigualdade em Moçambique com base em cenários de extensão da cobertura universal da protecção social para todos os idosos e aumento dos níveis de adequação. Foi produzido pelo Ministério da Economia e Finanças de Moçambique com o apoio da OIT (através do Programa Conjunto das Nações Unidas sobre Protecção Social, financiado pela Holanda, Suécia e FCDO) e UNU-WIDER, e foi lançado a 15 de Outubro de 2021 durante a Semana de Protecção Social de Moçambique.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; M - evaluation / avaliação; social protection / proteção social

Caracterização e Organização Social Dos Machababos a Partir dos Discursos de Mulheres Raptadas - Feijó, João (Observatório do Meio Rural, 2021)
A intensificação do conflito militar no Norte de Cabo Delgado despertou a atenção de jornalistas, investigadores, analistas de segurança e diplomatas. O facto de os rebeldes armados não darem entrevistas a jornalistas e investigadores resulta num grande desconhecimento sobre as suas dinâmicas internas nas zonas ocupadas, pelo que o mundo dos insurgentes constitui um território repleto de mistérios. Por outro lado, o rapto de centenas de jovens mulheres gera interrogações em torno do respectivo paradeiro, originando inquietação social. O pouco conhecimento existente acerca das formas de organização interna dos insurgentes resulta de testemunhos oculares de quem privou com o grupo, nomeadamente desertores ou mulheres que estiveram em cativeiro. A partir de 23 entrevistas a mulheres vítimas de agressão ou sequestro por grupos insurgentes foi possível concluir que os membros do grupo têm origens e percursos sociogeográficos heterogéneos, sendo a maioria oriunda do litoral Norte de Cabo Delgado, com registos de indivíduos provenientes do planalto de Mueda, do litoral de Nampula, assim como um crescente número de estrangeiros, provenientes da costa oriental africana e de países árabes. Os insurgentes dispõem de diferentes bases, instaladas em aldeias abandonadas por civis ou nas matas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Characterization and Social Organization of Machababos from the Discourses of Kidnapped Women - Feijó, João (Observatório do Meio Rural, 2021)
The intensification of the military conflict in Northern Cabo Delgado has attracted the attention of journalists, investigators, security analysts and diplomats. The fact that armed rebels do not give interviews to journalists and researchers results in a great ignorance about their internal dynamics in the occupied areas, and so the world of insurgents is a territory full of mysteries. On the other hand, the abduction of hundreds of young women raises questions about their whereabouts, causing social unrest. The little knowledge of the insurgents' forms of internal organization stems from eyewitness testimonies of those who lived with the group, including defectors or women who have been in captivity.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (ETT, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Hundreds Missing After Mozambique Attack (Human Rights Watch, 2021)
Hundreds of people remain missing five days after an Islamic State (ISIS)-linked armed group known as Al-Shabab raided the town of Palma in Mozambique’s northern Cabo Delgado province, killing and wounding an unknown number of civilians and causing thousands to flee.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Cabo Ligado 43 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique: Firing in Palma near Total's LNG project, population fleeing - Lusa (Mozambique, 2021)
The town of Palma, in Cabo Delgado, was under gunfire on Wednesday afternoon and the population is fleeing, different sources who were in communication with the headquarters of the district that hosts the gas projects in northern Mozambique told Lusa. Machine gunfire was heard in the town and the
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Cabo Ligado 42 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Economia Política da Caça Furtiva Em Moçambique - Centro para Democracia e Desenvolvimento (CDD) (Centro para Democracia e Desenvolvimento (CDD), 2021)
Este estudo documenta a situação da caça furtiva em Moçambique com recurso às ferramentas do jornalismo investigativo e na base de trabalhos de campo realizados no Parque Nacional do Limpopo e na Reserva Nacional do Niassa. Neste estudo está retratada a economia política da caça furtiva no País, nomeadamente os actores, a articulação dos interesses destes grupos (nacionais e internacionais), as formas de actuação e a relação da caça ilegal com a violação dos direitos humanos.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; corruption / corrupção; poverty / pobreza

Cabo Ligado 41 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Syrah Resources resumes graphite mining ahead of schedule after year's stoppage (Mozambique, 2021)
Australian mining company Syrah Resources has resumed production of graphite ahead of schedule at its Balama mine in Cabo Delgado, northern Mozambique, it said in a statement to shareholders on Tuesday. The plant's activities were halted in late March last year following the country's implementat
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; private sector / setor privado

Of zinc roofs and mango trees: tractors, the state and agrarian dualism in Mozambique - Cabral, Lídia (The Journal of Peasant Studies, 2021)
This paper reviews the latest mechanisation programme by the Mozambican government, asking how it is politically driven and how it shapes and is shaped by agrarian structures. Old ideas about agrarian dualism are reproduced today, albeit with a new language of public-private partnerships that are seen as potentially driving the modernisation of the peasantry. State-sponsored and privately-run service centres, featuring zinc roofed warehouses, are the government’s preferred route to modernisation, yet failing to reach the average farmer and understanding the motives and predicaments of private managers. Emerging small to medium farmers, who keep tractors under shady mango trees in their backyards, are also offering mechanisation services to their peers, which are instrumental to stepping up their production and commercial activities. The state’s push for mechanisation feeds uneven patterns of accumulation and social differentiation.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; agriculture / agricultura; government policy / politica governamental; private sector / setor privado

State Department Terrorist Designations of ISIS Affiliates and Leaders in the Democratic Republic of the Congo and Mozambique (United States Department of State, 2021)
The Department of State has designated the Islamic State of Iraq and Syria – Democratic Republic of the Congo (ISIS-DRC) and the Islamic State of Iraq and Syria – Mozambique (ISIS-Mozambique) as Foreign Terrorist Organizations under section 219 of the Immigration and Nationality Act, as amended.  The Department has also designated ISIS-DRC and ISIS-Mozambique as […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

US hits IS groups in Mozambique, Congo with terror sanctions (AP NEWS, 2021)
WASHINGTON (AP) — The Biden administration on Wednesday designated two Islamic State affiliates in Mozambique and the Democratic Republic of Congo as “foreign terrorist organizations,” imposing...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

A Insurgência Jihadi em Moçambique: Origens, Natureza e Início - Morier-Genoud, Eric (Cadernos IESE, 2021)
Resultante de uma investigação com trabalho de campo em Cabo Delgado em 2018 e 2019, este novo Cadernos IESE nº 21, da autoria de Eric Morier-Genoud, explica a origem, natureza, e dinâmica da guerra no norte de Moçambique com base numa análise da historicidade e das dinâmicas internas das sociedades locais. Defende o argumento segundo o qual é mais produtivo pensar nos insurgentes do Al-Shabaab em termos da sua trajectória histórica, evoluindo de uma seita islâmista para um grupo armado jihadi violento, passando actualmente por um processo de internacionalização que poderá se evoluir de várias formas no futuro.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado (Mozambique Conflict Observatory ) Cabo Ligado Weekly: 1-7 March - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Afinal, não é só Cabo Delgado! Dinâmicas da insurgência em Nampula e Niassa - Forquilha, Salvador; Pereira, João (IDeIAS, 2021)
Nos últimos três anos e meio, Moçambique enfrenta uma violência armada desencadeada por um grupo de natureza jihadista. Com origens na zona norte de Cabo Delgado e localmente conhecido pela designação Al-Shabaab, o grupo surgiu como uma seita religiosa (Morier-Genoud, 2020) e, de seguida, constituiu-se numa unidade militarizada, tendo partido para a violência armada a 5 de Outubro de 2017. Baseado em trabalho de campo nas províncias de Cabo Delgado, Nampula e Niassa, este texto procura analisar a insurgência com base em dinâmicas de alguns distritos de Nampula e Niassa. Com enfoque nos factores do avanço da insurgência no terreno, o texto sublinha o argumento, segundo o qual, a compreensão do desenvolvimento da insurgência em Cabo Delgado passa, entre outros aspectos, pela análise das dinâmicas sociais, económicas e religiosas das províncias vizinhas, nomeadamente Nampula e Niassa, que se transformaram em espaços férteis de recrutamento, particularmente a partir de 2018. O argumento é desenvolvido em dois momentos. No primeiro momento, o texto procura identificar e analisar os principais factores que conduziram ao alastramento da insurgência para mais distritos de Cabo Delgado e à tentativa de instalação de células de tendência radical em alguns distritos de Nampula e Niassa. No segundo momento, focaliza-se a atenção para as dinâmicas de recrutamento a nível interno, com destaque para alguns distritos localizados na zona costeira de Nampula e na fronteira entre a província de Niassa e a Tanzânia.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Estabelecimento Da Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) Nas Províncias de Tete, Gaza, Nampula - RMDDH (CDD - Centro para Democracia e Desenvolvimento Mozambique, 2021)
A Rede Moçambicana dos Defensores de Direitos Humanos (RMDDH) está a levar a cabo actividades de identificação e mapeamento de defensores de direitos humanos nas províncias, que incluem pessoas singulares e organizações da sociedade civil que estão na linha de frente na luta pela defesa dos direitos humanos. Financiado pela OCISA, o trabalho iniciou em Abril último na Província de Tete, centro de Moçambique, onde a RMDDH realizou vários encontros com organizações da sociedade civil que trabalham na área dos direitos humanos e com instituições governamentais e estatais
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Gaza; GP - Nampula; GP - Tete; L - portuguese / português; civil society / sociedade civil

Mozambique: ExxonMobil again postpones final decision on Rovuma LNG (Mozambique, 2021)
US oil company Exxon has postponed for the third consecutive year the Final Investment Decision on the natural gas exploration project in Mozambique, putting the $30 billion investment in doubt. According to Bloomberg news agency, which quotes the company's Senior Vice President Neil Chapman, Nei
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Total kicks off search for first Mozambique FSRU | Upstream Online - Hine (l_hine), Lucy (Upstream Online | Latest oil and gas news, 2021)
Floating regas unit could be used for imports that would ultimately help supply South Africa
Keywords: G - Mozambique / Moçambique; L - english / inglês

Regional Integration at the Forefront of Mozambique’s Energy Success - Hundermark, Charnè (cnbcafrica, 2021)
As one of leading resource-rich countries in sub-Saharan Africa, Mozambique has the potential to not only significantly advance its own socioeconomic status, but also dramatically boost economic growth throughout the region. According to the World Bank Group, regional integration helps countries to overcome divisions that impede the flow of goods, services, capital, people and ideas. As large-scale energy projects are expected to come online in Mozambique through 2023, the country has observed renewed political commitment to establishing sustainable regional integration with neighboring governments and private operators.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico

O que vi foi a morte: crimes de guerra no "cabo esqueçido" de Moçambique (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

What I saw is death: War crimes in Mozambique's forgotten cape (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Altona Rare Earths soars as it enters MoU to acquire rare earths project (Vox Markets, 2021)
Shares in Altona Rare Earths soared by over 60% today following the news that the group has entered into an MoU to acquire up to 70% in the Monte Muambe Rare Earths Project. Should it choose to proceed with the investment following a 90-day due diligence period, the project would represent its first venture into a carbonatite hosted REE asset.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Mozambique: Civilians killed as war crimes committed by armed group, government forces, and private military contractors – new report (2021)
The new report documents serious violations of international humanitarian law by all parties to the conflict in Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado Monthly: March 2021 - ACLED (ACLED, 2021)
In This Report: Analysis of the IS claim of the Palma attack in the context of the overall relationship between IS and the Cabo Delgado insurgency Discussion of growing tensions between displaced people, host communities, and aid organizations in districts with growing displaced populations Update on international involvement in the Cabo Delgado conflict and analysis of the role that South African companies Dyck Advisory Group and Paramount Group play in the conflict
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Narrativas Desqualificadoras à Sociedade Civil em Moçambique e Sua Contribuição Para o Fechamento Do Espaço Cívico - Salimo, Padil; Monjane, Celso (2021)
O presente estudo visa identificar e analisar as narrativas dominantes de deslegitimação do papel da sociedade civil e sua contribuição para a obstrução do espaço cívico em Moçambique. O estudo também analisa como essas narrativas são disseminadas e as dinâmicas de poder que as sustentam. O estudo pretende providenciar estratégias que se contrapõem às narrativas desqualificadoras, e na construção de novas narrativas. Para o efeito, foram analisadas peças informativas ou opinativas nas redes sociais e media convencionais que evidenciam práticas manifestas de desqualificação da sociedade civil e com potenciais efeitos na obstrução e/ou no fechamento do espaço cívico. Associado a isso, faz-se o mapeamento dos propulsores dessas narrativas, os grupos a que pertencem e as suas motivações.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civic space / espaço cívico; civil society / sociedade civil

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança

Cabo Ligado 39 - ACLED (ACLED, 2021)
On 22 February, insurgents conducted two attacks along the border between Nangade and Mocimboa da Praia districts. The first, a morning attack, took place at Ingalonga, Nangade district. Insurgents beheaded two people there. Later that day, across the border in Mitope, Mocimboa da Praia district, insurgents captured three women and three men who had been working in their fields. One woman was released, and the three men were beheaded. Local militias deployed to the area in response, but no clashes were reported. Three days later insurgents struck closer to the Nangade district capital, attacking the village of Luneque, which is only 10 kilometers from Nangade town. The attackers killed four civilians in the town, and caused many others to flee to the district capital. On the evening of 26 February, insurgents surprised residents of Quirinde, Palma district as they ate dinner. Residents fled, but insurgents killed seven, three of whom were beheaded. Insurgents also destroyed homes and looted food and other goods. Quirinde is a coastal village north of Palma town, about six kilometers east of Quionga, which insurgents attacked on 19 February. One source reports that helicopters belonging to government forces or government contractors pursued the Quirinde attackers, causing an indeterminate number of casualties. According to Pinnacle News, the government has deployed two battalions of the police Rapid Intervention Unit to the area in an attempt to prevent further insurgent attacks on the route between Palma and the Tanzanian border.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Waves and legacies: The making of an investment frontier in Niassa, Mozambique - García, Angela Kronenburg; Meyfroidt, Patrick; Abeygunawardane, Dilini; Sitoe, Almeida (AfricArXiv, 2021)
To understand how land-use frontiers emerge, we studied the actors driving investments in Niassa province, Mozambique. Our ethnographic research over 2017-2018 among commercial agriculture and forestry investors shows that successive waves of actors with different backgrounds, motives and business practices, arrived in Niassa to establish farms or plantations yet repeatedly failed. Waves come and go but leave sediments – legacies – that add up to gradually build the conditions for a frontier to emerge. The accumulation of these legacies has given rise to a new wave by actors from within the region, indicating that over time endogenous processes may replace externally-driven waves.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; Northern PEA; agriculture / agricultura; private sector / setor privado

Social Protection and Cash Transfers in Mozambique: between international consensus and local agency - Oliveira, Maria Clara; Cravo, Teresa Almeida (Cadernos de Estudos Africanos, 2021)
This article examines the rise of cash transfer programs and their embrace, since the 1990s, as a central element in global public policy on economic and social development and poverty reduction. Focusing on the example of Mozambique, an early adopter of such programs, it analyses the relationship between international organizations, development aid agencies, national government and local agents in the field, in the design and delivery of social protection policy. While external actors have been important in shaping Mozambican public policy, this study reveals the relevant role played by the country’s domestic actors in agenda-setting, conception and implementation of a cash transfer program as early as 1990, and its evolution over the subsequent three decades. In this interplay between international and local levels of decision- and policy-making, the article looks into the barriers to the program’s reach, pace and limited impact.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; social protection / proteção social

Ten Conflicts to Worry About in 2021 (ACLED, 2021)
A review of key developments in 2020 with a look toward trends to watch in the coming year.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, , Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Actualidade Económica de Moçambique: Preparação para Recuperação (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~^!!^.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Mozambique Economic Update : Setting the Stage for Recovery (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~^!!^.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Multinational enterprises, political institutions, and violence: a case study from Mozambique - Mairoce, Carlos; Silberberger, Magdalene; Zweynert, Joachim (Journal of Institutional Economics, 2021)
Based on the concept of limited and open access orders (LAO/OAO), this paper explains what appears to be a paradox: how was it possible that a former civil war country, Mozambique, which had been extremely successful in attracting foreign direct investment (FDI) and which the International Monetary Fund praised as a great Sub-Sahara African success story in 2007, only a few years later found itself on the brink of a new civil war? We argue that the destabilization of the country was the result of a toxic mix of domestic politics and a massive inflow of FDI. FDI provided rents to an increasingly dominant state party, FRELIMO, which could be appropriated one-sidedly. It then used these rents to oppress RENAMO, its previous civil war enemy and currently its main opposition party, to monopolize power. This strategy seemed to be successful until RENAMO, faced with the risk of being politically marginalized (and of losing its rents accordingly), returned to armed conflict in 2013. By analyzing the links between the macro-level of national politics and the micro-level of an enterprise and by embedding the interplay between polity and economy into an international context, the paper also makes a theoretical contribution to the LAO/OAO concept.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; extractive industries / indústrias extractivas; private sector / setor privado

Shaping Social Change with Music in Maputo, Mozambique - Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Manhiça, Anésio (IDS Policy Briefing, 2021)
In Mozambique, development programmes have traditionally drawn on music as a means to promote social transformation by educating citizens on key social development issues. Shifting the focus from music as a teaching medium to music as a rich source of information can provide vital insights into public opinion and political ideas, and significantly impact the development of citizen engagement projects. Maximum gains for development and civil society agencies can be achieved by mainstreaming gender into mutual learning activities between singers, audiences, and academics.
Keywords: *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; L - english / inglês; M - ethnography / etnografia; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento; gender / género

Mozambique: How Total plans to protects its $15bn major gas project - Le Bec, Christophe (The Africa Report.com, 2021)
Total is going ahead with its Mozambique LNG project despite a major armed insurgency in Cabo Delgado. This article discusses plans to secure its Afungi facility, including security forces involved. Facility employment is projected to triple by 2022, from 5,000 in 2020 to 15,000 by 2022.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; employment / emprego; extractive industries / indústrias extractivas; private sector / setor privado

Mapeamento das OSC em Moçambique - Costantini, Gianfrancesco; Macuane, José Jaime; Guirengane, Juscelina; de Araújo, Shaista (2021)
A mapping of CSOs and an analysis of key dynamics influencing CSOs actions and development Este documento é o relatório final do estudo de mapeamento das organizações da sociedade civil (OSCs) realizado em 2021, no contexto do processo de estruturação do Roteiro de Apoio à Sociedade Civil da União Europeia em Moçambique. Os objetivos do estudo são o de actualizar a informação do contexto de actuação da sociedade civil e as indicações estratégicas do mapeamento das OSCs realizado em 2015, sobre as características gerais da sociedade civil em Moçambique, e o de detalhar o papel das OSCs e dos espaços de diálogo a nível sectorial. A base do mapeamento é um conceito amplo e diferenciado das OSCs. Neste âmbito, são consideradas, além das Organizações Não-Governamentais (ONGs), todas as formas de agregação dos cidadãos e cidadãs, formais e informais, legalizadas e não legalizadas. De um ponto de vista metodológico-operacional, esta concepção implicou a identificação das entidades da sociedade civil em diferentes níveis. O mapeamento foi realizado através da consulta integrada e coordenada de diferentes fontes de informação. A consulta permitiu, por um lado, assegurar uma validação das informações recolhidas e, por outro, assegurar a representação dos pontos de vista e das perspectivas dos diferentes actores. No total, no contexto do mapeamento, foram consultadas 350 organizações da sociedade civil, incluindo entidades locais e nacionais aos diferentes níveis, assim como ONGIs internacionais.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; M - survey / inquérito; civil society / sociedade civil; ⛔ No DOI found

Mozambique - Combined Mid-Term Review of the Country Strategy Paper 2018-2022 and Country Portfolio Performance Review 2020 (African Development Bank, 2021)
The Bank Group’s Country Strategy Paper (CSP) 2018-2022 for Mozambique was approved by the Boards of Executive Directors in June 2018. The CSP was prepared in a context of economic downturn triggered by the deterioration of the country's financial situation and scaleddown dialogue between the Government of Mozambique (GoM) and Donor Partners (DPs). The CSP was anchored on two pillars: (i) "Development of infrastructure to enable transformative, inclusive growth and job creation", and (ii) "Support to agricultural transformation and value chain development".
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

Colateralização dos títulos de terra em Moçambique: bases para sua viabilização - Hamela, Hipólito; Macaringue, João; Rose, Ian (USAID, 2021)
No âmbito do processo de Revisão da Política Nacional de Terras e para responder aos consensus alcançados na IX Sessão do Forum de Consulta sobre as Terras (FCT) que incluiam a viabilização da transmissibilidade dos títulos de uso e aproveitamento da terra (DUAT) tornando este processo mais flexível, foi encomendado o presente estudo que tem como objectivo aferir, dentro do actual quadro legal, a viabilidade, sob o ponto de vista de oferta e da procura, da possibilidade de se implementar um programa de empréstimos, oferecendo como garantia, o DUAT. Do estudo resultará um ensaio piloto para testar os pressupostos que o estudo adopta como base, e que vão permitir a colateralização do direito de uso e aproveitamento da terra (DUAT) sem ferir os dispositivos legais vigentes. Também dele resulta a recomendação para a inclusão de elementos de clarificação no regulamento de terras o que tornará explícito que a colateralização do DUAT não é proibida. Para a realização deste trabalho foi feita uma revisão bibliográfica que incluiu os relatórios e declarações finais dos Foruns de Consulta sobre Terras, documentos do governo relativos à matéria de terras e estudos sobre a transmissibilidade dos títulos de uso e aproveitamento da terra. Também foi revista diversa legislação com impacto no uso e aproveitamento da terra com destaque para a Constituição da República, Lei e Regulamento de Terras, Código do Registo Predial e a legislação que cria a Central de Registo de Garantias Mobiliárias.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; governance / governação; land governance / gestão de terra

Moma Titanium Minerals Mine, Mozambique - Mining Technology | Mining News and Views Updated Daily - Mining Technology (Mining-technology, 2021)
Moma, one of the world’s biggest titanium mineral deposits, is located 160km from the city of Nampula in Mozambique, Africa. It is owned and operated by Kenmare Resources. The mine contains the titanium minerals ilmenite, rutile and zircon, which are used as feedstock to produce titanium dioxide pigment. It started production of heavy mineral concentrate (HMC) containing these three minerals in April 2007. It produced 1,201,100t of HMC and shipped approximately 853,100t of finished products in 2020. Kenmare carried out an expansion at the mine ten years ago to fulfil the growing demand for titanium dioxide feedstock in the market. The expansion was aimed to increase the design capacity of the mine by 50% while increasing the mine’s reserve estimate and annual production of HMC. Construction work on the expansion began in December 2010 and the works were completed in December 2013. The expanded mine has a mine life of more than 100 years. The first shipment of concentrated mineral sands was dispatched from Mama in Q2 2019, following the commissioning of the product stream in Q4 2018. The Moma mine had more than 1,420 employees at the end of 2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Análise da Proposta do Orçamento do Estado 2021 - Mussagy, Ibraimo H. (Observatório do Meio Rural, 2021)
A actual Proposta do Orçamento do Estado (POE) 2021 é a segunda para o quinquénio 2020-2024 e foi elaborada num contexto de transformações económicas e sociais impostas por um novo “normal” provocado pela pandemia da COVID-19, que resultou na maior recessão mundial estimada em cerca de -4.9% para 2020. Essa recessão foi causada pelas medidas de contenção que resultaram na paralisação da actividade económica em grande parte das economias. Em linha com as actuais tendências da economia mundial, a economia Moçambicana também tem registado uma desaceleração (parágrafo 2 da POE 2021). Este texto tem a finalidade de analisar a POE 2021, tendo em conta este contexto. Para tal, a análise foi feita com base nos seguintes documentos: Plano Económico e Social (PES) 2021, POE 2021, mapas integrantes¹, leis orçamentais anteriores e os Relatórios de Execução Orçamental (REO) recentes. Faz-se a articulação destes documentos para se poder perceber a evolução das componentes da POE 2021. O texto compreende três secções, nomeadamente a introdução, a análise do orçamento, onde, de forma específica, o texto analisa os pressupostos macroeconómicos subjacentes à proposta, a evolução das receitas e das despesas, faz uma discussão sobre o défice orçamental, destaca os orçamentos sectoriais com enfase para agricultura, onde o projecto SUSTENTA prevalece em grande parte da discussão, aborda a questão da descentralização e discute o endividamento público, e, na última secção, apresenta-se o resumo das constatações.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; budget / orçamento; decentralization / descentralização; education / educação; health / saúde

An Overview of the Policy and Market Landscape of Tobacco Production and Control in Mozambique - Nguenha, Nicole; Cunguara, Benedito; Bialous, Stella; Drope, Jeffrey; Lencucha, Raphael (International Journal of Environmental Research and Public Health, 2021)
Background: Tobacco growing has been considered a mainstay of Mozambique’s economy, but there is a dearth of analysis of the tobacco policy landscape in the country. Methods: Review of government and non-government documents and academic papers addressing Mozambique’s tobacco-growing history, the changes in the political economy of tobacco, and health policies addressing tobacco use and prevention of noncommunicable diseases. Results: Despite its tobacco growing and exporting history, the contribution of tobacco to the economy has been in steady decline in the past two decades, including in the areas dedicated to growing. At the same time there has been an increase in multinational control of the tobacco economy. In parallel, Mozambique’s commitment to addressing the growing burden of noncommunicable disease and accession to the Framework Convention on Tobacco Control indicate a potential for internal government tensions to balance immediate economic interests with long term health goals. Conclusions: With the decline in tobacco share of the overall economy, Mozambique may be well-positioned to explore alternative, sustainable livelihoods for farmers that grow tobacco, but it must overcome inter-sectoral barriers and advocate for a whole of government approach to address the health and economic impact of tobacco.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Relatório de Pesquisa Desigualdades e Resistência em Tempos de Pandemia: Impactos Da COVID-19 Nas Mulheres do Mercado Informal - Osório, Conceição; Loforte, Ana Maria; Vilanculo, Sérgio (WLSA Moçambique, 2021)
Este relatório de pesquisa buscou especificamente identificar no contexto mundial, regional e nacional as estratégias e as políticas públicas relativamente à situação das raparigas e mulheres, analisar as narrativas e discursos das organizações da sociedade civil e instituições de pesquisa, tanto as que têm como foco os direitos humanos, como as que definem como objecto a promoção da igualdade de género, e analisar o conteúdo dos media nacionais sobre a Covid-19, com destaque para as representações sobre violência de género. Para a realização da pesquisa foi importante a definição do grupo alvo, as mulheres que trabalham no informal, por serem das mais afectadas pela situação criada pela Covid-19, sendo muito pouco conhecidas as suas vozes, os seus problemas, necessidades e expectativas. A pesquisa foi enquadrada no Projecto “Mulheres e direitos humanos no contexto da COVID-19 em Moçambique” e surgiu no âmbito de uma parceria entre a WLSA Moçambique com as Aliadas e o CESC, procurando conhecer melhor como é que, em situação de pandemia, se configuravam os direitos humanos das mulheres, considerando as desigualdades estruturais e as relações desiguais de poder.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; informality / informalidade

Navigating Civic Space in a Time of COVID-19: The Case of Mozambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Institute for Social and Economic Studies, 2021)
This report builds on the Action for Empowerment and Accountability (A4EA) research project Navigating Civic Space, which seeks to analyze the extent to which COVID-19 is contributing to the opening or closing of space for civic action in three countries, namely Mozambique, Nigeria and Pakistan. Focusing on Mozambique, the report uses theoretical and methodological tools produced by the work stream and is essentially structured around the three main research questions: What is known about the civic space trend in Mozambique before the arrival of the COVID-19 pandemic?; How are different actors responding to the COVID-19 pandemic affecting the civic space in Mozambique?; What are the medium and long term implications for governance in Mozambique?
Keywords: G - Mozambique / Moçambique; L - english / inglês; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19

African Economic Outlook 2021: From Debt Resolution to Growth: The Road Ahead for Africa - African Development Bank (African Development Bank, 2021)
The 2021 edition of the African Economic Outlook focuses on debt resolution, governance, and growth in Africa. Chapter 1 examines Africa’s growth performance and outlook amid the COVID–19 pandemic. The chapter emphasizes policy options to mitigate the effects of the pandemic in the short, medium, and long terms. Chapter 2 explores the causes and consequences of Africa’s debt dynamics by showing how the changing structure and composition of debt create vulnerabilities. In chapter 3, the report takes stock of the challenges in the current global architecture for debt resolution and explores the link between governance and growth with an emphasis on proposed reforms to improve the processes of debt resolution, governance, and sustainable growth
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; governance / governação; health - COVID-19 / saúde – COVID-19

A COVID-19 e suas implicações na governação municipal em Moçambique: um estudo de caso a partir do município de Gondola - António, Bernardino (Desafios para Moçambique 2021, 2021)
Tomando como exemplo o município de Gondola, na província de Manica, este artigo analisa as implicações da COVID-19 na governação municipal, destacando a interacção entre a edilidade e os munícipes no desenvolvimento do mesmo. O texto defende o argumento segundo o qual, apesar de a COVID-19 ter impactado negativamente nas lógicas do Governo de Gondola, a pandemia, por si só, não constitui factor explicativo para a fraca interacção entre as autoridades e os munícipes, pois os baixos níveis de interacção entre os Vereadores e os cidadãos constitui um problema de carácter estrutural, que caracteriza o Governo não só ao nível das autarquias, mas também a outros níveis de governação em Moçambique. O artigo está organizado em três secções, além da introdução. Na primeira secção, faz se uma breve caracterização do município de Gondola, mostrando o contexto da análise aqui feita. Na segunda secção, aborda-se o papel dos municípios na gestão da COVID-19 em Moçambique. Na terceira secção, descreve-se a COVID-19 e as suas implicações no Governo de Gondola, destacando a questão da interacção entre as autoridades municipais e os munícipes. O artigo resulta de uma pesquisa realizada no município de Gondola em 20206, no âmbito do projecto de pesquisa «Barómetro da Governação Municipal», em curso no Instituto de Estudos Sociais e Económicos (IESE) desde 2017. A pesquisa baseou-se numa metodologia qualitativa, com recurso a entrevistas semiestruturadas, discussões em grupos focais e observação no terreno, realizadas em 10 bairros do município de Gondola, nomeadamente Mazicuera, Mucessua, Josina Machel, Bengo, Nhachoco, Eduardo Mondlane, 3 de Fevereiro, 7 de Abril, Francisco Manyanga e 25 de Junho. Foram realizadas quatro discussões em grupos focais e nove entrevistas semiestruturadas com moradores, membros do Governo Municipal (Presidente e Vereadores), membros da Assembleia Municipal, líderes comunitários, comerciantes locais e organizações da sociedade civil. A pesquisa de campo decorreu ao longo de 15 dias, entre Novembro e Dezembro de 2020
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; governance / governação; health - COVID-19 / saúde – COVID-19; politics / política

Alargando o espaço para o diálogo de políticas sul-sul: Aprender com as iniciativas lideradas pela sociedade civil - Cabral, Lídia; Levidow, Les; Schmitt, Claudia Job (Desafios para Moçambique 2021, 2021)
O presente documento incide especificamente no diálogo político e na aprendizagem que envolve organizações da sociedade civil, movimentos sociais e investigadores que trabalham na defesa de políticas, campanhas e acção-investigação relacionada com a segurança e a justiça alimentar de forma mais ampla. Ademais, explora que lições podem ser aprendidas com as experiências destes actores que são relevantes para se entender como os conceitos e ideias sobre políticas circulam e como promover intercâmbios com verdadeiros benefícios mútuos para os actores de diferentes contextos socioculturais. O documento começa com uma breve resenha da CSS brasileira e dos desafios encontrados, centrando-se especificamente na cooperação agrícola e alimentar (secção 2), seguida de uma visão geral do actual momento político que se vive no Brasil, destacando rupturas recentes e novas oportunidades (secção 3). Em seguida, esboça a natureza dos compromissos liderados pela sociedade civil e introduz um esquema de análise centrado em “quadros de acção colectiva” e uma pluralidade de formas e significados (secção 4). O documento aborda em seguida dois casos de espaços alternativos de debate sobre políticas e aprendizagem fora da esfera da CSS oficial. O primeiro caso é uma iniciativa de cooperação entre organizações camponesas brasileiras e moçambicanas, com vista a resgatar, preservar e gerir sementes nativas (secção 5). O segundo caso diz respeito à acção-investigação centrada na agro-ecologia e na construção de uma economia solidária no contexto da pandemia da COVID-19 (secção 6). Os casos ilustram que estes espaços alternativos capacitam os actores que, até agora, têm desempenhado um papel marginal nas relações formais da CSS. Estes espaços mobilizam conceitos contrahegemónicos, tais como a agro-ecologia, economia solidária, soberania alimentar e lutas territoriais. Redefinem ainda metodologias de diálogo, aprendizagem e tradução de conceitos para diferentes contextos. Uma discussão das implicações para a investigação e a prática conclui o artigo (secção 7).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; south-south cooperation / cooperação sul-sul

«Se alguém está cansado de viver» A economia informal e a segurança social - Castel-Branco, Ruth (Desafios para Moçambique 2021, 2021)
A fraca resposta do Estado aos impactos socioecónomicos da pandemia da COVID-19 salientou a necessidade de reformular o sistema da Segurança Social em Moçambique; de evoluir de um paradigma social trabalhista para um paradigma que reconhece a centralidade da economia informal e a responsabilidade redistributiva do Estado, assente num contrato social. Não existe uma única abordagem para a inclusão dos trabalhadores informais na protecção social. A economia informal é extremamente diversificada e estratificada por tipo de atividade, formas de organização e estruturas de rendimento. Portanto, é necessário considerar abordagens diferenciadas que respondem às várias realidades dos trabalhadores informais, incluindo a ausência de um empregador e a irregularidade dos rendimentos. As medidas de Segurança Social Não-Contributiva introduzidas durante a pandemia podem servir com base para um sistema redistributivo mais robusto. Mas no reforço do papel redistributivo do Estado, é importante não absolver os empregadores da sua responsabilidade de reprodução social. Por exemplo, o Regulamento de Trabalho Doméstico estipula que, por motivos do Instituto Nacional de Segurança Social, os trabalhadores domésticos devem ser considerados trabalhadores por conta própria (RdM, 2008). Porém, segundo a Lei de Trabalho (RdM, 2007b), os trabalhadores por conta própria são aqueles que: podem escolher os processos e meios de trabalho, sendo estes da sua propriedade, no todo ou em parte; não estão sujeitos a horários de trabalho, salvo se os mesmos resultarem da lei ou regulamentos; não se integram na estrutura produtiva ou cadeia hierárquica de uma única empresa, nem constituem elemento essencial ao desenvolvimento dos objectivos de qualquer entidade empregadora; e podem fazer-se substituir livremente. Esta inconsistência reflecte o poder negocial da classe empregadora na definição do Regulamento. Apesar de não serem trabalhadores informais, os trabalhadores domésticos são informalizados pela falta de protecções laborais e sociais adequadas e a sua devida aplicação. Portanto, é crítico garantir que medidas orientadas à expansão da Segurança Social – seja a Segurança Social Contributiva ou Não-Contributiva – estejam articuladas com medidas para reforçar os direitos laborais num contexto de fraca fiscalização, informalização e informalidade generalizada.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; health - COVID-19 / saúde – COVID-19; informality / informalidade; society / sociedade

Ampliando a protecção social em Moçambique - Chelengo, Márcia C.; Cardoso, José; Mataba, Gito (Policy Brief Crescimento Inclusivo em Moçambique, 2021)
– O PSSB é um programa fundamental para redução da pobreza e da desigualdade em Moçambique. – O aumento do valor das transferências para os agregados familiares beneficiários possui capacidade de reduzir a pobreza e a desigualdade no país. – Outra forma de melhorar estes indicadores é através da expansão do benefício para todas as famílias elegíveis, pois apenas um terço delas são beneficiadas atualmente. – A atualização dos valores das transferências monetárias distribuídas através do PSSB produziu impactos significativos sobre a redução da pobreza e da desigualdade apenas em um dos cenários, onde o aumento médio do benefício é aproximadamente 70% (cenário 2).
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social

Formalizing artisanal and small-scale mining in Mozambique: Concerns, priorities and challenges - Hilson, Gavin; Mondlane, Salvador; Hilson, Abigail; Arnall, Alex; Laing, Tim (Resources Policy, 2021)
This paper reflects critically on efforts made to formalize artisanal and small-scale mining (ASM) – low-tech, labour-intensive mineral extraction and processing – in Mozambique. Drawing on findings from interviews with policymakers, representatives from ASM associations and 200 individual miners, the paper captures the details of the country’s ASM formalization experience. Findings reveal that despite showing considerable promise at first, the drive to formalize ASM in Mozambique, which spans three decades, has lost considerable momentum. A bureaucratic licensing scheme, overlapping responsibilities at the Estatuto Orgaˆnico do Minist´erio dos Recursos Minerais e Energia (MIREME), and a shortage of information about miners have contributed to this slowdown. The themes underpinning the efforts to formalize ASM in Mozambique are not new but the case itself has its own unique nuances and storylines.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Anuário Estatístico - Statistical Yearbook 2020 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2021)
As in previous editions, the Statistical Yearbook 2020 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2016-2020 series The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Mozambique - Emergency Tracking Tool - Palma Crisis Report - 50 (27 March - 10 April 2021) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 10 April 2021, an estimated number of 603 were registered in the four districts bringing the total number of IDPs to 15,179 People who have been displaced from Palma continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Desafios para Moçambique - 2021 - Macuane, José Jaime; Siúta, Moisés (Instituto de Estudos Sociais e Económicos, 2021)
PARTE I – POLÍTICA Navegando o espaço cívico em contexto da pandemia da Covid-19: O caso de Moçambique / Crescêncio Pereira, Salvador Forquilha e Alex Shankland A Covid-19 e as vacinas em Moçambique: Algumas notas para reflexão a partir da teoria “sociedade de risco” / Lúcio Posse A Covid-19 e suas implicações na governação municipal em Moçambique: Um estudo de caso a partir do município de Gondola / Bernardino António PARTE II – ECONOMIA Política económica em contexto de pandemia: Uma reflexão em torno das medidas de mitigação dos efeitos da Covid-19 sobre a economia de Moçambique / Carlos Muianga e Yasfir Ibraimo A recessão económica em Moçambique: Foi a Covid-19? – Um olhar a partir do sector externo / Michael Sambo Essencial para quê? Uma visão global de reprodução social sobre a reorganização do trabalho durante a pandemia da Covid-19 / Sara Stevano, Rosimina Ali e Merle Jamieson PARTE III – SOCIEDADE “Se alguém está cansado de viver”: A economia informal, o estado e a segurança social / Ruth Castel-Branco Acção social em contexto da Covid-19: Respostas e desafios em Moçambique / Moisés Siúta e Félix Matusse Lições da Covid-19 sobre o papel da poupança doméstica: O que dizer de Moçambique? / Moisés Siúta PARTE IV – MOÇAMBIQUE NO MUNDO Globalização económica e desafios de desenvolvimento humano em contexto de crise em Moçambique / Salim Cripton Valá Alargamento de espaço para o diálogo de políticas Sul-Sul: Aprender com as iniciativas lideradas pela sociedade civil / Lídia Cabral, Les Levidow e Claudia Job Schmitt
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Inquérito Agrário Integrado 2020 - MADER (República de Moçambique - Ministério da Agricultura e Desenvolvimento Rural Direcção de Planificação e Políticas (DPP), 2021)
O crescimento agrícola em Moçambique é uma fonte essencial para promover o crescimento económico do País em geral e das famílias rurais em particular. O Programa do Governo para o Sector Agrário, em harmonia com a política económica do País, orienta-se para o alcance de grandes objectivos estratégicos, nomeadamente: (1) Segurança Alimentar; (2) Aumento do Rendimento Familiar; (3) Criação de Emprego/Inclusão Social e (4) Aumento da Produção e Produtividade. Este documento ilustra, de forma simples e clara, a situação e a dinâmica da agricultura em Moçambique durante o ano de 2020. O Inquérito Agrário Integrado (IAI 2020), indica que existem no país cerca de 4.3 milhões de explorações agro-pecuárias, das quais 4.167.702 (97.8%) são pequenas, 93.183 (2%) são médias, e 873 (<1%) são grandes explorações. Do total de cerca de 4.3 milhões de explorações (Pequenas e Médias), cerca de 6.9% receberam informação ou conselho técnico de extensão, 39.9% tiveram acesso à informação sobre preços e 0.6% acesso à crédito. A área cultivada foi de cerca de 5.5 milhões de hectares, onde 5.5% das explorações utilizaram pesticidas nos seus campos, 8.8% usaram estrume, 7.8% utilizaram fertilizantes químicos e 9.1% usou a rega. As principais culturas em diversas explorações são o Milho, Arroz, Mapira, Amendoim Pequeno, Feijão Nhemba, Feijão Boer, Mandioca, Algodão e Canade-açúcar. Grande parte das explorações cultivam Milho (83.8%), 23.6% Amendoim Pequeno, 18.3% Mapira, 12 .8% Arroz e 3.8% Mexoeira. O IAI 2020, realizado pela primeira vez com referencial distrital, é um Marco Estatístico e principal fonte de dados do sector agro-pecuário, assim como marco amostral, pois fornece dados fiáveis desagregados até ao nível Distrital, para apoiar o processo de planificação e tomada de decisão a todos níveis, baseadas em evidências científicas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura; demographics / demografia

Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Política económica em contexto de pandemia: uma reflexão em trono das medidas de mitigação dos efeitos da COVID-19 sobre a economia de Moçambique - Muianga, Carlos; Ibraimo, Yasfir (Desafios para Moçambique 2021, 2021)
Este artigo pretende reflectir sobre as medidas para mitigação dos efeitos da COVID-19 na economia de Moçambique e as suas implicações analíticas. Diferentemente de estudos anteriores sobre os impactos da pandemia e das medidas de mitigação adoptadas pelo Governo de Moçambique (Mapisse et al., 2021), este artigo parte da análise da estrutura da economia e do seu padrão de acumulação nas últimas duas décadas, na tentativa de melhor questionar a eficácia destas medidas. O artigo argumenta que, à semelhança das crises cíclicas pelas quais a economia de Moçambique passou nas últimas décadas (Castel-Branco and Ossemane, 2010; Castel-Branco, 2017), a crise provocada pela COVID-19 expõe e exacerba as fragilidades e vulnerabilidades do padrão de crescimento e a sua limitada capacidade em resolver questões centrais de transformação social e económica. Dadas as fragilidades e vulnerabilidades associadas ao padrão de crescimento económico e ao «modelo» de política económica, as medidas de mitigação dos efeitos da pandemia sobre a economia são limitadas relativamente à complexidade dos impactos socioeconómicos da COVID-19. Mais do que a sua limitada capacidade para relançar a actividade produtiva, dada a estrutura da economia, as mesmas são insuficientes para lidar com os impactos mais severos da pandemia, sobretudo para os grupos sociais mais vulneráveis. Entretanto, a COVID-19 tem chamado a atenção à necessidade de acção política e mudança «radical» na prossecução da política económica, incluindo o papel do Estado na economia (Stevano et al., 2021). Contudo, as principais medidas de política económica até então adoptadas continuam a seguir um «modelo» que, há décadas, se tem mostrado ineficaz em resolver, a médio e longo prazo, as questões de transformação económica e social do País. Este artigo está organizado em quatro secções, incluindo a introdução. A segunda faz uma breve descrição e análise da estrutura da economia e do padrão de crescimento económico em Moçambique, nas últimas duas décadas. O objectivo desta secção é fornecer uma base analítica que ajude a interrogar as medidas de mitigação dos efeitos da COVID-19 sobre a economia, enquanto, ao mesmo tempo, ajuda a explicar o tipo de economia que a pandemia encontrou, as suas características fundamentais e o seu funcionamento. A terceira secção descreve as principais medidas adoptadas pelo BM e pelo Governo para mitigar os efeitos da COVID-19, questionando-as em função da estrutura da economia e do quadro de implementação de política monetária e fiscal e as suas contradições e tensões. A quarta secção conclui e avança algumas questões para reflexão.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; government policy / politica governamental; health - COVID-19 / saúde – COVID-19

Innovative Finance for Employment: The Potential for Women and Urban Youth - MUVA; Social Finance Ltd (MUVA and Social Finance Ltd, 2021)
The need for female economic empowerment in Mozambique is clear; just 24% of women have access to wage employment, versus 50% of men. The situation is worse still in urban settings where 19-24-year-old women have the highest unemployment rates in the country. The national rate of formal employment is approximately 13%, and large scale formal job creation in the Oil and Gas sector is yet to materialise. Despite impressive economic growth in recent years, 50% of Mozambicans are still living in poverty and social and economic inequalities are continuing to grow. The challenges faced by disadvantaged urban youth and women (DUYW) are severe; without deliberate intervention to address the constraints facing them, this trend is set to worsen. In light of this challenge, MUVA commissioned a scoping study to assess the potential of innovative financing models to support the economic empowerment of disadvantaged urban youth and women. Innovative finance is a broad spectrum of mechanisms that offer an alternative to traditional activity based grant funding. It can include investment capital seeking a return, but also encompasses results based financing and broader risk mitigation mechanisms. If done correctly, innovative finance can support good interventions to better tackle entrenched social issues, by sharpening incentives, creating accountability for results, addressing specific barriers in the system, shifting where risk is held and fostering adaptive management. The study identified four innovative financing models that have the potential to enable disadvantaged urban youth and women in Mozambique to access economic opportunities. Some focus more on the supply side, working primarily with DUYW to improve their skills, employability and facilitate entry into the workforce. Others focus on the demand side, working with enterprises to enable them to scale, improve gender practices and encourage them to employ DUYW. Two of the shortlisted models sit across both demand and supply.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego; empowerment / empoderamento; gender / género; private sector / setor privado; urbanization / urbanização; youth / juventude

Navengando o espaço cívico em contexto da pandemia da COVID-19: o caso de Moçambique - Pereira, Crescêncio; Forquilha, Salvador; Shankland, Alex (Desafios para Moçambique 2021, 2021)
Este artigo circunscreve-se no âmbito do projecto de pesquisa Navigating Civic Space in a Time of Covid-19 (Navegando o Espaço Cívico em Tempo da Covid-19), que procurou analisar em que medida o coronavírus estava a contribuir para a abertura ou o fechamento do espaço para a acção cívica em três países, nomeadamente Moçambique, Nigéria e Paquistão. Com enfoque em Moçambique, este artigo serve-se de ferramentas teóricometodológicas produzidas pela equipa de pesquisa dos três países acima mencionados e estrutura-se essencialmente em torno das três principais questões da pesquisa: · O que se sabe sobre a tendência do espaço cívico em Moçambique antes da chegada da pandemia da COVID-19? · Como é que diferentes actores estão a responder à pandemia da COVID-19 e de que maneira estas respostas vêm a afectar o espaço cívico em Moçambique? · Quais são as implicações de médio e longo prazo para a governação em Moçambique? O material usado para a elaboração do artigo foi produzido com base numa abordagem metodológica que combina quatro componentes, nomeadamente a) avaliação de base sobre a natureza do espaço cívico em Moçambique antes da pandemia da COVID-19; b) painel virtual de observação, constituído por especialistas moçambicanos da sociedade civil, com reuniões mensais; c) análise de meios de comunicação social com recurso a catálogos de eventos; d) entrevistas com uma selecção de informantes-chave para complementar a informação produzida pelas outras componentes. Neste contexto, foi elaborado um relatório de avaliação de base (Pereira, C. & Forquilha, 2020) e foram realizadas seis sessões de painéis virtuais de observação. Com temas previamente acordados, as sessões mensais tinham a duração de duas horas e os assuntos nelas discutidos eram gravados, registados e transformados em relatórios mensais que, posteriormente, eram discutidos em encontros mensais internacionais, envolvendo equipas de pesquisa do IDS, IESE e os parceiros de pesquisa da Nigéria e do Paquistão.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; civic space / espaço cívico; health - COVID-19 / saúde – COVID-19; politics / política

A COVID-19 e as vacinas em Moçambique: algumas notas para reflexão a partir da teoria <sociedade de risco> - Posse, Lúcio (Desafios para Moçambique 2021, 2021)
No presente texto, procuro, por meio da teoria «Sociedade de Risco», elaborada por Ulrich Beck (2011 [1986]), reflectir sobre como os «moçambicanos» elaboram os seus significados e sentidos de risco em relação à COVID-19 e à vacina, e como estes têm estado a desenvolver os seus comportamentos na resposta à pandemia e à vacina. Em termos pragmáticos, procuro chamar a atenção para a necessidade da compreensão dos riscos, como forma de tentar fazer com que as respostas, não só à COVID-19, mas também a outros fenómenos, não fiquem reféns das percepções dos riscos, ao ponto de as comprometer – no sentido de ignorar ou exagerar –, porque, como refere (Beck, 2002:4), «o maior perigo não é o risco [em si], mas a percepção [que as sociedades podem desenvolver] do risco [ao ponto dos seus comportamentos se tornarem num obstáculo para a resolução dos problemas]». Com este texto, mostro que a percepção – à semelhança de outros contextos – que a sociedade moçambicana tem da COVID-19 e da vacina são produto da «racionalidade social do risco», na medida em que os seus sentidos e significados são determinados por questões socioeconómicas, culturais (particularmente os hábitos alimentares), raciais, climáticas, políticas e por experiências: (i) da colonização no uso da medicina para dominar e fazer experimentos clínicos nos africanos, e (ii) da falta de tratamento e da incapacidade dos sistemas de saúde darem resposta ao vírus e aos efeitos colaterais das vacinas, que por vezes causam a morte. Ademais, estas percepções têm estado a estruturar o comportamento dos moçambicanos, primeiro, no que se refere à doença, ao manifestarem, de um lado, a indiferença e/ou despreocupação por considerarem que a doença é dos «outros» e, do outro, pela tomada de medidas de prevenção, num claro sinal de pânico e; segundo, quanto à vacina ao manifestarem, de um lado, a desconfiança em relação à origem, segurança e objectivos da vacina e, do outro, ao receberem a vacina por acreditarem que, em termos de riscos/ benefícios, há muito mais benefícios em receber a vacina.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; politics / política

A recessão económica em Moçambique: foi a COVID-19? Um olhar a partir do sector externo - Sambo, Michael Godet (Desafios para Moçambique 2021, 2021)
Este artigo argumenta que a crise económica em Moçambique não resulta da eclosão da pandemia em si, e dos seus efeitos directos na economia moçambicana, mas sim, que a pandemia exacerbou uma crise pré-existente. O artigo resulta de análise bibliográfica e documental, com ênfase para a análise de dados estatísticos de múltiplas fontes internacionais e nacionais, destacando as fontes oficiais, e analisa as dinâmicas económicas no contexto da COVID-19, com enfoque nas relações económicas de Moçambique com o resto do Mundo desde antes da eclosão da pandemia até aos princípios de 2021. Além da introdução, este artigo é desenvolvido em duas secções seguidas da conclusão. A primeira secção analisa as dinâmicas das políticas públicas no contexto da dependência externa, e a segunda investiga as dinâmicas da economia de Moçambique em relação ao resto do mundo, analisando os antecedentes e as variações no âmbito da COVID-19, com vista a aferir a sua relação; segue-se finalmente uma conclusão e implicações da análise.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19

Lições da COVID-19 sobre o papel da poupança doméstica: O que dizer de Moçambique? - Siúta, Moisés (Desafios para Moçambique 2021, 2021)
O presente artigo procura discutir lições que se podem tirar em relação ao papel da poupança para Moçambique, no âmbito da pandemia da COVID-19. O artigo inspira-se na pesquisa sobre poupança, pobreza e protecção social desenvolvida pelo Instituto de Estudos Sociais e Económicos (IESE), que estabelece a ligação entre poupança e protecção social, tendo em vista estudar mecanismos que permitam desenvolver um sistema de protecção social financeiramente viável em Moçambique (Siúta, 2019b). O objectivo deste artigo é estabelecer a ligação entre a poupança e a COVID-19, discutindo o seu papel no âmbito da resposta à pandemia. A metodologia usada, além da revisão de literatura, inclui a exploração de dados sobre a evolução da pandemia em diversos países, fornecidos pela Organização Mundial da Saúde (OMS/WHO (World Health Organization)), cuja base de dados foi preparada e disponibilizada publicamente por Ritchie et al. (2020). Para completar a análise através da exploração de dados sobre a economia dos países, analisando, principalmente, a evolução da poupança doméstica e do produto dos países, recorreu-se à base de dados dos indicadores de desenvolvimento dos países, disponibilizada pelo Banco Mundial (World Bank, 2021). O artigo, incluindo a presente introdução, subdivide-se em quatro secções. Nas secções a seguir, na primeira, discute-se a relevância da poupança doméstica, no contexto da pandemia da COVID-19, com base numa abordagem teórica da poupança; a segunda secção, baseada em dados sobre a poupança doméstica e a capacidade de testagem e vacinação contra a COVID-19, procura discutir a relevância da poupança doméstica nos países ao redor do Mundo, incluindo o caso de Moçambique. Na última secção, apresenta-se uma breve discussão sobre o contexto moçambicano e a relevância da poupança doméstica.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; poverty / pobreza; social protection / proteção social; society / sociedade

Acção Social em contexto de COVID-19: Respostas e desafios em Moçambique - Siúta, Moisés; Félix, Matusse (Desafios para Moçambique, 2021, 2021)
O presente artigo tem como objectivo partilhar as medidas de resposta em contexto da COVID-19 implementadas pelo INAS, no âmbito dos programas do Governo para assistência social, tendo em conta que a eclosão da pandemia constituiu mais um factor a colocar o subsistema nacional da Segurança Social Básica (SSB) sob pressão, a fim de dar resposta a um grupo cada vez mais crescente de cidadãos moçambicanos em situação de extrema pobreza e de vulnerabilidade. O artigo está divido em cinco secções, incluindo esta introdução. São abordados os seguintes assuntos: segunda secção, a dimensão da COVID-19 e a relevância da assistência social; terceira, resposta à pandemia no âmbito dos programas do INAS; quarta, os principais desafios da acção social na resposta à pandemia; e a quinta secção apresenta considerações finais e possíveis lições
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - COVID-19 / saúde – COVID-19; social action / ação social; social protection / proteção social

Essencial para quê? Uma visão global de reprodução social sobre a reorganização do trabalho durante a pandemia da COVID-19 - Stevano, Sara; Ali, Rosimina; Jamieson, Merle (Desafios para Moçambique 2021, 2021)
O presente artigo pretende investigar a noção de trabalho essencial através de uma lente feminista global centrada na reprodução social. Abordam-se duas questões principais: primeiro, o que é trabalho essencial e como é que esta terminologia tem sido utilizada em diferentes países do Sul e do Norte Global. Através de uma revisão da literatura, decretos, documentos orientadores e artigos de jornal, procedemos ao mapeamento dos significados de trabalho essencial em todo o Mundo, utilizando como exemplos África do Sul, Brasil, Canadá, Inglaterra, Índia, Itália e Moçambique. Em segundo lugar, tomando como ponto de partida a afirmação feita pelos teóricos da reprodução social de que o reconhecimento de formas de trabalho desvalorizadas como essenciais constitui uma via para revalorizar o trabalho socialmente reprodutivo (Bhattacharya, 2020; Stevano et al., 2021), perguntamos se este potencial foi explorado até agora e, caso contrário, que limitações, omissões e contradições o estão a impedir. A perspectiva global é complementada por um «foco» sobre Moçambique como um país de baixa renda, localizado no Sul Global, ocupando uma posição periférica nas economias globais e regionais e com uma grande percentagem de trabalhadores vulneráveis e essenciais. As ilustrações de Moçambique baseiam-se na investigação preliminar sobre o trabalho nas agro-indústrias, realizado pelas autoras antes da pandemia, em combinação com a revisão de artigos de jornal, documentos orientadores, observações e evidência primária seleccionada durante a pandemia
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; health - COVID-19 / saúde – COVID-19; social reproduction / reprodução social

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Informe Orçamental da Acção Social - Moçambique 2021 - UNICEF (UNICEF and International Labour Organization (ILO), 2021)
O orçamento para a protecção social de 2021 equivale a 10.1 mil milhões de MT Embora as dotações para a protecção social como parte do PIB tenham triplicado na última década – demonstrando um grande empenho político em relação ao sector – o Governo de Moçambique (GdM) precisa aumentar ainda mais o espaço fiscal destinado a programas básicos (não contributivos) de Protecção Social com vista a atingir os seus objectivos estratégicos. O Programa Subsídio Social Básico (PSSB) continua a ser o programa com o maior orçamento, seguido pelo Programa Acção Social Produtiva (PASP) e Programa Apoio Social Directo (PASD), respectivamente. Os programas de protecção social do INAS destinam-se a 1.772. 708 agregados familiares beneficiários no no âmbito do Plano Económico e Social de 2021 O orçamento do PSSB de 2021 revela uma melhoria significativa em termos de equidade na afectação, comparativamente aos anos anteriores, embora a Zambézia ainda esteja subfinanciada relativamente a outras províncias
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; social action / ação social; social protection / proteção social

Social Action Budget Brief - Mozambique 2021 - UNICEF and ILO (UNICEF and International Labour Organization (ILO), 2021)
Highlights The 2021 budget for social protection is worth MZN 10.1 billion. This represents a 50 percent nominal increase relative to the 2020 initial allocation (i.e. the first allocation approved by Parliament in 2020) before the onset of the COVID-19 pandemic. However, it represents a 2 percent nominal decrease relative to revised allocation (i.e. the allocation that was revised by Parliament in November 2020 in response to COVID-19), a 4 percent nominal decrease relative to updated allocation (i.e. funds that arrive at the disposal of social protection institutions), and a 26 percent nominal increase relative to the actual expenditure in 2020 (i.e. funds that were spent at the end of budget year) (see Glossary of budget terminology). It is important to highlight that 2020 revised allocation to the sector was exceptionally high as a result of financial support provided by international finance institutions and development partners to implement the sector’s response plan to COVID-19. While part of these funds appeared in the 2020 budget revision, they are de facto being executed in 2021 (i.e. when the actual transfers to beneficiaries of the Direct Social Support Programme - Post Emergency (PASD-PE) are taking place).
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; Social Protection PEA; budget / orçamento; social action / ação social; social protection / proteção social

Globalização económica e desafios do desenvolvimento humano em contexto de crise em Moçambique - Valá, Salim Cripton (Desafios para Moçambique 2021, 2021)
Este capítulo analisa a relação entre a globalização económica e os desafios de desenvolvimento humano em Moçambique, em contexto de crise, advogando que a não exploração das oportunidades da globalização coloca acrescidos obstáculos ao sucesso na implementação das estratégias de desenvolvimento económico e social nacionais. Entre as questões abordadas, destacam-se as seguintes: é adequado, num ambiente de crise, manter o foco na globalização económica?; que opções de caminhos para promover crescimento inclusivo e gerar mais empregos?; o desenvolvimento humano no País está comprometido devido à crise económica e ao advento da COVID-19? e; como gerar riqueza para assim reduzir a pobreza e promover desenvolvimento sustentável?
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; poverty / pobreza

Electricity access and social sustainability in Mozambique - Salite, Daniela; Cotton, Matthew; Kirshner, Joshua (Oxford Policy Management, 2020)
The demand for access to electricity in developing countries is rapidly increasing as intergovernmental organisations, national governments, and business leaders recognise the social and economic value of infrastructure investment. The institutions that govern energy investment and planning recognise a ‘trilemma’ of system development: low-carbon energy sources are needed to meet global climate change mitigation goals, while also meeting service reliability demands and energy security measures alongside maintaining service affordability, particularly for residents on the lowest incomes in rural, urban, and peri-urban communities. Integrating traditional, centralised grid networks based upon large-scale generation technologies (in the case of Mozambique, this includes hydropower from the Cahora Bassa Dam) with decentralised off-grid renewables such as solar projects in rural communities is a significant technical and governance challenge. Energy providers are tasked with a social mandate to deliver good quality electricity at an affordable price to consumers while widening access to underserved populations. Providing access to clean and reliable energy sources is embodied in Sustainable Development Goal 7 as one of the preconditions for socioeconomic development, poverty reduction, and human wellbeing (Pueyo and Maestre, 2019; UN Energy, 2005). International development practitioners and policy networks recognise the tangible benefits of electricity as a form of energy service provision. These tangible benefits include lighting and powering appliances at domestic, private, and institutional levels and increased telecommunications coverage, which collectively provide new personal and business development opportunities, healthcare and food safety benefits, and improved leisure and night-time education prospects (UN Energy, 2005). They also minimise the health risks and ecological impacts associated with black-carbon fuels such as charcoal, which diminish air quality within residential buildings (Anenberg, 2017) and lead to deforestation (Sedano et al., 2016). In order to enhance electricity sector performance, many sub-Saharan African countries have implemented significant governance reforms. It is necessary, however, to evaluate whether such reforms facilitate expanded social access to electricity, whether they improve service quality, public utility, and financial stability, and whether they lead to broader social and environmental sustainability goals. In this policy brief, we assess these dimensions related to the case of Mozambique, a country where major progress has been made to increase population-wide access to electricity from around 6% in 2004 (Chambal, 2010) to 32% in 2019 (EDM, 2020a). Though policy progress is significant, challenges remain, particularly in rural areas, where only around 6% of the population have electricity access (EDM, 2018a).
Keywords: G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; ⛔ No DOI found

Jovens moçambicanos descontentes com falta de oportunidades (DW.COM, 2020)
No Dia Mundial da Juventude, jovens da província moçambicana de Nampula queixam-se da falta de emprego, de habitação e de acesso ao crédito financeiro. O novo coronavírus também é um dos maiores problemas atualmente.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; employment / emprego; youth / juventude

Humanitarian Response Plan Mozambique (Humanitarian Programme Cycle 2021, 2020)
OCHA Humanitarian Response Plan for Northern Mozambique Conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; displaced communities / comunidades deslocadas

Relatório Independente da Iniciativa de Transparência na Indústria Extractiva - EITI (Extractive Industries Transparency Initiative (EITI), 2020)
Este é o nono relatório de reconciliação dos pagamentos efectuados pelas empresas que operam na indústria extractiva e os recebimentos do Estado. Foram reconciliadas 97% das receitas tributárias provenientes da indústria extractiva. As diferenças apuradas entre os pagamentos das empresas e os recebimentos do Estado correspondem a 0,17% dos montantes confirmados pelo Estado em 2019.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Project for Construction of Bridges on N380 in Cabo Delgado - JICA (2020)
Project outline Project Overview： - This project is to secure smooth and safe connectivity at the road N380 (Sunate - Oasse) through reconstruction of bridges, Messalo1 (45m)/ Messalo-3 (60m)/ Mapuede (45m), thereby contributing to facilitate the economy of Cabo Delgado and neighboring countries
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; infrastructure / infrastrutura

Instituições que aprendem - Relatório para a XXVII Cimeira Ibero-Americana de Chefes de Estado e de Governo - Oliván Cortés, Raúl (XXVII Cimeira Ibero-Americana, 2020)
A pandemia da Covid-19 surgiu de súbito num momento de transição para as instituições e organizações sociais de meio mundo. Antes ainda de se ter ultrapassado a crise de confiança da última década entre os cidadãos e os governos, num momento de grande impulso das iniciativas de governo aberto e de planos de inovação e transformação digital para tornar mais democráticas e eficientes as administrações através de programas políticos encaminhados para configurar um novo contrato social, verde e digital no quadro da Agenda 2030, o coronavírus provocou um choque histórico alterando o curso do século XXI e exigindo uma aceleração de todos os processos em andamento. A complexidade e dimensão da pandemia revelou a necessidade de arquiteturas institucionais mais flexíveis, ágeis e resilientes, capazes de incorporar toda a energia civil para aprenderem com o seu talento e criatividade, dando maior protagonismo à cidadania (ativistas, empreendedores, tecido associativo, academia, makers…) não só na tomada de decisões mas também na configuração e implementação das estratégias. À medida que se afastava do centro a milhões de empregados para teletrabalhar a partir de casa, tornou-se mais poderosa a ideia de pensar nas organizações como fluxos que excedem os organigramas estáticos de lugares e pessoas. Transformar as hierarquias em redes, concebê-las como corpos sociais dinâmicos, não só alarga o seu raio de ação e conectividade externa, mas também reativa as suas forças internas, aflora as lideranças ocultas, multiplica o valor social produzido e maximiza o uso eficiente dos recursos numa época de limitações. Os laboratórios de inovação pública, social ou cidadã, ou laboratórios de governo, a par de outras formas de inovação aberta e configuração social, reivindicam-se como projetos inspiradores de uma mudança de paradigma: de instituições que ordenam para instituições que aprendem. Pensar nas organizações sob a ótica da ciência das redes e da ética dos rizomas – nós, ligações, hubs, comunidades… – deverá permitir-nos uma aproximação à complexa e subtil tarefa de configurar os ecossistemas de inovação e criatividade no âmbito público e social. Este relatório propõe um modelo denominado Hexágono da Inovação Pública (HIP) que promove uma transformação sistémica através de seis vetores (OPEN_ aberto, TRANS_ transversal, FAST_ rápido, PROTO_ modelado, CO_ colaborativo e TEC_ tecnológico) baseados nas propriedades das redes e na análise de 105 metodologias usadas pelas agências mais inovadoras do mundo. Incluem-se uma ferramenta de autodiagnóstico e o HIP-SIM, uma primeira aproximação a um software aberto para visualizar, modelar e simular a criação de ecossistemas inovadores com o qual queremos favorecer a comunidade e o debate internacional.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - tool / ferramenta; decentralization / descentralização; government policy / politica governamental; innovation / inovação

Guião metodológico para gestão de terras urbanas: gestão de terras urbanas municipais - República de Moçambique: Ministério do Meio Ambiente (República de Moçambique: Minitério da Terra e Ambiente, 2020)
O objectivo deste manual é auxiliar os municípios no contexto da gestão de terra, com especial foco na regularização do DUAT (Direito de Uso e Aproveitamento da Terra) e respectivas construções. O manual pretende abranger o maior número de situações que ocorrem no dia-a-dia, apresentando soluções apoiadas na presente legislação. Pretende-se que o manual seja um valioso material de apoio à capacitação das equipas técnicas dos municípios e áreas urbanas. O objectivo do manual é igualmente informar o público e capacitar os técnicos dos municípios e outras instituições com melhores técnicas e práticas para aperfeiçoar a gestão de terras de acordo com a legislação actual.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; governance / governação; land governance / gestão de terra; urbanization / urbanização

Economia Política da Governação de Recursos Naturais em Nampula - Salimo, Padil (Akilizetho – ADS, 2020)
A Akilizetho-ADS elaborou um estudo denominado Economia Política da Governação dos Recursos Naturais, em Nampula. A pesquisa foi feita entre Dezembro de 2019 e Janeiro de 2020. A abordagem do estudo foi baseada numa análise de economia política e circunscrito apenas aos recursos minerais e hidrocarbonetos. O objectivo do estudo foi de compreender as relações entre governos, empresas extractivas, comunidades, sociedade civil e reflectir sobre as dinâmicas de governação da indústria extractiva e suas implicações sobre os direitos das comunidades afectadas.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; natural resources / recursos naturais

Mozambique: Analytical Report on Decentralisation - Salimo, Padil (Asociação Nacional de Municipios de Mozambique - ANAMM, EU and UCLG Africa, 2020)
The United Cities and Local Governments of Africa (UCLGA) commissioned this report in coordination with the National Association of Municipalities of Mozambique (ANAMM) to analyse the political economy of decentralisation of Mozambique. The report provides information in support of the ANAMM discussion and dialogue toward the new European Union (EU) programming process of cooperation with local authorities (LAs) for the 2021-2027 period. This report was developed in line with another called “Compendium of References” which is also part of the preparation for the EU programming process of cooperation with the Las. The analytical report on political economy pretends to explore the extent to which the central government embraced the conceptualisation of territorial development, the level of commitment of central government in recognizing the role of local authorities in the territorialisation of the national development agenda, and the opportunities and constraints created by the decentralisation system for the empowerment of local authorities as developmental actors. The political economy analysis catches the key aspects of how political and economic power influences the way how decentralisation is implemented and contested, the incentives behind the political actors and interests groups and how they impact the decentralisation reforms outcomes. The report serves as a background document to a seminar of the members of the ANAMM, which is part of a process of building consensus over the key priority action to include in the municipalities’, or interchangeably called in the report also as local authorities, roadmap for dialogue with the central government and the EU Delegation in Maputo, Mozambique. The expected result involves the following: (i) An analysis of the political economy of decentralisation, the feasibility of the new local authorities (LAs) driven political agenda and the opportunities and constraints created by the decentralisation reforms; (ii) An overview of the state of art regarding the territorialising of national policies and global agendas including SDGs, in terms of both policies and programs adopted in the framework of the national development plan; (iii) A SWOT quick analysis of the ANAMM; and (iv) The state of the art concerning the territorialisation of national policies and global programs, including Sustainable Development Goals (SDGs), both at the level of policies and programs implemented within the framework of the National Development Plan.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Qualidade da assistência pré-natal em Nampula, Moçambique - Muleva, Belarmina Reis (Universidade de São Paulo, 2020)
A realização da consulta pré-natal de alta qualidade está diretamente relacionada aos melhores indicadores maternos e fetais e à prevenção de morbimortalidade materna. Em Moçambique, estudos sobre assistência pré-natal mostram que a maior parte das mulheres fez pré-natal, mas apenas metade fez as quatro ou mais consultas preconizadas pelo Ministério da Saúde. Além disso, as gestantes têm se apresentado aos centros de saúde para fazerem sua primeira consulta pré-natal somente no final do segundo trimestre da gestação. Essas questões mostram que a qualidade da assistência ao pré-natal é ainda um desafio, embora haja poucos estudos sobre o tema naquele contexto. Objetivo: Avaliar a qualidade da assistência pré-natal entre as mulheres do município de Nampula, em Moçambique. Método: Trata-se de um estudo quantitativo, do tipo transversal, realizado no município de Nampula, em Moçambique, na África. A amostra constou de 393 mulheres de 18 a 49 anos, com parto ocorrido em maternidade ou no domicílio no segundo semestre de 2019. As entrevistas foram conduzidas por meio de instrumento estruturado, aplicado face-a-face, até 15 dias após o parto. A qualidade da assistência pré-natal foi analisada com base nas diretrizes do Ministério da Saúde de Moçambique. A qualidade do pré-natal foi categorizada em inadequada e adequada. Modelos de regressão logística múltipla foram conduzidos para analisar os aspectos associados a ter realizado pré-natal adequado. Resultados: As mulheres participantes do estudo tinham, em média, 26 anos de idade, e metade tinha ensino primário (52,4%). Embora todas as mulheres tenham realizado o pré-natal, apenas 13,0% tiveram o pré-natal classificado como adequado. Mulheres que realizaram pré-natal em gestações anteriores (OR=4,28; IC95%=1,45-12,62) e com gravidez planejada (OR=2,51; IC95%=1,11-5,68) foram as que tiveram mais chance de ter um pré-natal adequado. Observou-se que a assistência pré-natal não atendeu ao que é preconizado, como a idade gestacional de início do pré-natal, número mínimo de consultas a serem feitas, realização de alguns exames (hemograma, glicemia, tipagem sanguínea e fator Rh) e oferta de orientações sobre sinais de risco e de parto. Quanto à satisfação com a assistência pré-natal recebida, mais da metade das mulheres mostrou-se insatisfeita com o tempo de espera para ser atendida pela profissional de saúde. Conclusão: De modo geral, os critérios preconizados para que uma assistência ao pré-natal seja de alta qualidade não estão incorporados na prática clínica no município de Nampula.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - health services / serviços de saúde; health - maternal and child / saúde - materno-infantil; health / saúde

Covid-19: Organizações questionam gastos do Governo moçambicano | DW | 11.08.2020 - Deutsche Welle (DW.COM, 2020)
Em Moçambique, a sociedade civil aponta falta de transparência e pede esclarecimentos ao Governo sobre os 14 mil contratos sem concurso público e os 68 mil milhões de meticais gastos durante o estado de emergência.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; health - COVID-19 / saúde – COVID-19; health / saúde; transparency / transparência

Mozambique Crisis Response Plan 2020 - IOM - International Organisation for Migration (IOM - International Organisation for Migration, 2020)
The overall objective of IOM's strategy is to support displaced persons and other affected populations in Mozambique to build resilience and progress towards sustainable solutions to displacement while ensuring a continuous response to critical humanitarian needs and rapid response capacities in case of a new disaster and crisis. Recovery and resilience in Mozambique will be facilitated through an effective and locally owned framework that addresses the lifesaving and longer-term needs of affected populations. Ultimately, the plan aims at establishing the basis for recovery and crisis prevention in communities and continuing being a key partner of the Government of Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; displaced communities / comunidades deslocadas

Alternative Expressions of Citizen Voices: The Protest Song and Popular Engagements with the Mozambican State - Manhiça, Anésio; Shankland, Alex; Taela, Kátia; Gonçalves, Euclides; Maivasse, Catija; Tadros, Mariz (Institute of Development Studies, 2020)
This study examines Mozambican popular music to investigate three questions: Are notions of empowerment and accountability present in popular music in Mozambique? If so, what can these existing notions of empowerment and accountability reveal about relations between citizens and state institutions in general and about citizen-led social and political action in particular? In what ways is popular music used to support citizen mobilisation in Mozambique? The discussion is based on an analysis of 46 protest songs, interviews with musicians, music producers and event promoters as well as field interviews and observations among audiences at selected popular music concerts and public workshops in Maputo city. Secondary data were drawn from radio broadcasts, digital media, and social networks. The songs analysed were widely played in the past two decades (1998–2018), a period in which three different presidents led the country. Our focus is on the protest song, conceived as those musical products that are concerned with public affairs, particularly public policy and how it affects citizens’ social, political and economic life, and the relationship between citizens and the state.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; empowerment / empoderamento

The presource curse in Africa: Economic and political effects of anticipating natural resource revenues - Frynas, Jedrzej George; Buur, Lars (The Extractive Industries and Society, 2020)
The notion of the ‘resource curse’ suggests that large inflows of extractive industry revenues cause many adverse macro-economic and political effects. The resource curse literature focuses on the impact of actual inflows of extractive resource revenues. However, anticipation of future resource revenues can also lead to negative macro-economic and political effects even before resource extraction takes place, which points to the role of behavioral aspects of the ‘resource curse’. Using empirical evidence from three African countries, this article investigates to what extent the anticipation of future extractive revenues led to ‘presource curse’ effects. It finds that all three countries experienced negative effects as a result of anticipation of future extractive revenues, including economic growth volatility, higher levels of national debt, eroded governance and societal conflicts. Given the phenomenal increase in oil, gas and metal ore exploration across Africa, it is likely that many countries experience the negative effects of a presource curse without natural resource extraction or long before natural resources are actually extracted.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

The politics of domestic gas: The Sasol natural gas deals in Mozambique - Salimo, Padil; Buur, Lars; Macuane, Jose Jaime (The Extractive Industries and Society, 2020)
This article explores the ways in which the ruling Frelimo elite in Mozambique engaged creatively with the opportunities and constraints created by Sasol's Pande and Temane natural gas project as they have evolved from the early 2000s until today. This is a period that has seen ruling-elite actors become involved in various projects related to the production of electricity from ‘domestic natural gas’. We argue that focusing on the initial gas investment and how it evolved over time makes it possible to understand the dynamics related to deal-making during the formative years when the Mozambican petroleum industry was reformed by separating its commercial and regulatory functions. More specifically we explore how access to revenues and rents related to natural gas projects have evolved. We point out that, although the Pande-Temane gas project has increased revenue generation, most of the gas was sold to the South African major, Sasol, for a very low amount of revenue during the first phase of the project. Revenues from the second phase, starting in 2012, did not increase dramatically, even though Mozambique acquired access to 50% of the gas from the extension of the pipeline and increased production. Instead, the increase in domestic gas allocated to the Mozambican market involved the allocation and distribution of gas to private companies at special prices, most of which were controlled by dominant ruling-elite factions under the Chissano and Guebuza governments. We argue that this has been the main mechanism for the transfer of rents from the public to the private domain.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Niassa: MASC desencoraja envolvimento de jovens nos ataques terroristas - User, Super (2020)
A Fundação MASC - Mecanismo de Apoio a Sociedade Civil, no Niassa, desencoraja o envolvimento de jovens nos ataques terroristas na vizinha província d...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; civil society / sociedade civil; conflict / conflito; youth / juventude

The Secret to the Northern Mozambique Insurgency’s Success - Emilia Columbo (War on the Rocks, 2020)
This has been a banner year for Ahlu-Sunnah Wa-Jama (ASWJ) — or al-Shabaab, as locals call it — operating in northern Mozambique. Between January and
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

First confirmed occurrence of the yellow fever virus and dengue virus vector Aedes (Stegomyia) luteocephalus (Newstead, 1907) in Mozambique - Abílio, Ana Paula; Kampango, Ayubo; Armando, Eliseu J.; Gudo, Eduardo S.; das Neves, Luís C. B.; Parreira, Ricardo; Sidat, Mohsin; Fafetine, José M.; de Almeida, António Paulo G. (Parasites & Vectors, 2020)
Mozambique, same as many other tropical countries, is at high risk of arthropod-borne virus (arbovirus) diseases and recently two dengue virus (DENV) outbreaks occurred in the northern part of the country. The occurrence of some important vector species, such as Aedes (Stegomyia) aegypti (Linnaeus) and Ae. (Stg.) albopictus (Skuse), besides several other sylvatic vectors, have been reported in the country, which may indicate that the transmission of some arboviruses of public health importance may involve multiple-vector systems. Therefore, knowing the occurrence and distribution of existing and the new important vectors species, is crucial for devising systematic transmission surveillance and vector control approaches. The aim of this study was to map the occurrence and distribution of mosquito species with potential for transmitting arboviruses of human and veterinary relevance in Niassa Province, Northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lago; GP - Niassa; L - english / inglês; health / saúde

Indonesia's Guaranteed Microfinance Programme (KUR): Lessons from the First Stage of Implementation - ProQuest (2020)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Influence of institutional factors on the performance of the agricultural sector in Mozambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Abstract: This paper is a review of the institutions and the performance of the agricultural sector in Mozambique, using an analysis table adapted to the assessment of the connections between the institutions and economic development. In the first part, information is presented on the performance of the sector between 2008 and 2017, showing a per capita reduction in productivity and the production of foodstuffs. The second part offers an analysis on the extent to which, and the way that, the development of the sector institutions influenced agricultural performance during that period. There was found to have been institutional instability that affected performance in the sector, which was unable to slow the reduction in production and productivity, which could reflect a wider socioeconomic and institutional environment, i.e. beyond the agricultural sector. The third part looks at some elements for reflection on institutional issues that could contribute to the debate on the future development of the agricultural sector. We refer to the need to think about the future of agriculture in Mozambique from a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; institutions / instituições

Influência de Factores Institucionais no Desempenho do Sector Agrário em Moçambique - Carrilho, João Z.; Ribeiro, Rui N. (2020)
Este artigo constitui uma revisão das instituições e do desempenho do sector agrário em Moçambique, aplicando um quadro de análise adaptado à avaliação da ligação entre as instituições e o desenvolvimento económico. Na primeira parte, apresenta-se informação sobre o desempenho do sector entre 2008 e 2017, verificando-se redução da produtividade e da produção per capita de alimentos. A segunda parte oferece uma análise sobre a medida em que, e o modo como, a evolução das instituições do sector influenciou o desempenho da Agricultura nesse período. Verifica-se ter havido instabilidade institucional que afectou o desempenho do sector, não se tendo logrado travar a redução da produção e da produtividade, o que eventualmente reflecte um ambiente socioeconómico e institucional mais amplo, isto é, além do sector agrário. Na terceira parte, colocam-se alguns elementos de reflexão sobre questões institucionais que possam contribuir para o debate sobre o desenvolvimento futuro do sector agrário. Sugere-se a necessidade de pensar o futuro da Agricultura em Moçambique numa perspectiva de longo prazo, com foco na adopção e estabilização de um quadro institucional orientado para o aumento da produtividade agrária e para a preservação do ambiente.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura; institutions / instituições

Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic: Synthesis and policy recommendations - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions, 2020)
We now proceed to bringing together the different elements of previous chapters with the aim of presenting the essence of this country study of Mozambique. In the next section, we take stock and revisit our points of departure from Chapters 2 and 3. This background work culminated in the identification of nine thematic areas, subsequently subjected to individual in-depth studies in Chapters 4–12. We outline the core findings from these studies, and present our integrated analysis of key institutional weaknesses. Next, we go a decisive step further, and analyse and discuss their proximate causes and deep factors. We end with a series of ideas for reform, as an input to national reflection, debate, and action.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; ⛔ No DOI found

Moçambique numa encruzilhada: um diagnóstico institucional: Síntese e recomendações de política - Cruz, Antonio S; Ferreira, Ines A; Flentø, Johnny; Tarp, Finn (Economic development and institutions – Mozambique at a fork in the road: an institutional diagnostic, 2020)
Neste capítulo reunimos os diferentes elementos dos capítulos anteriores com o objectivo de apresentar a essência deste estudo sobre Moçambique. Na secção seguinte, fazemos um balanço e revisitamos os nossos pontos de partida dos Capítulos 2 e 3. Este trabalho de fundo culminou na identificação de nove áreas temáticas, posteriormente sujeitas a estudos individuais aprofundados nos Capítulos 4-12. Descrevemos as principais conclusões destes estudos e apresentamos a nossa análise integrada das principais fraquezas institucionais. Segue-se um passo decisivo, em que analisamos e discutimos as causas imediatas e os factores profundos destas fraquezas. Finalmente, terminamos com um conjunto de ideias de reforma, como contributo para a reflexão nacional, o debate e a acção.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; ⛔ No DOI found

Desenvolvimento económico e instituições em Moçambique: Factores que afectam a gestão das finanças públicas - Cruz, António S.; Mafambissa, Fausto J. (2020)
Moçambique alcançou um desenvolvimento socioeconómico incipiente mas ainda frágil, desde 1975. Apesar de o sistema de gestão das finanças públicas ter sido reformado e melhorado, o seu desempenho tem vindo a enfraquecer desde 2013. Utilizando uma abordagem económica institucional, identificámos a estratégia de crescimento económico, o princípio da separação de poderes e o grau de descentralização como factores-chave que afectam o sistema de gestão das finanças públicas. Como a actual estratégia baseada nos recursos naturais parece estar a falhar, sugerimos uma estratégia alternativa de crescimento balanceado no contexto de um sistema político democrático efectivo. Isso implicaria a identificação de políticas prioritárias necessárias para promover um desenvolvimento sustentável e inclusivo.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; institutions / instituições

Economic development and institutions in Mozambique: Factors affecting public financial management - Cruz, António S.; Mafambissa, Fausto J. (2020)
Abstract: Mozambique has achieved incipient but still fragile socio-economic development since 1975. The public financial management system has been reformed and improved, but its performance has weakened since 2013. Applying an institutional economics approach, we have identified the economic growth strategy, the separation of powers principle, and the degree of decentralization as key factors affecting the public financial management system. As the current strategy based on natural resources seems to be failing, we suggest an alternative balanced growth strategy in the context of an effective democratic political system. It would entail the identification of policy priorities required for fostering sustainable and inclusive development.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; institutions / instituições

Alcançando os mais vulneráveis na resposta da proteção social à crise da Covid-19 em Moçambique: Oportunidades e Desafios - de Lima Vieira, Ana Carolina; Vicente Andrés, Rubén; Monteiro, Denise (OIT, 2020)
O Governo de Moçambique está a responder ao impacto negativo socioeconómico da Covid-19 através da expansão do seu sistema de proteção social priorizando as populações mais vulneráveis à crise: aquelas residentes nas áreas urbanas, periurbanas e fronteiriças. Com o apoio dos parceiros de desenvolvimento, está a conseguir assegurar uma resposta política rápida, inovadora e coordenada.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; social protection / proteção social; ⛔ No DOI found

Donor relations and sovereignty - Flentø, Johnny; Simao, Leonardo Santos (2020)
As a sovereign country, Mozambique initially relied on international solidarity and managed its donor relations well. Donor dependency entailed some loss of agency for the government as it allowed donors to challenge its capacity but never its authority. However, in the last decade, donor countries have expressed disappointment with reforms and challenged the government’s legitimacy. This is not only because of developments in Mozambique. Donor countries have become less enthusiastic about long-term, harmonized development cooperation and less concerned with aid effectiveness for poverty alleviation and inclusive growth. Aid budgets are under pressure and development finance is linked more to other donor countries’ foreign policy concerns, especially security and commerce. Mozambique should expect increasing instrumentalization of aid budgets by donors. It must be able to address its partners’ concerns other than those of poverty alleviation, human rights, and democracy and carefully weigh conflicting interests of its partners against its own long-term interests. The institutions Mozambique developed to deal with donors are not well suited to today’s challenges. They focus on less relevant areas of the relationship with foreign countries, which often serve other agendas. Reforms could start with strengthening Mozambique’s foreign service as a genuine coordinator of foreign relations and the establishment of greater discipline around national plans and strategies. Institutionalizing strong links between the foreign ministry and key economic ministries under the leadership of the prime minister could help.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo

Relações com os doadores e soberania - Flentø, Johnny; Simao, Leonardo Santos (2020)
Como país soberano, Moçambique confiou inicialmente na solidariedade internacional e geriu bem as suas relações com os doadores. A dependência em relação a estes implicou que o Governo experimentasse alguma perda de capacidade de intervenção, permitindo que os doadores desafiassem a sua competência, embora nunca a sua autoridade. No entanto, na última década, os países doadores expressaram o seu desapontamento com as reformas e contestaram a legitimidade do Governo. Isto não se deve apenas aos desenvolvimentos ocorridos em Moçambique. Os países doadores ficaram menos entusiasmados com a cooperação para o desenvolvimento harmonizada a longo prazo e menos preocupados com a eficácia da ajuda ao desenvolvimento no alívio da pobreza e no crescimento inclusivo. Os orçamentos de ajuda ao desenvolvimento estão sob pressão e o financiamento do desenvolvimento está mais ligado às preocupações de política externa de outros países doadores, especialmente nas áreas da segurança e do comércio. Moçambique deve esperar uma instrumentalização crescente dos orçamentos de ajuda ao desenvolvimento por parte dos doadores. E deve ser capaz de abordar as preocupações dos seus parceiros para além da redução da pobreza, dos direitos humanos e da democracia e ponderar cuidadosamente o conflito entre os interesses dos seus parceiros e os seus próprios interesses a longo prazo. As instituições que Moçambique desenvolveu para lidar com os doadores não estão adequadamente adaptadas aos desafios actuais. Concentram-se em áreas menos relevantes da relação com países estrangeiros, que muitas vezes servem outras agendas. As reformas poderiam começar pelo reforço do serviço de política externa de Moçambique como um verdadeiro coordenador das relações externas e pelo estabelecimento de uma maior disciplina em torno de planos e estratégias nacionais. Uma ajuda poderia ser a institucionalização de ligações fortes entre o Ministério dos Negócios Estrangeiros e os principais ministérios económicos sob a liderança do primeiro-ministro.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo

Reformas de descentralização em Moçambique: o papel das instituições na definição dos resultados - Forquilha, Salvador (2020)
Com a introdução das reformas económicas nos finais dos anos 1980 e a abertura do espaço político e o fim da guerra civil no início dos anos 1990, teve início em Moçambique o processo de descentralização. Diferentes pesquisas desenvolvidas nos últimos anos mostram que, à semelhança do que acontece em outros países da África subsaariana, o impacto das reformas de descentralização na promoção do desenvolvimento local e no aprofundamento da democracia em Moçambique é modesto. Como explicar esse impacto modesto? Com base em três reformas importantes do processo da descentralização em Moçambique, nomeadamente os '7 milhões', a municipalização e a governação descentralizada provincial, este artigo procura responder à pergunta analisando a maneira como diferentes dimensões das instituições afectam os resultados das reformas. O argumento principal do artigo sublinha a ideia segundo a qual os resultados das reformas de descentralização em Moçambique são condicionados pela natureza e pelos mecanismos do funcionamento do sistema político. Entre os factores/constrangimentos institucionais, a capacidade do Estado e autonomia face aos interesses privados, particularmente de grupos políticos, destacam-se nas três reformas analisadas ao longo deste artigo. Neste contexto, as reformas cristalizam a maneira como os interesses de grupos, particularmente políticopartidários, capturam o Estado e as usam como um mecanismo de manutenção e reforço do poder político. Nesse sentido, a descentralização, mais do que um meio para a melhoria da provisão de serviços públicos e o aprofundamento da democracia, funciona como um instrumento para o reforço do controlo do Estado e a acomodação das elites. Provavelmente, este é o maior desafio que a descentralização enfrenta em Moçambique e, por isso, constitui um aspecto fundamental a tomar em conta em qualquer reforma nessa área, no contexto do aprofundamento da democracia e da promoção do desenvolvimento local.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; institutions / instituições

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Saúde, desenvolvimento e factores institucionais: o caso de Moçambique - Garrido, Paulo Ivo (2020)
Este texto tem por objectivo central mostrar o impacto que as instituições têm no desempenho do sector da Saúde em Moçambique. No texto demonstra-se que, de entre os Determinantes Sociais da Saúde, as instituições têm um papel central no desempenho do sector da Saúde — e, por seu intermédio, no desenvolvimento económico e social — dos moçambicanos, em especial dos mais pobres e mais vulneráveis, como as crianças, as mulheres, as pessoas com deficiência e os idosos. Argumenta-se também que as deficiências e ineficiências do funcionamento do sector da Saúde em Moçambique resultam em larga medida do facto de as instituições com influência no sector da Saúde serem controladas por uma minoria de privilegiados que não dá a prioridade devida às necessidades básicas em saúde da maioria da população. Finalmente, argumenta-se que as medidas de carácter institucional mais importantes para a melhoria do estado de saúde dos moçambicanos são a revisão da Constituição da República, o reforço do Sistema Nacional de Saúde (em particular do Serviço Nacional de Saúde) e a redução da pobreza e das iniquidades económica e social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Natural resources, institutions, and economic transformation in Mozambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
In the light of Mozambique’s natural resources boom—especially its large-scale investments in mining, oil, and gas—this paper analyses the prospects for the extractive industries to contribute to economic transformation from an institutional perspective. To this purpose, we address the institutional dynamics of the resources sector and consider the underlying causes of the identified outcomes. The National Development Strategy, as the instrument presenting the vision for economic transformation and diversification, is discussed. The paper is based on a desk review—documental and bibliographic—and on primary data gathered by the authors as part of their research into the field of natural resources and the political economy of development. We conclude that, given Mozambique’s political patronage and clientelism, intra-ruling elite competition, limited productive base, weak state capacity, high level of poverty, and recurrent fiscal deficits, the prospects of the current resource boom leading to economic transformation, despite its considerable potential, are at best uncertain.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Recursos naturais, instituições e transformação económica em Moçambique - Macuane, Jose Jaime; Muianga, Carlos (2020)
Face ao boom de recursos naturais em Moçambique — em especial dos seus grandes investimentos em exploração mineira, petróleo e gás —, este documento analisa a perspectiva de as indústrias extractivas contribuírem para a transformação económica de um ponto de vista institucional. Para esse efeito, abordamos a dinâmica institucional do sector dos recursos e consideramos as causas subjacentes aos resultados identificados. É discutida a Estratégia Nacional de Desenvolvimento enquanto instrumento que apresenta a visão para a transformação e diversificação económica. O documento baseia-se numa revisão documental e bibliográfica e em dados primários recolhidos pelos autores no âmbito da sua investigação no campo dos recursos naturais e da economia política do desenvolvimento. Concluímos que, dado o patrocínio político e o clientelismo de Moçambique, a competição no interior da elite governante, a base produtiva limitada, a fraca capacidade do Estado, o elevado nível de pobreza e os défices fiscais recorrentes, as perspectivas de que o actual boom de recursos leve à transformação económica, apesar do seu considerável potencial, são, na melhor das hipóteses, incertas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; economic development / desenvolvimento económico; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Extractive Industry Transparency Index 2019-2020 - Mapisse, Inocência; Mate, Rui; Cortez, Edson (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2020)
The extractive industry, particularly the oil and gas sector, has proved promising in the Mozambican economy with potential to contribute to economic growth. It is expected that in the next 3 years the country will show growth in the order of two digits. However, in order to ensure the transmission of growth to economic development based on the exploitation of these resources, there are aspects that should not be ignored such as transparency in governance in the sector. This aspect is also recognized by the government of Mozambique through the Report on Transparency, Governance and Corruption published in July 2019, which emphasizes that the opacity in this sector can give rise to serious conflicts of interest and harm the perception of the population about the real benefits that this industry provides to the country. Although the country is part of the Extractive Industry Transparency Initiative (EITI), whose focus is on the reconciliation of payments made by companies and receipts reported by the Government in the extractive industry sector, there is a gap regarding detailed information on several aspects: tax, social, governmental and other equally relevant and that should be made available on a project-by-project basis.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; transparency / transparência

O sector da educação em Moçambique: do acesso à qualidade epistémica do ensino primário - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Desde os primeiros anos de independência nacional, em 1975, o objectivo central da política educativa de Moçambique tem sido o de assegurar que todas as crianças em idade escolar tenham acesso à escola e nela permaneçam até concluírem a educação básica. Na prossecução deste objectivo, a expansão do acesso ao ensino primário foi realizada com relativo sucesso, uma vez que já se alcançou uma taxa líquida de cobertura escolar de quase 100%. Contudo, o impressionante aumento das taxas de escolarização não tem sido acompanhado por uma correspondente melhoria da qualidade da aprendizagem, havendo, em relação a este aspecto, sinais preocupantes de um retrocesso considerável. Partindo desta observação, o estudo identifica e analisa as variáveis do contexto institucional por detrás da 'escolarização sem aprendizagem'. Os resultados do estudo apontam para a (i) fraca capacidade do Estado, (ii) excessiva dependência da ajuda externa e (iii) fraco envolvimento e participação das comunidades na gestão das escolas, como sendo os factores de maior influência na fraca qualidade da aprendizagem no ensino primário.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

The education sector in Mozambique: From access to epistemic quality in primary education - Mário, Mouzinho; Monjane, Celso M.; Santos, Ricardo (2020)
Abstract: From the early days of national independence in 1975, the central aim of the educational policy in Mozambique has been to ensure that all school-age children have access to school and can remain there until they have completed their basic education. In the pursuit of this aim, the extension of access to primary education was achieved relatively successfully, given that it reached a net rate of school coverage of almost 100 per cent. However, the impressive increase in school attendance rates has not been accompanied by a corresponding improvement in the quality of learning, and there are worrying signs of a considerable setback in relation to this aspect. Using this observation as a starting point, the study identifies and analyses the variables in the institutional context behind ‘schooling without learning’. The results of the study point to (i) weak state capacity; (ii) excessive dependence on external aid; and (iii) poor community involvement and participation in school management, as being factors with a major influence on the poor quality of education in primary schools.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; education / educação; government policy / politica governamental; youth / juventude

Colocar o sistema financeiro ao serviço dos pobres e das PME - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
O esforço de inclusão financeira alcançou resultados positivos, tendo a bancarização da população moçambicana aumentado consideravelmente, em particular depois de 2011-12. Contudo, o impacto económico e social foi limitado, considerando que a produtividade agrícola se tem mantido baixa e os níveis de pobreza ainda são elevados. A doutrina neoliberal na esfera económica, a sua expressão nas políticas monetárias restritivas e a fraqueza do sistema de democracia multipartidária têm sido factores institucionais de constrangimento ao desenvolvimento económico e social. Consequentemente, este estudo propõe algumas medidas de reforma institucional para se expandir o crédito aos agricultores familiares de subsistência, às pequenas e médias empresas, à população em geral e às famílias de rendimento mais baixo em particular. Os jovens poderão beneficiar de créditos mais acessíveis para habitação. Os produtores familiares rurais também necessitam de um suporte sistémico público.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Putting the financial system to work for the poor and SMEs - Osman, Abdul Magid; Osman, Djamila Pontes (2020)
Abstract: The financial inclusion effort achieved positive results, with the number of Mozambicans having access to banking services increasing considerably, particularly after 2011–12. However, the economic and social impact was limited, considering that farm productivity has remained low and poverty levels are still high. The neoliberal doctrine in the economic sphere, its expression in the restrictive monetary policies, and the weakness of the multi-party democracy system have been institutional factors restricting economic and social development. Consequently, this study proposes some institutional reform measures to expand credit to family subsistence farmers, small and medium-sized enterprises, the population in general, and low-income families in particular. Young people could benefit from more accessible housing loans. Rural family farmers also need systemic, public support.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; financial inclusion / inclusão financeira; fiscal policy / política fiscal; monetary policy / política monetária; poverty / pobreza; private sector / setor privado; youth / juventude

Estado de Direito e independência judicial - Trindade, João Carlos (2020)
Estado de Direito e a independência judicial ainda são um projecto por concretizar em Moçambique. As diferentes tentativas de reforma do sistema de justiça até aqui experimentadas, principalmente após a mudança de orientação política e estratégica imprimida a partir da Constituição de 1990, tiveram sempre um cunho imediatista e conjuntural, sob pressões internas e externas nem sempre claras ou bem-intencionadas. É preciso levar a cabo uma verdadeira reforma estrutural para que o Poder Judicial se afirme como verdadeiro poder e, desse modo, favoreça o crescimento equilibrado das empresas, o aumento da produtividade, do investimento e do emprego, e, concomitantemente, a defesa dos direitos e dos legítimos interesses dos indivíduos e dos grupos com menos recursos económicos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Law - Rule of Law / Law - Estado de Direito; corruption / corrupção; economic development / desenvolvimento económico; law / direito

Rule of law and judicial independence - Trindade, João Carlos (2020)
Abstract: The rule of law and judicial independence are a project yet to be achieved in Mozambique. The different attempts made so far to reform the legal system, mainly after the change in political and strategic direction brought about by the Constitution of 1990, were always short-sighted and conjunctural in nature, under domestic and foreign pressure that was not always clear or well-intentioned. Real structural reforms need to be made for the judiciary to be able to affirm itself as a real power and, in this way, favour balanced growth of companies, increased productivity, investment and jobs and, at the same time, the defence of the rights and legitimate interests of individuals and groups with fewer economic resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; Law - Rule of Law / Law - Estado de Direito; corruption / corrupção; economic development / desenvolvimento económico; law / direito

Mozambique LNG Project Could Be Transformational For Mozambique — If Western Environmentalists Don’t Interfere | Africa Oil & Power (2020)
NJ Ayuk discusses the Mozambique LNG project.
Keywords: #Reporting & Media / Reportagem & Mídia; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; private sector / setor privado

Mediating bureaucrats: embedded economic action in the Mozambican sugar industry - Buur, Lars; Nystrand, Malin J. (The Journal of Modern African Studies, 2020)
This article develops the concept of ‘mediating bureaucrats’ by exploring their role during liberal reforms that led to rehabilitation of the sugar industry in Mozambique. By focusing on how relations between the state, government and business are mediated by a group of cadres who have occupied positions in different social domains, the article argues that these ‘mediating bureaucrats’ cannot easily be identified in one-dimensional terms as belonging to either the public or private sector, the state or the market. It is argued that as ‘socially embedded actors’, the group of ‘mediating bureaucrats’ are in a position to translate and mediate between diverse and sometimes conflicting interests and aspirations of the state, the government and business. We use the rehabilitation of the sugar industry in Mozambique to show how mediating bureaucrats adopted two practices – muddling through and translation – in order to straddle conflicting interests during different reform initiatives in post-independence Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Insurgência: No lançamento da ADIN Nyusi ameaça reagir em caso de atentado a coesão - Anacleto, Delfim (Deutsche Welle (DW), 2020)
O norte de Moçambique passa a partir de hoje a contar com uma Agência de Desenvolvimento integrado para promover o crescimento económico e social. E em Pemba, Filipe Nyusi falou com o bispo de Pemba sobre a insurgência.
Keywords: *indexed; ADIN (Agency for Integrated Development of the North); G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Narrativas Alternativas: Lançamento Do Álbum Moçambique Yethu! #stopviolenciaextremista - MASC, Fundação (Fundação MASC, 2020)
Desde o final de 2017, Cabo Delgado, tem sido palco de violentos ataques de grupos […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; civil society / sociedade civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

LAND-at-Scale: Scaling Community Legal Literacy, Land Rights Certification and Climate Resilience in Mozambique - Centro Terra Viva-Estudos e Advocacia Ambiental (CTV); Firma, Terra (Rijksdienst voor Ondernemend Nederland (RVO), 2020)
The main objective of the Land at Scale Program is to increase community legal awareness and strengthen security of land tenure rights, creating capacity at local level to implement and leverage the progressive provisions of the Mozambican legal framework. The programme will contribute to community preparation to intervene in an informed manner in the land sector and will also contribute to the delimitation of community and individual land-use rights based on good faith occupation and customary rights, and their integration into the formal land system. To achieve these objectives, the proponents plan to conduct a large-scale campaign, across selected districts from all three regions of the national territory, with two main and interlinked interventions, namely: 1. Social Preparation & Legal Literacy (Component A), and 2. Community Land Rights Registration and Certification (Component B).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; governance / governação; land governance / gestão de terra

Learning lessons and curbing criticism: Legitimizing involuntary resettlement and extractive projects in Mozambique - Wiegink, Nikkie (Political Geography, 2020)
Since 2011, thousands of people have been resettled in the province of Tete, central Mozambique to make way for open-pit coal mines. These resettlements have received widespread criticism for impoverishing already vulnerable communities and for the repressive action taken against local opposition. This repression is part of a broader array of reactions “from above” that have emerged in relation to protest. One of these reactions “from above” is that representatives of the government of Mozambique and extractive multinational companies increasingly address resettlement in Tete as a process to learn lessons from. These lessons learning practices legitimize future resettlement processes elsewhere, particularly in relation to a highly valued project of liquid natural gas (LNG) extraction in northern Mozambique. Moreover, this approach results in the de-facto co-optation of environmentalist non-governmental organizations (NGOs), whose agendas and funding possibilities are also increasingly tuned towards learning lessons from “Tete” to improve future resettlement elsewhere. Meanwhile, the opposition of those affected by resettlement in Tete is losing resonance, allowing the coal mining companies to continue with business as usual. The data presented in this article is derived from observations made during government-organized national conferences on resettlement in November 2016 and 2018, and additional ethnographic fieldwork over the course of 2016 and 2017 in Maputo and Tete. I take these conferences as a starting point to analyze the politics of evaluation, the legitimization of displacement for extractive projects, and the co-optation of criticism.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês

Total signs agreement with the Government of Mozambique regarding the security of Mozambique LNG project (Total.com, 2020)
Map Mozambique
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; private sector / setor privado

Como Está Cabo Delgado? Webinar 2: Economia Política Dos Recursos Naturais - Observatório do Meio Rural (2020)
Com a entrada no novo milénio, e em virtude do aumento da procura de matérias primas nos mercados internacionais, intensifica-se um modelo de desenvolvimento assente na exploração de recursos naturais. Em Cabo Delgado emerge uma economia extractiva, fortemente dirigida para mercados externos e dependente da oscilação de preços nos mercados internacionais, que o país não tem condições de controlar. Grandes multinacionais envolvem-se numa acesa competição pelo acesso a recursos, em complexas alianças com elites nacionais, também elas em disputa entre si. Neste webinar pretende-se reflectir sobre as lógicas de acumulação aqui envolvidas, assim como o impacto que poderá ter para Moçambique em termos de receitas fiscais, e de desenvolvimento nacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; natural resources / recursos naturais

Depois da ADIN, Celso Correia “ganha” Agência do Zambeze e passa a controlar o desenvolvimento do centro e norte de Moçambique - Nuvunga, Adriano (Centro para a Democracia e Desenvolvimento (CDD), 2020)
Tal como procedeu no caso da passagem da tutela da ADIN para Celso Correia, o CDD defende que a Agência do Zambeze deve estar sob tutela do Conselho de Ministros e a sua direcção deve prestar contras ao Primeiro-Ministro. À semelhança da ADIN, a Agência do Zambeze tem uma visão holística de desenvolvimento e uma actuação transversal que abrange todos os sectores económicos e sociais do Governo, pelo que não faz sentido a sua direcção responder a um Ministro responsável por um único sector, seja ele de Economia ou de Desenvolvimento. Pela sua importância estratégica para o desenvolvimento do pontecial do Vale do Zambeze, a Agência do Zambeze deve ser dirigida por gestores de reconhecido mérito recrutados através por um concurso público transparente e independente, como forma de evitar a gestão danosa e as infracções financeiras denunciadas pelo Tribunal Administrativo em 2018. Quando o Governo de Armando Guebuza criou a Agência do Zambeze em 2010, o objectivo principal era de “assegurar a eficácia e a eficiência no desenvolvimento da parte nacional da bacia hidrográfica do Vale do Rio Zambeze, uma das regiões cujo potencial de recursos e as possibilidades de aproveitamento estudadas apontam como susceptível de, rapidamente, contribuir para o desenvolvimento e crescimento económico e humano auto-sustentado do país”. Volvidos 10 anos depois, a Agência do Zambeze ainda não deu sinais de estar a explorar as potencialidades do Vale do Zambeze para dinamizar o desenvolvimento das províncias do centro do país, que concentram boa parte da população pobre de Moçambique. O Vale do Zambeze tem potencial energético, grandes depósitos de minerais como carvão e ferro, para não falar do potencial agro-pecuário subaproveitado. Não foi por acaso que o político português Almeida Santos uma vez declarou: “Quem tem o Vale do Zambeze não pode ser um país pobre”6. Mas os cerca de 12 milhões de pessoas que vivem nas quatro províncias atravessadas pelo Vale do Zambeze continuam num vale de pobreza.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; rural development / desenvolvimento rural

Broadening the Analysis of Peace in Mozambique: Exploring Emerging Violence in Times of Transnational Extractivism in Cabo Delgado - Alberdi, Jokin; Barroso, Manuel (Global Society, 2020)
This article explores the contemporary expressions of violence and oppression linked to the action of the extractive industry in the northern province of Cabo Delgado, Mozambique. Twenty-five years after the signing of the General Peace Agreement, the debate on peace in the country has remained confined to the resurgence of armed clashes between RENAMO combatants and State security forces in recent years. It is proposed here, however, that the current range of violence that challenge peace in Mozambique is broader and more diverse, requiring an analysis that considers the arrival of transnational extractivism. This study, taking Cabo Delgado province as a case-study, aims to broaden the scope of academic debates by establishing a dialogue with the practice of local peacebuilding, and contributions from the critical political economy of development and the collective capability approach.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; extractive industries / indústrias extractivas

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Our voices must be heard – Youth hubs discuss economic exclusion - Matsinhe, Julião (Centro para a Democracia e Desenvolvimento, 2020)
Youth hubs discuss economic exclusion. Unemployment was singled out as the most pressing challenge that young people face. As an answer to unemployment, these young people highlighted that education must equip students with relevant skills to be innovative and entrepreneurs, and to be competitive in the labor market.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Face ao conflito no norte, o que Moçambique pode aprender da sua própria guerra civil (1976 – 1992)?: Uma análise das dinâmicas da insurgência em Cabo Delgado - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Analisa as dinâmicas da insurgência em Cabo Delgado e procura interrogar o que Moçambique pode aprender dos seus ciclos de violência armada, particularmente a guerra civil, para fazer face ao actual conflito no Norte do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura

How Do Donor-led Empowerment and Accountability Activities Take Scale into Account? Evidence from DFID Programmes in Contexts of Fragility, Conflict and Violence - Anderson, Colin; Fox, Jonathan; Gaventa, John (2020)
Development donors invest significantly in governance reform, including in contexts characterised by conflict and fragility. However, there is relatively little comparative study of their change strategies, and little understanding of what works and why. This paper explores the strategies of six recent DFID-funded programmes in Mozambique, Myanmar, and Pakistan with empowerment and accountability aims. Document review and field interviews are used to analyse the application of multi-scalar or multi-level change strategies, since such approaches are hypothesised to potentially generate more leverage for public accountability reforms. Analysis suggests that these strategies can strengthen citizen ability to navigate governance systems to resolve problems and claim accountability, and can bolster pro-accountability coalitions’ internal solidarity and external legitimacy. Multi-level strategies also appear associated with establishing more significant pressure for reform than exclusively local or national approaches. Yet conventional project reporting focuses on counting activities and outputs rather than analysing the dynamic, interactive processes at work in these strategies, and few evaluations are publicly accessible. To fully understand what kinds of action strengthen citizen demands for accountability requires a more transparent and rigorous approach to learning from donor-led governance interventions.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Republic of Mozambique Joint World Bank-IMF Debt Sustainability Analysis - IDA; IMF (International Development Association (IDA) and the International Monetary Fund (IMF), 2020)
Mozambique’s debt remains in distress, which is unchanged from the previous DSA published in June 2019. Consideringthat, to a large extent, future borrowingand governmentguarantees reflect state participation in the sizable liquified natural gas (LNG) development, debt is deemed sustainable in a forward-looking sense. Participation in the recently announced G20 initiative would provide debt service relief in the near term, thus flattening the projected sharp deterioration in debt liquidity indicators due to the COVID-19 pandemic. The possibility of an extension of the G20 initiative into 2021 would be a further mitigating factor for the debt sustainability assessment. The present value (PV) of external public and publicly guaranteed (PPG) debt relative to GDP is projected to remain above the prudent threshold with a gradual declining path dropping below the threshold by 2028.The PV of PPG external debt relative to exports would drop below the prudent threshold in 2024. The ratio of external public debt service to fiscal revenues would drop below the prudent threshold temporarily in 2020 but would breach again the threshold until 2030. The debt service-to-exports ratio would remain around the prudent threshold until 2023, when it drops and remains below the threshold for the rest of the projection period.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; economic development / desenvolvimento económico

Unpacking the Potential Socioeconomic Impact of the Coronavirus Pandemic in Mozambique: A United Nations Situation Analysis and Policy Recommendations - United Nations Mozambique (United Nations, 2020)
The Coronavirus pandemic arrives in Mozambique at a time when, after several years of modest economic performance, the Mozambican economy was starting to show signs of recovery. Hence, the latest projections of the IMF of November 2019 had the Mozambican economy growing at 6% in 2020, with medium term projections reaching 9% and above after 2023, following the initiation of LNG exploration operations in the north of the country. Despite this improving macroeconomic outlook prior to the outbreak of the Coronavirus pandemic, living conditions for many Mozambicans remain harsh. Poverty afflicts almost half of the population, 46.1% according to the 2014/15 national household survey, and many people continue without access to basic services, with the proportion of Mozambicans with access to basic water supply, basic sanitation and electricity remaining at very low levels: 55.7%, 29.4% and 27.4% in 2017, respectively. Moreover, despite improvements in healthcare conditions, Mozambicans, especially women and children, continue to be severely afflicted by disease and sickness. In general, living conditions tend to be worse in rural than in urban parts of the country. The coronavirus pandemic is almost certainly going to change this short- and medium-term economic outlook and could potentially have a very significant socioeconomic impact in Mozambique. However, while all available evidence points in this direction, at this stage it is difficult to ascertain and quantify the extent of this impact, given the speed at which things are changing around the world and the uncertainly surrounding the epidemiological profile of the Coronavirus, which makes it hard to assess how long the containment and lockdown measures being applied around the world will need to remain in place. While a detailed quantification of the socioeconomic impact of the coronavirus pandemic may not be feasible, it is still useful to identify possible transmission channels through which the pandemic may affect the Mozambican economy and society. It is also useful to identify key issues that are likely shape shortand medium-term socioeconomic prospects in Mozambique as a result of the Coronavirus pandemic outbreak in Mozambique. The following sections outline some of these.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde

Desenvolvimento socioeconómico de Cabo Delgado num contexto de conflito - João Feijó; António Souto; Jerry Maquenzi (Observador Rural, 2020)
Um conjunto de contradições internas e de longa duração estruturam as relações socioeconómicas na província, estando em grande medida na origem da conflitualidade actual. Não obstante a crescente interferência de factores externos na dinamização do conflito, os dados disponíveis permitem-nos concluir que, enquanto persistirem elementos internos de contradição, não será possível encontrar uma solução sustentável para o conflito. Não obstante o conflito implicar, inevitavelmente, uma intervenção militar, para prover a segurança das populações e de bens, as profundas contradições internas existentes obrigam à realização de um plano de desenvolvimento social e económico, entendido como a melhor estratégia de contra-insurgência, limitando o alastramento do conflito armado por outras zonas da província marcadas pela pobreza e por históricas relações de protesto em relação ao Estado. Uma vez que as informações são escassas e imprecisas e a situação militar no terreno é bastante imprevisível, torna-se difícil definir linhas gerais para um plano de intervenção. Não obstante, neste documento pretende-se apresentar um conjunto de elementos que devem ser considerados, de forma coerente, na implementação de qualquer projecto de desenvolvimento, distinguindo as diferentes áreas socioeconómicas de intervenção na província de Cabo Delgado, em função da realidade actual.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict / conflito; economic development / desenvolvimento económico

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Mozambique Political Process Bulletin 58, 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Protecção social em contexto de terrorismo: que implicações tem a insurgência islâmica nos mecanismos formais de protecção social em Moçambique? - Siúta, Moisés (IDeIAS, 2020)
O impacto do terrorismo em Moçambique é uma realidade que não se restringe apenas à zona Norte do país. O IDeIAS nº 137, da autoria de Moisés Siúta, procura discutir as suas implicações nos sistemas formais de protecção social tendo em conta o desafio que enfrentam de garantir protecção e bem-estar social da população nas regiões mais afectadas sem, no entanto, deixar para trás a população vulnerável a diversos riscos como seca, cheias e a pandemia.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito; social protection / proteção social; ⛔ No DOI found

Spatio-temporal patterns of wildfires in the Niassa Reserve –Mozambique, using remote sensing data - Nhongo, Eufrásio; Fontana, Denise; Guasselli, Laurindo (2020)
Wildfires are among the biggest factors of ecosystem change. Knowledge of fire regime (fire frequency, severity, intensity, seasonality, and distribution pattern) is an important factor in wildfire management. This paper aims to analyze the spatiotemporal patterns of fires and burned areas in the Niassa Reserve between 2002-2015 using MODIS data, active fire product (MCD14ML) and burned area product (MCD64A1). For this, the annual and monthly frequencies, the trend of fires and the frequency by types of forest cover were statistically analyzed. For the analysis of the spatial dynamics of forest fires we used the Kernel density (Fixed Method). The results show a total of 20.449 forest fires and 171.067 km^2 of burned areas in the period 2002-2015. Fire incidents were highest in 2015, while the largest burned areas were recorded in 2007. The relationship between increased fires and burned areas is not linear. There was a tendency for fires to increase, while for burnt areas there was stabilization. Forest fires start in May and end in December. August-October are the most frequent period, peaking in September. Fires occur predominantly in deciduous forests and mountain forests because of the type of vegetation and the amount of dry biomass. There is a monthly spatial dynamics of wildfires from east to west in the reserve. This behavior is dependent on vegetation cover type, fuel availability, and senescence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; natural disasters / desastres naturais

The implementation of ASEAN single window in Indonesia as an effort to facilitate the flow of import and export in Indonesia - Arifin, Jamilah (2020)
On 9 December 2005, All ASEAN member countries signed the Agreement to Establish and Implement the ASEAN Single Window. ASEAN Single Window (ASW) is a one window system that connects ASEAN countries or National Single Window (NSW) to facilitate the electronic exchange of customs data that can be used by traders to obtain permits, customs clearance, and other documents. Indonesia has been implementing this Agreement from 2008 with the system of Indonesia National Single Window (INSW) in order to improve the smooth flow of goods and the performance of export-import services. By using the normative legal research, the research aims to determine the implementation of the ASEAN Single Window (ASW) system as an effort to facilitate the flow of exports and imports in Indonesia. The research shows that the implementation of ASEAN Single Window in Indonesia through Indonesia National Single Window System has helped improve efficiency and import export activities through its service contribution.
Keywords: *indexed; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Baseline Assessment of Facility and District Capacity: Alcançar Qualidade de Serviços de Saúde para Mulheres e Crianças - USAID; fhi360; Alcançar (FHI 360, 2020)
The Alcançar Baseline Assessment of Facility and District Capacity was conducted to establish an evidence base against which to measure project performance and impact over the life of the project and to inform project priorities and planning. The assessment includes a census of health centers and hospitals in Nampula province - the population of facilities that the project is expected to influence. Trained data collection teams interviewed facility and district staff to collect current information on (1) facility infrastructure and policies, (2) human resources, (3) ordering and management of maternal and child health (MCH) commodities, (4) provision of MCH services (5) knowledge of MCH care components, and (6) emergency referral capacity. Additionally, they reviewed and extracted data from facility registers over a 6-month period and observed antenatal care (ANC) consultations. Data collectors visited each of the district health offices (Serviço Distrital de Saúde, Género, Criança e Acção Social, SDSMAS) to gather information on district health capacity to provide clinical mentoring, implement quality improvement and death audits, and manage commodities. This assessment report presents selected results.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; health - maternal and child / saúde - materno-infantil; health / saúde

Economic brief - The Africa Infrastructure Development Index (AIDI) 2020 - African Development Bank (African Development Bank, 2020)
The development of infrastructure in Africa is critical for fostering economic growth and improving the living standards of Africans. It contributes significantly to human development, poverty reduction, and the attainment of the Sustainable Development Goals (SDGs). Investment in infrastructure accounts for over half of the improvements in economic growth in Africa witnessed over the last decade and has the potential to contribute much more, given a conducive environment.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Mozambique - Invest in the Energy Sector of Mozambique - African Oil and Power (Africa Energy Series, 2020)
Since initial exploratory drilling in 2007 by U.S. operator Anadarko, Mozambique has uncovered vast natural gas volumes within its offshore basins, and now carries the potential to be the fourth largest natural gas exporter globally. With discoveries ranging from Anadarko’s initial 480 feet of gas found in Area 1 in 2010, to Eni’s discovery of 425 billion cubic meters one year later, the onus now lies on major operators including Royal Dutch Shell, Total, Eni and more to develop the requisite infrastructure to exploit the reserves, generate exports and bring revenue into the country. Potential inhibitors to the development of such resources include two ‘black swan’ events that have occurred since early-2020. In addition to the onset of COVID-19 in March – including a specific outbreak on Total’s Mozambique LNG development – the gas-rich Cabo Delgado province is facing a growing Islamist insurgency that began in the country in 2017. Nevertheless, the world-class nature of Mozambique’s gas assets has offset such inhibitors, and the country recently secured the largest foreign direct investment in Africa to date through its Mozambique LNG development. Gas monetization projects push forward on schedule, as the nation continues on its path to becoming a global energy giant.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

A governação municipal em contextos de alternância política em Moçambique: algumas notas a partir do município de Gurué (2014-2018) - António, Bernardino (Desafios para Moçambique 2020, 2020)
O artigo discute duas questões principais. A primeira é sobre o conflito nas relações de poder entre o Governo Municipal e o Governo Distrital na questão das lideranças comunitárias dos bairros do município, onde se procura mostrar a forma como a Frelimo, através do uso do poder de tutela administrativa e financeira do Estado, restringia a governação do Movimento Democrático de Moçambique (MDM), possibilitando a existência de duas estruturas comunitárias conflituantes ao nível dos bairros. A segunda refere-se à luta pelo protagonismo político-partidário entre os dois poderes na prestação de serviços públicos, destacando a forma como afectava a prestação dos serviços de abastecimento de água e do bem-estar dos cidadãos naquela autarquia. Para analisar estas questões, o artigo desenvolve duas secções, além desta introdução. A primeira secção, que se segue, aborda as eleições e a alternância política nas autarquias em Moçambique, analisando todas as eleições, desde as primeiras, realizadas em 1998, até as eleições de 2013, e a experiência da governação nas autarquias que tiveram alternância política no passado. A segunda retrata os desafios da governação do MDM no município de Gurué. Este artigo é resultado de uma pesquisa realizada no município de Gurué em 2018, no âmbito do projecto de pesquisa Barómetro da Governação Municipal, em curso no Instituto de Estudos Sociais e Económicos (IESE). A pesquisa baseou-se numa metodologia qualitativa, com recurso a entrevistas semiestruturadas, discussões em grupos focais e observação no terreno, realizadas em 11 bairros do município de Gurué nomeadamente Contap, Escola Secundária, Barragem, Archote, 25 de Junho, Serra, Lussa A, Lussa B, Moneia, Cimento e Malessane. Foram realizadas nove discussões em grupos focais e 22 entrevistas semiestruturadas com moradores, membros do Governo Municipal (vereadores), membros da Assembleia municipal, líderes comunitários, comerciantes locais, vendedores informais, partidos políticos e funcionários do Governo Distrital de Gurué. A pesquisa de campo decorreu ao longo de 20 dias, entre Abril e Junho de 2018.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; governance / governação

Geografia Eleitoral e Insurgência em Cabo Delgado - Brito, Luís de (Desafios para Moçambique, 2020)
This chapter looks at the origins of the extremist insurgency in Cabo Delgado and posists that to understand its origins, we must look beyond religious extremeism and to other factors in order to analyse the situation from difference perspectives. This study looked at electoral data in Cabo Delgado to determine if there is a relationship bwtween voting patterns, including abstention, and political cleavages and social conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; electoral geography / geografia eleitoral

The Price of a Green Conscience - Brown, Jasmine; Ewald, Jonas; Fritz, Heiko (Linneaus University, 2020)
Scholars and civil society organizations have over the last decade referred to large-scale carbon sequestration TPPs as "carbon colonialism" (Carmody and Taylor, 2016) as well as a "development by dispossession" dressed in new clothing behind words such as climate change mitigation and development (Kröger, 2012). Concerns have been raised that the trade-offs from the implementation of industrial tree plantations (ITPs) may result in conflicting effects on countries' overall development (The Oakland Institute, 2019; Osborne, 2015; Nel & Hill, 2013). Moreover, NGO's and think tanks, such as FIAN (2012) and the Oakland Institute (2017, 2019), have released reports in which such tree planting projects are accused of displacing people and violating human rights (FIAN, 2012; The Oakland Institute, 2017, 2019; Carmody & Taylor, 2016). This thesis explores the impacts of carbon forestry projects, emphasizing the impacts of ITPs on local livelihoods and their subsequent effects on development. Three dimensions have been chosen to limit the scope of this thesis: (1) food security; (2) access to land; and (3) employment & income. The thesis is conducted using a qualitative desk study and secondary analysis of two multiple case studies of Uganda and Mozambique. The findings presented suggest carbon forestry projects may negatively affect all three dimensions, ultimately affecting communities' sustainable development. The author recommends further research to evaluate the complex effects of carbon forestry projects.
Keywords: *snowball; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; poverty / pobreza

BTI 2020 Mozambique Country Report - BTI (2020)
“Mozambique faces five major challenges: violence between political camps, impunity with regard to corruption, violations of human rights, the debt crisis and the security threat of Islamist terrorism.”
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Finanças Internacionais e Formação do Capitalismo Nacional em Moçambique - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
Este capítulo descreve e explica como e por que razão a economia moçambicana e as suas dinâmicas de expansão e de crise, as suas contradições e os seus paradoxos foram estruturados e articulados pela sua relação de dependência com o capital financeiro privado internacional, e as implicações desta relação para as características, as dinâmicas e as opções de acumulação privada de capital e de desenvolvimento da sociedade como um todo em Moçambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; natural resources / recursos naturais; private sector / setor privado

Ligações Económicas Entre a África do Sul e Moçambique: dinâmicas pós-coloniais e pós-apartheid entre 1990 e 2002 - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
O artigo concentra-se na análise dos fluxos de bens e serviços, trabalho e capital entre as duas economias, dentro de estruturas de acumulação historicamente específicas, o que permite fazer alguma discussão sobre opções e possibilidades para desenvolvimentos futuros. O artigo argumenta que os vínculos económicos entre os dois países foram construídos ao longo dos anos por causa de forças dinâmicas (ligações e pressões económicas, agentes sociais e políticas públicas) que operam nas duas economias. Tais forças dinâmicas, como o complexo mineralenergético da África do Sul, ainda estão em operação. Nos últimos anos, o mecanismo pelo qual o capitalismo sul-africano influenciou a economia moçambicana e, em geral, as economias na África Austral, mudou de recrutamento de mão-de-obra migrante para estratégias de internacionalização das corporações sul-africanas envolvendo investimento directo estrangeiro (IDE), internacionalização do sistema financeiro e expansão do seu poder sobre a economia, controlo de recursos estratégicos e de mercados e desenvolvimento do comércio livre, ao mesmo tempo que as circunstâncias históricas da queda do Apartheid e das lutas das classes trabalhadoras sul-africanas impuseram a reestruturação de políticas e de relações de trabalho na sociedade sulafricana (Ashman, Fine & Newman, 2011; Castel-Branco, 2002b, 2017b). Este artigo está organizado em quatro secções principais, a saber: um breve resumo histórico para enquadrar as tendências e padrões das relações económicas entre a África do Sul e Moçambique; uma descrição e análise dessas tendências e padrões num contexto pós-colonial e pós-Apartheid; uma identificação dos principais desenvolvimentos que poderiam, na época, moldar futuras ligações; e uma secção final que resume os argumentos e aponta para a necessidade de a África Austral se libertar da herança hegemónica do capitalismo monopolista sul-africano para poder desenvolver um processo de articulação, solidariedade e desenvolvimento regional real.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico

O Trabalho Doméstico Em Moçambique: Uma Década após a Formalização - Castel-Branco, Carlos Nuno (Desafios para Moçambique 2020, 2020)
O estudo verifica que houve alguns avanços na última década, incluindo: a definição de um quadro regulamentar para o trabalho doméstico, a proliferação de organizações de trabalhadores domésticos filiadas ao movimento sindical e uma maior valorização por parte da sociedade (e dos empregadores) deste sector. No entanto, existem vários desafios, entre os quais: um quadro regulamentar fraco e fracamente implementado; a dificuldade de mobilização colectiva num sector íntimo, disperso, e ultra-explorado; um baixo nível de colaboração entre organizações de trabalhadores domésticos e a marginalização de organizações no contexto de um movimento sindical machista e de um movimento feminista classista. O estudo identifica algumas oportunidades, incluindo a ratificação da Convenção 189, a revisão de Lei de Trabalho, que pode criar uma abertura para reforçar o quadro regulamentar, e o reforço das organizações de trabalhadores domésticos e de colaborações estratégicas entre o movimento sindical e o movimento feminista. Porém, o estudo também identifica algumas ameaças, como a crise económica e financeira, que aumentou o custo de vida e aprofundou uma política de austeridade, a falta de vontade política por parte do Estado e a concorrência entre as organizações da sociedade civil. Com base nesta análise, o estudo apresenta as seguintes recomendações para o Estado e para o movimento sindical e feminista.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego; gender / género

A Segurança Social em Moçambique - Castel-Branco, Ruth Kélia (Desafios para Moçambique 2020, 2020)
Este artigo começa por uma análise do actual sistema de Segurança Social, seguida por uma discussão das medidas de emergência que foram propostas, as sugestões rumo a um sistema de Segurança Social universal, e os riscos – principalmente o risco da financeirização da Segurança Social com a terceirização dos sistemas de registo e pagamentos. O artigo é concluído com uma discussão do tipo de mobilização que será necessário para garantir a expansão adequada da Segurança Social. Como disse o abolicionista Frederick Douglass, «sem luta não há progresso... O poder não concede nada sem demanda. Nunca concedeu e nunca concederá» (Frederick, 1851).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; social protection / proteção social

A segurança social em Moçambique: conversa para o boi dormir ou um instrumento de redistribuição viável? - Castel-Branco, Ruth Kélia (Desafios para Moçambique 2020, 2020)
Nas últimas décadas, houve uma ressurgência de interesse na Segurança Social como instrumento redistributivo capaz de reduzir a pobreza e a desigualdade e promover o crescimento económico inclusivo. Este crescente interesse a nível global deve-se ao reconhecimento de que o desenvolvimento social não resulta inevitavelmente do crescimento económico, e, aliás, pode ser bem o contrário: que formas de Segurança Social vinculadas ao emprego formal são inadequadas dada a informalidade generalizada e que transferências monetárias não contributivas são possíveis mesmo em países em vias desenvolvimento como Moçambique (Mkandawire, 2011). Nas duas décadas anteriores à crise da Ematum, Moçambique registou um índice de crescimento médio de 7,5 % do PIB. Porém, impulsionado por uma indústria extractiva intensiva em capital, este não resultou em melhores condições de vida para a maioria dos moçambicanos. A Crise da Ematum piorou a situação. Segundo simulações da UNU-WIDER, a crise resultou no aumento do índice da pobreza de 46,1 % em 2014, e de aproximadamente 60 % em 2016 (Mambo et al., 2018). Alarmado pela situação, o antigo Ministro de Administração Estatal, Óscar Monteiro, sugeriu, durante a reunião do Comité Central da Frelimo em Maio de 2019, a rápida expansão do sistema de Segurança Social em Moçambique, mas o Governo optou por não a fazer: "A gravidade da situação requer medidas urgentes. E eu digo isto não porque não é apenas uma questão eleitoral, mas é uma questão de humanidade... Porque é que nós não começamos a distribuir dinheiro, usando a rede existente, ampliando, melhorando... Esse dinheiro não se vai perder... Esse dinheiro vai aumentar o consumo, vai encorajar a produção, vai financiar a recuperação. (Monteiro, 2019)" A crise da Covid expôs mais uma vez a fragilidade do nosso modelo de desenvolvimento económico, e a fraqueza dos mecanismos de redistribuição existentes. Projecções da UNU-WIDER concluíram que apenas 7 % dos moçambicanos tinham as condições para sobreviver a um lockdown total (Jones, Egger & Santos, 2020). O Governo acabou por optar por um lockdown parcial, permitindo que várias instituições públicas e privadas continuassem abertas. No entanto, a questão da expansão da Segurança Social continua oportuna não só como medida de resposta de emergência durante a crise da Covid, mas também como instrumento redistributivo com a capacidade de promover o desenvolvimento inclusivo. Este artigo começa por uma análise do actual sistema de Segurança Social, seguida por uma discussão das medidas de emergência que foram propostas, as sugestões rumo a um sistema de Segurança Social universal, e os riscos – principalmente o risco da financeirização da Segurança Social com a terceirização dos sistemas de registo e pagamentos. O artigo é concluído com uma discussão do tipo de mobilização que será necessário para garantir a expansão adequada da Segurança Social. Como disse o abolicionista Frederick Douglass, «sem luta não há progresso... O poder não concede nada sem demanda. Nunca concedeu e nunca concederá» (Frederick, 1851).
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; health - COVID-19 / saúde – COVID-19; social protection / proteção social

Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade

Ugandenses e Tanzanianos do Al-Shabaab: um olhar à dimensão internacional do conflito em Cabo Delgado - Chichava, Sergio (Desafios para Moçambique, 2020)
O conflito militar que, desde 5 de Outubro de 2017, se abate sobre Moçambique, com particular incidência na província de Cabo Delgado e protagonizado por um grupo localmente conhecido por Al-Shabaab, cuja pretensão é substituir o Estado laico por um Estado regido pela Sharia, tem sido regularmente descrito pelas autoridades moçambicanas como tendo, além de uma dimensão interna, uma componente externa. Desde o início do conflito, as autoridades locais falam da prisão ou da procura de vários estrangeiros que estariam a treinar, financiar e dirigir a «insurgência» em Cabo Delgado com vista a retardar o desenvolvimento do País e a explorar ilegalmente diversos recursos naturais. De entre os diversos estrangeiros frequentemente mencionados, o destaque vai para tanzanianos e ugandenses. Por seu turno, o Al-Shabaab tem vindo a reclamar uma dimensão internacional, declarando fidelidade ao Estado Islâmico (EI) ou Daesh. Ao que tudo indica, o Daesh também reconhece o Al-Shabaab, que designa por «soldados do Califado» pertencentes ao Estado Islâmico da Província da África Central (ISCAP, no acrónimo inglês), uma região cujos contornos geográficos ainda não estão bem claros, mas que englobaria actualmente, além Moçambique, a República Democrática do Congo (RDC), País onde está baseado o grupo islamista ugandês Forças Democráticas Aliadas (ADF), que também tem sido apresentado nalguns fóruns como tendo relações com o Al Shabaab em Moçambique, através da presença de alguns dos seus militantes neste País, ou através do recrutamento e treino de jovens moçambicanos na RDC. Com base nos elementos acima, o objectivo deste texto é fazer uma breve análise da componente internacional do AlShabaab, olhando para a sua ligação com a Tanzânia, o Uganda e o EI. Mais precisamente, olhando para o perfil dos cidadãos ugandeses e tanzanianos que têm sido referenciados como sendo do Al-Shabaab, o texto procura responder às seguintes questões: quem são os tanzanianos e ugandeses do Al-Shabaab? Como chegaram a Moçambique? O que pretendem? Porque escolheram a província de Cabo Delgado? Será o Al-Shabaab uma filial do Estado Islâmico? Para responder a estas questões, primeiro apresenta-se o perfil dos tanzanianos e ugandeses do Al-Shabaab; a seguir, apresentam-se algumas hipóteses sobre as suas pretensões; e, por último, abordam-se alguns elementos sobre a possível ligação do Al-Shabaab ao Daesh ou ao EI.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Demonstration fields’, anticipation, and contestation: agrarian change and the political economy of development corridors in Eastern Africa - Chome, Ngala; Gonçalves, Euclides; Scoones, Ian; Sulle, Emmanuel (Journal of Eastern African Studies, 2020)
In much of Eastern Africa, the last decade has seen a renewedinterest in spatial development plans that link mineralexploitation, transport infrastructure and agriculturalcommercialisation. While these development corridors haveyielded complex results–even in cases where significantinvestments are yet to happen–much of the existing analysiscontinues to focus on economic and implementation questions,where failures are attributed to inappropriate incentives or lack of‘political will’. Taking a different–political economy–approach,this article examines what actually happens when corridors‘hitthe ground’, with a specific interest to the diverse agriculturalcommercialisation pathways that they induce. Specifically, thearticle introduces and analyses four corridors–LAPSSET in Kenya,Beira and Nacala in Mozambique, and SAGCOT in Tanzania–which are generating‘demonstrationfields’, economies ofanticipation andfields of political contestations respectively, andas a result, creating–or promising to create–diverse pathwaysfor agricultural commercialisation, accumulation anddifferentiation. In sum, the article shows how top-down grand-modernist plans are shaped by local dynamics, in a process thatresults in the transformation of corridors, from exclusivist‘tunnel’visions, to more networked corridors embedded in localeconomies, and shaped by the realities of rural Eastern Africa.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Estudo de caso: Cabo Delgado (Moçambique). A terra onde não se come o que se produz e produz o que não se come - Cunha, Teresa; José, André Cristiano; Monjane, Boaventura; Bidaurratzaga, Eduardo; Casimiro, Isabel; Trindade, João Carlos; Alberdi, Jokin; Cruz, Lucinda; Valle, Luísa de Pinho (Gernika Gogoratuz, 2020)
No final do seminário e das oficinas-grupos de trabalho procedeuse a um debate aberto para partilha das reflexões e identificação de conclusões principais: • A participação em espaços de consulta/decisão está muito condicionada pela falta de conhecimentos de quem participa, mas também pela falta de transparência e assimetria da informação. • A exclusão social está na base da pouca ou fraca participação e monitoria. • A qualidade da monitoria nos processos de governação e desenvolvimento é fraca. • A monitoria da governação e desenvolvimento é vista pelos poderes como «acções-sombra» ou «mandatados da oposição». • Os governantes têm medo de falar de desenvolvimento com a cidadania. Preferem discutir questões do partido. • Existem poucos espaços de participação criados e também reclamados. • Existe uma confusão de papéis e das suas compatibilidades entre as lideranças e a administração. • Não se aplica a lei, em muitos casos. • Existem lideranças reconhecidas e não reconhecidas. • Algumas iniciativas começam a ter os seus resultados na província, sobretudo no contexto urbano e relacionadas com grupos de jovens. • Algumas organizações da sociedade civil reproduzem dinâmicas de poder e definem o que é ou não prioritário para as comunidades (nos seus gabinetes). • Também existe corrupção e fraca prestação de contas entre as organizações da sociedade civil, não só na Administração/Governo. • Os jovens de Cabo Delgado necessitam ter formação e emprego nos grandes projectos de desenvolvimento.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture / agricultura; conflict - civil war / conflito - guerra civil; conflict / conflito

Análise de Economia Política da Governação Local Moçambique - Eurosis (Mozambique Monitoring and Evaluation Mechanism and Services (MMEMS), 2020)
A governação local em Moçambique continua a desenvolver-se em duas vertentes: a desconcentração de poderes, através dos órgãos locais do Estado (secretarias de Estado da província, administrações distritais, etc), e a devolução do poder através dos órgãos de poder local (presidentes de conselhos autárquicos e governadores provinciais eleitos). O processo de criação de autarquias tem sido muito lento e a maioria dos cidadãos vive em áreas geridas pelos órgãos locais do estado e não por órgãos eleitos directamente por si. Não é ainda claro como vai funcionar a administração pública no novo figurino que criou a representação do Estado nas províncias onde existem governadores eleitos e um governo estabelecido. O que é claro, é a forte tendência para a centralização do partido político no poder e para a intervenção directa na gestão local da coisa pública, o que afecta a inclusão, transparência e prestação de contas em todas as áreas de governação. O quadro de políticas e legal é disperso e omisso em relação a como se realiza a participação dos cidadãos e cidadãs na governação em geral e como se promove a inclusão, transparência e prestação de contas. É também limitado o quadro em que operam serviços fundamentais para a transparência da administração pública, como por exemplo, os serviços de inspecção de saúde e educação, cujo quadro regulatório limita o potencial destas intervenções. Este contexto cria oportunidades para o exercício de poder discricionário a todos os níveis e leva a que intervenções fiquem dependentes do interesse político dos líderes aos vários níveis para a sua implementação. Num contexto de uma corrupção generalizada, isto é um obstáculo à realização de actividades e sustentabilidade das intervenções. Apesar das limitações apontadas, existem oportunidades e espaços para promover uma maior participação dos cidadãos e melhor prestação de contas do sector público, os quais podem ser usados como base para novas intervenções. Assim, apesar da ausência de um bom quadro legal, há alguma legislação e posições públicas do governo que remetem para um primado do cidadão, para um serviço público de qualidade e inclusivo e para o combate à corrupção. Há também mecanismos e processos que assumem a participação informada dos cidadãos nos processos de decisão sobre questões do desenvolvimento em geral (IPCC, assembleias autárquicas e provinciais) e da saúde e educação em particular (comités das unidades de serviços). Existem formalmente instituições e processos que têm como função garantir uma administração pública isenta e de qualidade (inspecção, tribunais administrativos provinciais, gabinetes anticorrupção). O nível de funcionamento destes mecanismos e processos varia muito e está dependente do interesse dos governantes locais, da mobilização comunitária e dos recursos existentes). Assim, pode dizer-se que há uma base para sobre a qual trabalhar para conseguir mais transparência, prestação de contas e inclusão ao fortalecer a governação local ao nível provincial, distrital e local (da unidades de prestação se serviços). Também o apoio à inspecção de saúde e educação pode contribuir para a melhoria da qualidade de serviços prestados aos cidadãos ao assegurar um melhor seguimento das regras e protocolos de prestação de serviços. É importante notar, contudo, que para além dos obstáculos acima referidos, o presente momento coloca desafios particulares ao desviar a atenção do governo para a resposta aos conflitos armados e à pandemia do COVID-19.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; GP - Cabo Delgado; GP - Nampula; GP - Zambézia; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; education / educação; governance / governação; health / saúde; institutions / instituições

The political economy of regional hydropower investments in Africa - Eyita-Okon, Ekeminiabasi (2020)
Africa has abundant potential to generate hydroelectric power. Yet with an uneven record of building large dams, much of this potential remains untapped. This thesis addresses the question of why some large dam projects have been built and others have not. The problem of credible commitment by host governments to prospective investors is central to the explanation. The problem is that while large dam projects require large investments over lengthy periods, after construction is complete host governments may face strong temptations to renege on their agreements with investors –in an environment that lacks a supranational authority to enforce agreements. Anticipating this, investors will be reluctant to invest, and many potentially mutually beneficial hydroelectric dams will go unbuilt. The empirical part of the thesis begins with a statistical analysis of hydroelectric potential and realised capacity in Africa compared to other regions. This is followed by comparative case studies of the Cahora Bassa dam in Mozambique, completed in 1974, and the Grand Inga dam in the Democratic Republic of Congo (DRC), still unbuilt despite plans stretching back decades. I show that the credible commitment problem in the Cahora Bassa case was overcome through strategic interaction between the Portuguese colonial host government and the South African apartheid government, which was the main investor and the principal consumer of the power generated. The credible commitment problem in the Grand Inga case has been much more intractable due to the larger numbers of investors and consuming countries involved, and importantly to political risk within the DRC. The thesis contributes to the understanding of how Africa can better exploit its hydroelectric potential, in an era of increasing emphasis on renewable energy sources
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, João, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Desafios para Moçambique - 2020 - Forquilha, Salvador (Instituto de Estudos Sociais e Económicos, 2020)
PARTE I – POLÍTICA Cabo Delgado e o risco sistêmico da Guerra em Moçambique / Severino Ngoenha, Giverage do Amaral e Alcido Nhumaio Face ao conflito no Norte, o que pode Moçambique aprender com a sua própria guerra civil (1976-1992)? Uma análise das dinâmicas da insurgência em Cabo Delgado / Salvador Forquilha e João Pereira Geografia eleitoral e insurgência em Cabo Delgado / Luís de Brito Paz e reconciliação em Moçambique: conjunturas críticas e dependência da trajectória / Bernhard Weimer e Natália Bueno Programas, sim, mas para fazer o quê? Uma análise dos manifestos eleitorais dos partidos políticos para as eleições moçambicanas de 15 de Outubro de 2019 / Michel Cahen A Governação Municipal em contextos de alternância política em Moçambique: Algumas notas a partir do município de Gurué (2014-2018) / Bernardino António PARTE II – ECONOMIA Finanças internacionais e formação do capitalismo nacional em Moçambique / Carlos Nuno Castel-Branco A economia de Moçambique e os conflitos e tensões à volta das condições de produção e reprodução agrícula / Carlos Muianga Tensões, conflitos e inconsistências nas relações entre a política fiscal e monetária em Moçambique / Yasfir Ibraimo Desafios e contradições para uma abordagem sobre trabalho e emprego em Moçambique / Rosimina Ali Investimento directo estrangeiro e o desenvolvimento socioeconómico em Moçambique: Dinâmicas, tensões e desafios / Michael Godet Sambo PARTE III – SOCIEDADE Protecção social e os principais obstáculos ao financiamento das empresas através da Bolsa de Valores de Moçambique / Moisés Siúta A segurança social em Moçambique: Conversa para boi dormir ou um instrumento de redistribuição viável? / Ruth Kélia Castel Branco Trabalho em função do género, trabalho migratório: Reformar os regimes do açúcar em Xinavane, Moçambique / Alicia Hayashi Lazzarini O trabalho doméstico em Moçambique: Uma década após a formalização / Ruth Kélia Castel Branco Pânico e medo: Desafio dos media moçambicanos na cobertura da COVID-19 / Celestino Joanguete PARTE IV – MOÇAMBIQUE NO MUNDO Ugandeses e Tanzanianos do Al-Shabaab: Um olhar à dimensão internacional do conflito em Cabo Delgado / Sérgio Chichava Ligações ecnómicas entre a África do Sul e Moçambique: Dionâmicas pós-coloniais e pós-Apartheid entre 1990-2002 / Carlos Nuno Castel-Branco
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Introdução - Forquilha, Salvador (Desafios para Moçambique 2020, 2020)
Trinta anos depois da aprovação da primeira Constituição multipartidária da história do País,2 Moçambique continua a enfrentar grandes desafios no processo da construção democrática. Com efeito, não só as instituições que resultaram das reformas políticas no âmbito da nova Constituição têm demonstrado fragilidades no seu funcionamento, como também as regras do jogo político têm sido marcadas por uma certa instabilidade, consubstanciada, por exemplo, nas sucessivas revisões da legislação eleitoral. Nos últimos índices de democracia,3 Moçambique tem registado recuos significativos na sua pontuação. Depois de ter passado de regime híbrido para regime autoritário (The Economist, 2019), o País passou da posição 116, em 2018, para a posição 120, em 2019 (The Economist, 2020). No que se refere à situação económica, a trajectoria do País tem sido marcada por crises e contradições, resultantes, essencialmente, das estruturas sociais de produção, das dinâmicas de dependência e do sistema social de acumulação (Castel-Branco, C.N., 2020a). No plano social, apesar de ter havido uma ligeira melhoria em termos de bem-estar e uma redução percentual da taxa de pobreza de consumo em 5 % entre 2008/2009 e 2014/2015, de acordo com os dados do Inquérito aos Orçamentos Familiares (IOF) 2014/2015, análises indicam que ainda persistem diferenças significativas regionais e entre os espaços urbano e rural ao longo do País. Com efeito, «a redução da pobreza no período entre 1996/1997 e 2014/2015 foi substancial tanto nas áreas rurais como urbanas, mas a redução foi mais acentuada nas áreas urbanas entre 2008/2009 e 2014/2015. A nível regional, evidencia-se que o Norte piorou a própria situação em termos de taxa de pobreza de consumo, passando de 45 % para 55 %, enquanto o decréscimo das taxas de pobreza no Centro e no Sul foi, respectivamente, de 10 e 18 pontos percentuais. Entre 2008/2009 e 2014/2015, a pobreza diminuiu em todas as províncias do Centro e Sul, particularmente em Maputo (província e cidade), enquanto nas três províncias do Norte as taxas de pobreza estagnaram ou cresceram» (Arndt et al., 2018: 311). Os dados acima também indicam que a pobreza é muito resiliente em relação ao crescimento económico – no mesmo período em que baixou 5 % (a uma média anual de -0,8 %) o PIB cresceu 50 % (a uma média anual de 7 %), revelando que o padrão de crescimento económico é pouco eficiente a reduzir pobreza.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; poverty / pobreza

Face ao conflito no norte, o que pode Moçambique aprender com a sua própria guerra civil (1976-1992)? Uma análise das dinâmicas da insurgência em Cabo Delgago - Forquilha, Salvador; Pereira, João (Desafios para Moçambique 2020, 2020)
A história de Moçambique dos últimos 50 anos tem sido marcada por ciclos de violência armada de contestação ao Estado, não só colonial, como também pós-colonial. Com efeito, desde a guerra anticolonial levada a cabo pela Frente de Libertação de Moçambique (Frelimo), passando pela guerra civil, que opôs a Resistência Nacional Moçambicana (Renamo) ao Governo da Frelimo, até às crises político-militares pós-eleitorais, a violência armada tem estado presente no processo da construção do Estado em Moçambique. No início de Outubro de 2017, começou uma outra contestação violenta ao Estado na província de Cabo Delgado. No dia 5 de Outubro de 2017, um grupo de homens armados atacou as instituições do Estado na vila sede de Mocímboa da Praia. Inicialmente associado a um banditismo de mera perturbação da ordem pública, o fenómeno ganhou rapidamente proporções alarmantes. Os ataques começaram a multiplicar-se. Dois meses depois do primeiro ataque, a Polícia já havia detido 251 suspeitos, dos quais 37 eram cidadãos de nacionalidade tanzaniana (O País, 2017). Em Dezembro de 2017, a Polícia da República de Moçambique, ao mais alto nível, esteve na zona e visitou os distritos de Mocímboa da Praia e Palma. No comício popular que realizou na vila sede de Mocímboa da Praia, o Comandante Geral da Polícia, Bernardino Rafael, deu um «ultimato» aos atacantes de Mocímboa da Praia, decretando sete dias para se entregarem às autoridades (O País, 2017). No entanto, a violência continuou e, nas semanas e meses que se seguiram ao ataque à vila sede de Mocímboa da Praia, a situação de segurança piorou no terreno e os ataques espalharam-se para outros distritos da zona norte de Cabo Delgado. Entre finais de Março e meados de Abril de 2020, a violência armada atingiu níveis nunca vistos antes, com o assalto e a ocupação temporária de quatro vilas nos distritos de Mocímboa da Praia, Quissanga, Muidumbe e Ibo. Que factores estão na origem do avanço da insurgência no terreno? Que tipo de relação se vai desenvolvendo entre os insurgentes e as populações locais? Existe algum potencial para que a insurgência se alastre para o Sul, em direcção à zona costeira de Nampula? Como tem vindo o Estado a responder à insurgência? Estas perguntas são uma parte importante do programa de pesquisa intitulado «Estado, violência e desafios de desenvolvimento no Norte de Moçambique», em curso no IESE desde Agosto de 2019.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - civil war / conflito - guerra civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Decentralization reforms in Mozambique: The role of institutions in the definition of results - Forquilha, Salvador; UNU-WIDER (WIDER Working Paper, 2020)
Abstract: With the introduction of the economic reforms in the late 1980s, the opening up of the political arena and the end of the civil war in the early 1990s, the decentralization process began in Mozambique. Different research developed in recent years shows that, as is the case in other countries in sub-Saharan Africa, the impact of the decentralization reforms on the promotion of local development and the strengthening of democracy in Mozambique is modest. How can this modest impact be explained? Based on three important reforms in the decentralization process in Mozambique, namely the ‘7 million’, municipalization and decentralized provincial governance, this article seeks to answer this question by analysing how different aspects of the institutions affect the results of the reforms. The main argument in the article underlines the idea according to which the results of the decentralization reforms in Mozambique are constrained by the nature and by the operation mechanisms of the political system. Of these institutional factors/constraints, state capacity and independence from private interests, particularly political groups, stand out in the three reforms analysed throughout this article. In this context, the reforms develop according to group interests, particularly party political interests, which capture the state and use the reforms as a mechanism for maintaining and bolstering political power. In this sense, rather than being a means of improving the provision of public services and strengthening democracy, decentralization works more as an instrument for reinforcing state control and pandering to the elite. This is probably the biggest challenge decentralization is facing in Mozambique, therefore making it a fundamental issue to be taken into account in any reform in this area, within the context of strengthening democracy and promoting local development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Tensões, Conflitos e Inconsistências nas Relações Entre a Política Fiscal e Monetária em Moçambique - Ibraimo, Yasfir (Desafios para Moçambique 2020, 2020)
Este artigo descreve e analisa as tensões, os conflitos e as inconsistências nas relações entre as políticas fiscal e monetária em Moçambique, procurando explicar porque existem, como se reproduzem ao longo do tempo e as implicações que têm para a transformação económica. O artigo argumenta que as tensões, os conflitos e a inconsistência nas relações entre a política fiscal e monetária emergem da estrutura económica e dos padrões de acumulação dominantes na economia, o que impede o processo de transformação e diversificação da base produtiva nacional. A transformação dos padrões de acumulação pode minimizar os conflitos, tensões e inconsistências. Contudo, enquanto se mantiver este padrão de acumulação, o conflito entre a política fiscal e monetária permanecerá. O artigo está organizado em quatro secções principais. A primeira é esta introdução. A segunda descreve a estrutura da economia de Moçambique e os padrões de acumulação, destacando a evolução da produção industrial, as exportações do País e as limitações da estrutura e do padrão de acumulação para as políticas fiscal e monetária. A terceira descreve e analisa algumas medidas de política fiscal e monetária que podem ser adoptadas para transformar o padrão de acumulação e eliminar as tensões, os conflitos e as inconsistências nestas políticas. A quarta apresenta as principais conclusões do artigo.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; fiscal policy / política fiscal; monetary policy / política monetária

A4EA Insights: Country briefing on Mozambique - IDS (IDS, 2020)
The Action for Empowerment and Accountability Research Programme (A4EA) examines different forms of social and political action to understand how and under what conditions they contribute to real world change, including gains in empowerment for the most excluded and marginalised, and for increased accountability of authorities. A4EA work is highly relevant to FCDO’s expressed goals of developing research-led solutions to building open societies and supporting conflict resolution, including through a focus on strengthening democratic institutions, human rights and effective, accountable governance. In Mozambique, A4EA projects include long-term work to understand poor and marginalised people’s experiences of different authorities, in-depth research on the dynamics of protest and claims for accountability and better services in a range of key sectors including energy and transport, exploration of women’s leadership and representation, and analysis of donor governance programmes. Working with a range of Mozambican research partners including the Instituto de Estudos Sociais e Económicos (IESE), Kaleidoscopio, Fórum Mulher and the Centro de Integridade Pública (CIP) we have completed six A4EA projects that included research in Mozambique, and have five studies currently ongoing.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês

Anuário Estatístico da Província de Nampula 2019 - INE (Instituto Nacional de Estatística, Governo de Moçambique, 2020)
O Anuário Estatístico da Província de Nampula 2019 é uma publicação estatística de carácter geral que a Delegação do Instituto Nacional de Estatística em Nampula leva aos utilizadores e ao público em geral, como um vínculo para a disseminação dos principais indicadores económicos, sociais e demográficos da Província.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Anuário Estatístico - Statistical Yearbook 2019 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2020)
À semelhança das edições anteriores, o Anuário Estatístico 2019 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios. O mesmo constitui parte da série de publicações que o Instituto Nacional de Estatística (INE), na sua missão de proporcionar, à sociedade moçambicana, informação estatística que permita o conhecimento da realidade do País, disponibiliza aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2015-2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; L - portuguese / português; Northern PEA; demographics / demografia

Indicadores Básicos de Agricultura e Alimentação 2015-2019 - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística (INE), 2020)
1. Esta publicação apresenta os indicadores básicos de agricultura e alimentação dos últimos 5 anos, como alternativa da base de dados na plataforma online “countryStat” produzida com fontes administrativas, mas descontinuada em 2019. A publicação não abrange todos indicadores cobertos como desejado, porque alguns requerem harmonização metodológica e outros ainda não são produzidos com regularidade pelos sectores. 2. A compilação desta publicação baseou-se na recolha e tratamento preliminar das bases de dados disponibilizadas pelas fontes administrativas dos sectores. A seguir, a equipa de produção fez a limpeza e validação de dados, resultando na publicação com 10 grupos de indicadores. 3. Nos indicadores socio-demográficos, destaca-se a população de Moçambique, como principal activo da produção, ao atingir a magnitude de 29,3 milhões de habitantes em 2019, 66,2% da qual vivia na área rural, e continuando concentrada em Nampula e Zambézia com 6,03 e 5,43 milhões de habitantes respectivamente. 4. O segundo indicador refere-se à insegurança alimentar aguda, cujo resultado indica um grande agravamento, ao partir de 3,6% em 2013 para 29,9% de famílias em 2019, um comportamento assumido também pela desnutrição aguda em crianças que de 1,9% em 2013 deteriorou-se para 12,3% em 2019. 5. Nos indicadores económicos, ressalta o peso do PIB do sector agrário a preços constantes, ano base de 2014, que estabilizou-se em torno de 23%, entre 2015 e 2019, tendo a respectiva taxa de crescimento registado 1,2% em 2019, abaixo da média nacional que foi de 2,3% face a 2018. O orçamento do estado alocado ao sector continuou abaixo de 10% em todo quinquénio, tendo-se fixado em 4,9% em 2019 6. A mecanização agrícola, medida pelo número de tractores alocados pelo Fundo do Desenvolvimento Agrário ao sector privado para agricultura familiar, reduziu, ao partir de 361 em 2015 para 26 unidades em 2019. No entanto, a área lavrada pelos provedores deste serviço e os produtores beneficiados aumentaram 97% e 781% respectivamente entre 2015 e 2019. 7. O crédito concedido ao sector agrário manteve-se insignificante se comparado com o resto da economia ao corresponder a um peso de 3,65% em 2015 e 3,71% em 2019. 8. A produção per capita de cereais continuou baixa para garantir a segurança alimentar, ao registar 71(Kg/hab) em 2015 e 94,3 kg em 2019. Para mandioca e batata doce, a situação continuou bem e melhor com a produção per capita de 267 kg em 2015 e 336 kg em 2019. A produção das culturas de rendimento foi estável no período de referência, facto observado nas mudas de cajueiros produzidas em torno de 4,5 milhões em 2019. Os produtos pecuários apresentaram, ao longo do quinquério, valores per capita baixos. Com efeito, a carne de frango registou uma produção per capita de 3,8 kg em 2019, partindo de 2,5 kg em 2015. Na produção de carne bovina, destacou-se a Província de Maputo com quase a metade da produção do País, 7 266 toneladas em 2019. Manica e Sofala destacaram-se na produção de leite de vaca ao deter 41,3 % e 25,1 % do total em 2019, respectivamente. A produção de pescado per capita caiu para 11,6 em 2019, depois de 13,7 kg em 2018 e 12,4 kg em 2017. Contudo, ressalta-se a produção de peixe marinho com 177 071 toneladas em 2019 correspondentes a 59,5% de toda a produção do sector. 9. No comércio externo, evidencia-se a exportação de açúcar e produtos de confeitaria, com crescimento de 22,9% da contribuição na receita aduaneira de 2019.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - indicators / indicadores; Northern PEA; agriculture / agricultura

Pânico e Medo: Desafios Dos Media Moçambicanos na Cobertura da COVID-19 - Joanguete, Celestino (Desafios para Moçambique 2020, 2020)
O principal foco do estudo são os diferentes enquadramentos da tonalidade discursiva adoptada pelos media nas suas narrativas sobre o novo coronavírus. Nesta perspectiva, a principal concentração como objecto de estudo são a rádio, a televisão, o jornal e as redes sociais da Internet. Neste último medium, escolhemos analisar especificamente as narrativas do Facebook e WhatsApp por serem as redes sociais mais populares em Moçambique. Socorremo-nos de duas metodologias de estudo bastante presentes no campo das ciências sociais, a análise de conteúdo desenvolvida por Bardin (2006) e a de observação sistemática. Foi fundamental adoptar estes métodos pela vantagem de permitirem recolher dados no momento da ocorrência dos factos, sem criar situações artificiais, e avaliar alguns aspectos para os quais não há outras técnicas de recolha de evidências. Uma análise sobre os diversos atributos descritivos do coronavírus permitiu compreender a construção do discurso mediático e a sua influência social. A análise de conteúdo das narrativas dos media moçambicanos facilitou a compreensão dos elementos constitutivos de textos jornalísticos, nas produções discursivas dos quais os termos, os adjectivos, as imagens, as descrições, o foco e as temáticas desempenham o papel fundamental.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; health - COVID-19 / saúde – COVID-19; health / saúde

Trabalho em Função do Género, Trabalho Migratório: Reformar os Regimos do Açúcar em Xinavane, Moçambique - Lazzarini, Alicia Hayashi (Desafios para Moçambique 2020, 2020)
O açúcar tem desempenhado um papel fundamental e controverso em Moçambique. Desde 1996, o Governo moçambicano e a iniciativa privada aproveitaram-se da ideia de que a África é a «última fronteira» do investimento (Diop et al., 2015; The Economist, 2013; Sizemore, 2012) para reinvestir numa economia devastada pela guerra civil e «reabilitá-la». Com um crescimento de sete por cento e, nos últimos anos, uma das taxas mais elevadas de investimento estrangeiro em África, Moçambique tem sido apresentado como um país posicionado para um crescimento explosivo. O açúcar tem desempenhado um papel crucial na transformação do presumível potencial da paisagem moçambicana em produtividade e na restauração da capacidade da nação para competir em mercados globais. A Açucareira de Xinavane tem sido o exemplo notável deste esforço de reabilitação. Antigamente conhecido como uma propriedade colonial menor, o actual empreendimento conjunto entre o Governo de Moçambique e a empresa sul-africana Tongaat Hulett tornou a Açucareira a maior plantação de açúcar do País. Entre 2005 e 2013, a área de cana-de-açúcar cultivada triplicou de 6000 para mais de 17 000 hectares (ha), com um aumento correspondente na produção de cana-de-açúcar, de 500 000 para 1,5 milhões de toneladas. A nova abordagem da produção de Xinavane enfatiza as técnicas de quantificação, cálculo e gestão originárias dos institutos de pesquisa de açúcar da África do Sul. Representantes da empresa e da indústria nacional descrevem a reabilitação da fábrica como a implementação directa da prática industrial padrão, apesar de enfrentar um contexto de «desenvolvimento» desafiador. Nas descrições do Governo e da indústria, o açúcar fornecerá empregos, infra- -estruturas necessárias e centros rurais com bancos, escolas e hospitais que beneficiarão todos os moçambicanos. Com este objectivo, foram levados a Xinavane peritos industriais regionais para formar gestores moçambicanos, supervisionar o restabelecimento e o crescimento da indústria e, finalmente, tornar possível o «progresso» económico e social de um país emergente de uma situação de conflito e, assim, construir uma economia capitalista competitiva. O presente artigo levanta questões sobre as tensões no seio desta abordagem tecnicamente estruturada. Analisa sobretudo as estratégias emergentes de gestão do trabalho, e identifica a forma como as «novas» práticas gerem uma força de trabalho grande e anteriormente indisciplinada. Esta gestão tem sido realizada através da divisão geográfica e de género, que não só reforça as baixas valorizações sociais e materiais da vida e do trabalho rural moçambicano, mas também restabelece um regime de trabalho profundamente associado à violência do passado colonial. Ao interrogar a dinâmica material e discursiva da «ciência da indústria» e da «tecnologia» na prática, ponho em causa os alegados impactos modernizadores desta abordagem «nova» no Moçambique pós-colonial.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; employment / emprego; gender / género

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Plano de monitoria e avaliacao dos programas de seguranca social basica - Macamo; Malôa, Chessira; Bazo, Geral; Mataba, Gito; Naene, Hélder; Maússe, Miguel; Machume, Olga; Monteiro, Vanádio (Instituto Nacional de Acção Social (INAS), 2020)
O presente documento foi desenvolvido pela equipa técnica do Instituto Nacional de Acção Social (INAS), com apoio técnico e financeiro da Organização Internacional do Trabalho (OIT) como resultado de acções promovidas pelo Sector no desenvolvimento e implantação de um modelo prático, eficiente e eficaz de Monitoria e Avaliação para os programas de Segurança Social Básica. O Plano de Monitoria e Avaliação dos programas de segurança social básica geridos pelo INAS obedece à Acção Estratégica número 33 do Plano Operacional da ENSSB 2016-2024, que visa “Operacionalizar o novo Sistema de Monitoria e Avaliação (M&A) do INAS e concluir o desenvolvimento de um sistema de M&A mais abrangente para o Subsistema de Segurança Social Básica”. Neste contexto, e à luz do Decreto 63/2018 de 26 de Junho, o INAS, IP criou na sua estrutura orgânica a Repartição Central de Monitoria e Avaliação para reforçar a sua capacidade ao nível nacional. As acções que culminaram com a elaboração do plano obedeceram uma metodologia prática e objectiva na medida que além de promoção de sessões de formação, sessões de debate e definição de quadros de monitoria e avaliação, foi também realizado um estudo ou análise que permitiu a definição de um RoadMap de M&E para os Programas de Segurança Social Básica implementados pelo Instituto Nacional de Acção Social. Como o presente documento consolida-se assim um instrumento unificado para guiar de forma prática as acções de M&A de todos Programas de Segurança Social Básica implementados pelo INAS até 2024. Este documento foi igualmente inspirado no modelo de Sistema de M&A do curriculum TRANSFORM, o que permitiu não só a definição do modelo apresentado no presente documento, mas também contribuiu consideravelmente na definição de uma periodicidade de revisão e melhoria do modelo, atendendo ao facto do presente modelo ser novo para o INAS tanto ao nível central como a nível das Delegações. O presente plano, aborda de forma detalhada a M&A os indicadores inerentes a cadeia de processos incluindo o pagamento terceirizado das transferências monetárias no PASD-PE e do PSSB incluindo a componente PSSB-SC tendo em conta todas fases de implementação.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - evaluation / avaliação; Social security / segurança social; social protection / proteção social

Campanha Agrícola 20/21: Mais de 300 mil hectares lavrados na campanha agrícola 2020/21 - MADER (Agricultura, 2020)
Mais de 300 mil hectares lavrados na campanha agrícola 2020/21
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Análise do Plano Económico e Social e Orçamento do Estado de 2020 nas Áreas da Saúde, Água e Saneamento - Marrengula, Constantino (Forum de Monitoria do Orçamento, FMO Mais, PAANE, 2020)
Os objectivos e os pilares do PES e OE de 2020 não mudaram, substancialmente, em comparação com o que foram as prioridades do quinquênio 2015-2019. Em linha com os compromissos internacionais, o Governo procurou manter os pesos relativos da despesa nos sectores prioritários, com particular realce para a educação e a saúde. Contudo, o aumento dos preços e dos encargos da dívida, que se seguiu à descoberta das dívidas não declaradas, baixou o valor real das provisões feitas nestes sectores. O valor de cerca de 26 mil milhões de Meticais reservado para a saúde em 2020 representa uma redução em relação ao que tinha sido programado para 2019, não obstante os desafios impostos pela pandemia da Covid19. A redução em termos reais do orçamento da saúde, ocorre num quadro geral, em que todas as metas previstas para o quinquênio passado foram revistas em baixa, ou não foram cumpridas. Por exemplo, num ano eleitoral como foi 2019, a taxa de realização da meta de recrutamento de profissionais para o sistema nacional da saúde situou-se em volta de 50%. As metas do PES e OE 2020 da saúde não parecem suficientes para que o sector recupere dos incumprimentos do quinquênio passado, num contexto que conta com a pandemia da Covid-19. Para o sector de água e saneamento, os acordos assinados com o Exim Bank da Índia, o Banco Mundial, e a SADC deram um novo impulso ao Programa PRAVIDA, mas o nível de realização das metas do PES e do orçamento do sector não foi substancialmente diferente do que aconteceu na saúde. Quando o orçamento aumentou em 2019 a taxa de execução do orçamento baixou para 32%, com incumprimentos em intervenções com impacto directo na pobreza, tanto rural como na zona peri-urbana. A revisão em baixa das metas do PES de 2020, em comparação com o definido para 2019, alarga o tempo necessário para que a intervenção do Estado no sector faça a diferença no acesso à água e saneamento. Num cenário de crescimento populacional, quanto mais conservadora e lenta for a intervenção maior é o atraso na correcção dos problemas identificados, o que certamente tem implicações na materialização dos objetivos de desenvolvimento sustentável. Reverter o cenário que sustenta as taxas de execução sub-óptimas dos orçamentos aprovados e a queda em termos reais das disponibilidades nos sectores prioritários constitui o principal desafio das Finanças Públicas em Moçambique. Embora não esteja claro o que poderá ser o futuro destes sectores depois da pandemia da Covid-19, a curto prazo torna-se importante encontrar formas de usar melhor o que se tem, retomar a trajectoria de sustentabilidade da dívida pública e normalizar as relações com os principais parceiros de apoio orçamental. Como se pode perceber da dinâmica dos indicadores da saúde, água e saneamento, os custos sociais de sub-utilizar o potencial existente e manter o status quo nas Finanças Públicas são demasiado altos para serem desconsiderados.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health - WASH / saúde - água, higiene e saneamento; health / saúde

Programas, sim, mas para fazer o quê? Uma análise dos manifestos eleitorais dos partidos para as eleições Moçambicanas de 15 de ooutubro de 2019 - Michel Cahen (Desafios para Moçambique 2020, 2020)
Os principais partidos publicaram Manifestos eleitorais que podem ser úteis para o eleitor que desejar entrar nos detalhes das propostas partidárias. Mas são utilizados aqui como fontes de análise para ter uma melhor compreensão da natureza destes partidos e das suas culturas políticas. Escolheram-se aqui os partidos que se apresentam na maioria das províncias. A Frelimo, a Renamo e o MDM apresentam-se às três eleições (presidenciais, legislativas e provinciais), o Podemos não apresentou um candidato para as presidenciais e apresenta-se em oito das onze províncias para as legislativas. A Nova Democracia decidiu apresentar candidatos somente nas legislativas, onde estará presente em todas as províncias. Começa-se por analisar o Manifesto do partido no poder, a Frelimo, para depois analisar o do principal partido de oposição e, enfim, o do terceiro partido, o MDM. Por último, serão analisados os Manifestos de dois novos partidos: Podemos e Nova Democracia. Chama-se a atenção do leitor para o facto de este artigo não estudar estes partidos políticos como tais, mas somente os Manifestos eleitorais, isto é um tipo de texto muito contextual.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; politics / política

A Economia de Moçambique e Os Conflitos e Tensões À Volta Das Condições De Produção E Reprodução Agrícola - Muianga, Carlos (Desafios para Moçambique 2020, 2020)
Este artigo é uma tentativa de fornecer elementos a partir dos quais possamos compreender conflitos e tensões à volta das condições de produção e reprodução agrícola em Moçambique. O foco é na análise de como as estruturas económicas afectam as condições sociais de produção e reprodução agrícola e ajudam a explicar conflitos e tensões à sua volta. A análise oficial dominante sobre os problemas do desenvolvimento agrário no País é frequentemente feita recorrendo à descrição de um conjunto de obstáculos à melhoria das condições de produção, em particular do «sector familiar», cuja produção e produtividade são consideradas muito baixas (GdM, 2008, 2011a, 2011b, 2015). Olhando criticamente para esta análise dominante, o artigo defende que as estruturas dominantes da economia determinam as condições sociais de produção e reprodução na agricultura, a sua transformação e a natureza dos conflitos e tensões à sua volta. Além disso, os processos socioeconómicos, políticos e institucionais que emergem destas estruturas, sustentando a sua reprodução e expansão, limitam as possibilidades reais de desenvolvimento de forças produtivas na agricultura. Associadas ao fraco desenvolvimento destas forças produtivas, as condições e os mecanismos de produção e reprodução constituem, por sua vez, uma base para a reprodução e expansão destas estruturas económicas. O artigo está organizado em cinco secções, incluindo a introdução. A segunda secção procura definir os conceitos de produção e reprodução, mostrando como estes dois processos são lógica, orgânica e estruturalmente relacionados. A operacionalização destes conceitos permite-nos ter bases para identificarmos e compreendermos as condições de produção e reprodução agrícola e a forma como estas se manifestam num contexto específico e complexo de relações sociais de produção. A terceira secção descreve alguns elementos da estrutura da economia, com foco nas dinâmicas dominantes. Com recurso a esta análise, a quarta secção discute alguns dos conflitos e tensões à volta das condições de produção e reprodução agrícola no País nos últimos anos e a forma como a sua natureza constitui um bloqueio sistemático ao desenvolvimento das forças produtivas na agricultura e no campo.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura

A Pharmaceutical Logistics still far from answering health concerns of the country: budgetary weaknesses - N'weti (N'weti, 2020)
Key Messages: - Pharmaceutical logistics make up only 7% of total projected costs for the health sector through 2019; - The expansion and demand of the health sector in the forthcoming years will not be accompanied by the necessary increase in resources for the pharmaceutical logistics sector; - Increased nancing in the area of PL is necessary, preferably from internal sources, to allow the implementation of PELF recommendations; - It is estimated that 13% of the value of the approximately $3,929 million needed to procure and manage drugs and commodities during 2014-2019 will be wasted. - The health sector is heavily reliant on external funding, with 81% of funding for medicines comming from external partners; - There is concerning public evidence of systematic stock-outs of medicines in public pharmacies throughout the country. Research by Nweti (2014-2015) in 37 health acilities in four provinces using the community score card as a survey tool, found that stock-out of essential medicines was one of the barriers to accessing quality health services. Another study carried out by Wagenaar, et al. (2014) in Sofala Province, which assessed 26 facilities showed that only one out of the 26 facilities assessed in 2011, 2012, and 2013 had all of the 15 essential medicines.
Keywords: G - Mozambique / Moçambique; L - english / inglês; budget / orçamento; health / saúde

Uma Logística Farmacêutica ainda distante de responder às preocupações de saúde do país: as fragilidades orçamentais - N'weti (N'weti, 2020)
A área de logística farmacêutica (LF) é vital pelo facto de assegurar que os medicamentos e produtos médicos estejam disponíveis no país e nos pontos de entrega e inclui seleção de medicamentos, quanti cação, procurement, controle de qualidade, armazenamento, transporte e distribuição. O Governo de Moçambique reconhece a importância deste sector e como parte da agenda de reforma do MISAU desenhou o Plano Estratégico de Logística Farmacêutica (PELF) juntamente com o respectivo Plano Operacional (2013). O PELF visa responder a necessidade de providenciar reformas a área de logística farmacêutica melhorando a gestão nanceira, procurement, inventariação, gestão do armazenamento, transporte, distribuição, uso de medicamentos e gestão de recursos humanos. Relatórios disponíveis apontam para a existência de vários desafios na implementação do PELF sendo que a falta de recursos financeiros é um dos maiores desafios para a implementação do quadro de recomendações deste documento. Em Moçambique a LF é actualmente uma das áreas menos favorecidas em termos de dotação orçamental cabendo-lhe 7% do total de envelope de recursos do sector da saúde projectados até 2019 (MISAU/DNPC, 2013). Esta tendência ao ser estacionária ao longo dos próximos 5 anos certamente estará em descompasso com a expansão e aumento da demanda pelos serviços públicos de saúde o que poderá comprometer a prestação do sector de saúde. A actual fonte de nanciamento e práticas de alocação orçamental na área de LF é também problemática. A estimativa da taxa de desperdício de medicamentos e consumíveis representa cerca de 13% do investimento total de $3,929 milhões de dólares da área de Logística Farmacêutica. Uma redução da taxa de desperdício para 5% implicaria numa economia de 332 milhões de dólares durante o PESS 2014 - 2019 (Dutta et al., 2014). Adicionalmente mais de 81% dos fundos para área de medicamentos são nanciados por parceiros externos (Dutta et al., 2014). Esta dependência de fundos externos é preocupante num cenário de incerteza do nanciamento externo ao sector de saúde (Dutta et al., 2014). Os níveis de satisfação da disponibilidade de medicamentos essenciais a nível central apesar de registarem progressos contrastam com a disponibilidade de medicamentos a nível das unidades sanitárias (MISAU, 2013, 2014). Várias Organizações da Sociedade Civil (OSC) incluindo a N ́weti, MSF o CIP tem denunciado sistemáticas rupturas de medicamentos nas unidades sanitárias das províncias do sul, centro e norte do país. Face as rupturas sistemáticas de medicamentos nas unidades sanitárias e a imprevisibilidade do nanciamento externo é crucial que o Governo de Moçambique incremente o volume de nanciamento para a área de LF sobretudo na base de recursos domésticos. A falta de recursos está a afectar grandemente a implementação do PELF e de igual modo a capacidade do sector de saúde em providenciar de forma e ciente serviços de saúde de qualidade.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; health / saúde

Cabo Delgado e o Risco Sistémico da Guerra em Moçambique - Ngoenha, Severino; do Amaral, Giverage; Nhumaio, Alcido (Desafios para Moçambique 2020, 2020)
Em Moçambique a guerra é um risco sistémico: na linguagem de Thomas Hobbes, é a mãe de todos os riscos. A guerra é transversal a todos os outros riscos em termos de consequências sociais, económicas, políticas e culturais: destrói as infra-estruturas, como a rede escolar, os hospitais, as vias de acesso e os tecidos sociais; enfraquece a economia; paralisa a agricultura; apodera-se da indústria; e instala a fome, a miséria e toda a espécie de desgraças. A guerra é o maior dos riscos sistémicos de Moçambique não apenas pelos seus efeitos altamente destrutivos, mas porque agrava a probabilidade de ocorrência dos demais riscos aos quais o País está sistemática e concomitantemente exposto. Em geral, as considerações sobre a guerra em Moçambique são feitas de duas maneiras diferentes. De um lado, a abordagem político-militar, que privilegia a busca de mecanismos de diálogo entre os beligerantes, o que supõe o conhecimento e o reconhecimento entre as partes e das razões que levam uns e outros a optar por um confronto armado. Esta abordagem tem sido a adoptada pelos diferentes governos moçambicanos que enfrentaram conflitos nos seus mandatos, ou seja, todos. Actualmente não parece que uma tal via se vislumbre salutar nas estratégias contra os dois conflitos armados em curso no Centro e Norte do País. Por outo lado, a abordagem técnico-científica, que parte do pressuposto de que o fenómeno da guerra é complexo e privilegia uma epistemologia interdisciplinar, na qual participam muitos saberes disciplinares no esforço de apreender as suas razões e causas. Esta abordagem procura entender o que leva o País a fazer da guerra o seu modus vivendi, o que leva grupos, partidos e facções militares a optarem sistematicamente pela confrontação militar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

O Cabo do Medo - O Daesh em Moçambique 2019-2020 - Rogeiro, Nuno (UCCLA, 2020)
Toda a verdade sobre a situação explosiva do domínio do Norte de Moçambique pelo Daesh. É o primeiro livro a nível mundial que revela em primeira mão o que se está a passar na zona de Cabo Delgado: a conquista e subjugação das populações, a violência bárbara com recurso a decapitações e execuções sumárias, a exploração das pessoas e dos recursos disponíveis, a impotência das autoridades moçambicanas em impor a ordem e a paz social. Um livro de grande acualidade que desvenda uma realidade tão chocante quanto desconhecida. “Uma análise exaustiva da ocupação desta terra boa (nordeste de Moçambique), de gente boa, pelo Daesh. Tem de ser combatido mas, primeiro, tem de ser compreendido.” Nuno Rogeiro
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Desafios e Contradições Para Uma Abordagem Sobre Trabalho e Emprego em Moçambique - Rosimina Ali (Desafios para Moçambique 2020, 2020)
As condições de emprego são dominadas por trabalho irregular, instável, mal pago, precário e com alta rotatividade; em que os trabalhadores têm de se envolver em múltiplas actividades produtivas e reprodutivas (dominadas por trabalho mal pago e não pago) para garantir o seu sustento e a sua disponibilidade a baixo custo para o capital. O caso dos trabalhadores das agroindústrias é um exemplo. A base de rentabilidade do capital assente nestas condições laborais instáveis e irregulares, produtivas e reprodutivas. Ademais, nos moldes produtivos actuais, a capacidade de a economia lidar com crises sociais, económicas, políticas e/ou ambientais é limitada. A pandemia do novo coronavírus (COVID-19) não é excepção mas uma expressão que revela que a força de trabalho não é um «mero» recurso ou mercadoria, mas é vital na economia e nos processos de (re)produção social, através da sua subordinação formal ou informal ao capital; sendo esta última forma de subordinação dominante, mas negligenciada. A crise intensifica os problemas estruturais já existentes no sistema prevalecente, que precisam de ser transformados, como a incapacidade da economia de prover o acesso a condições sociais básicas, indispensáveis à reprodução da força de trabalho (onerosa e encarregada aos trabalhadores e suas famílias). Se as inter-relações co-constitutivas entre produção e reprodução permanecerem não abordadas e a economia não transformada, a fragmentação das condições sociais do trabalho e dos modos de vida conduzirá a uma acumulação de miséria, com crises sistemáticas no sistema económico e o colapso da reprodução social, comprometendo a efectividade das intenções de políticas públicas «em mais e melhores empregos». Este artigo desdobra-se em cinco secções. A segunda secção olha analítica e metodologicamente para a relação orgânica entre os mercados de trabalho, acumulação e reprodução social, que permitem entender a natureza e a organização do trabalho. Ao olhar para as condições de emprego em particular nas estruturas produtivas agroindustriais e as condições gerais de reprodução social da força de trabalho no País, a terceira e quarta secções, respectivamente, mostram porque é crucial mudar a organização das estruturas e relações produtivas. A última secção conclui salientando a urgência do entendimento e da transformação da actual estrutura económica e laboral e identificando algumas áreas críticas e desafios a enfrentar pela política pública.
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; employment / emprego

Investimento Directo Estrangeiro e o Desenvolvimento Socioeconómico em Moçambique: Dinâmicas, Tensões e Desafios - Sambo, Michael Godet (Desafios para Moçambique 2020, 2020)
Considerando a estrutura económica de Moçambique e analisando a estrutura do IDE que aflui a Moçambique, este artigo argumenta que o aumento de IDE na economia não é necessariamente a condição para o desenvolvimento se não for maximizada a captação e utilização das receitas. Embora a lógica de fomento do desenvolvimento económico através do investimento adoptada pelo Governo de Moçambique no PQG 2015-2019 tenha um embasamento teórico, o seu enquadramento é simplista e pouco considera a natureza do investimento, o contexto em que este é aplicado e o seu efeito estrutural na economia. O argumento resulta, além da revisão bibliográfica e documental, de uma análise dos dados económicos oficiais de Moçambique, com destaque para os dados do IDE publicados pelo Banco de Moçambique, conjugados com a análise dos materiais de trabalhos de campo sobre o IDE na província de Nampula em 2016 e na Província de Gaza em 2019. O texto está estruturado em três partes além da introdução e conclusão. A primeira faz um enquadramento teórico da discussão, a segunda analisa as dinâmicas de IDE na economia e a terceira analisa algumas evidências empíricas dos efeitos socioeconómicos causados pelos projectos de IDE nas comunidades receptoras dos projectos.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português

Accessing global value chains: The politics of promoting export-driven industrialisation and upgrading in the Mozambican cashew processing industry - Saulich, Christina Lisa (2020)
Successful export sectors in manufacturing and agribusiness are important drivers of structural transformation in Sub-Sahara African countries. Backed by industrial policies and active state involvement, a small number of successful productive export sectors has emerged in Sub-Saharan Africa. This thesis asks the question: How do politics shape the promotion of export-driven industrialisation and firm-level upgrading in Sub-Saharan Africa? It exemplifies this question with an in-depth, qualitative study of the cashew processing industry in Mozambique in the period from 1991 until 2019. Mozambique used to be one of the world’s largest producers and processors of cashew nuts in the 1960s and 1970s. At the end of the 20th century, the cashew processing industry broke down completely but has re-emerged as one of the country’s few successful agro-processing exports. The thesis draws on theoretical approaches from the fields of political science, notably the political settlements framework, global value chain analysis and the research on technological capabilities to explore why the Mozambican Government supported the cashew processing industry and how Mozambican cashew processors acquired the technological capabilities needed to access the global cashew value chain and to upgrade. It makes an important theoretical contribution by linking the political settlements framework and the literature on upgrading in global value chains to study how politics shaped productive sector promotion and upgrading in the Mozambican cashew processing industry. The findings of the thesis are based on extensive primary data, including 58 expert interviews and 10 firm surveys, that was collected in Mozambique in 2018 as well as a broad base of secondary literature. The thesis argues that the Mozambican Government supported the cashew processing industry because it became important for the Government’s political survival. Promoting the cashew sector formed part of an electoral strategy for the ruling FRELIMO coalition and a means to keep FRELIMO factions united by offering economic opportunities to key constituencies. In 1999, it adopted a protectionist cashew law that created strong incentives for cashew processing in Mozambique. This not only facilitated the re-emergence of the cashew processing industry after its breakdown. The law and the active involvement of the National Cashew Institute (INCAJU) also affected the governance of the local cashew value chain, the creation of backward linkages, and the upgrading paths of cashew processors. The findings of the thesis suggest that the cashew law reduced the pressure on the cashew processing industry to upgrade. The law further created opportunities for formal and informal rent creation for members of the political elite and lower level FRELIMO officials that prevented a far-reaching reform of the law. The thesis shows that international buyers do not promote upgrading among Sub-Sahara African firms in global value chains with market-based or modular governance. Moreover, firms that operate in countries where industrial policies are not enforced effectively cannot draw on the support of government institutions to enhance their capabilities and to upgrade. Firms therefore mainly depended on costly learning channels at firm level, e.g. learning by doing or hiring skilled labour, and/or on technical assistance from donors to build the technological capabilities needed to access global value chains and to remain competitive. The findings of the thesis suggest that researchers, governments, development practitioners and consultants need to rethink their understanding of upgrading in GVCs in four ways. First, they need to move away from understanding upgrading in terms of moving towards more complex, higher value-added activities in GVCs (functional upgrading). Instead, it is important to consider the potential of other, more realistic types of upgrading for firms in low-income countries, such reducing risks by diversifying suppliers and buyers or increasing rewards by making production processes more efficient. Second, they need to replace an overly positive view on upgrading that neglects possible side-effects at sector and/or country level. Third, GVC participation on its own does not promote upgrading among local supplier firms in Sub-Saharan Africa. The interests of lead firms and Sub-Sahara African supplier firms may not be aligned or even conflicting. Targeted industrial policies and the creation of institutions that effectively promote capability building among firms therefore become even more important. Finally, upgrading needs to be understood as a process that is not only shaped by interactions between firms, but also by local domestic politics. The findings of the thesis are highly relevant for scholars from the fields of political science, development studies, and economics. Its practical implications and tools, e.g. a technological capabilities matrix for the cashew industry, are of interest for development practitioners, members of public institutions in Sub-Sahara African countries, local entrepreneurs, and representatives of local business associations that are involved in promoting export sectors and upgrading among local firms.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura

‘We all have the same right to have health services’: a case study of Namati’s legal empowerment program in Mozambique - Schaaf, Marta; Falcao, Joana; Feinglass, Ellie; Kitchell, Erin; Gomes, Nadja; Freedman, Lynn (BMC Public Health, 2020)
Background: Legal empowerment and social accountability are two strategies that are increasingly used to address gaps in healthcare in low- and middle-income countries, including failure to provide services that should be available and poor clinical and interpersonal quality of care. This paper is an explanatory case study of a legal empowerment effort that employs community paralegals and trains Village Health Committees (VHCs) in Mozambique. The research objective was to explore how community paralegals solved cases, the impact paralegals had on health services, and how their work affected the relationship between the community and the health sector at the local level. Methods: The case study had two components: (1) a retrospective review of 24 cases of patient/community grievances about the health system, and (2) qualitative investigation of the program and program context. The case reviews were accomplished by conducting structured in-depth interviews (IDIs) with those directly involved in the case. The qualitative investigation entailed semi-structured Key Informant Interviews (KIIs) with district, provincial, and national health managers and Namati staff. In addition, focus group discussions (FGDs) were held with Health Advocates and VHC members. Results: Case resolution conferred a sense of empowerment to clients, brought immediate, concrete improvements in health service quality at the health facilities concerned, and seemingly instigated a virtuous circle of rightsclaiming. The program also engendered incipient improvements in relations between clients and the health system. We identified three key mechanisms underlying case resolution, including: bolstered administrative capacity within the health sector, reduced transaction and political costs for health providers, and provider fear of administrative sanction. Conclusions: This study contributes to the limited literature regarding the mechanisms of legal empowerment case resolution in health systems and the impact of hybrid legal empowerment and social accountability approaches. Future research might assess the sustainability of case resolution; how governance at central, provincial, and district level is affected by similar programs; and to what extent the mix of different cases addressed by legal empowerment influences the success of the program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; empowerment / empoderamento; health / saúde

Protecção Social e Os Principais Obstáculos ao Financiamento das Empresas Através da Bolsa de Valores de Moçambique - Siúta, Moisés; Chishte, Ussene (Desafios para Moçambique 2020, 2020)
O objectivo deste artigo é discutir o papel da Bolsa de Valores de Moçambique como uma das vias que mobiliza financiamento para as empresas moçambicanas tendo em conta as barreiras explícitas e implícitas que tanto a Bolsa como as empresas enfrentam no desempenho das suas funções no mercado financeiro em particular e na economia moçambicana em geral. A consecução deste objectivo está associada à de outros três objectivos específicos. Primeiro, estabelecer o quadro teórico dentro do qual a relação entre a Bolsa de Valores e as empresas pode ser discutida. Segundo, descrever o contexto em que a Bolsa de Valores e as empresas moçambicanas operam. Por fim, terceiro, discutir a forma como os principais desafios do ambiente económico nacional, enfrentados pela Bolsa e pelas empresas, afectam o acesso a financiamento, o crescimento e o desenvolvimento das empresas moçambicanas. O presente artigo está divido em seis secções incluindo a presente introdução. A segunda secção, estabelece a relação entre a protecção social e o financiamento das empresas. A terceira e a quarta secções procuram enquadrar a Bolsa de Valores conceptual e teoricamente. A quinta secção apresenta as características dos principais intervenientes no sistema financeiro nacional destacando os principais aspectos que contribuem para a compreensão dos principais obstáculos ao financiamento das empresas e da população no contexto económico actual. A sexta secção discute os obstáculos ao financiamento das empresas no sistema financeiro com foco particular para a sua relação com a Bolsa de Valores de Moçambique. Por fim, a sétima secção apresenta as considerações finais, sintetizando a relação entre a protecção social e o financiamento às empresas e realçando a importância das empresas no crescimento e desenvolvimento da actividade económica do País, assim como na geração de emprego para o bem-estar da população. Adicionalmente, a mesma secção faz uma breve reflecção sobre a maneira como a política pública tem contribuído negativamente para o financiamento das empresas privadas nacionais.
Keywords: *indexed; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; Social Protection PEA; social protection / proteção social

Redressing the gender imbalance: a qualitative analysis of recruitment and retention in Mozambique’s community health workforce - Steege, Rosalind; Taegtmeyer, Miriam; Ndima, Sozinho; Give, Celso; Sidat, Mohsin; Ferrão, Clara; Theobald, Sally (Human Resources for Health, 2020)
Findings: In-depth interviews (n = 30), key informant interviews (n = 1) and focus group discussions (n = 3) captured experiences and perceptions of employment processes. Intra-household decision-making structures mean women may experience additional barriers to join the APE programme, often requiring their husband’s consent. Training programmes outside of the community were viewed positively as an opportunity to build a cohort. However, women reported difficulty leaving family responsibilities behind, and men reported challenges in providing for their families during training as other income-generating opportunities were not available to them. These dynamics were particularly acute in the case of single mothers, serving both a provider and primary carer role. Differences in attrition by gender were reported: women are likely to leave the programme when they marry, whereas men tend to leave when offered another job with a higher salary. Age and geographic location were also important intersecting factors: younger male and female APEs seek employment opportunities in neighbouring South Africa, whereas older APEs are more content to remain. Conclusion: Gender norms, roles and power dynamics intersect with other axes of inequity such as marital status, age and geographic location to impact recruitment and retention of APEs in Maputo Province, Mozambique. Responsive policies to support gender equity within APE recruitment processes are required to support and retain a gender-equitable APE cadre.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Informe Orçamental Acção Social - Mozambique 2020 - UNICEF (UNICEF and Organização Internacional do Trabalho (OIT), 2020)
Principais Mensagens: 1. Apesar do aumento contínuo registado na dotação orçamental destinada à protecção social desde 2010, o nível do espaço fiscal dedicado aos programas de protecção social básica (não contributiva) ainda está aquém das necessidades e, a menos que seja consideravelmente melhorado, é pouco provável que o sistema cumpra a meta estabelecida na ENSSB 2016-2024 (2,23 por cento do PIB). 2. A cobertura específica dos programas de Protecção Social definidos no PQG 2015-2019 não foi cumprida em resultado de dotações sectoriais insuficientes, bem como de ineficiências na execução orçamental. Com o impacto negativo da COVID-19 na renda da população moçambicana, as necessidades de protecção social são maiores do que nunca. Por conseguinte, é ainda mais necessária uma rápida expansão da cobertura, e consequentemente, torna-se necessário proceder a uma dotação orçamental muito maior para 2020 e 2021. 3. O apoio orçamental dos principais doadores (tais como o Banco Mundial e outros) constitui uma importante oportunidade para o sector da Protecção Social cumprir os ambiciosos objectivos de expansão da cobertura. É necessário um mecanismo sólido de monitoria, informação e prestação de contas que garanta o acesso aos recursos, pelo que uma utilização eficaz do e-INAS poderia ser a solução-chave. 4. Embora seja atribuída uma maior dotação orçamental às províncias com maior índice de pobreza / vulnerabilidades, uma grande lacuna ainda está por preencher. No orçamento de 2020, a dotação per capita (por pessoa pobre) nas províncias desfavorecidas do Norte é muito mais baixa do que a das províncias relativamente mais ricas do Sul. Como forma de reduzir a desigualdade, é necessária uma expansão da cobertura, bem como a priorização de áreas com taxas de pobreza mais elevadas.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; social action / ação social; social protection / proteção social

State Budget Proposal for Fiscal Year 2020 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2020)
Key messages: 1. The value of the State Budget for 2020 is MT 345.4 b. The 2020 State Budget marks the beginning of a new governance cycle (2020-2024) and is aligned with the strategic objectives and priorities defined in the new 5-year plan (PQG 2020-2024). However, the current global COVID19-induced economic uncertainty has led the Government of Mozambique to a restrictive approach to the budget aimed at prioritizing the provision of basic services to the population. 2. The Council of Ministry’s Decree n.2/2020 established the principles and norms of the provincial decentralized governance, both political and financial. However, this was not yet reflected in 2020 State Budget. 3. The government’s new overarching development strategy, the “Government’s Five-Year Plan (PQG 2020-2024)” has 3 strategic priorities and 3 strategic pillars. In the 2020 State Budget, Priority II: Promote Economic Growth, Productivity and Job Creation, received the majority of funding, worth 44 percent of budget. Priority I: Develop Human Capital and Social Justice was allocated 35 percent of 2020 State Budget resources. 4. This year the Government has prioritized the allocation of resources to essential sectors, namely Health, Education and Agriculture & Rural Development. The allocation to these three sectors is worth 48 percent of 2020 State Budget (excluding debt servicing and financial operations) or 34 percent of the entire budget. Relative to last year, the allocation to the Education sector increased while those of the Health and Agriculture sectors decreased. 5. In the 2020-2024 PQG, the Government set the goal of allocating 65.2 percent of resources to priority economic and social sectors. This year’s cumulative allocation to priority areas is worth 68 percent of the State Budget less financial operations and debt servicing, or 48 percent of the entire State Budget including financial operations and debt servicing. Of the priority Economic and Social sectors supported by UNICEF, Education was allocated Meticals (MT) 66.3 billions (b), Health MT 26.7 b, Social Action MT 6.7 b and WASH MT 7.1 b in the State Budget for 2020. 6. The allocation to Education increased by 17 percent in nominal terms and by 9 percent in real terms relative to 2019 Budget. The sector allocation is worth 19.2 percent of 2020 State Budget. Excluding financial operations and debt servicing, education represents 27.1 percent. As a share of Mozambique’s GDP, the Education sector’ allocation represents 6.1 percent. 7. The Health allocation represents a 5 percent nominal decrease and an 11 percent real terms-decrease compared to last year’s budget. Such decrease is explained by the heavy reduction in externally-funded on-budget resources to the sector. Health is worth 7.7 percent of the 2020 budget. Excluding financial operations and debt servicing, the sector represents 10.9 percent. As a share of the expected GDP for 2020, the Health Budget is worth approximately 2.5 percent. Relative to last year, the sector allocations decreased both as a share of government expenditure and as a share of GDP. 8. The Ministry of Health has developed a National Plan for COVID-19 preparedness and response which will be allocated approximately MT 1.8 b or USD 28.4 m through off-budget resources, of which 56 percent will be allocated to drugs and supplies. The Ministry of Health COVID-19 Plan however does not include budget for water services and hygiene measures essential to Infection prevention and control (IPC). 9. The 2020 initial allocation to Social Action dropped by 7 percent in nominal terms and by 14 percent in real terms compared to 2019. However, spending for INAS Social Protection Programs as a share of budget and as a share of GDP is on par with those of last year. Still, given the risk of increased vulnerabilities due to COVID-19, larger allocations to INAS programs are recommended.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Cadernos IESE, 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito

Paz e Reconciliação em Moçambique: conjunturas críticas e dependência da trajectória - Weimer, Bernhard; Bueno, Natália (Desafios para Moçambique 2020, 2020)
Com base em estudos anteriores (Bueno, 2017; 2019; Weimer, 2020), recorremos aos conceitos de dependência da trajectória (em inglês, path dependence) e conjunturas críticas (em inglês, critical junctures) como duas lógicas explicativas para construir a nossa análise. Como se explica mais adiante, estas lógicas são muito usadas em análises históricas. Revisitamos, assim, o caso de Moçambique e examinamos o desenvolvimento da reconciliação, dando maior prioridade ao acordo de paz assinado em Agosto de 2019. Defendemos que, por muito que estes acordos de paz se inscrevam em contextos mais amplos de conjunturas críticas para a construção da paz, democratização e descentralização, as leis de amnistia a eles ligados podem inscrever-se numa lógica de dependência da trajectória. Na segunda secção do artigo, ocupamo-nos, primeiro, da literatura sobre conjunturas críticas, dependência da trajectória, reconciliação e amnistia para apresentar os principais debates sobre os conceitos usados neste estudo, bem como para definir o potencial explicativo que resulta da inter-relação entre esses elementos. Deste exercício resulta a chamada «abordagem contabilística», que, depois, aplicamos ao caso de Moçambique na terceira secção, que é dedicada à análise da reconciliação no País, examinando sobretudo o seu desenvolvimento no contexto do Acordo de Paz e Reconciliação de Maputo. Finalmente, na última secção, sintetizamos o argumento, apresentamos algumas observações finais e fazemos algumas recomendações políticas assentes na literatura e nas melhores práticas internacionais
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; conflict - civil war / conflito - guerra civil

Mozambique Annual Report 2020: Responding to a Year of Crisis - Wojnar, Andrea M; Lomelin, Jessica; Baker, Daniel; Salu, Karlina; Macangira, Assane; Manjate, Epidauro (UNFPA, 2020)
In the case of Mozambique, the pandemic came on the heels of two destructive cyclones that had devastated large parts of the country in 2019 and whose consequences were still being felt. In northern Mozambique, increasing violence in Cabo Delgado province resulted in a surge of internally displaced persons into local communities in Cabo Delgado, Nampula and Niassa provinces. With host communities ill equipped to meet the needs of those displaced, this population movement created a new humanitarian crisis in the midst of the pandemic. Like all of our governmental, civil society and donor partners, the resilience of UNFPA was tested, and we had to adjust quickly after the first case of COVID-19 was confirmed in March and the Government declared a state of emergency. At the most basic level, women continued to get pregnant and babies were still being born, even in the middle of a pandemic. Addressing the needs of adolescent girls and young women could not be put on hold. Helping to meet the needs of the symbolic target of UNFPA’s work – “the 10-year-old girl” – could not wait until she was 11. Helping to meet her aspirations for the future, advocating and working for her growth and self-fulfillment as a woman leading a healthy, productive and violence-free life – these could not wait a year.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - COVID-19 / saúde – COVID-19; health / saúde; youth / juventude

Social and Behaviour Change Communication Interventions in Mozambique - Cooper, Rachel (2019)
Social and behaviour change communication (SBCC) is the use of communication to change behaviours by positively influencing knowledge, attitudes and social norms at the individual and community level. Approaches to SBCC include, but are not limited to: media campaigns, peer educators and mentors, small group sessions, community dialogues and events, and digital tools. This rapid literature review focuses on SBCC interventions in Mozambique across four sectors: family planning (FP); girls’ empowerment; water, sanitation and hygiene (WASH), and nutrition. The most common SBCC approaches across the four sectors include: Inter-personal communication, Community participatory approaches, SMS based platforms, and Media channels. This review draws on evaluations of SBCC intervention, donor reports, and qualitative evidence collected by implementers and funders. There is a relatively large evidence base for FP and nutrition interventions, and a comparatively smaller one for WASH and girls’ empowerment. No lessons learned from integrating WASH and nutrition programming could be found during the course of this review. Although there are examples of nutrition programming including WASH in their counselling interventions, as well as calls for the development of multisectoral programmes. For example, in 2017, UNICEF signed a multi-sectoral proposal covering WASH, nutrition, and behaviour change funded by the EU. The programme will work in Nampula and Zambezia Provinces between 2017 and 2021.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health / saúde; ⛔ No DOI found

Faith communities, youth and development in Mozambique - Chifeche, Victoria; Dreyer, Yolanda (HTS Teologiese Studies / Theological Studies, 2019)
In Mozambique, poverty is pervasive because of factors such as the civil war (1976–1992) and its aftermath, political instability, food scarcity and natural disasters. This article elucidates the situation of post-civil war Mozambique from a socio-political perspective with a specific focus on children and the youth as a particularly vulnerable group. Many children and young people have been displaced and are subject to work exploitation and sexual abuse. Female children also fall victim to the cultural practice of child marriage. The absence of comprehensive social measures for the protection of vulnerable young persons has a detrimental effect on their welfare and future prospects. The aim of the article is to explore the role that faith communities and church institutions can play in this context. From an inclusive congregational perspective, the inclusion of youth in all aspects of faith communities as a strategy for development is discussed. From a human rights and theological perspective, participatory action is required for faith communities and church institutions to contribute to making a life of human dignity possible for children and young people.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; institutions / instituições; youth / juventude

Republic of Mozambique: Final Report General and Provincial Assembly Elections - European Union Election Observation Missionn (European Union Election Observation Mission, 2019)
On 15 October, Mozambicans elected the president, members of the Assembly of the Republic, members of the 10 provincial assemblies, and 10 provincial governors. Although there was a considerable number of participants, including recently registered political parties, the electoral process was dominated by the three main parties: the ruling Mozambican Liberation Front (FRELIMO), the main opposition Mozambican National Resistance (RENAMO), and the Mozambican Democratic Movement (MDM)
Keywords: G - Mozambique / Moçambique; L - english / inglês; electoral geography / geografia eleitoral

Democratization of Health Services: Dynamics of Administrative Resistances (N'weti - comunicação para saúde, 2019)
This policy brief, apart from describing the dilemmas of the democratization process of health services it, aims to analyze its implications on the dynamics of social accountability in the health sector and, finally, to inform on possible ways for a more coherent democratization, considering the normative discourses
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; decentralization / descentralização; health / saúde

Scenarios for Violence in the Resource-rich Cabo Delgado Province - Devermont, Judd; Columbo, Emilia (Center for Strategic and International Studies (CSIS), 2019)
The government of Mozambique has a rapidly shrinking window within which to implement a more comprehensive and effective strategy to weaken the Ahlu Sunna wa Jama (ASWJ) insurgents in Cabo Delgado and prevent the group from becoming an entrenched, long-term security problem. This report projects that the security situation in Cabo Delgado will most likely deteriorate during the next 18 months if the ASWJ insurgency continues to recruit new fighters and maintains a high frequency of attacks, as they have done since October 2017. Another key destabilizing factor is a government response that prioritizes military action over community development programs as its primary line of effort against the group. The government’s heavy-handed counterinsurgency approach risks further alienating the local population, driving them to lend active and passive aid to the militants. While the complete pacification of the group is unlikely during the next 18 months, a concerted whole-of-government approach would help undercut the group’s momentum. This includes outreach to the local community, programs, and policies designed to address specific grievances, and the use of targeted military operations. Maputo’s partners in the international community and private sector also have an important role to play. They can leverage their political influence and financial resources to press the Mozambican government to shift its current approach toward one that addresses the underlying grievances driving the insurgency. In doing so, Maputo and its partners have a better opportunity to not only undercut the present violence but potentially prevent future armed groups from emerging.
Keywords: G - Mozambique / Moçambique; GP - Cabo Delgado; L - english / inglês; security / segurança; ⛔ No DOI found

The Genesis of Insurgency in Northern Mozambique - Matsinhe, David M.; Valoi, Estacio (Institute for Security Studies (ISS), 2019)
Insurgents have attacked towns and villages in Cabo Delgado, the poorest province in Mozambique. The government has responded by sending in the military to stamp out the assailants, using ‘whatever it takes’, amid suspicions that foreign fighters from Tanzania have radicalised local youth who are behind the violence. Other measures to counter the violence include an extra-judicial state of emergency and the suppression of information.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; youth / juventude

Coesão social e violência política em Moçambique: notas para debate - Forquilha, Salvador; Gonçalves, Euclides (Conferência do IESE – “Desafios para Moçambique: Dez anos pensando o país”, 2019)
Perguntas e método de pesquisa Contexto: • Dados da primeira fase de uma pesquisa programática no norte de Moçambique Pergunta: • Como operacionalizar operacionalizar a noção de coesão social em Moçambique? • Que subsídios a noção de coesão social pode oferecer para a compreensão da violência política em Moçambique? Recolha de dados • Período: Abril e Maio de 2019 • Locais: Cidade de Maputo, Chiúre (Cabo Delgado), Chimbunila (Niassa) e Mussuril (Nampula) • Entrevistas: Representantes e membros de partidos políticos, líderes comunitários e religiosos, grupos de camponeses e jovens • Análise de dados: Mapeamento de factores com potencial para conflicto (conflict mapping)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique - Khadiagala, Gilbert M.; Manhique, Jorge R. (WFD - Moçambique, 2019)
The inclusion of persons with disabilities is an essential element of a strong democracy and a just society. Persons with disabilities (PWDs) being included means that they have a full and equal opportunity to participate in society and in political decision-making processes, to develop their capacities, and to contribute to national progress Like everywhere, persons with disabilities in Mozambique face physical, social, economic and/or environmental barriers to participation. For example, 17 percent of persons with disabilities in Mozambique have been refused entry into a school or preschool because of their disability. Prior to its ratification of the International Convention on the Rights of People with Disability (ICCPD), which protects and promotes the rights and dignity of persons with disabilities, Mozambique had already pioneered progressive measures to promote the inclusion of persons with disability through specific principles in the Constitution of the Republic and the development of multisectoral plans on disability. Furthermore, the Mozambican Government proposed a new set of commitments that were presented at the London Summit in July 2018, reaffirming its adherence to the International Convention on the Rights of People with Disability. The Mozambican Minister for Gender, Children and Social Action, Her Excellency Cidália Manuel Chaúque Oliveira, today spoke at an event on 18th December to launch the study, ‘Towards Social, Economic and Inclusive Policies for People with Disability in Mozambique.’ The study is the result of consultations with people with disabilities of different types and other stakeholders working to promote the rights of persons with disabilities (PWDs) in the Nampula, Beira and Maputo regions of Mozambique. The consulations aimed to find out about the socio-economic and political situations of PWDs and the barriers they face, as well as propose solutions to those problems. The consultation is part of the effort to establish a National Agenda for greater social, economic and political inclusion of PWDs in Mozambique. The study identifies the opportunities for, progress made, obstacles to, and consensus on national policies and strategies. It articulates a ways forward for building an inclusive society and achieving social justice. The study contibutes to Mozambique’s efforts work effectively towards national and international commitments to inclusive development. The study was undertaken as part of the Commonwealth Partnership for Democracy (CP4D) programme. It was carried out by WFD Mozambique in partnership with the Mozambican Association of People with Disability (ADEMO), the Mozambican Forum of Associations for People with Disability (FAMOD), and the Assembly of the Republic of Mozambique, in collaboration with the Ministry of Gender, Children and Social Action and with the technical advice of the Centre for Human Rights of the University of Pretoria in South Africa.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Conferência Internacional Sobre a Educação da Rapariga - ROSC (ROSC - Fórum da Sociedade Civil para os Direitos da Criança, 2019)
O Movimento de Educação para Todos (MEPT) em coordenação com o Ministério da Educação e Desenvolvimento Humano (MINEDH), realizou nos dias 6 e 7 de Junho do corrente ano, em Maputo, a Conferência Internacional Sobre a Educação da Rapariga com o lema “Desafios, Partilha de Experiências e Boas Práticas para Assegurar a Retenção da Rapariga no Sistema de Ensino.” Esta conferência tinha como objetivos: → Troca de experiências em torno de políticas e práticas existentes a nível nacional e internacional para assegurar a retenção da rapariga no sistema de ensino e discutir estratégias e possíveis soluções para a redução dos índices de abandono escolar por parte das raparigas na África Subsariana; → Apreciar os instrumentos e experiências existentes para prevenir a gravidez infantil e combater a violência baseada no género nas escolas a nível da região; → Olhar para os instrumentos e experiências existentes de boas práticas na região para o tratamento de casos de alunas grávidas nas escolas e a sua reintegração.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género

Final Evaluation Report - “Improving oversight in Mozambique's governance” (2016-2019) - FCG International Ltd (FCG International Ltd, 2019)
An external evaluation of the project was conducted in April - May 2019. It looked into the strategy, performance and attainment of the general development goals. The results of the evaluation will be taken into account in the planning of a possible second phase of the project. According to the evaluation, the project is highly relevant both for the strategic partnership between Finland and Mozambique, as well as for the sustainability and inclusiveness of the economic growth arising from the extractive industries and the development of democratic governance. Finnish discretionary government transfers are used to support the Improving Oversight in Mozambique’s Governance 2016–2019 project, which aims to strengthen parliamentary oversight of the management of natural resources in Mozambique. It is a joint project of three organisations; Netherlands Institute for Multiparty Democracy (NIMD), Political Parties of Finland for Democracy (Demo Finland) and Instituto para Democracia Multipartidária from Mozambique (IMD). The project was launched in Mozambique in 2017 and it will be closed at the end of 2019; with a budget of EUR 1,500,000. The evaluation emphasises that strengthening parliamentary oversight is a long-term objective. The project has managed to reach preliminary results in a short time frame in that, for example, Members of Parliament have a better understanding of the challenges met by the extractive industries, and for the first time in Mozambique, there is regular exchange of information and cooperation between national and provincial parliaments. However, performance is not on a sustainable foundation. Sustainable impacts require that a greater number of MPs are trained and the training and research centre of Parliament and the technical secretariats of the provincial parliaments are strengthened. In addition to capacity building, the Parliament should be strengthened by creating wider partnerships and networks with other actors in society. In order to consolidate the results of the project and to improve their sustainability, the evaluation strongly recommends the Ministry for Foreign Affairs to continue the project in cooperation with the new Parliament, which will be elected in October 2019, and with provincial parliaments. It would be useful for the new MPs starting their work at the beginning of 2020 that they make use of the materials produced during the project and consult the MPs who were trained during the project. Additionally, the evaluation recommends the Ministry for Foreign Affairs to continue the project with the same partners, because they have managed to establish well-functioning and confidential relations with the Parliament and other political actors.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; decentralization / descentralização; governance / governação

Tanzaniano recruta jovens no Niassa para ataques em Cabo Delgado - Governo de Moçambique (Governo de Moçambique, 2019)
Alguns jovens do distrito de Mecula, no Niassa, norte de Moçambique, são recrutados para integrarem o grupo de malfeitores que protagonizam ataques armados nos distritos do norte da vizinha província de Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Niassa; L - portuguese / português; youth / juventude

Powering the state: The political geographies of electrification in Mozambique - Power, Marcus; Kirshner, Joshua (Environment and Planning C: Politics and Space, 2019)
This paper explores the role of electricity infrastructures in helping to create, expand or limit the contours of the state in post-colonial Mozambique. Through a focus on recent electrification campaigns and attempts to improve sustainable energy access, we argue that the extension of electricity infrastructures helps to counter the state’s ‘blindness’ and to provide a more permanent visibility for the state whilst potentially enhancing its capacity to order, arrange and ‘read’ its territory and citizenry (particularly in contested rural peripheries). We argue that the material and symbolic work of large-scale infrastructural works around rural electrification and grid extension constitute an important means through which the state performs and narrates its presence and role in order to gain meaning and importance in the lives of rural residents and to forge connections with them. Aside from extending the power and reach of state institutions and their territorial authority, we contend that the development of electricity infrastructures also helps to create neoliberal subjectivities and advance neoliberalisation whilst creating lucrative opportunities for elite accumulation. We examine the different forms of institutional, material and discursive power that influence why some ways of organising energy are privileged over others and reflect on the resulting implications for energy access inequalities and state–citizen relations.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Input subsidies in Mozambique: The future of peasant farmers and their seed systems - Lewis, Linzi (African Centre for Biodiversity, 2019)
In this paper, we discuss and assess the input subsidy programmes in Mozambique, as part of the larger agriculture policy landscape, the impact this has had on the agricultural sector in Mozambique, and particularly on smallholder farmers. Input subsidy programmes in Mozambique are fragmented and operate more along the lines of projects and pilots. Therefore, this paper selects a few key projects to explore approaches being taken by the Mozambican government, along with international donors, providing agricultural inputs to peasant farmers. Notably we consider the more recent Food and Agriculture Organization (FAO)’s input subsidy programme, and the World Bank funded Agriculture and Natural Resources Landscape Management (SUSTENTA) programme/project, implemented by the National Sustainable Development Fund2 (FNDS), under the Ministry of Land, Environment and Rural Development (MITADER). This paper provides a brief background to agriculture in Mozambique, followed by the agricultural policies, plans and budgets guiding agricultural investments in the country. After briefly outlining the agricultural sector – notably seed, fertiliser and agro-dealers in the country – we discuss and analyse selected input subsidy programmes in Mozambique. The paper closes with a conclusion and recommendations to feed into future discussions with farmers, farmer organisations, non-governmental organisations (NGOs) and others in Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Subsídios em insumos em Moçambique: O futuro dos agricultores camponeses e dos seus sistemas de sementes - Lewis, Linzi (African Centre for Biodiversity, 2019)
Neste artigo, discutimos e avaliamos os programas de subsídios em insumos em Moçambique, como parte do panorama mais amplo da política agrícola, o impacto que estes têm tido no sector agrícola em Moçambique e particularmente nos pequenos agricultores. Os programas de subsídios em Moçambique são fragmentados e operam mais ao logo das linhas de projectos e pilotos. Este artigo selecciona, portanto, alguns dos projectos principais para explorar abordagens que estão a ser usadas pelo governo Moçambicano, juntamente com doadores internacionais, para fornecer insumos agrícolas aos produtores camponeses. Notavelmente consideramos o programa de subsídios em insumos mais recente da FAO (Organização para Alimentação e Agricultura), e o projecto/ Programa Agrícola e de Gestão de Paisagens de Recursos Naturais (SUSTENTA) financiado pelo Banco Mundial, implementado pelo Fundo Nacional de Desenvolvimento Sustentável (FNDS), debaixo do Ministério da Terra, Ambiente e Desenvolvimento Rural (MITADER). Este ensaio oferece um breve histórico da agricultura em Moçambique, seguido por políticas, planos e orçamentos agrícolas que guiam os investimentos agrícolas no país. Após brevemente esboçar o sector agrícola – nomeadamente os vendedores de sementes, de fertilizantes e de agroinsumos no país – – discutimos e analisamos programas seleccionados de subsídios em insumos em Moçambique. O artigo encerra com uma conclusão e com recomendações para contribuir para discussões futuras com agricultores, organizações de agricultores, organizações não-governamentais (ONGs) e outros em Moçambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; agriculture / agricultura

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Resultados Definitivos: Censo 2017 - Instituto Nacional de Estatística - INE (2019)
O Censo foi realizado em todo o País de 1 a 15 de Agosto de 2017.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Welcoming two decades of decentralization in Indonesia: a regional development perspective - Talitha, Tessa; Firman, Tommy; Hudalah, Delik (Territory, Politics, Governance, 2019)
Since the start of the reform in the late 1990s, Indonesia has implemented an ambitious decentralization policy. One of its aims is to foster regional development from below by giving subnational governments a greater discretion in determining programmes that are more aspirational to the interests of the community and to local and regional development objectives. The decentralized government system has been implemented for almost two decades, yet limited studies have been conducted to examine its trajectory. Within this context, the study offers a comprehensive review of two crucial issues in the empirical literature on decentralization, notably regional disparity and spatial fragmentation. It is found that the rapid transition toward a decentralized system during the early years of the decentralization reform had an adverse impact on regional development. However, after several adjustments and improvements throughout the process, the decentralization practice in Indonesia began to show positive outcomes, which was signified by a declining trend of regional disparity and spatial fragmentation. It is argued that institutional rearrangement has become a crucial aspect in resolving the regional issues and, thus, improving regional development.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização

Inequalities in Maternal and Child Health in Mozambique: A Historical Overview - Chavane, Leonardo António; Gonçalves, Célia Maria de Deus (IDS, 2019)
Inequity in access and utilisation of health-care services contribute to bad health outcomes, particularly among high risk groups such women and children. Since the declaration of independence in Mozambique in 1975, the newly formed government established, as a priority, maternal and child health (MCH) and the fight against the inequity between the rural and urban areas of residence. In the following years, Mozambique witnessed the improvement of access to and utilisation of the MCH services throughout the country. With the aim to examine the degree of inequity on MCH access, utilisation and outcomes across the country and among different determinants, we conducted a desk review, founded mainly on nationwide surveys such as Demographic and Health Surveys, the Multi-indicator Cluster Survey and the Aids and Malaria Indicators Survey in addition to evidence from articles published in peer reviewed journals, Ministry of Health data bases and reports, International Agencies Reports and other grey literature. We conclude that there are signs of inequity reduction in the MCH health indicators. Areas requiring further investment include the need to reduce the geographical differences to access and utilisation of health services, and the need to continue investing in women’s education as key to improving the health of mothers and children.
Keywords: G - Mozambique / Moçambique; L - english / inglês

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

IV Recenseamento Geral Da População E Habitação 2017: Resultados Definitivos - INE (Instituto Nacional de Estatística, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Como é do conhecimento geral, o Censo 2017 tinha por objectivo estabelecer o conhecimento estatístico, quantitativo e qualitativo, tão exacto quanto possível, da população moçambicana e de todos os demais residentes e presentes no território nacional, bem como do parque habitacional (Lei do Recenseamento, n.º 4/79 de 19 de Maio). O Censo 2017 foi realizado em todo o território nacional de 1 a 15 de Agosto de 2017. Os resultados disponibilizados através da presente publicação referem-se a 1 de Agosto desse ano (momento censitário, ou seja, referência temporal à qual a informação recolhida durante o recenseamento é relativa).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 - INS; ICF (INS/Mozambique, INE, PNCM, ICF, 2019)
O presente relatório resume os resultados do Inquérito Nacional sobre Indicadores de Malária em Moçambique, conduzido pelo Instituto Nacional de Saúde (INS), em colaboração com o Programa Nacional de Controlo da Malária (PNCM) e o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através The Demographic and Health Surveys (DHS) Program. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos Contra a Malária (PMI) e o Fundo das Nações Unidas para a Infância (UNICEF).
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Sah, Anjali; Le, Ha (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies (IDS)-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to US$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

One-stop service policy as a bureaucratic reform in Indonesia - Umar, Akmal; Madani, Muhlis; Amrin; Farida, Umi; Yusriadi, Yusriadi; Elpisah; Bin Tahir, Saidna; Sakkir, Geminastiti (Academy of Strategic Management Journal, 2019)
Bureaucratic reform is an effort to improve the system of government administration, especially institutional aspects, management, and human resources of the apparatus. One of the bureaucratic reforms in Indonesia is the establishment of the One-Stop Service (OSS) office which handles and integrates all forms of licensing. This article examined how the implementation of public service reform and how the change of management practices had been implemented in the OSS of Bone Regency. Data were collected through a semi-structured interview with 16 of OSS' employees and nine service-users. This study applied a qualitative approach using a case study design. Techniques of data collection used three kinds of
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Cyclones Idai and Kenneth - OCHA (United Nations Office for the Coordination of Humanitarian Affairs, 2019)
In March and April 2019, Southern Africa was hit by two subsequent cyclones that left a trail of destruction in their path, and close to 2.2 million people in need urgent assistance in Mozambique alone. On the night of 14 to 15 March Tropical Cyclone Idai made landfall near Beira City, Sofala Province, in central Mozambique. The cyclone brought torrential rains and winds to Sofala, Zambezia, Manica and Inhambane provinces. Cyclone Idai continued across land as a Tropical Storm and hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. Idai left more than 600 people dead and an estimated 1.85 million people in need in Mozambique alone. On 24 April, Tropical Cyclone Kenneth passed north of the Comoros Islands, hitting the northern island of Ngazidja. On the evening of 25 April, the cyclone made landfall in Mozambique between the districts of Macomia and Mocimboa da Praia in Cabo Delgado province. With wind gusts of up to 220km/h, Tropical Cyclone Kenneth became the strongest cyclone to ever hit the African continent. Cyclone Kenneth left 374,000 people in need. Tropical Cyclone Kenneth reportedly caused three deaths, at least 20 injuries and extensive damage to houses across the archipelago. Preliminary estimates indicate that at least 1,000 people were displaced, most of them children. While assessments are ongoing, initial reports from the Comoros indicate that several villages were flooded due to sea surges and broken dykes, and that power was cut in multiple locations. Roads have reportedly been damaged and cut off by fallen trees, while telephone poles are down in multiple locations. Latest updates on the response can be found here. It is the first time in recorded history that two strong tropical cyclones have hit Mozambique in the same season. Cyclone Idai As of 9 April, the official death toll caused by Cyclone Idai stands at 602 people, with more than 1,600 people injured, according to the Government. Many people are displaced, and communicable diseases are on the rise. Of particular concern are cholera and malaria. An oral vaccination campaign reached over 800,000 people by early April 2018. Many schools are damaged or used as shelter for displaced people. Humanitarian partners continue to call for any relocations out of schools or elsewhere to be safe, dignified and voluntary. In figures People in need 1.85M People targeted 1.72M Funding needed $282M   Cyclone Kenneth The cyclone hit Mozambique more north than Cyclone Idai, with Quissanga, Macomia, and Ibo districts in Cabo Delgado hardest-hit, according to preliminary government reports. At least 45 deaths have been reported and 18,029 people were initially reportedly displaced, according to the National Disaster Management Institute (INGC). Cyclone Kenneth made landfall at the end of the rainy season, when river levels were already high, increasing the risk of river flooding. Humanitarian needs in Mozambique have sky-rocketed, and the humanitarian response will need to rapidly scale-up while capacity and funding are limited. In figures People in need 374K People targeted 374K Funding needed $104M     On 16 March, Cyclone Idai hit eastern Zimbabwe with heavy rains and strong winds. The storm caused high winds and heavy precipitation in Chimanimani and Chipinge districts causing riverine and flash flooding and subsequent deaths, destruction of livelihoods and properties. The homes of at least 4,000 households are destroyed or currently uninhabitable. The seven districts affected by Cyclone Idai- Chipinge, Chimanimani, Buhera, Bikita, Mutare, Gutu, and Chiredzi - multisectoral support will be required to speed recovery. The livelihoods of over 270,000 people across these districts has been affected. Those lviing in Chipinge and Chimanimani districts are worst hit. In early March, heavy rains and flooding linked to Cyclone Idai killed 60 people, displaced nearly 87,000 people and affected nearly 870,000 persons. The Government of Malawi declared a ‘state of disaster’ on 8 March and subsequently launched a Flood Response Plan and Appeal on 28 March to support life-saving humanitarian interventions in 15 affected districts. Humanitarian partners and the Government of Malawi have reached over 400,000 persons with immediate life-saving relief support which includes food, medicine, shelter, protection services and other non-food-items such as water, sanitation and hygiene supplies. A Post Disaster Needs Assessment (PDNA) has been undertaken by the Malawi Government, UN, World Bank and European Union to assess damages, losses and priority recovery needs and costs. The data and information collected will inform the Government’s recovery plan.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; climate change / mudanças climáticas; natural disasters / desastres naturais

Impacto Dos Conflitos Armados Na Vida Das Mulheres e Raparigas Em Moçambique: Relatório Da Pesquisa De Campo Nas Províncias De Nampula, Zambézia, Sofala E Gaza - Lawyers Without Borders (Lowyers Without Borders, 2019)
O presente estudo pretende entender como a violência político-militar no país afectou as mulheres e as raparigas e que medidas foram tomadas de forma a apoiar as mulheres víctimas da violência. O estudo visa trazer à luz os diferentes tipos de violações de direitos humanos e de violência cometidos contra as mulheres e raparigas no contexto dos conflitos armados considerando que, e segundo Moura, Silva et all (2012) “A inexistência de dados, estudos e análises sobre violências (directas) contra mulheres e jovens do sexo feminino na Guiné-Bissau, Angola e em Moçambique, torna difícil a tarefa de traçar com precisão uma tipologia das violências cometidas contra estes grupos, ou aferir a sua evolução no pós-conflito armados”. Em termos de actores, o estudo privilegiou, entre outros aspectos, a análise dos principais perpetradores e as suas motivações, entre outros aspectos como forma de definir o perfil das víctimas do conflito armado usando critérios como a faixa etária, o gênero, grau de escolaridade, estado civil, filhos e perfil social e económico. Por outro lado, e considerando o papel da mulher como um factor importante na sociedade, o estudo analisou igualmente a participação directa ou indirecta das mulheres no conflito armado moçambicano cuja maior tónica incidiu sobre a guerra dos 16 anos. No final, o estudo identificou propostas de medidas de reparação – de carácter individual e colectivo derivados das consequências dos conflitos armados na vida de mulheres e raparigas em Moçambique a partir da escuta das reivindicações das próprias víctimas.
Keywords: G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Gaza; GP - Nampula; GP - Sofala; GP - Zambézia; L - portuguese / português; conflict / conflito; gender / género

Hiring of Foreigners in Mozambique - Regulatory Regimes and Practices - JICA (Agency for Promotion of Investment and Exports (APIEX), 2019)
The laws and regulations for hiring foreign nationals have been enacted with the aim of protecting the national workforce, ensuring the availability of jobs for them, while limiting employment of foreigners to those positions with levels of technical and professional skills and qualifications which are either nonexistent or insufficient in the country. Historically, the main instrument used by the Mozambican Government to achieve foreign investment promotion balanced with national employment, was the hiring of foreign employees through the quota mechanism, which is still in use at present. In the present context, it is fundamental that the regime of hiring foreign labour allows for certain flexibility but at the same time does not compromise the structural principle of protecting the local labour force. This document is prepared to provide the current regulatory framework for hiring of foreign nationals, as a reference mainly for foreign investors considering employing foreigners in their projects in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; employment / emprego

Sound of One Hand Clapping: Information Disclosure for Social and Political Action for Accountability in Extractive Governance in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (IDS, 2019)
Corruption through opaque public contracts costs Africa billions of dollars in revenue loss annually. Globally, initiatives to address this have centred on information disclosure (ID) but under what conditions does it work to promote accountability in the extractive sector that for a long time has seen its revenue management as being a major cause of conflict in Africa? Our study on this issue in Mozambique reveals intriguing findings, which suggest that protagonists of ID would need to recalibrate their strategies for promoting accountability. The study on ID in extractive governance in Mozambique has found 17 factors that connect to result in citizen and institutional inaction in demanding government accountability. The lessons from the study for policy and practice are that unless there is a link between ID and a government’s reputation, which scales up to the risk of a ruling government losing power, accountability is unlikely to occur when new information is disclosed.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; corruption / corrupção; decentralization / descentralização; extractive industries / indústrias extractivas; natural resources / recursos naturais

Recent evidence of the development of micro, small and medium enterprises in Indonesia - Tambunan, Tulus (Journal of Global Entrepreneurship Research, 2019)
This paper examines the development of micro, small and medium enterprises (MSMEs) in Indonesia. It has three research issues, namely the role of MSMEs, their constraints, and the importance of MSMEs for the creation of business opportunities for women. More specifically, the study aims to answer the following research questions. First, how important are MSMEs in Indonesia? Second, what are their main constraints? Third, how important are they, especially micro and small enterprises (MSEs), for the creation of business opportunities for women? Fourth, is the growth of MSEs a sign of increased entrepreneurial spirit or a reflection of poverty? This study adopted descriptive analysis using secondary data. It shows that MSMEs in Indonesia are dominated by MSEs, and accounted for almost 100% of all existing firms but only contributed between 58 to 61% of gross domestic product (GDP). About 42.84% of MSEs are owned by women, although the ratio of female to male entrepreneurs in MSEs varies by province. Poverty seems to be the main force behind the growth of MSEs. This study ends with some policy recommendations that the government should: (i) conduct trainings that focus on online marketing, entrepreneurship, management, and improving the quality of product and business efficiency; (ii) provide alternative funding facilities with low interest rates and non-burdensome requirements; and (iii) provide assistance directly in the production site for new entrepreneurs in their first years of running businesses. In addition, all gender discrimination treatments that have been burdensome for women to run own businesses must be eliminated. This study has, however, several limitations, especially with respect to the third and fourth research questions. Secondary data used does not have information about the main/initial motivation of MSME owners to run their own business and their socio-economic profiles.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

The State of ICT in Mozambique 2018 - Gillwald, Alison; Mothobi, Onkokame; Rademan, Broc (RIA Policy Paper, 2019)
Mozambique has a challenging path ahead if it is to realise the full potential of the ICT sector in developing its economy and to make progress on the information communication technology targets that are intended as enabling the achievement of the United Nations’ Sustainable Development Goals. Mozambique’s successes include licensing and regulatory achievements in telecommunications, which have stimulated competition and contributed to meeting national policy objectives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; infrastructure - energy / infrastrutura - energia; infrastructure / infrastrutura

Transition from Civil War to Peace: The Role of the United Nations and International Community in Mozambique - Adedokun, Ayokunu (Peace and Conflict Studies, 2019)
With the heavy involvement of the United Nations (UN) and the international community, the Rome General Peace Agreement of 1992 ended more than 16 years of civil war in Mozambique. The peace agreement and post-conflict initiatives by the international community was successful in transforming the Mozambique National Resistance (Renamo) from a rebel group into a viable political party. Key components of the United Nations and the broader international community success in negotiating peace and creating conditions for political stability and democracy in Mozambique were (a) the provision of disarmament, demobilization and reintegration (DDR) before democratisation, (b) decentralization of humanitarian and relief efforts to provincial and district levels, (c) provision of financial support directly for the development of political parties, and (d) budget support to sectors relevant to peacebuilding. Though imperfect, Mozambique remains an important case study in how the UN and international community can help in post-conflict environments. Thus, the paper argues that success in peacebuilding operations depends on credible and impartial international support through the UN, as opposed to peacebuilding operations through the United States of America or Russia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Midwives’ perspectives on (dis)respectful intrapartum care during facility-based delivery in sub-Saharan Africa: a qualitative systematic review and meta-synthesis - Bradley, Susan; McCourt, Christine; Rayment, Juliet; Parmar, Divya (Reproductive Health, 2019)
Background: In the past decade, the negative impact of disrespectful maternity care on women’s utilisation and experiences of facility-based delivery has been well documented. Less is known about midwives’ perspectives on these labour ward dynamics. Yet efforts to provide care that satisfies women’s psycho-socio-cultural needs rest on midwives’ capacity and willingness to provide it. We performed a systematic review of the emerging literature documenting midwives’ perspectives to explore the broader drivers of (dis)respectful care during facility-based delivery in the sub-Saharan African context. Methods: Seven databases (CINAHL, PsychINFO, PsychArticles, Embase, Global Health, Maternity and Infant Care and PubMed) were systematically searched from 1990 to May 2018. Primary qualitative studies with a substantial focus on the interpersonal aspects of care were eligible if they captured midwives’ voices and perspectives. Study quality was independently assessed by two reviewers and PRISMA guidelines were followed. The results and findings from each study were synthesised using an existing conceptual framework of the drivers of disrespectful care. Results: Eleven papers from six countries were included and six main themes were identified. ‘Power and control’ and ‘Maintaining midwives’ status’ reflected midwives’ focus on the micro-level interactions of the mother-midwife dyad. Meso-level drivers of disrespectful care were: the constraints of the ‘Work environment and resources’; concerns about ‘Midwives’ position in the health systems hierarchy’; and the impact of ‘Midwives’ conceptualisations of respectful maternity care’. An emerging theme outlined the ‘Impact on midwives’ of (dis)respectful care. Conclusion: We used a theoretically informed conceptual framework to move beyond the micro-level and interrogate the social, cultural and historical factors that underpin (dis)respectful care. Controlling women was a key theme, echoing women’s experiences, but midwives paid less attention to the social inequalities that distress women. The synthesis highlighted midwives’ low status in the health system hierarchy, while organisational cultures of blame and a lack of consideration for them as professionals effectively constitute disrespect and abuse of these health workers. Broader, interdisciplinary perspectives on the wider drivers of midwives’ disrespectful attitudes and behaviours are crucial if efforts to improve the maternity care environment - for women and midwives - are to succeed.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; power / poder

Na senda dos tractores: três crónicas para um retrato da cooperação Brasil-Moçambique - Cabral, Lídia (Desafios para Moçambique 2019, 2019)
Na sua última visita a Moçambique, em 2010, enquanto Presidente do Brasil, Lula da Silva destacava os laços fraternais entre o Brasil e Moçambique e o carácter contra-hegemónico do Sul para uma ordem internacional mais equânime, ao mesmo tempo que notava os avanços do investimento privado e os contributos do empresariado brasileiro. Agendas geopolíticas e mercantis fundiam-se em torno de narrativas de libertação, equidade e progresso social, desde o Brasil até à África. Este texto oferece um retrato da cooperação Brasil-Moçambique para o desenvolvimento, partindo desse momento da história e centrando-se especificamente na cooperação técnica e comercial dirigida à mecanização agrícola. Não se trata de uma análise exaustiva da cooperação brasileira em Moçambique, mas sim de uma reflexão sobre a sua trajectória temporal e espacial e os seus desdobramentos a partir de um elemento específico: a venda a crédito bonificado de tractores brasileiros a fim de promover a modernização e o desenvolvimento tecnológico do sector agrícola em Moçambique. O tractor é um excelente gancho para abordar questões de economia política da cooperação e do sector agrícola – questões estas que dizem respeito aos interesses em jogo, ao papel do Estado no sector e à sua articulação com o sector privado, e ao processo de acumulação de terra e riqueza e de reconfiguração do campo.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; south-south cooperation / cooperação sul-sul

Social Cohesion Indicators Bank: illustrative indicators to measure changes in social cohesion - Catholic Relief Services (Catholic Relief Services, 2019)
WHAT IS SOCIAL COHESION? Social cohesion is a concept with various interpretations.2 Some definitions emphasize social harmony and inclusion, human solidarity in diversity, and the inclusive wellbeing of a community or society. Others focus on the social fabric: the abundance of connections and associations in a society, and the presence of linkages and counterbalances that shape the relationship between citizen and the state. CRS views social cohesion as the strength, quality and diversity of relationships between and among individuals, groups and communities, coupled with linkages between society and the state, markets and other institutions, all based on trust, respect, mutuality and equal opportunity, for the dignity and wellbeing of every person and the common good of all.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; society / sociedade

Religion and Use of Institutional Child Delivery Services: Individual and Contextual Pathways in Mozambique - Cau, Boaventura Manuel; Agadjanian, Victor (International perspectives on sexual and reproductive health, 2019)
CONTEXT: Research on institutional child delivery in Sub-Saharan Africa typically focuses on availability and accessibility of health facilities. Cultural factors, including religion, that may facilitate or hinder the use of such services have not been well examined and remain poorly understood. METHODS: The relationship between religious affiliation and delivery in a health facility was explored using data from a household survey of 1,297 women aged 18-50 and a census of 825 religious congregations, both conducted in a predominantly Christian district in Mozambique in 2008. Multilevel logistic regression analyses were conducted to predict the likelihood of recent institutional delivery according to both individual religious affiliation and the concentration of religious congregations of certain denominations in the community of residence. RESULTS: Approximately 63% of deliveries occurred in a health facility. The odds of such deliveries were lower among women who belonged to Apostolic churches or had no religious affiliation than among members of Catholic or mainline Protestant churches, net of other factors (odds ratios, 0.5 and 0.6, respectively). In addition, regardless of a woman's religion, the odds that she had an institutional delivery increased by 9% for each additional Catholic or mainline Protestant congregation in her community of residence (1.1). CONCLUSIONS: Organized religion is associated with critical health outcomes in Mozambique and, potentially, in other Sub-Saharan African contexts. Policymakers should consider designing programs and interventions that promote the use of institutional delivery services among members of religious groups characterized by low use of these services and in areas where such religious groups have a strong presence.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Desafios para Moçambique - 2019 - Chichava, Sérgio (Instituto de Estudos Sociais e Económicos, 2019)
PARTE I – POLÍTICA O dever de pesquisar na periferia do mundo / Michel Cahen Multipartidarismo, geografia do voto e descentralização em Moçambique / Luís de Brito Desafios da descentralização fiscal em Moçambique: o caso dos municípios / Celeste Banze “Grão a grão enche a galinha o papo?” Evidências sobre o Imposto Pessoal Autárquico em 13 cidades moçambicanas / Eduardo Nguenha Identidades étnicas e governação municipal: algumas notas para a reflexão a partir do caso da Beira / Lúcio Posse PARTE II – ECONOMIA Dinâmicas de endividamento público em Moçambique na década 2009-2018: uma análise do contributo do livro Desafios para Moçambique / Yasfir Ibraimo Investimento, recursos naturais e Desafios para Moçambique / Carlos Muianga PARTE III – SOCIEDADE Protecção social nos livros Desafios para Moçambique : reflexão inspirada nos 12 anos de pesquisa do IESE / António Francisco Protecção social e poupança em 10 edições do Desafios: que tipo de protecção social pode Moçambique desenvolver? / Moisés Siúta Natureza demográfica e consequências do crescimento urbano em Moçambique / Rogers Hansine & Carlos Arnaldo PARTE IV – MOÇAMBIQUE NO MUNDO O IESE e a pesquisa sobre “Moçambique no Mundo” (2010-2018) / Sérgio Chichava Panorama, reflexões e desafios do IDE da China em Moçambique no contexto dos BRICS / Michael Sambo Brasil e Moçambique na cooperação Sul-Sul: entre avanços e recuos / Natália N. Fingermann Brasil e Moçambique: construindo a cooperação em defesa / Danilo Marcondes Na senda dos tractores: três crónicas para um retrato da cooperação Brasil-Moçambique / Lídia Cabral
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Conflict at a Crossroads: Northern Mozambique at a Crossroads - Devermont, Judd; Columbo, Emilia (Northern Mozambique at a Crossroads, 2019)
On October 5, 2017, a group of armed men attacked three police stations in Moçimboa da Praia, starting nearly two years of violence and insecurity that still show no sign of ending. Between the first October incident and August 27, 2019, extremists conducted 173 attacks—79 percent of which were committed against civilians—resulting in over 350 deaths, according to the Armed Conflict Location and Event Database (ACLED).1 There is no consensus on the name or construct of the group committing the violence, but for the purposes of this paper, we will refer to the group as Ahlu Sunnah Wa-Jama (ASWJ), which is one of the several names that observers and local communities have ascribed to the militants.2
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; youth / juventude

Independent Report of the Extractive Industries Transparency Initiative - EITI (Extractive Industries Transparency Initiative (EITI), 2019)
This is the ninth report reconciling payments made by companies operating in the extractive industry and receipts from the State. 97% of tax revenues from the extractive industry were reconciled. The differences between the payments by the companies and the receipts from the State correspond to 0,17% of the amounts confirmed by the State in 2019
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources / recursos naturais

Gender Inequality in Employment in Mozambique - Gradín, Carlos; Tarp, Finn (South African Journal of Economics, 2019)
We investigate the gender employment gap in the expanding non-subsistence sector of the economy in Mozambique, a country still characterized by a large subsistence agricultural sector. We show evidence that the gender gap has widened over time and we identify two structural factors strongly associated with it. One factor is the still relatively lower level of female human capital, with less attained education, as well as literacy and Portuguese proficiency rates. The lower conditional employment probabilities of married women, as compared with men, is the other factor. These findings point at expanding women´s education and facilitating the access of married women to the emerging labour market as the most effective ways of achieving a more inclusive growth path that does not leave women behind.
Keywords: G - Mozambique / Moçambique; L - english / inglês

Anuário Estatístico - Statistical Yearbook 2018 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2019)
À semelhança das edições anteriores, o Anuário Estatístico 2018 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

IV Recenseamento geral da população e habitação 2017: resultados definitivos Moçambique - Instituto Nacional de Estatística (INE) (Instituto Nacional de Estatística, Governo de Moçambique, 2019)
O Instituto Nacional de Estatística (INE) apresenta nesta publicação os resultados definitivos do IV Recenseamento Geral da População e Habitação de 2017 (Censo 2017) referentes a Moçambique. Esta publicação encontra-se estruturada em duas partes: • A primeira inclui principais conceitos e definições necessári os para a interpretação dos resultados; • A segunda é composta por quadros que foram definidos como prioritários para as publicações em suporte de papel.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Health equity monitoring is essential in public health: lessons from Mozambique - Llop-Gironés, Alba; Cash-Gibson, Lucinda; Chicumbe, Sergio; Alvarez, Francesc; Zahinos, Ivan; Mazive, Elisio; Benach, Joan (Globalization and Health, 2019)
Background: Countries must be able to describe and monitor their populations health and well-being needs in an attempt to understand and address them. The Sustainable Development Goals (SDGs) have re-emphasized the need to invest in comprehensive health information systems to monitor progress towards health equity; however, knowledge on the capacity of health information systems to be able do this, particularly in low-income countries, remains very limited. As a case study, we aimed to evaluate the current capacity of the national health information systems in Mozambique, and the available indicators to monitor health inequalities, in line with SDG 3 (Good Health and Well Being for All at All Ages). Methods: A data source mapping of the health information system in Mozambique was conducted. We followed the World Health Organization’s methodology of assessing data sources to evaluate the information available for every equity stratifier using a three-point scale: 1 - information is available, 2 - need for more information, and 3 an information gap. Also, for each indicator we estimated the national average inequality score. Results: Eight data sources contain health information to measure and monitor progress towards health equity in line with the 27 SDG3 indicators. Seven indicators bear information with nationally funded data sources, ten with data sources externally funded, and ten indicators either lack information or it does not applicable for the matter of the study. None of the 27 indicators associated with SDG3 can be fully disaggregated by equity stratifiers; they either lack some information (15 indicators) or do not have information at all (nine indicators). The indicators that contain more information are related to maternal and child health. Conclusions: There are important information gaps in Mozambique’s current national health information system which prevents it from being able to comprehensively measure and monitor health equity. Comprehensive national health information systems are an essential public health need. Significant policy and political challenges must also be addressed to ensure effective interventions and action towards health equity in the country.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - health information systems / saúde - sistema de informação de saúde; health - maternal and child / saúde - materno-infantil; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde

The Health Budget: The Disparity Between Political Discourse and Practice - N'weti (N'weti, 2019)
Key Messages: - Health is a human right and is constitutionally protected in Mozambique; - The health sector is considered a priority sector by the Government of Mozambique; - The health sector is amongst the least funded by the State Budget in the past four years, (with less than 8% on average), against the 15% assumed in Abuja; - For the year 2014, of the 762.8 million USD allocated to the health sector, 44% came from external sources (REO MOH, 2014). The combined PROSAUDE resources, and the speci c "off-budget" projects’ funding demonstrates the enormous reliance on external partners to support the country’s health strategy; - There is an urgent need to increase internal State Budget funding for the health sector to ensure sustainability.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; budget / orçamento; health / saúde

Obstacles to advancing women’s health in Mozambique: a qualitative investigation into the perspectives of policy makers - Qiu, Mary; Sawadogo-Lewis, Talata; Ngale, Katia; Cane, Réka Maulide; Magaço, Amilcar; Roberton, Timothy (Global Health Research and Policy, 2019)
Background: Despite substantial investment in women’s health over the past two decades, and enthusiastic government support for MDG 5 and SDG 3, health indicators for women in Mozambique remain among the lowest in the world. Maternal mortality stayed constant from 2003 to 2011, with an MMR of 408; the estimated HIV prevalence for women of 15–24 years is over twice that for men; and only 12.1% of women are estimated to be using modern contraception. This study explores the perspectives of policy makers in the Mozambican health system and affiliates on the challenges that are preventing Mozambique from achieving greater gains in women’s health. Methods: We conducted in-depth interviews with 39 senior- and mid-level policy makers in the Ministry of Health and affiliated institutions (32 women, 7 men). Participants were sampled using a combination of systematic random sampling and snowball sampling. Participants were asked about their experiences formulating and implementing health policies and programs, what is needed to improve women’s health in Mozambique, and the barriers and opportunities to achieving such improvement. Results: Participants unanimously argued that women’s health is already sufficiently prioritized in national health policies and strategies in Mozambique; the problem, rather, is the implementation and execution of existing women’s health policies and programs. Participants raised challenges related to the policy making process itself, including an ever-changing, fragmented decision-making process, lack of long-term perspective, weak evaluation, and misalignment of programs across sectors. The disproportionate influence of donors was also mentioned, with lack of ownership, rapid transitions, and vertical programming limiting the scope for meaningful change. Finally, participants reported a disconnect between policy makers at the national level and realities on the ground, with poor dissemination of strategies, limited district resources, and poor consideration of local cultural contexts. Conclusions: To achieve meaningful gains in women’s health in Mozambique, more focus must be placed on resolving the bottleneck that is the implementation of existing policies. Barriers to implementation exist across multiple health systems components, therefore, solutions to address them must also reach across these multiple components. A holistic approach to strengthening the health system across multiple sectors and at multiple levels is needed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Relatório De Diagnóstico Sobre Transparência, Governação E Corrupção - República de Moçambique (International Monetary Fund (IMF), 2019)
A economia de Moçambique encontra-se num ponto de viragem, e os esforços para abordar as vulnerabilidades em matéria de governação e corrupção podem ter um impacto positivo duradouro. Já tomámos medidas para abordar as vulnerabilidades em matéria de governação e corrupção. Contudo, reconhecemos que subsistem falhas em diversas áreas relevantes da economia. A fim de abordar algumas das debilidades restantes, temos reformas de governação em curso e em perspectiva em várias áreas, muitas delas apoiadas por diversos doadores. Reconhecemos que a implementação eficaz continua a suscitar preocupações. Reconhecemos que a falta de transparência pode igualmente exacerbar as preocupações com a governação e agravar o risco de conflitos de interesse. Embora reconheçamos que temos um papel essencial a cumprir na melhoria da governação e no combate à corrupção, não podemos fazê-lo sozinhos. Estamos preparados e dispostos a tomar medidas concretas.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; corruption / corrupção; transparency / transparência

Impacto das Uniões Prematuras na Educação, Saúde e Nutrição em Moçambique: Resumo do Documento - ROSC (ROSC - F;orum da Sociedade Civil para os Direitos da Criança, 2019)
As uniões prematuras constituem um dos principais problemas sociais na África Austral que, pelas suas consequências negativas em cadeia: gravidez precoce,desnutrição crónica,fístula obstétrica,abandono escolar,se tornam um problema igualmente económico, uma barreira ao desenvolvimento socioeconómico. No caso de Moçambique, o problema afecta cerca de metade das raparigas com menos de 18 anos, o que faz do país um dos cinco mais afectados a nível da Comunidade dos Países da África Austral (SADC). Para fazer face a este problema, várias acções têm sido levadas a cabo, entre campanhas de sensibilização, programas de resgate de meninas em situação de vida marital precoce, lobby e advocacia para o fortalecimento do quadro institucional e legal, bem como estudos para melhor informar as acções referidas. No entanto, quase todas as pesquisas feitas à volta das uniões prematuras têm sido na perspectiva sociológica ou antropológica. Por isso, o Fórum da Sociedade Civil para os Direitos da Criança (ROSC), no âmbito das acções da Coligação para a Eliminação dos Casamentos Prematuros (CECAP), com o apoio da OXFAM, através do Programa AGIR, decidiu realizar este estudo de perspectiva económica, para aferir o impacto que as uniões prematuras têm na educação, saúde e nutrição no país. Este estudo foi elaborado com quatro finalidades: primeira, contribuir para o debate sobre o impacto das uniões prematuras; segunda, elucidar aos actores-chave sobre as consequências das uniões prematuras para o desenvolvimento do país; terceira, despertar a consciência dos tomadores de decisão e da sociedade no geral sobre os impactos negativos das uniões prematuras na educação, saúde e nutrição; quarta e última finalidade, contribuir para despertar a atenção para a necessidade do desenho de programas, políticas e leis que visam mitigar os impactos negativos das uniões prematuras
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; education / educação; gender / género; health / saúde

Representação Comunitária na Gestão de Terras e Recursos Naturais. Nota Técnica - Salomão, Alda; Mário, T. V.; Tanner, Christopher (SPEED+; USAID, 2019)
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; agriculture / agricultura

Protecção social e poupança em 10 edicões dos desafios: que tipo de protecção social pode Moçambique desenvolver? - Siúta, Moisés S. (Desafios para Moçambique 2019, 2019)
Que tipo de protecção social poderá Moçambique desenvolver sem poupança interna e profundamente dependente da poupança externa? Esta é a questão principal que este artigo pretende discutir. A discussão é feita em dois sentidos: mostrar a importância da pesquisa dentro da qual a pergunta surgiu e mostrar a relevância da relação que a mesma estabelece entre a poupança e a protecção social. No primeiro sentido, a relevância da pesquisa é demostrada na abordagem das limitações e deficiências do sistema e formas de protecção social vigentes em Moçambique, destacando-se os elementos que podem contribuir para melhorar o sistema de protecção social moçambicano, abordados dentro do trabalho de pesquisa do IESE. Em geral, os resultados da pesquisa apontam como principal deficiência do sistema de protecção social em Moçambique a sua incapacidade de fornecer protecção digna aos cidadãos, que se socorrem das suas diversas formas (e.g.: demográfica ou financeira) e mecanismos de funcionamento (e.g.: familiar, comunitário, financeiro público e privado). No segundo sentido, a importância da pergunta principal do artigo é fundamentada teórica e empiricamente por meio da identificação das relações existentes entre a protecção social e a poupança e da forma como essas relações se manifestam no caso particular em Moçambique. Por exemplo, o artigo discute o quadro teórico de análise do papel da poupança no crescimento e desenvolvimento económico (figura 1) e a forma como este influencia e determina o tipo, as formas e a qualidade da protecção social que Moçambique pode oferecer aos seus cidadãos. Além do quadro teórico, recorrendo a dados empíricos dos países do mundo inteiro, busca-se enquadrar a economia e o sistema de protecção social moçambicano e estabelecer a relação entre o tipo, as formas e a qualidade da protecção social com o nível de poupança, crescimento e desenvolvimento económico.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; poverty / pobreza; social protection / proteção social; ⛔ No DOI found

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

Informe Orçamental: Acção Social - Moçambique 2019 - UNICEF (UNICEF, 2019)
Em 2019, pela primeira vez na história documentada, dois fortes ciclones tropicais atingiram Moçambique na mesma estação do ano. No dia 14 de Março, o ciclone tropical IDAI atingiu o porto de Beira (afectando 50 distritos em 5 províncias ), e seis semanas mais tarde, o ciclone Kenneth atingiu o norte de Moçambique (afectando 14 distritos em duas províncias). A devastação causada pelos ciclones poderá elevar o número de crianças que necessitam urgentemente de assistência humanitária nas áreas afectadas – em termos de cuidados de saúde, nutrição, protecção, educação, água e saneamento - para aproximadamente 1.5 milhões, em Moçambique. No Orçamento do Estado de 2019, foram alocados ao Sector de Acção Social - compreendido na sua definição restrita como o sector gerido pelo Ministério do Género, Criança e Acção Social (MGCAS) e o Instituto Nacional de Acção Social (INAS) - 6.9 mil milhões de Meticais (mm), o que representa a maior dotação de todos os tempos, tanto em termos nominais quanto reais. O orçamento do sector da Acção Social de 2019 absorve uma participação de 2% de todo o Orçamento do Estado e de 0.7% do Produto Interno Bruto previsto. Apesar do aumento da verba à Acção Social, Moçambique não está em vias de atingir o objectivo da Estratégia Nacional de Segurança Social Básica (ENSSB) de alocar 2.23% do PIB ao sector até 2024. Em termos nominais, os recursos internos alocados à Acção Social no Orçamento de 2019 equivalem a 4.6 mil milhões de Meticais (mm), o que representa um aumento de 7% em relação a 2018. Em termos proporcionais, a relação entre os recursos internos e externos é de 67 a 33 por cento, em 2019. Porém, o maior investimento externo é o crédito do Banco Mundial ao Programa de Assistência Social Directa (PASP); embora isto seja identificado como recursos externos no Orçamento do Estado, o programa PASP é de facto integralmente financiado a nível interno, uma vez que o Governo Moçambicano terá que pagar o empréstimo e os juros correspondentes. A significativa auto-suficiência do sector de Protecção Social indica o compromisso do Governo relativamente ao sector, bem como a sustentabilidade e a apropriação dos programas dos sectores que não dependem de financiamento externo e do propósito dos doadores. Mais de 90 por cento do orçamento do sector foi afectado ao INAS, dos quais a maior parte foi direccionada para as suas delegações, o que é equiparável à participação do ano anterior. Os gastos com o sector da Acção Social são efectivamente bastante descentralizados: a relação entre os recursos centrais e não centrais é de 13 a 87 por cento em 2019. Os programas de protecção social receberam um total de 5.4 mil milhões de Meticais no orçamento de 2019. Isto corresponde a 78 por cento do orçamento do Sector da Acção Social, 1.6 por cento do Orçamento Geral do Estado e 0.5 por cento do PIB. Em 2019, os programas do INAS visaram 609.405 agregados familiares beneficiários. Isto representa um aumento de 7 por cento em relação aos 567.290 agregados familiares beneficiários visados em 2018. Embora a meta de 2019 aumente a cobertura de Protecção Social para aproximadamente 22 por cento dos agregados familiares pobres e vulneráveis, é pouco provável que a meta de 25 por cento do Programa Quinquenal do Governo (PQG) seja cumprida até o final do ano. As dotações per capita para os pobres aumentaram em relação aos anos anteriores, mas ainda não são equitativas em todo o país, o que é motivo de preocupação no actual contexto de espaço orçamental limitado e aumento das desigualdades. Com efeito, embora tenham sido envidados esforços para melhorar o direccionamento dos programas de Protecção Social, as províncias de Niassa, Zambézia e Nampula - que recebem as maiores dotações nominais - recebem a verba mais baixa “porpobre” (i.e., dotação por pessoa considerando apenas pessoas que vivem abaixo do nível nacional definido de pobreza).
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; social action / ação social; social protection / proteção social

State Budget Proposal for Fiscal Year 2019 – Mozambique, Analysis of the Social and Economic Sectors - UNICEF (UNICEF Mozambique, 2019)
Key messages: 1. The envelope of resources for the 2019 State Budget is set to increase to MT 340 billion (from MT 303 billion in 2018), representing Mozambique’s largest nominal budget; however, once factoring in the depreciated currency and high inflation of recent years as well as high debt servicing payments, the purchasing power of this envelope –including for priority sectors– no longer represents a historical high. 2. The share of resources dedicated to investment in Mozambique has been steadily declining, particularly since 2015, due to frozen donor support and a crowding out effect by proportional increases in financial operations and recurrent spending. While in the 2019 Budget Proposal investment has increased to a 30 percent share of total spending, it is still far below the 40 percent norm registered a decade ago. 3. Over the past decade, the share of resources dedicated to the district level has increased at the expense of resources directed to the provincial level; meanwhile central-level expenditure has remained unchanged. In the 2019 Budget Proposal, the central level will, as usual, receive the most resources (64 percent), followed by districts (19 percent), provinces (15 percent), and then municipalities (2 percent). 4. Relative to the Government’s Five Year Plan (PQG), “Priority II: Develop Human and Social Capital” (i.e. priority economic and social sectors) is expected to receive the largest share of funding in the 2019 Budget Proposal. 5. The government has set the goal of allocating at least 60 percent of resources to the priority sectors (according to its methodology of excluding financial operations and debt servicing from the denominator); however, because financial operations and debt servicing have soared as a share of total spending, their 60 percent is no longer a reliable benchmark (e.g. priority sector allocations grew 3.5 times in nominal terms from 2009 to 2019 while the entire budget grew 4 times over the same period) . Proportional priority sector spending as a share of the entire budget (including financial operations and debt servicing) has dropped significantly in recent years. In the 2019 Budget Proposal, it is projected at 51 percent of the entire budget. 6. Among Priority Economic and Social Sectors, Water & Public Works, Transport & Communications, and Agriculture & Rural Development more than doubled their proposed allocations for 2019 relative to 2018 initial allocations. The Education, Health, and Social Action Sectors are also expected to receive a larger allocation than in 2018, but the increase will be smaller. The Infrastructure Sector (mainly the roads sub-sector) will be the only one experiencing a cut in allocation relative to the 2018 Budget.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento

Introduction: The Accountability Politics of Reducing Health Inequalities: Learning from Brazil and Mozambique - Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P.; Waisbich, Laura Trajber; Shankland, Alex; Bloom, Gerald; Coelho, Vera Schattan P. (Novos estudos CEBRAP, 2019)
Inequality is a key political issue of our times. It has political consequences, fuelling conflict and raising legitimacy chal‑ lenges for regimes around the world, in democratic and non‑demo‑ cratic settings alike. At the centre of these challenges is the question of accountability: who can be held accountable, on what basis, how and by whom for tackling or failing to tackle which inequalities. In the field of global health, inequality has long been a key issue. A significant body of work — in global health and health systems research — has approached the issue of health inequalities and in‑ equities by highlighting the role of social determinants (Marmot, 2015; Wilkinson; Pickett, 2006; Barreto, 2017). A more recent and less developed stream of work frames them in terms of political de‑ terminants: in other words, seeing them as issues that may be ad‑ dressed through politics as well as policy.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde

Rethinking health accountability in Mozambique: Beyond donors and government? (Institute of Development Studies, 2018)
As I explored in my previous blog, the health sector and provision of health services in Mozambique is an uneven playing field. Since 1980 it has been shaped by a range of donors who have strategically positioned themselves according to their political weight and ability to contribute with ‘commodities’ and financial resources.  Although donors’ contributions […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; health / saúde

Juventude urbana e redes sociais em Moçambique: a participação política dos conectados desamparados - Tsandzana, Dércio (Comunicação e Sociedade, 2018)
Nos últimos 10 anos, os estudos sobre a participação política por intermédio das redes sociais marcam o debate na área dos estudos dos média. Em Moçambique, de forma particular, e no mundo, de forma geral, a juventude representa o centro galvanizador que encontra no uso das redes socias uma ferramenta quase ideal de expressão sobre as suas frustrações decorrentes da sua situação de gritante miséria social – desemprego e incerteza de vida constante a que os jovens se encontram expostos. Com o presente artigo, pretendemos analisar o papel das redes sociais, concretamente o Facebook, no engajamento político e social da juventude urbana em Moçambique, considerando um horizonte que abarca os últimos quatro anos, 2014-2017. Como resultado, concluímos que embora a sua expansão nos últimos anos, as redes sociais ainda não podem ser consideradas, no seu todo, como espaços que permitam uma efectiva participação política da juventude, decorrente do facto de a internet ser menos abrangente, por um lado, e do fraco interesse da juventude em questões políticas em Moçambique, por outro. EN: In the last 10 years, studies on political participation through social networks have marked the debate in the field of media studies. In Mozambique, particularly, and in the world, in general, youth represent the galvanizing centre that finds in the use of social networks an almost ideal tool of expression about their frustrations due to their situation of blatant social misery – unemployment and constant life uncertainty to which youth are exposed. With this article, we intend to analyse the role of social networks, specifically Facebook, in the political and social engagement of urban youth in Mozambique, considering a timeline that covers the last four years, 2014 to 2017. As a result, it is concluded that, despite the expansion of social networks in recent years, they cannot yet be considered as spaces for effective political participation by youth, due to the fact that the internet is less comprehensive, on the one hand, and the weak youth interest in political issues in Mozambique, on the other.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; G - south / sul; GD - Beira; GP - Maputo; GP - Sofala; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

When a health system turns into a Tower of Babel: Mozambique's experience - Namburete, Denise (Institute of Development Studies, 2018)
Likened to the Tower of Babel legend, the Mozambican national health system speaks several languages and pursues a range of different interests, answering to a number of partners and other bilateral and multilateral actors who all have some kind of circumstantial and contextual interest. When the Paris Declaration on Aid Effectiveness was endorsed, Mozambique may […]
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Moçambique - recessão antes do boom: Reflexões sobre picos de investimento e novas fontes de gás - Roe, Alan (2018)
Este artigo surge na sequência de um artigo anterior onde se considerou em termos gerais muitas das questões que Moçambique enfrenta hoje em dia na gestão dos seus novos recursos extractivos. Em primeiro lugar descreve-se o pico de investimento já desencadeado pelas novas descobertas de gás em Moçambique. Depois apresenta-se em resumo alguma da literatura mais recente sobre os efeitos desses picos noutros países e contextos. De seguida analisam-se os principais aspectos dos resultados económicos decepcionantes testemunhados até 2018, e analisase selectivamente algumas das implicações destes resultados nas políticas futuras. O artigo conclui explorando a epidemiologia de um grande pico do investimento público — uma questão que tem relevância para o pico adicional que ainda é esperado. Ao seguir esta sequência de argumento, procura-se igualmente compreender melhor diversas questões fundamentais de política geral que surgem no contexto das grandes descobertas de novos recursos.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Mozambique - bust before boom: Reflections on investment surges and new gas - Roe, Alan R. (WIDER Working Paper Series, 2018)
This paper is a sequel to an earlier paper that looked in broad terms at many of the issues that Mozambique faces today in managing its new extractive resources. The paper first describes the investment surge that has already been prompted by new gas discoveries in Mozambique. It then summarizes some of the more recent literature that has examined the effects of such surges in other country contexts. It next examines the main aspects of the disappointing economic outcomes that have so far been seen through 2018, and selectively analyses some of the implications of these outcomes for future policy. The paper concludes by exploring the epidemiology of a large public investment surge—an issue that has relevance for the further surge that is still anticipated. In following this sequence of argument, the paper also throws light on a number of critical general policy questions that arise in the context of major new resource discovery.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

Understanding Decentralization in Mozambique with a Ziblatt-Mann Framework - Ferrant, Coline (International Relations, 2018)
In this article, Ferrant examines decentralization reforms in Mozambique since 1994, through an analysis of primary and secondary sources, and a framework that draws from the theses of political scientist Daniel Ziblatt and sociologist Michael Mann.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; ⛔ No DOI found

‘Goats eat where they are tied up’: illicit and habitual corruption in Mozambique - Tvedten, Inge; Picardo, Rachi (Review of African Political Economy, 2018)
The article shows that corruption is structural and omnipresent in Mozambican society, eﬀectively legitimising corrupt practices at all levels. Using an anthropological approach, it argues that smallscale corruption has the most immediate eﬀects for the urban and rural poor and is so common that it has become an integrated part of daily life, or ‘habitual’. While most of the poor relate to corruption through tacit acceptance and acts of compliance, its practical implications are most severe for the very poorest, who cannot aﬀord to take part in corrupt exchanges and are excluded from vital social relationships and social services. A few case studies included re: Northern Moz.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; corruption / corrupção; institutions / instituições; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Actualidade Económica de Moçambique: Transitando para um crescimento mais inclusivo (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

Mozambique Economic Update: Shifting to More Inclusive Growth (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

Making Information Disclosure in Extractive Governance Count for Accountability in Mozambique - Awortwi, Nicholas; Nuvunga, Adriano (Partnership for African Social and Governance Research (PASGR), 2018)
A recent study on information disclosure in the extractive sector has found 18 factors that result in citizen and institutional (state and non-state) inaction in demanding government accountability. Conducted by the Partnership for African Social and Governance Research (PASGR) in collaboration with the Centre for Public Integrity (CIP), as part of the Action for Empowerment and Accountability (A4EA) research programme, the study shows that citizens and/or institutions are unlikely to demand government accountability when: • citizens’ are experiencing high levels of economic vulnerability but much of the access to economic opportunities are anchored around state patronage and network; • a single political party has dominated governments for a long period of time and the mode of selection of Parliamentarians is defined by a ‘party list’, and not directly elected by the people; • CSOs have weak citizens’ mobilisation strategies and information disclosure is presented in a written form in a context where adult illiteracy rate is 45%; • there is an institutional culture of ‘submissiveness’ created out of fear of the political regime
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; extractive industries / indústrias extractivas

The Construction Sector in Mozambique - Cruz, António S.; Fernandes, Francisco; Mafambissa, Fausto J.; Pereira, Francisco; Cruz, António S.; Fernandes, Francisco; Mafambissa, Fausto J.; Pereira, Francisco (2018)
Abstract: The construction sector value added in Mozambique grew at an average annual rate of 12.8 per cent in 1993–2015. Investment in the basic infrastructure of health, education, and housing improved families’ and communities’ living conditions. Investment in roads, communications, and office facilities boosted economic activities and reduced transaction costs. Construction value added grew by only 1.1 per cent in 2016. Challenges ahead include enabling a business environment conducive to expanding small and medium companies in the formal sector; reducing production costs and increasing international competitiveness; improving the prioritizing and programming of public investments; and improving training systems and basic public infrastructure quality.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; infrastructure / infrastrutura

What are the prospects for Mozambique to diversify its economy on the back of 'local content'? - Dietsche, Evelyn; Esteves, Ana Maria (WIDER Working Paper Series, 2018)
In recent years, Mozambique has made international headlines for the significant hydrocarbon deposits found offshore. These have increased the country's extractive resource endowments, in addition to its mining and onshore natural gas sector. It is expected that these industries will contribute to economic diversification and social development, not least by means of procuring locally produced goods and services and hiring Mozambicans. A key factor to achieve this is building domestic capital?in people, institutions, and infrastructure.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); ⛔ No DOI found

Islamic Insurgency in Cabo Delgado: Extractive Industry, Youth Revolt and Global Terrorism in Northern Mozambique - Bonate, Liazzat J. K. (The University of the West Indies, St Augustine, 2018)
The violent insurgency in northern Mozambican province of Cabo Delgado, that started in October 2017 and is still ongoing, caught the government of the country and the public by surprise. Although this insurgency remains largely unexplored and little understood, the only study done so far has suggested that it is being carried out by Muslim youth connected to Islamic radicalism, in particular to the Harakat alShabaab of Somalia and its offshoots in Kenya, Tanzania, and as far as DRC.1 Islam has a long history in Mozambique, since probably the eighth century.2 According to the 2017 National Population Census, Muslims account for about 18% of the total population the country and 58% of the Cabo Delgado inhabitants. However, Mozambique had never had any visible Islamist radical political movement before.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; youth / juventude

The Political Economy of Social Protection in Mozambique - Buur, Lars; Salimo, Padil (SSRN Electronic Journal, 2018)
In the view of international donors, multilateral organisations and government officials, social protection in Mozambique benefits from strong government commitment to it. Their argument is that, in contrast to many African countries, the government has demonstrated a level of commitment and support to social protection that is quite unprecedented. This view relies on the fact that more than 90 per cent of the budget allocated to the implementation of social protection programmes comes from the state budget and that, even within the complex context of the financial crisis that has devastated the economy since 2013, social protection has continued to receive special attention from the government in its budget allocations. Based on a political economy analysis, this paper challenges the common narrative of social protection in Mozambique, by arguing that social protection has been used as a means to mobilise resources from international agencies, in order to ensure the political survival of the Frelimo government. The paper argues that government support of social protection emerged as a reaction to the poor performance of poverty-reduction initiatives, becoming also a mechanism to overcome social protests after the 2008 and 2010 riots in Mozambique, which threatened to jeopardise the stability of the regime and its reproduction of power.
Keywords: *indexed; *tagged; Ethnographic Studies; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Social Protection PEA; development partners / parceiros de cooperação; social protection / proteção social

Minas a céu aberto de Moçambique - Munguambe, Arcénio Artur; Mandlate, Clarência Matias (Wutivi University, 2018)
Moçambique é um dos países da África com muitos recursos naturais. O grau de conhecime nto geológico até agora atingido, mostra que todos os recursos minerais considerados apresentam perspectivas favoráveis para a sua exploração. A indústria extrativa é o sector que tem grandes empregadores de mão-de-obra e tem um grande impacto rural podendo constituir grandes focos de desenvolvimento e de combate a pobreza nas áreas onde se encontra inserido. Neste caso, o presente trabalho visa identificar os principais recursos naturais e agrupar em metálicos e não metálicos e as respectivas empresas mineradoras.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Gender Roles, Relationships and Social Equity in Post-Harvest Management in Mozambique - FANRPAN (ood, Agriculture and Natural Resources Policy Analysis Network, 2018)
Key Recommendations: 1. Gender and other general policies in the agricultural sector should be revised to reflect clear priorities for lowering post-harvest losses (PHL). 2. Crop scientists should be trained and crop-specific PHM research infrastructure should be developed so that PHM can be included as a research component for all crops. 3. Academic and research units should be located in the field, close to the farmers, so that researchers and/or university students are closer to the beneficiaries. 4. PHM programs, projects, and activities must include information and technology development and dissemination relevant to the end-users, including women, children, the youth, and poorer farmers. 5. PHL should be reduced by increasing access to carts/wheelbarrows and their respective repair kits and to draught animals, repairing critical sections of rural roads, and increasing farmers’ access to bags/sacks that are not infested and in good condition. 6. Reduce PHL along the value chain from farm to plate by extending innovations to some of the socially perceived “female-roles” of PHM. 7. Development and dissemination of PHM innovations must also be part of policies, strategies, and practices to promote a better workload distribution by increasing male participation in labourdemanding PHM activities culturally assigned to women. 8. Since women in polygamous marriages and single mothers are easier to work with when it comes to promoting investment in PHM improvements due to their decision-making power in the households, they should be given priority in work plans. 9. Prioritize female farmers in PHM capacity-building initiatives, because they are the ones who deal with most of the PHM activities. 10. Local tools manufacturers should benefit from incentives to lower the cost for the development of manufacturing, processing, and packaging equipment to make them accessible to women and the poor.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; gender / género

Power, conflict and natural resources: The Mozambican crisis revisited - Macuane, José Jaime; Buur, Lars; Monjane, Celso Marcos (African Affairs, 2018)
This article explores how the present socio-economic crisis in Mozambique is linked to the prospects of natural resource windfalls for the country. Drawing on the political settlement approach, it explores how the distribution of power both within and outside the ruling elite is structured and consequently how the underlying political processes have been shaped by the expectations of natural resource windfalls. The article argues that the present socio-economic crisis in Mozambique is not due to national resource assets in themselves. Instead, the political and economic downturn in Mozambique should be understood as a manifestation of how the political settlement has been organized and rent mobilization controlled by the ruling elite. To understand how the prospect of rents from natural resource sectors have influenced the political settlement, we have argued that one has to look at the dynamics of power both within and outside the ruling elite and the incentives they create for elites to use the control of power and access to economic benefits to achieve narrow and short-term gains rather than inclusive and longer-term goals.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; extractive industries / indústrias extractivas; natural resources / recursos naturais; power / poder

O processo de empoderamento das raparigas em Marrere - Estudo de caso do Projeto Mwarusi - Eloisa Nair Lopes da Costa (Instituto Universitário de Lisboa, 2018)
Desde o Acordo Geral de Paz, assinado em 1992, Moçambique realizou reformas políticas de intervenção no combate à pobreza. Contudo, em 2006, verificou-se que 54% da população moçambicana ainda se encontrava abaixo da linha de pobreza. Foi então que, Moçambique, em parceria com organizações internacionais iniciou os seus esforços na promoção de programas centrados na igualdade e equidade de género e a sua atuação junto de comunidades mais vulneráveis, tendo em conta particularmente a educação e a saúde. Para estes avanços contribuíram os Objetivos de Desenvolvimento do Milénio e o Plano de Ação para a redução da pobreza absoluta. O estudo de caso desenvolvido nesta dissertação tem como objetivo compreender o modo pelo qual o Projeto Mwarusi, implementado pela Girl Move Foundation, contribui para um empoderamento efetivo das raparigas no bairro de Marrere em Nampula, Moçambique, compreender o seu impacto na comunidade e a sua aplicabilidade a outras comunidades e grupos. Para compreender o Projeto Mwarusi e, em particular, a situação da mulher moçambicana e as políticas de promoção de igualdade, equidade e empoderamento existentes em Moçambique, foi necessário realizar-se uma análise multivariada que nos permitiu obter um conhecimento não só teórico, ao nível das perspetivas em questão, como prático que nos deu a oportunidade de conhecer a comunidade, a sua cultura e as suas tradições. Esta investigação tem, então, como objetivo a análise do Projeto Mwarusi, através de uma observação participante ao longo das sessões do projeto, através da realização de entrevistas semiestruturadas e questionários on-line aplicados a seis guias, a oito mentoras do Projeto Mwarusi, o que nos permitirá avaliar o sucesso e impacto do Projeto Mwarusi e, por último, através do acompanhamento do desenvolvimento do projeto entre 2015 e 2018.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; empowerment / empoderamento; gender / género; youth / juventude

Heroína continua sendo uma das maiores exportações - Hanlon, Joseph (Centro de Integridade Pública (CIP) / Public Integrity Centre, 2018)
O relatório presente baseia-se no artigo de fundo sobre Moçambique escrito para a Iniciativa Global por Joseph Hanlon. Estudos recentes mostram que houve nos últimos tempos mudanças significativas no modo como o comércio da heroina é controlado. Apesar deste negócio ser bem conhecido das embaixadas, só em 1 de Junho de 2010 o Presidente Barack Obama dos EUA designou Mohamed Bachir Suleman (MBS) como um “barão da droga”, declarando ser ilegal para cidadãos e companhias dos EUA, ou quaisquer companhias operando nos EUA, fazerem transacções comerciais ou financeiras, com MBS ou três das suas empresas. Acredita-se que MBS ainda controla uma grande parte do negócio da heroina que passa por Moçambique, mas a importância da sua posição e das famílias a ele ligadas parece ter diminuido. Este artigo divide-se em quatro secções. A primeira descreve aquilo que é conhecido sobre o negócio da heroina em concreto e os movimentos dentro de Moçambique. A segunda secção fala de MBS, o maior negociante de heroina. A terceira é sobre a política nacional e internacional do negócio regulado da heroina em Moçambique. A secção final trata do crescimento recente do negócio paralelo não regulado.
Keywords: G - Mozambique / Moçambique; L - portuguese / português

The Uberization of Mozambique's heroin trade - Hanlon, Joseph (2018)
Mozambique is a significant heroin transit centre and the trade has increased to 40 tonnes or more per year, making it a major export which contributes up to $100 mn per year to the local economy. For 25 years the trade has been controlled by a few local trading families and tightly regulated by senior officials of Frelimo, the ruling party, and has been largely ignored by the international community which wanted to see Mozambique as a model pupil. But the position is changing and Mozambique may be coming under more donor pressure. Meanwhile the global move toward the gig economy and the broader corruption of Mozambican police and civil service makes it easier to organise alternative channels, with local people hired by mobile telephone for specific tasks. Mozambique is part of a complex chain which forms the east African heroin network. Heroin goes from Afghanistan to the Makran coast of Pakistan, and is taken by dhow to northern Mozambique. There, the Mozambican traffickers take it off the dhows and move it more than 3000 km by road to Johannesburg, and from there others ship it to Europe.
Keywords: G - Mozambique / Moçambique; L - english / inglês

Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Decreto n.º 47/2018 - República de Moçambique (Boletim da República, 2018)
Decreto n.º 47/2018: Concernente à revisão dos Programas de Segurança Social Básica, criados pelo Decreto n.º 52/2011, de 12 de Outubro e revoga o Decreto n.º 52/2011, de 12 de Outubro.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; law / direito; social protection / proteção social

Energy Protests in Fragile Settings: The Unruly Politics of Provisions in Egypt, Myanmar, Mozambique, Nigeria, Pakistan, and Zimbabwe, 2007–2017 - Hossain, Naomi; Aremu, Fatai; Buschmann, Andy; Chaimite, Egidio; Gukurume, Simbarashe; Javed, Umair; da Luz (aka Azagaia), Edson; Ojebode, Ayobami; Oosterom, Marjoke; Marston, Olivia; Shankland, Alex; Tadros, Mariz; et al. (IDS, 2018)
How do popular protests about the basics of everyday life, specifically about energy, come about in settings where political authority is fragmented and conflict and repression common? How do state and political actors respond to protests which disrupt social and economic life, and undermine public authority? To what extent do such mass protests, often justified as inherently moral struggles over the basics of everyday life, empower the powerless or hold the powerful to account in such political settings? And how do external actors shape these events? These are the questions addressed in this paper, part of a research project under the UK Aid-funded Action for Empowerment and Accountability (A4EA) programme at the Institute of Development Studies, Sussex. It is a preliminary effort to make sense of a specific category of popular protests, mass protests about the affordability or availability of fuel or energy, seen as among the contentious ‘politics of provisions’, or elite-mass struggles over policies governing the necessities of everyday life. The paper aims to: (a) contribute to theoretical debates about the kinds of social and political action that strengthen accountability and empower the marginalised in fragile and conflict-affected settings; (b) make an empirical contribution to the contentious politics literature with new evidence about the nature of energy-related protests (or ‘fuel riots’) in developing countries, to strengthen the political economy analysis of energy subsidy reforms and austerity programmes, shedding new light specifically on the tendencies of non-democratic regimes to maintain high fuel subsidies; and (c) generate knowledge about how the behaviour and practices of external actors shape how energy protests play out in these fragile political settings, in order to inform policy and practice.
Keywords: G - Mozambique / Moçambique; L - english / inglês

Mozambique Country Strategy Paper 2018 -2022. Supporting Mozambique towards the HIGH5s - Santos, Almeida (African Development Bank, 2018)
The African Development Bank Group’s Country Strategy Paper (CSP) 2018-22 for Mozambique comes at a time when the country adopted its long term development strategy ‘ENDE’ 2015-35. The CSP was prepared on the basis of extensive consultations held with the Government of Mozambique, Development Partners, the private sector and the civil society. The main objective of the ENDE is the improvement of the livelihoods of the population through the structural transformation of the economy, and the expansion and diversification of national production. The strategy is to be implemented through the 5-Year Government Programs (PQGs). The PQG goal for 2015-19 is to increase employment, productivity and competitiveness to improve living conditions of Mozambicans, in an environment of peace, harmony and tranquillity, while consolidating democracy and inclusive participatory governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Representation and Inclusion in School Councils in Mozambique - Taela, Kátia; López Franco, Erika; Alex, Shankland; Maivasse, Catija; Chilengue, Nárcya; Goodfry, Claudino (Institute of Development Studies, 2018)
This study was conducted as part of the Citizen Engagement Programme (Programa Cidadania e Participação (CEP)) in Mozambique – an empowerment and social accountability initiative to improve the quality of education and health services by increasing citizens’ influence on the management of schools and health units, the formulation of education and health policies, and the provision of education and health services. In education, CEP enabled citizen monitoring of services through the community scorecard (Cartão de Pontuação Comunitária (CPC)), focusing on the link between CPC action plans and the work plans of the co-management mechanism in schools – the school councils. CEP has also promoted the channelling of issues beyond the capacity and mandate of schools to higher levels of the national education system. This work identified a need to better understand the role of school councils as a link between the school and the community, and also in escalating important matters to higher levels of management in the education system, beyond that of school authorities. It was in this context that the Institute of Development Studies and the Centre for Learning and Capacity Building for Civil Society, both members of the CEP consortium, proposed to undertake a qualitative study on representation and inclusion in school councils. The primary aim of this study was to widen the knowledge base available to civil society and to government on the factors that contribute to good performance by school councils in building inclusivity and social accountability to improve the quality of education services.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; Important; L - english / inglês; M - ethnography / etnografia; access to services / acesso a serviços; citizenship & participation / cidadania e participação; civil society / sociedade civil; decentralization / descentralização; education / educação; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Comunicado: Conferência “Como está Moçambique?” - Instituto de Estudos Sociais e Económicos (IESE) (Instituto de Estudos Sociais e Económicos (IESE), 2018)
Veja e aceda ao comunicado subscrito pelas organizações da sociedade civil – Observatório do Meio Rural (OMR), Centro de Integridade Pública (CIP), Mecanismo de Apoio à Sociedade Civil (MASC) e Instituto de Estudos Sociais e Económicos (IESE), resultante da conferência “Como está Moçambique?”, que decorreu no dia 16 de Maio último, no Hotel Montebelo Indy, em Maputo. Leia o comunicado aqui.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

Radicalização Islâmica No Norte De Moçambique: O Caso Da Mocímboa Da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (2018)
Contextualização da pesquisa: - No dia 5 de Outubro de 2017, um grupo de homens armados, aparentemente com motivações religiosas, ataca instituições do Estado (postos policiais) na Vila da Mocímboa da Praia; - Rapidamente, o assunto da radicalização islâmica no norte de Moçambique passou a chamar a atenção do Governo, sector privado, sociedade civil, parceiros de cooperação, analistas, comentadores, cidadãos comuns, etc. - Para muita gente, as perguntas comuns eram: De onde vem esse grupo da Mocímboa da Praia? Existe fundamentalismo islâmico em Moçambique? Não são homens da Renamo disfarçados de fundamentalistas islâmicos? - Foi neste contexto que o IESE e o MASC decidiram realizar uma pesquisa exploratória como preparação para uma pesquisa mais aprofundada.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Livelihood Interventions and Biodiversity Conservation in Quirimbas National Park - Chevallier, Romy (South African Institute of International Affairs (SAIIA), 2018)
Coastal livelihood interventions can help communities by providing additional incomes, while protecting and maintaining resources and the environment. The identification and promotion of resilient and diversified livelihood opportunities are crucial to enhance communities’ adaptive capacity to respond to the multiple stresses and shocks in a changing coastal environment. Coastal livelihood opportunities are especially important in their support for biodiversity conservation in and around protected areas. Quirimbas National Park (QNP) in Mozambique has some of the greatest marine biodiversity in the region and is one of the country’s largest and most important protected areas. This policy insight considers the most appropriate livelihood-focused interventions for coastal communities in the QNP, taking account of past and current project experiences. In areas where communities and park officials need additional support, it makes recommendations on how to best enhance initiatives.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; natural resources / recursos naturais

National Action Plan on Women, Peace, and Security (2018-2022) - República de Moçambique / Republic of Mozambique Ministry of Gender, Child and Social Action (2018)
Main plan objectives include legislation re women, peace, security; integrating gender perspectives in all actions re: conflict prevention/management; guarantee participation of women in decision making, structures in peace and security processes; promoting mechanisms to secure increased recruitment, retention, promotion of women in defense, security, justice sectors; reinforce fights against all forms of violence against women/girls in armed and non-armed conflict; expanding efforts for security, physical and mental health and dignity of women and girls; securing rights of women and girl in conflict and post-conflict situations. Plan's main objectives align with the Southern Africa Development Community's Regional Strategy on women, peace, and seucirty (2018-2022).
Keywords: #Policy Document / Documento de Política; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; government policy / politica governamental

Contract farming for improving smallholder incomes: What can we learn from effectiveness studies? - Ton, Giel; Vellema, Wytse; Desiere, Sam; Weituschat, Sophia; D'Haese, Marijke (World Development, 2018)
Contract farming is a sales arrangement between a farmer and a firm, agreed before production begins, which provides the farmer with resources or services. Many governments and donors promote contract farming as part of agricultural development policies. However, there is serious concern whether smaller farmers can benefit from these arrangements. This paper presents the results of a systematic review that analysed the evidence in the literature on income effects for smallholders. The review included all studies with an econometric design to reduce selection bias in effect estimates. The meta-analysis covered 26 empirical instances of contract farming in 13 developing countries. The contracts varied widely, with varying service packages provided by the firm to the farmers. Using truth table analysis, we explored combinations of services associated with relatively high or relatively low income effects. The meta-analysis resulted in an overall pooled average effect size of 38%. However, we show that there are publication and survivor biases. Non-significant effects are systematically underreported. Moreover, all studies assessed the effectiveness of the contractual arrangement when these had already survived the start-up problems. Both sources of bias lead to an overestimation of the average income effect. The findings point to the need for substantial income effects for contract farming arrangements to survive over time. Both firms and farmers face risks; for example, farmers may side-sell products after having received the services from the firm. The most effective contractual arrangements included a price premium, especially when there was no farmers’ organisation to broker the contract between the farmer and the firm. We show that smallholders can benefit from the contractual arrangement. However, the poorest farmers are rarely included; we show that, in 61% of the cases, the contract farmers had significantly larger landholdings or more assets than the average farmers in the region.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture - agricultural markets / agricultura - mercados agrícolos; agriculture / agricultura

Mozambique plantation leaves no land or jobs for villagers - Adler, Nils (New Internationalist, 2018)
In northern Mozambique, villagers were promised jobs to replace land taken for forestry. Five years later, they’re still waiting, discovers Nils Adler.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Inverted State and Citizens’ Roles in the Mozambican Health Sector - Dias, Jose; Tomé, Tassiana (IDS Bulletin, 2018)
This article aims to understand the inversion of roles between the state and citizens, by exploring its historical roots and current implications for processes of social accountability in Mozambique, particularly in the health sector. This is a practice-based reflection grounded in the evidence collected through the implementation of Community Scorecards in the health sector in 13 districts of Mozambique. The evidence has revealed a transfer of responsibilities from local governance institutions and service providers to the communities; diluting the frontiers between the state and citizens’ duties and rights, resulting in the inversion of roles. This inversion results in the minimisation of the state’s performance of its duties and accountability in the health sector to respond to local communities’ needs, allegedly due to the lack of financial resources. It also leads to the overburdening of local communities, who assume the responsibility of meeting their own demands, risking participation fatigue.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; Important; L - english / inglês; Northern PEA; accountability / responsabilização; health / saúde

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Vampires, Jihadists and Structural Violence in Mozambique: Reflections on Violent Manifestations of Local Discontent and their Implications for Peacebuilding - Weimer, Bernhard (2018)
This essay seeks to explain, in a historical perspective, recent violent attacks on local institutions and representatives of the Mozambican state. Case studies are taken from three Mozambican Provinces, to which historical cases are added showing similar patterns and targets of armed attacks. Based on desk research , interviews and the review of anthropological and political economy literature, the main causes of local conflicts – all of which with their specific contexts and narratives – are identified as being threefold: Firstly, the historically entrenched political economy dominated by Frelimo deals with discontent and dissent in an authoritariina and often violent way, or, in the words of the anthropologist Bjørn Bertelsen, with ‘warfare as governance’. Secondly, the Limited Access Order firmly established in Mozambique produces socioeconomic exclusion of local social, economic and political stakeholders and interests, notably when it is linked to the extraction of natural resources. A third factor is a ‘now future’ perspective of Mozambican youth, the demographic majority. Caught in ‘waithood’ (Alcinda Honwana), it is alienated from their local communities and cultures, but not absorbed by the society and economy. This makes particlulary male youth vulnerable to global influences, and promises of peers, sometimes associated with radical religious thought and crime networks. The essay further examines the extent to which N-E part of Mozambique with its enormous investments in a Liquified Natural Gas industry is vulnerable to the influence of militant Islam. The study concludes with suggestions to address the local conflicts, emerging at a time, when the long standing ‘warfare’ between the Frelimo Government and Renamo is being negotiated towards a political settlement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

The Impact Analysis of ASEAN-Japan Comprehensive Economic Partnership (ajcep) for Trade Flow and Economic Growth’s Convergence - Darsono, Tri Arifin; Hakim, Dedi Budiman; Rindayati, Wiwiek (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2018)
Free Trade Area (FTA) between ASEAN and Japan, which is called ASEAN-Japan Comprehensive Economic Partnership (AJCEP), has been established since 2002 as goods and services flow gateway. AJCEP plays an important role to bring the development, economic security, and economic power. It can also boost the economic growth among member of ASEAN-Japan. The objectives of this research were to analyze the factors that can influence the ASEAN-Japan countries import with non-member, to analyze the occurrence of trade creation and trade diversion in trading sector among ASEAN-Japan countries with non-member, and to analyze the occurrence of economic growth's convergence in ASEAN-Japan Comprehensive Economic Partnership (AJCEP) not only among ASEAN-Japan countries, but also with non-member trading partners. The Gravity Model was used to analyze import factors and observing the occurrence of trade creation or trade diversion. The GMM model was used to observe the convergence of economic growth. The research are used Panel data methods with periods 2000 until 2013 in 13 countries.      The research found that the coefficient values in trade creation and trade diversion dummy were 0.92 and 31.41. The positive value in trade creation and trade diversion indicated the occurrence of trade creation in the import flow among ASEAN-Japan countries and non-member trading partners, as well as finding the convergence of economic growth among ASEAN-Japan countries. The convergence level was of 0.0153417 can be interpreted that the velocity to reach steady state condition was 2.00 percent per year with the assumption of ceteris paribus. The duration to reach convergence condition or half life of convergence was about 34 years. The research found the trade creation from AJCEP agreement and the occurrence of economic growth’s convergence. Based on the result, Indonesian government would likely to make relationships among countries member and non-member to invest in real sector that will boost economic growth in Indonesia. Keywords: ASEAN-Japan Comprehensive Economic Partnership, Growth’s convergence, gravity model, GMM model, trade creation, trade diversion.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

New Action Plan for Health Promotion in Cabo Delgado (Mozambique) (2018)
In Cabo Delgado - Mozambique, we are giving support to the Provincial Health Directorate (DPS-CD) in developing an essential tool for the promotion of health in the Province: The Action Plan for Health Promotion.
Keywords: *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; health / saúde

Extractives and economic diversification in Mozambique: will local content do the trick? (Research Brief 2/2018, 2018)
Research Findings - It is unlikely that the extractives sector can any time soon be used to finance visionary transformation strategies aimed at achieving economic diversification. Due to the country’s fiscal situation and delays in developing the offshore natural gas sector, it seems that extractives will not provide additional revenues for at least another decade, if not longer. If the fiscal crisis results in the further deterioration of the provision of public goods and services, the business environment will become worse for the country’s micro, small and medium-sized enterprises. There is the risk that the gap will widen even further between the skills and entrepreneurial capabilities available in the country, and those required by foreign investment projects and their supply chains. Such a prospect does not match well with the expectations that local content policies can provide the silver bullet for diversifying the economy.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector / setor privado

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Elite Bargains and Political Deals Project: Mozambique Case Study - Vines, Alex (UK Government Stabilisation Unit, 2018)
This case study is one of a series commissioned to support the Stabilisation Unit’s (SU) development of an evidence base relating to elite bargains and political deals. The project explores how national and international interventions have and have not been effective in fostering and sustaining political deals and elite bargains; and whether or not these political deals and elite bargains have helped reduce violence, increased local, regional and national stability and contributed to the strengthening of the relevant political settlement. Drawing on the case studies, the SU has developed a series of summary papers that bring together the project’s key findings and will underpin the revision of the existing ‘UK Approach to Stabilisation’ (2014) paper. The project also contributes to the SU’s growing engagement and expertise in this area and provides a comprehensive analytical resource for those inside and outside government
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; decentralization / descentralização; electoral geography / geografia eleitoral

Moçambique Avaliação de Pobreza: Crescimento Forte, Mas Não Partilhado (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; poverty / pobreza

Mozambique Poverty Assessment: Strong But Not Broadly Shared Growth (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; poverty / pobreza

Country Results Brief 2018 - Mozambique - African Development Bank (African Development Bank, 2018)
Over the last decade, Mozambique has been one of the fastest-growing African economies, enjoying average economic growth of about 8% between 2004 and 2015. It received strong support from the international community during the period (for example, in 2014 it received US$2 billion in official development assistance). In parallel, the country has embarked on major reforms — especially fiscal reforms and tax administration — and has opened up to foreign investment, particularly for the exploitation of its natural resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; governance / governação; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; private sector / setor privado

Dinâmicas e dilemas do emprego, trabalho e bem-estar nas agro-indústrias florestais em Niassa - Ali, Rosimina (Emprego e transformação económica e social em Moçambique, 2018)
O artigo argumenta que o tipo de emprego que é gerado nas agro-indústrias florestais em Niassa reflecte o modo de organização produtivo prevalecente, no qual a base de rentabilidade das empresas está assente no pagamento de salários baixos e em condições sociais de trabalho precárias, sendo os trabalhadores responsáveis pela sua própria reprodução social. A reprodução social da força de trabalho, dadas as estruturas produtivas e de acumulação prevalecentes, é garantida pela interdependência de diversificadas formas de trabalho, remuneradas e/ou não remuneradas, quer agrícolas ou não. Nos moldes actuais de organização da produção e do trabalho, o emprego nas plantações florestais é maioritariamente casual, instável e inseguro, e desenvolve-se num contexto de tensões e contradições nas relações sociais produtivas. As precárias condições laborais têm implicações na disponibilidade e no tipo de força de trabalho que é gerada, nas condições da sua reprodução e produtividade bem como na sustentabilidade da estrutura produtiva prevalecente, na medida em que o trabalho é estruturado (e estrutura as) pelas estruturas produtivas. Este artigo está organizado em seis secções. A segunda secção olha para as dinâmicas do trabalho na província do Niassa e nos distritos em análise, com enfoque na ligação entre o trabalho assalariado, a agricultura familiar e a crise económica em Niassa. Segue-se, a terceira secção, que apresenta um breve panorama do desenvolvimento das indústrias florestais em Niassa e sua ligação com a situação do trabalho na província. A quarta secção analisa a organização produtiva do trabalho, os padrões e condições de emprego nas agro-indústrias florestais. Posteriormente, na quinta secção, descreve-se a experiência laboral e explica-se qual tem sido o impacto deste trabalho para o bem-estar dos trabalhadores e suas famílias. Essa experiência explica, em parte, tanto o descontentamento dos trabalhadores com o emprego criado, como as reclamações feitas pelas empresas sobre o trabalho. A sexta secção conclui, reflectindo sobre a necessidade de transformação dos moldes actuais de organização produtiva e do trabalho e avança algumas questões a enfrentar.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

MUVA Urban Youth Survey: A statistical profile of urban youth in Maputo and Beira, Mozambique - Arau, Andres; Bhalla, Garima; Bischler, Jana; Jasper, Paul (MUVA / OPM, 2018)
The MUVA Urban Youth Survey was conducted as part of the research activities for MUVA, a five-year DFID-funded female economic empowerment programme in urban Mozambique. MUVA works toward testing and finding solutions to help women and girls access opportunities to decent work by addressing the constraints they face. The objective of the survey is to obtain a statistical profile of the youth living in the MUVA target areas in Maputo and Beira to help inform policies about female economic empowerment and connected areas such as education, youth employment, family planning, and financial and digital inclusion. The survey covers a variety of thematic areas such as education, employment and economic activities, financial inclusion, fertility and family planning, time use, social norms, social capital, and digital inclusion. The analysis in this report places a focus on the different constraints young women face compared to young men, especially with regards to how this affects their ability to participate in the labour market. This report is the first in a series of publications on this survey. It summarises key findings across all subject areas. Shorter, less technical thematic briefs will be produced as part of the dissemination activities. A technical compendium will be accompanying this report with all relevant statistical/technical information.
Keywords: G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; GD - Beira; GP - Maputo; L - english / inglês; M - survey / inquérito; gender / género; youth / juventude

Mozambique's social protection system: an overview of the Basic Social Subsidy Programme (PSSB), the Direct Social Action Programme (PASD), the Productive Social Action Programme (PASP) and the Social Assistance Services (PAUS) - Arruda, Pedro (International Policy Centre for Inclusive Growth, 2018)
Mozambique has four main social protection responses in place, including a cash transfer programme (the Basic Social Subsidy Programme—PSSB), a food voucher and in-kind transfer programme (Direct Social Action Programme—PASD), a public works programme (Productive Social Action Programme—PASP), and a set of institutional care services for vulnerable adults, elderly people and children without a home (Social Assistance Services—PAUS). We open this brief with an analysis of relevant social protection policies in Mozambique, followed by a description of the institutional set-up of the Mozambican social protection system. The following section discusses the core features of each of the country’s four flagship social policies, assessing the scale of these programmes and how they relate to each other. In the conclusion, we recall previous critiques regarding the excessive amount of categorical criteria mediating eligibility for these Mozambican social protection initiatives. We make the case for expediting the implementation of the recently developed management and information system—e-INAS—in the hope that it will integrate the databases of the flagship social protection initiatives and increase their reach. Most importantly, we question whether the active search for beneficiaries by health workers contributes to the equity of the PASD, and propose impact evaluation studies for the country’s flagship social programmes, which can lead to a rational revamping of the entire social protection system.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Education Service Delivery in Mozambique: A Second Round of the Service Delivery Indicators Survey - Bassi, Marina; Medina, Octavio; Nhampossa, Lúcia (World Bank, 2018)
This report presents the findings of the second round of the Service Delivery Indicators Survey (SDI) in Mozambique. The SDI analyses the performance of the education sector by assessing the quality of service delivery at the school level. SDI has been implemented in nine countries in Africa, including Mozambique in 2014.5 The study includes a set of indicators that measures teachers and principals’ ability and effort, as well as the availability of key inputs and resources that contribute to the functioning of a school. These metrics enable education authorities and schools to identify gaps and track progress over time (and across countries). The analysis is centered around three main questions: what do providers know? (teacher ability), what do providers do? (teacher effort), and what do providers have to work with? (input availability).
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - indicators / indicadores; Northern PEA; education / educação

Desafios para Moçambique - 2018 - Forquilha, Salvador (Instituto de Estudos Sociais e Económicos, 2018)
PARTE I – POLÍTICA Aptos para Alcançar os seus Objectivos? Obstáculos de ordem administrativa à mobilização da receita local nos municípios Moçambicanos / Armin von Schiller, Salvador Forquilha, Saida Bink, Dominique Klawonn, Jonathan Krull, Alina Sennewald, Conrad Steinhilber e Juliane von Boeselager Urbanização, Serviços Públicos e Recursos Fiscais – Os Principais Desafios para as Autarquias Moçambicanas. Uma análise com enfoque às transferências fiscais intergovernamentais / Abdul Ilal e Bernhard Weimer Uma Economia Política da Reforma Eleitoral em Moçambique / Marc De Tollenaere Estudos Eleitorais em África. Desafios teóricos, metodológicos e conceptuais / Zefanias Matsimbe Alfabetismo Político entre Moçambicanos Alfabetizados. Digitalização e erosão da participação política / Ilídio S. Nhantumbo PARTE II – ECONOMIA Teste à Vontade de Consolidação Fiscal Orçamental em Moçambique. O problema da desorçamentação / António Francisco e Ivan Semedo Efeitos Macroeconómicos da Dívida Pública e do Serviço da Dívida. Uma análise empírica de Moçambique / Yasfir Ibraimo Desenvolvimento Industrial em Contexto de Integração Económica Regional. O caso do sector de equipamentos e serviços industriais em Moçambique e na África do Sul / Epifânia Langa e Maria Nkhonjera Geração de Emprego e Bem-estar. Que contradições existem à luz da agro-indústria em Niassa? / Rosimina Ali A Questão da Terra e os Debates sobre Opções de Transformação Agrária e Rural em Moçambique / Carlos Muianga PARTE III – SOCIEDADE Evolução da Pobreza e do Bem-estar em Moçambique, 1996/97-2014/15 / Channing Arndt, Finório Castigo, Maimuna Ibraimo, Sam Jones, Kristi Mahrt, Vincenzo Salvucci, Ricardo Santos e Finn Tarp Vítimas da Riqueza? A reprodução da pobreza em zonas de minerção / Michael Sambo Relações Laborais e Movimentos de Protesto no Sector do Açúcar / Uacitissa Mandumele Desigualdades de Género em Contextos Rurais em Moçambique. Estudos de caso em localidades na província de Nampula / Aleia Rachide Agy PARTE IV – MOÇAMBIQUE NO MUNDO Acordos de Protecção de Investimentos dos BRICS na África: Mais do mesmo? / Ana Garcia, Yasmin Bitencourt e Bárbara Dias A Transferência de Tecnologia do Brasil para Moçambique para a Fabricação Local de Medicamentos Genéricos: Condições históricas e práticas de uma cooperação em saúde e tecnologia / Ali Brossard Antonielli Migração, Movimento e Urbanização em Angola e Moçambique / Cristina Udelsmann Rodrigues Os Homens e as Mulheres pelo Mundo: O factor humano na ajuda ao desenvolvimento em Moçambique / Marc De Tollenaere
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

The Evidence Is In: How Should Youth Employment Programs In Low-Income Countries Be Designed? - Fox, Louise; Kaul, Upaasna (Policy Research Working Papers, 2018)
Youth in many low-income countries are entering the labor force in unprecedented numbers, yet many struggle to secure rewarding livelihoods. This paper outlines the economic development challenges that constrain youth's transition into employment, and it parses the evidence on which programs and policies appear to speed that transition. It concludes that it may be time for a fundamental reassessment of approaches for addressing youth employment and the youth transition in low-income countries. Employment opportunities in low-income countries reflect the pace of economic and structural transformation. In designing strategies, policies, and programs to meet the entry-into-employment challenge for youth, the starting point is to diagnose the economy and current/future employment opportunities. Combined with the analysis of youth employment problems from a structural transformation perspective, evidence from rigorous evaluations of youth employment interventions provides new insight into which kinds of interventions are more likely to help youth succeed in certain contexts. The evidence reviewed here casts serious doubt on the efficacy and value of training interventions to help youth enter formal wage employment. The case is stronger for interventions that speed the transition to self-employment in farming or non-farm household enterprises. Support for development of transferable character skills and social integration among youth through positive youth development programs should be tested further for employment and earnings impacts, perhaps along with cash transfers to youth or access to finance. In reviewing the evidence on the cost-effectiveness and sustainability of youth employment impacts, the paper also notes the need for better measures of displacement and general equilibrium effects.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; employment / emprego; youth / juventude

Elevating Indonesia's Performance in Ease of Doing Business Index (Policy Reforms to Improve the 'Starting a Business' Indicator) - Freddy, Imelda Magdalena; Saputri, N. (2018)
Indonesian President Joko Widodo has set a target of improving the country’s ranking in The World Bank’s Ease of Doing Business (EODB) index from 72nd to 40th by 2019. One barrier to meeting this challenge is Indonesia’s ranking in the Starting a Business Indicator, where it is 144th among 190 countries. According to the EODB Report, it takes 23 days and 11 procedures to register a business in Indonesia. To address this problem, the central government has implemented changes requiring parallel procedures with local governments and introduced a program called the Online Single Submission system (OSS), established in July 2018. However, there are major barriers to the success of these changes, including a lack of information for businesses, inadequate IT infrastructure, and failure to synchronize the central and local governments under the OSS. As a result, policy changes and the OSS have not been working as intended. Case studies in Jakarta, Bandung, and Bandar Lampung revealed that there are two regulations—one implemented by the local government and the other implemented by the central government—that should be revised to speed up business registration. The government should also remove a procedure from the business registration process and develop collaboration with local private sectors and business associations to improve the OSS. These changes would reduce the time required for registering a business by 17 days. These reforms would benefit small and medium businesses the most, since they are the most common types of business in Indonesia (approximately 98% of all businesses). Such a reduction in the time required to register a business would be enough to improve Indonesia’s Starting a Business Indicator ranking from 144th to 75th. Based on our findings, we recommend four policy changes. First, the Jakarta provincial government should revise the Regulation of the Head of Investment and One Stop Integrated Services 23/2017 Article 2d. The Mandatory Labor Affairs Report (MLAR) stipulated in this regulation should be removed as a business registration requirement. Its content is duplicates data provided by the BPJS Ketenagakerjaan documents as part of national social security program. In addition, requiring an MLAR contradicts the regulation of the Minister of Manpower (MOM) 14/2006, which says it is not required for business registration. Second, Government Regulation 24/2018 Article 78 should be reformed to require that the central government collaborate with local business associations to disseminate information about the OSS. This collaboration will ensure that information reaches even remote areas. Third, Government Regulation 24/2018 Article 88 should be reformed to ensure that the ministries related to the OSS assist local governments to synchronize standard operating procedures and regulations to implement the OSS. This assistance should continue for one year, after which there should be a penalty for local governments that fail to comply with the new procedures for registering businesses through the OSS. Fourth, Government Regulation 24/2018 Article 91 should be changed to ensure the government will collaborate with the private sector to improve the IT infrastructure in all regions to support the OSS. Participation by the private sector is important because they have the resources to provide internet access and computers needed to implement the OSS in districts and municipalities across Indonesia.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Empregados do Quintal (male domestic workers) in Nampula City: Domestic work, masculinities and matrilinearity - Humbane, Jossias Helder Jamisse (2018)
This study questions why domestic work that is generally considered a feminine job is yet a field dominated by men in the city of Nampula, Mozambique. In the attempt to explain this phenomenon, the research explores economic, social and cultural aspects. Due to the fact that Nampula is a province with a strong Islamic presence and the majority of the population identify themselves as belonging to the Makhuwa ethnic group—which is traditionally defined by a matrilinear kinship system—I argue that the domestic sector remaines masculinised because of the influence of the matrilinear values and gendered practices. I also argue that the Islamic patriarchal values play a decisive role as men see themselves as the exclusive family providers and for that reason forbid their wives to develop and to get engaged in economic activities outside the household. This study also explores notions of masculinity in connection with domestic work and examines how male domestic workers, coming from rural areas and employed in the city, perceive and perform their masculine identities. How does the job of the domestic worker shape particular understandings of masculinity? Given the fact that many domestic workers in Nampula are immigrant people from the rural areas of the Zambézia province, I argue that migrating and working in the city is considered as a way to achieve a manhood as immigrants have access to goods that can only be purchased in urban contexts and are scarce in the villages. The access to all these “modern” commodities and the experience of the city make the immigrant young boys to gain respect in their original communities.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; employment / emprego; gender / género

Barómetro Municipal 2017. Relatório de dados quantitativos. - IESE (Instituto de Estudos Sociais e Económicos (IESE), 2018)
É o novo relatório de pesquisa produzido por uma equipa de investigadores do Instituto de Estudos Sociais e Económico (IESE), coordenada por Salvador Forquilha, no quadro de um projecto de investigação em curso sobre a avaliação dos munícipes em relação ao desempenho da governação municipal em Moçambique. Este primeiro “Barómetro da Governação Municipal 2017” (BGM) explora dados quantitativos relativos à percepção dos munícipes sobre as diferentes vertentes da actuação dos órgãos e serviços municipais e que podem permitir às autoridades municipais melhor conceberem os seus planos de governação e a responderem de maneira mais eficaz às expectativas dos munícipes. Refira-se que nesta primeira fase do projecto BGM foram abrangidos oito municípios, cobrindo diferentes regiões do país, nomeadamente Beira, Ilha de Moçambique, Lichinga, Manjacaze, Nampula, Pemba, Quelimane e Tete.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; governance / governação

Anuário Estatístico - Statistical Yearbook 2017 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2018)
À semelhança das edições anteriores, o Anuário Estatístico 2017 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Inquérito Nacional Sobre Indicadores de Malária - IIM (National Malaria Indicator Survey - MIS) 2018 Folheto (Brochure) - INS (2018)
O objectivo do IIM 2018 é disponibilizar as estimativas de indicadores demográficos e de saúde básicos, relacionados com a malária. As informações recolhidas através do IIM 2018 destinam-se a ajudar os decisores políticos e gestores do programa de controle de malária na avaliação e concepção de estratégias para melhorar a saúde da população do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Afrobarometer Round 7. Summary of Results for Mozambique, 2018 - Ipsos Mozambique (Ipsos Mozambiqu, 2018)
Afrobarometer is a pan-African, non-partisan research network that conducts public attitude surveys on democracy, governance, economic conditions, and related issues in countries across Africa. Six rounds of surveys were conducted between 1999 and 2015, and Round 7 surveys are being carried out in 2016-2018. Afrobarometer conducts face-toface interviews in the language of the respondent’s choice with nationally representative samples of 1,200 or 2,400 respondents. Afrobarometer is produced collaboratively by social scientists from across Africa. Coordination is provided by the Center for Democratic Development (CDD) in Ghana, the Institute for Justice and Reconciliation (IJR) in South Africa, the Institute for Development Studies (IDS) at the University of Nairobi in Kenya, and the Institute for Empirical Research in Political Economy/School of African Economics (IERPE/ASE) in Benin. Michigan State University (MSU) and the University of Cape Town (UCT) provide technical support to the network.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Navigating in the Midst of Uncertainties: Challenges in Disaster Risk Governance in Mozambique - Koivisto, Jenni (Karlstads universitet, 2018)
Disasters cause heavy losses for societies and may quickly erode any development efforts. Consequently, disaster risk reduction (DRR) is an integral part of development work that should be addressed at multiple levels. Global DRR frameworks, scholars and practitioners all advocate disaster risk governance (DRG) strategies that are multi-stakeholder, polycentric and multisectoral. While various substantive knowledge gaps and questions arising from multiple risks and the crosscutting nature of DRR have been relatively well addressed, uncertainties relating to multiple DRR actors operating and collaborating at different scales have gained less attention in previous studies. This thesis investigates the uncertainties in DRG in Mozambique, a low-income country that regularly faces natural hazards. These hazards often cause heavy loss of life and livelihoods and economic damage. The four articles that together constitute this thesis focus on different sets of uncertainties and factors that have constrained or allowed Mozambique to take major steps in this policy area. By exploring strategic and institutional uncertainties related to stakeholder involvement, coordination and policy disputes, this thesis reveals different challenges and opportunities that affect DRR policymaking in Mozambique. This thesis concludes that Mozambique has managed to take important steps in DRR. However, as a consequence of the different challenges to DRR practice in Mozambique, policymaking can be short-sighted and makes slow progress, thus increasing the disconnect between theory, policies and practice. This thesis thus argues that DRG research and practice need to better take into account power-relations; coordination and capacity issues; and responsibilities and transparency across scales, both in Mozambique and elsewhere.
Keywords: G - Mozambique / Moçambique; L - english / inglês; collaboration / colaboração

Falta de alimentos agrava-se em zonas atacadas na província de Cabo Delgado - Macuácua, Amandio Roberto (Jornal Notícias, 2018)
A falta de alimentos está a agravar-se em zonas do interior na província de Cabo Delgado por causa dos ataques causados por grupos armados que têm levado a população a abandonar terras, alerta um relatório ontem divulgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Mozambique’s private sector in the context of conflict - Macuane, José Jaime (International Growth Centre, 2018)
This case study analyses the interactions between conflict and private sector development in Mozambique. In the 42 years following its independence, Mozambique faced a 16-year civil war from 1976/77 to 1992, an interim period of peace that lasted 20 years, and recurring, low-level conflict involving the same belligerents since 2013. This case study examines the conflict dynamics in post-independence Mozambique, and how the private sector has developed in response to both conflict and peace.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; private sector / setor privado

Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA) 2015 - Ministério da Saúde- MISAU; Instituto Nacional de Estatística - INE; ICF (MISAU/Moçambique, INE, and ICF, 2018)
O presente relatório resume os resultados do Inquérito de Indicadores de Imunização, Malária e HIV/SIDA em Moçambique (IMASIDA 2015), conduzido pelo Instituto Nacional de Saúde (INS) do Ministério da Saúde (MISAU), em colaboração com o Instituto Nacional de Estatística (INE). O inquérito contou com a assistência técnica da ICF, através do Programa de Inquéritos Demográficos e de Saúde (Programa DHS). A assistência técnica adicional foi proporcionada pelo CDC (Centers for Disease Control and Prevention) dos Estados Unidos da América, através do seu escritório em Moçambique. O inquérito foi financiado pela Agência dos Estados Unidos para o Desenvolvimento Internacional (USAID) através dos fundos da Iniciativa do Presidente dos Estados Unidos para o Controlo da Malária (PMI), Fundo Global (FG-Rondas 8 e 9), Organização Mundial de Saúde (OMS), Fundo das Nações Unidas para a Infância (UNICEF), Aliança Internacional para a Saúde/Universidade de Washington (HAI/UW), Fundo das Nações Unidas para a População (FNUAP), Conselho Nacional de Combate ao HIV e SIDA (CNCS), através do seu Fundo Comum e Plano de Emergência do Presidente dos Estados Unidos para o Alívio da SIDA (PEPFAR), através do CDC.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Programa Conjunto das Nações Unidas para a Protecção Social em Moçambique 2017-2020 - Ministério do Género, Criança e Acção Social - Governo de Moçambique (Ministério do Género, Criança e Acção Social - Governo de Moçambique, 2018)
A Protecção Social é amplamente reconhecida como um conjunto efectivo de intervenções políticas para reduzir a pobreza, a vulnerabilidade a desigualdade e promover o crescimento económico inclusivo. Na última década, o sistema de Protecção Social Básica de Moçambique consolidou-se com a Estratégia Nacional de Segurança Social 2010-2014, todavia o sector ainda permanece fragmentado. A Estratégia Nacional de Segurança Social básica 2016-2024 (ENSSB II), que cobre o período de, aprovada pelo Conselho de Ministros em Fevereiro de 2016 oferece uma oportunidade única para abordar a fragmentação e alinhar melhor as partes envolvidas na materialização de um conjunto ambicioso de metas. A Estratégia tem quatro objectivos principais: 1. Incrementar o nível de consumo e resiliência da população que vive em situações de pobreza e vulnerabilidade; 2. Contribuir para o desenvolvimento do capital humano através da melhoria da nutrição, do acesso aos serviços básicos de saúde e educação do segmento da população que vive na pobreza e vulnerabilidade; 3. Prevenir e mitigar os riscos de violência, abuso, exploração, discriminação e exclusão social através dos serviços sociais e, 4. Desenvolver a capacidade institucional dos sectores governamentais que coordenam a segurança social básica. O Programa Conjunto foi estruturado em torno de um pacote coerente de intervenções, incluídas na ENSSB II e totalmente alinhadas ao Plano Operacional, em torno das 38 “Acções Estratégicas”, mas naquelas onde as agências da ONU têm mandato, capacidade de trabalho com parceiros governamentais visando fortalecer ainda mais o quadro de trabalho da Protecção Social. No decorrer do programa (2018-2019), as duas agências da ONU envolvidas (OIT e UNICEF) irão trabalhar com os parceiros a nível nacional, provincial e distrital para alcançar os seguintes resultados: 1. Até 2020, programas e políticas claras concebidos para operacionalizar a ENSSB II 2. Até 2020, evidências sólidas, advocacia e comunicação claras para as componentes principais da ENSSB II 3. Até 2020, o MGCAS tem reforçada a sua capacidade para coordenar e implementar a ENSSB II
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social

How do gender relations affect the working lives of close to community health service providers? Empirical research, a review and conceptual framework - Steege, Rosalind; Taegtmeyer, Miriam; McCollum, Rosalind; Hawkins, Kate; Ormel, Hermen; Kok, Maryse; Rashid, Sabina; Otiso, Lilian; Sidat, Mohsin; Chikaphupha, Kingsley; Datiko, Daniel Gemechu; Ahmed, Rukhsana; et al. (Social Science & Medicine, 2018)
Close-to-community (CTC) providers have been identiﬁed as a key cadre to progress universal health coverage and address inequities in health service provision due to their embedded position within communities. CTC providers both work within, and are subject to, the gender norms at community level but may also have the potential to alter them. This paper synthesises current evidence on gender and CTC providers and the services they deliver.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

The Importance of Lender-borrower Relationships to the Availability of Small and Micro Credit: Case Study on Indonesian Kredit Usaha Rakyat Loans - Suryani, Embun (International Journal of Economics and Financial Issues; Mersin, 2018)
This study aims to examine how the relationships between a borrower and his potential lender affect the decisions of potential lender whether or not to provide or extend funds to the borrower. The author explores the available literature and original fieldwork to create a framework to capture this relationship. The study employs descriptive qualitative data to analyze and examine the research questions. The result shows that borrowers who build their commercial transactions with their lender on intensive relationships are more likely to receive and extend loans. The relationship effects arise because it motivates both lender and borrower to share private resources and facilitate access to loan opportunities, but does not influence the price of loans. To sum up, the lender-borrower relationships are valuable and seem to operate through quantities, trust and the length of these relationships. Furthermore, these relationships are more appropriate to be implemented for small and micro-lending.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

The Performance of Indonesia’s Public Credit Guarantee Scheme for MSMEs: A Regional Comparative Perspective - Tambunan, Tulus T.H. (Journal of Southeast Asian Economies, 2018)
Access to finance has been a key constraint for Indonesia’s micro, small and medium enterprises (MSMEs) that lack tangible assets to be used as collateral. Consequently, credit guarantee schemes (CGSs) are important instruments to meet MSMEs’ financial needs. This paper examines the effectiveness of the KUR (community business credit), a partial public CGS in Indonesia, by comparing it with similar schemes in other ASEAN member states (AMS). The findings suggest that the KUR programme, despite its limited coverage, has been quite effective throughout the country. Some of the critical factors behind its success include: wide dissemination of the programme; simplicity of the application procedure; full participation and support from banks; and strong coordination between all stakeholders.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

An Exploratory Study of Four Urban Community Libraries in Nampula City, Mozambique: Do They Satisfy Community Informational Needs? - Szabo, Elizabeth Eva; Vieira, Ilidia (Libri, 2017)
This exploratory study describes the characteristics of four independent urban community libraries in Nampula city, located in northern Mozambique, East Africa. In a country where public library services are inadequately equipped to address the educational, informational and cultural needs of its citizens, the emergence of urban community libraries in the city indicates that the population is seeking better alternative sources of information. The study profiles four urban libraries to identify their role in the communities they serve and determine whether they conform to Mostert’s (1998) community library model. A case-study design was used with data collection techniques of structured interviews to collect qualitative data from library directors and librarians, a multiple choice questionnaire to obtain user responses, while further statistical data was obtained from collection, circulation and library user records. Findings indicate these four urban libraries only minimally adhere to Mostert’s model and are instead mimicking existing public and school libraries by catering to predominantly secondary and university level students. As a result, the educational, informational and cultural needs of other key groups in the community, such as the illiterate, neo-literate and disadvantaged, are ignored. This is due to a lack of trained library professionals and restrictive library policies.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; access to services / acesso a serviços; education / educação

Cidadania e Mudanças na Saúde e Educação em Moçambique: O Cartão de Pontuação Comunitária - Franco, Erika Lopez; Citizen Engagement Programme (CEP) (2017)
Este documento sumariza as aprendizagens feitas ao longo da implementação do Cartão de Pontuação Comunitária (CPC) no quadro do Programa Cidadania e Participação (CEP), o qual terminou em Dezembro de 2017. O CEP foi um programa de responsabilização social que tinha como objectivo final aumentar a influência dos cidadãos na melhoria da qualidade dos serviços de saúde e educação em Moçambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - portuguese / português; Northern PEA; access to services / acesso a serviços; citizenship & participation / cidadania e participação; community scorecard (CSC) / cartão de pontuação comunitária (CPC); education / educação; health / saúde

Trabalhando com Rádios Comunitárias: Desafios e Lições Aprendidas pelo CEP - Programme, Citizen Engagement (2017)
O programa Cidadania e Participação (CEP) é um programa de responsabilização social que visa melhorar a qualidade dos serviços nas escolas e unidades sanitárias das zonas onde o programa é implementado. A teoria de mudança do CEP sugere que o fortalecimento do envolvimento dos cidadãos na monitoria dos serviços e na governação das unidades de prestação dos mesmos, pode melhorar a qualidade de serviços prestados e, a longo prazo, contribuir para maior bem-estardos cidadãos. O programa teve uma forte componente de aprendizagem e disseminação de informação e experiências. É no âmbito deste mandato de aprendizagem que se elaborou o presente documento que visa sintetizar as aprendizagens do CEP relativas ao trabalho com rádios comunitárias para efeitos de informação, consciencialização e mobilização. A finalidade deste trabalho é de deixar registadas experiências e as lições que podem ser úteis para outros programas de responsabilização social, a nível de base, e não só. As observações, constatações e recomendações aqui apresentadas têm como base os relatórios de trabalho produzidos pelas rádios comunitárias (RC), os relatórios das organizações da sociedade civil (OSC) locais que implementaram o CEP, as diversas actividades de acompanhamento presencial do trabalho das RC por pessoal ligado ao programa, análises internas ao nível das unidades de gestão do programa, e as contribuições das rádios comunitárias recolhidas em três seminários de reflexão organizados pelo CEP em Nampula, Manica e Gaza, entre Agosto e Outubro de 2017. Ao longo do documento mantiveram-se algumas expressões usadas pelas fontes de informação.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; ⛔ No DOI found

Analysis Banking Role to Performance Improvement on Indonesia Small Medium Enterprises - Hedwigis (EUROPEAN RESEARCH STUDIES JOURNAL, 2017)
This study aims to analyze the role of banks to increase small and medium enterprises and economic growth in Yogyakarta province, Indonesia. The focus of this study examines how the role of banks in terms of lending to small and medium enterprises, credit to the private sector and its impact on economic growth in Yogyakarta Province. The data used in this research is secondary data obtained from the Central Bureau of Statistics.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Avaliação Dos Impactos Dos Investimentos Nas Plantações Florestais Da Portucel-Moçambique Nas Tecnologias Agrícolas Das Populações Locais Nos Distritos De Ile E Namarrói, Província Da Zambézia - Sitoe, Almeida (Observatório do Meio Rural, 2017)
O presente estudo é parte integrante do projecto “Efeitos dos grandes projectos sobre o meio rural e a agricultura (Portucel- Moçambique)” realizado pelo Observatório do Meio Rural (OMR). Especificamente, as questões que o presente estudo procura responder são: (i) quais as mudanças que ocorreram em termos de acesso a tecnologias de produção agrícola nos distritos de Ile e Namarrói desde que a Portucel iniciou as suas actividades; e (ii) que impactos houve nos sistemas de produção agrícola em termos de produtividade e rendimento. Para responder às questões colocadas neste estudo, foi realizada uma visita de reconhecimento aos dois distritos, encontros com quadros de direcção e operários da empresa Portucel Moçambique, encontros com os provedores de serviços à Portucel Moçambique, as instituições do Estado e as Comunidades abrangidas pelos projectos de plantações florestais nos distritos de Ile e Namarroi, Província da Zambézia.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; rural development / desenvolvimento rural; ⛔ No DOI found

The political economy of corridors, commercialisation and agrarian change in eastern Africa - Scoones, Ian; Smalley, Rebecca (IESE Conference - Challenges of social and economic research in times of crisis, 2017)
The political economy of agricultural growth corridors: some first thoughts: • Neither state-driven ‘high modernism’ (Scott) nor enclave capitalism (Ferguson), but context-specific hybrid dynamic. • Endogenous capital and dynamics of accumulation crucial: diverting, upsetting , recasting grand plans and investments. • Contested visions of ‘development’ and ‘progress’ being played out, challenging and reconfiguring authority, with tensions and contradictions among elite alliances. • The everyday politics of corridors: contentious local politics (and resistances) intersect with wider corridor politics, influencing outcomes. • Who wins and who loses depends on terms of incorporation, predicated on both contemporary politics, but also long-run historical antecedents
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Parte I - Dívida Pública, Sistema Financeiro e Mobilização De Recursos - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº25 Quão viável é a análise de sustentabilidade da dívida externa de Moçambique? Uma análise crítica dos indicadores de sustentabilidade da dívida externa de Moçambique IDeIAS Nº71 Dívida pública, acumulação de capital e a emergência de uma bolha económica IDeIAS Nº85 Introdução à problemàtica da dívida pública: contextualização equestões imediatas IDeIAS Nº86 A dívida secreta moçambicana: impacto sobre a estrutura da dívida e consequências económicas IDeIAS Nº87 Rebatendo mitos do debate sobre a dívida pública em Moçambique IDeIAS Nº88 Cenários, opções e dilemas de política face à ruptura da bolha económica IDeIAS Nº89 Crónica de uma crise anunciada: dívida pública no contexto da economia extractiva IDeIAS Nº73 Estado e a capitalização do capitalismo doméstico em Moçambique IDeIAS Nº74 Acumulação especulativa e sistema inanceiro em Moçambique IDeIAS Nº23 Acumulação de reservas cambiais e possíveis custos derivados – cenário em Moçambique IDeIAS Nº30 A dívida pública interna mobiliária em Moçambique: alternativa ao financiamento do déice orçamental? IDeIAS Nº44 Taxas directoras e produção doméstica IDeIAS Nº69 Por que é que a emissão de Obrigações do Tesouro não é a melhor alternativa para inanciar o reembolso do IVA às empresas? IDeIAS Nº82 Saldos rolantes no orçamento do Estado Moçambicano: Nyusi encontrou cofres vazios? IDeIAS Nº93 A face oculta do orçamento do Estado moçambicano: saldos de caixa são ictícios? IDEIAS Nº59 A Política macroeconómica e a mobilização de recursos para inanciamento do investimento privado em Moçambique IDeIAS Nº63 Poupança interna moçambicana: 2000-2010, uma década inédita IDeIAS Nº64 Poupança interna: Moçambique e os outros IDeIAS Nº72 Finança islâmica: quando terá Moçambique um sistema inanceiro Halal? IDeIAS Nº56 Haverá possibilidade de ligação entre grupos de poupança e crédito cumulativo informais e instituições inanceiras formais?
Keywords: G - Mozambique / Moçambique; L - portuguese / português; budget / orçamento; economic development / desenvolvimento económico; mobilization / mobilização

Parte II - Crescimento Económico, Investimento Privado E Dinâmicas De Acumulação - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº13 Moçambique: de uma economia de serviços a uma economia de renda IDeIAS Nº29 Relexões sobre a relação entre infra-estruturas e desenvolvimento IDeIAS Nº55 Ligações com megaprojectos: oportunidades limitadas a determinados grupos IDeIAS Nº60 Ligações entre os grandes projectos de IDE e os fornecedores locais na agenda nacional de desenvolvimento IDeIAS Nº76 Dilemas das ligações produtivas entre empresas numa economia afunilada IDeIAS Nº75 Padrões de investimento privado e tendências especulativas na economia moçambicana IDeIAS Nº68 Consumo agregado moçambicano: evolução e relevância estratégica IDeIAS Nº47 Moçambique: entre estagnação e crescimento IDeIAS Nº77 Estratégias de crescimento económico e desenvolvimento na CPLP IDeIAS Nº39 Investimento directo chinês em 2010 em Moçambique: impacto e tendências
Keywords: G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico

Parte III - Pobreza, Protecção Social e População - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº40 Moçambique no Índice de Desenvolvimento Humano: comentários IDeIAS Nº35 Será que crescimento económico é sempre redutor da pobreza? Relexões sobre a experiência de Moçambique IDeIAS Nº80 Vulnerabilidade dos estratos urbanos pobres: caso da pobreza alimentar em Maputo IDeIAS Nº17 Estratégias individuais de sobrevivência de mendigos na cidade de Maputo: engenhosidade ou perpetuação da pobreza? IDeIAS Nº12 Armando Guebuza e a pobreza em Moçambique IDeIAS Nº15 Protecção social no contexto da bazarconomia de Moçambique IDeIAS Nº32 Protecção social inanceira e protecção social demográica: ter muitos filhos, principal forma de protecção social em Moçambique? IDeIAS Nº26 A relatividade da pobreza absoluta e segurança social em Moçambique IDeIAS Nº31 Pobreza em Moçambique põe governo e seus parceiros entre a espada e a parede IDeIAS Nº34 Pauperização rural em Moçambique na 1ª década do século XXI IDeIAS Nº28 Crescimento demográico em Moçambique: passado, presente … que futuro? IDeIAS Nº33 Em que fase da transição demográica está Moçambique IDeIAS Nº45 Moçambique e a explosão demográica”: somos muitos? Somos poucos? IDeIAS Nº37 Envelhecimento populacional em Moçambique: ameaça ou oportunidade? IDeIAS Nº46 Desaios da duplicação da população idosa em Moçambique IDeIAS Nº54 Viver mais para viver pior? IDeIAS Nº65 Por que Moçambique ainda não possui pensão universal para idosos? IDeIAS Nº81 Moçambique: um dos piores países para os idosos. Porquê?
Keywords: G - Mozambique / Moçambique; L - portuguese / português; poverty / pobreza; social protection / proteção social

Parte IV - Eleições, Governação Local e Sociedade Civil - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº2 Uma nota sobre o recenseamento eleitoral IDeIAS Nº5 Beira – o im da Renamo? IDeIAS Nº6 Sem surpresas: abstenção continua maior força política na reserva em Moçambique … até quando? IDeIAS Nº8 Sobre os votos nulos IDeIAS Nº20 Sobre a transparência eleitoral IDeIAS Nº22 Uma análise preliminar das eleições de 2009 IDeIAS Nº48 Sobre resultados eleitorais e dinâmica eleitoral em Sofala IDeIAS Nº50 Uma relexão sobre o calendário e o recenseamento eleitoral para as eleições autárquicas de 2013 IDeIAS Nº38 Comissão Nacional de Eleições: uma reforma necessária IDeIAS Nº83 Rever o sistema eleitoral IDeIAS Nº3 Orçamento participativo: um instrumento da democracia participativa IDeIAS Nº16 A primeira reforma iscal autárquica em Moçambique IDeIAS Nº18 Relexões sobre parcerias público-privadas no inanciamento de governos locais IDeIAS Nº21 Pequenos provedores de serviços e remoção de resíduos sólidos em Maputo IDeIAS Nº41 Estado e informalidade: como evitar a “tragédia dos comuns” em Maputo? IDeIAS Nº66 Reformas de descentralização e serviços públicos agrários em Moçambique: porquê persistem os desaios? IDeIAS Nº70 Autonomização local para quê? Questões económicas no debate sobre autonomia local IDeIAS Nº24 Sociedade civil em Moçambique e no mundo IDeIAS Nº27 Sociedade civil e monitoria do orçamento público IDeIAS Nº58 As “revoltas do pão” de 2008 e 2010 na imprensa IDeIAS Nº61 Indignai-vos! IDeIAS Nº19 “O inimigo é o modelo”! Breve leitura do discurso político da Renamo IDeIAS Nº62 Media e campanhas eleitorais
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; governance / governação

Parte V - Recursos Naturais e Desenvolvimento - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº10 Indústrias de recursos naturais e desenvolvimento: alguns comentários 487 IDeIAS Nº11 Recursos naturais, meio ambiente e crescimento sustentável 495 IDeIAS Nº14 Terra, desenvolvimento comunitário e projectos de exploração mineira 503 IDeIAS Nº42 Análise ao Exercício de Reconciliação do Segundo Relatório da ITIE em Moçambique 509 IDeIAS Nº43 ITIEM – Análise dos Obstáculos Legais, Transparência do Regime Fiscal e Completa Adesão à ITIE 515
Keywords: G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; natural resources / recursos naturais

Laws and Regulations Related to Foreign Direct Investment in Mozambique - JLA Advogados (Agency for Promotion of Investment and Exports (APIEX), 2017)
After becoming an independent State, Mozambique was plagued by a long and severe civil war, which ultimately resulted in an economic collapse led by the lack of investment, nationalization of privately owned industries, as well as widespread food shortage. The 1992 peace agreement marked the transition from civil war to peace, culminating in the country’s first democratic elections of 1994 and the emergence of the Front for the Liberation of Mozambique (Frelimo) as the dominant political force in the country; a fact that still holds true today. In 1993 the Mozambican Government approved the Investment Act to foster and promote both national and foreign investmentsin the country, granting various benefits and incentives, which include: tax and custom duties exemptions, free remittance of funds, and the possibility of hiring more foreign workers than those permitted by law. These incentives vary according to the economic and industrial activity pursued and the region of implementation of the project. Mozambique’s rapid economic expansion over the past decades has had only a moderate impact on poverty reduction, and the geographical distribution of poverty remains largely unchanged. Despite the recent discoveries of natural resources in the oil & gas sectors, Mozambique is undergoing serious economic and political crisis and needs to improve its social indicators. The country ranked 178th out of 187 countries in the most recent Human Development Index (HDI). The adult literacy rate is 56% (fifty six percent), and average life expectancy at birth is just 50,3 (fifty point three) years. In January 2015, after the 5th (fifth) peaceful election process, Mozambique’s fourth president came into office Mr. Filipe Nyusi. His party also secured a strong majority in the parliament, with 144 seats out of 250 in total.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês

No Niassa, jovens consomem cada vez mais álcool de forma excessiva - Deutsche Welle (DW.COM, 2017)
Na província do norte de Moçambique, muitos adolescentes e jovens entregam-se ao vício por falta de ocupação profissional.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; employment / emprego; youth / juventude

Maternal and Newborn Mortality: Community Opinions on Why Pregnant Women and Newborns Are Dying In Natikiri, Mozambique - Belo, C; Pires, P; Josaphat, J; Siemens, R; Rooke, E; Spence-Gress, C (International Journal of Research, 2017)
Background and objective: maternal and neonatal mortality rates in Mozambique are high, due to insufficient numbers of qualified health workers, lack of equipment and materials, referral system deficiency, difficulties to access health services and gender issues. This study assesses the barriers to health care access, regular attendance at ante natal consultations, institutional delivery and postnatal and neonatal follow-up. This is part of the baseline study for an implementation research project to reduce maternal and neonatal mortality in Natikiri, Nampula, Mozambique. Conclusion: local community members and health professionals were asked to state what they thought would be the best way to intervene. These ideas were then discussed further at a conference with health professionals and government representatives. Six intervention strategies to address identified problems were decided on and will be the basis for the ongoing implementation research project. They were: 1. Expanding family planning especially with adolescents. 2. Community based transport system for pregnant women. 3. Strengthening maternal and child health services by training maternity personnel in obstetrical emergency care and neonatal resuscitation. 4. Providing four quality prenatal visits. 5. Providing quality cesarean deliveries. 6. Supporting the Mozambican Government's campaign against bribery.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Estudo sobre o Impacto do Programa de Responsabilização Social ao Nível dos Municípios – MuniSAM (2017)
O estudo ilustra as dinâmicas e os resultados alcançados por este programa da Concern Universal, no que respeita às mudanças no comportamento das comunidades e das autoridades municipais e à melhor…
Keywords: G - Mozambique / Moçambique; L - portuguese / português

Following the donor-designed path to Mozambique’s US$2.2 billion secret debt deal - Hanlon, Joseph (Third World Quarterly, 2017)
Strenuous efforts by donors and lenders over four decades turned Mozambique from a socialist success story into a neoliberal capitalist one. The private sector dominates; a domestic elite dependent on foreign companies has been created.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Maternity care system in Maputo, Mozambique: Plans and practice? - Long, Qian; Madede, Tavares; Parkkali, Saara; Chavane, Leonardo; Sundby, Johanne; Hemminki, Elina (Cogent Medicine, 2017)
Mixed methods were used with various data sources to describe organisation and delivery of maternity care in Maputo city, Mozambique in early 2010s and to compare the plans with the service provision in practice. In the public health sector, maternity care was organised to be area based and hierarchical with a planned referral system. The provision of basic and emergency maternity care was publicly funded, largely dependent of donor funds, and free of charge for users. Even though Maputo City was better resourced than the rest of the country, there was a large lack of health professionals. Women’s choices and self-referrals, even to higher levels of care, were common, which broke the plans of areas responsibility, gate keeping and care by medical needs. Private services for maternity care had emerged for those who were able to pay, leading to dual practices of health professionals and shortage of care providers in the public system at odd hours. Information of maternity care was aggregate and poorly stored. The gap between “planned” services delivery and “practice” in a real-life requires overall health system strengthening to improve efficiency and effectiveness of health services delivery.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - south / sul; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Avaliacao Nacional sobre o Ambiente Propício para Actuação das OSC: O caso de Moçambique - Francisco, Albino (Joint - Liga de ONGs em Moçambique, 2017)
O presente relatório apresenta as principais constatações resultantes de um estudo realizado em Moçambique pela JOINT – Liga de ONGs em Moçambique, com o objectivo de fornecer uma caracterização do ambiente propício para a intervenção da Sociedade Civil no país. O estudo é parte das Avaliações Nacionais sobre o Ambiente Propício (EENA), uma metodologia de pesquisa juntamente desenvolvida pela CIVUS e ICNL, no âmbito da Iniciativa de Espaço Cívico. As avaliações EENA estão sendo implementadas em 16 países, ao longo dos últimos dois anos, um dos quais Moçambique. Este estudo, designado “Avaliação Nacional sobre o Ambiente Propício para a Actuação (EENA)” das Organizações da Sociedade Civil (OSC) em Moçambique, avaliou o ambiente propício em sete dimensões, nomeadamente: (1) Formação; (2) Operação; (3) Acesso a Recursos; (4) Expressão; (5) Reunião Pacifica; (6) Relações entre o Governo e a Sociedade Civil; e (7) Tributação. Em geral, a principal constatação do estudo mostra que o ambiente propício para a actuação das OSC em Moçambique não é favorável, permanecendo sérios desafios que constrangem a intervenção das OSC aos diferentes níveis. A actual situação de instabilidade política e militar, e de grave crise económica e financeira, tem resvalado para situações de intolerância política e limitações ao exercício das liberdades fundamentais por parte dos cidadãos, situação que concorre para tornar mais complexo o ambiente de actuação das OSC no país. O estudo conclui que, com base na análise do quadro legal e da percepção sobre a sua prática, permanecem sérios desafios na intervenção das OSC em Moçambique. Embora em algumas dimensões o ambiente legal e prático é mais favorável do que em outras, em geral o ambiente não pode ser considerado propício, recomendando: - A revisão da Lei 8/91, a Lei das Associações, adequando-a aos actuais desafios de desenvolvimento das OSC e do país de forma a permitir o acesso simplificado ao registo a todos os níveis e facilitar a operação efectiva das OSC; - A criação de uma arquitectura de financiamento mais equitativa para as OSC, que alivie a dependência dos fundos externos e permita o acesso aos fundos públicos internos; - Tornar a legislação em vigor sobre a liberdade de expressão e de reunião pacífica efectivamente conhecida e implementada em conformidade, garantindo o respeito pelos direitos dos cidadãos e das OSC em geral; - A criação de um ambiente político que garanta a participação efectiva das OSC nos processos de governação aos diferentes níveis; - Estabelecimento de um sistema tributário mais justo e adequado ao contexto real de operação das OSC em Moçambique
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

Mozambique Urbanization Review: Accelerating Urbanization to Support Structural Transformation in Mozambique (World Bank Group, 2017)
The Mozambique Urbanization Review aimed at contributing to the country’s policy and institutional reform agenda on how to harness the full potential of urbanization to promote economic growth and poverty reduction. The study carried out in-depth analyses of the urbanization process, uncovering how urbanization has been influenced by national, regional, and international factors. It identified and analyzed key policy and institutional constraints in increasing the economic benefits of urbanization, including economic, transport, land, and decentralization policies. The study concluded that faster urbanization could increase the pace of economic growth and poverty reduction, but this should not be achieved at the expenses of investments in rural development and agriculture. However, constraints in the creation of productive urban jobs, limited connectivity throughout the system of cities, and dysfunction urban land markets have undermined its economic outcomes. Based on the main findings, the study proposed an emerging national urban reform agenda to enhance the benefits from urbanization in Mozambique focused on: (i) strengthening rural-urban linkages, including reforms to local government finances, enhancing trade and commuting flows; (ii) making urban land systems more equitable and efficient; and, (iii) deepening decentralization to provide a broader remit to municipalities for urban planning and domestic resource mobilization.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; urbanization / urbanização

Colonial State Formation Without Integration: Tax Capacity and Labour Regimes in Portuguese Mozambique (1890s–1970s) - Alexopoulou, Kleoniki; Juif, Dácil (International Review of Social History, 2017)
Abstract Samir Amin (1972) divided the African continent into three “macro-regions of colonial influence” with distinct socio-economic systems and labour practices: Africa of the colonial trade or peasant economy, Africa of the concession-owning companies, and Africa of the labour reserves. We argue that Mozambique encompassed all three different “macro-regions” in a single colony. We reconstruct government revenue (direct/indirect taxes) raised at a district level between 1930 and 1973 and find persisting differences in the “tax capacity” of the three regions throughout the colonial period. The tax systems, we claim, developed in response to existing local geographic and economic conditions, particularly to labour practices. Portuguese colonial rule adapted to and promoted labour practices such as migration and forced labour to maximize revenue. The extent to which the lack of integration played a role in the post-colonial state and fiscal failure should be studied further. , TRANSLATED ABSTRACTS FRENCH – GERMAN – SPANISH Kleoniki Alexopoulou et Dácil Juif. Formation d’un État colonial sans intégration: la capacité fiscale et les régimes de travail au Mozambique portugais (1890-1970) . Samir Amin (1972) a divisé le continent africain en trois “macro-régions d’influence coloniale” dotées de systèmes socio-économiques et de pratiques de travail distincts: l’Afrique du commerce colonial ou de l’économie paysanne, l’Afrique des sociétés propriétaires de concessions et l’Afrique des réserves de main d’œuvre. Nous soutenons que le Mozambique a englobé toutes les trois “macro-régions” différentes dans une seule colonie. Nous reconstruisons les recettes publiques (impôts directs/indirects) prélevées au niveau du district entre 1930 et 1973, et nous relevons des différences persistantes dans la “capacité fiscale” des trois régions durant toute la période coloniale. Les systèmes fiscaux, selon nous, se sont développés en réponse à des conditions géographiques et économiques locales, et particulièrement à des pratiques de travail. La règle coloniale portugaise s’est ajustée à et a encouragé certaines pratiques de travail, telles que la migration et le travail forcé, afin d’optimiser les revenus. Le point auquel le manque d’intégration a joué un rôle dans l’État post-colonial et l’échec fiscal devraient faire l’objet d’études plus approfondies. Traduction: Christine Plard , Kleoniki Alexopoulou und Dácil Juif. Koloniale Staatsformierung ohne Integration: Steuerkraft und Arbeitsregime im portugiesisch regierten Mosambik (1890er bis 1970er Jahre). Samir Amin (1972) hat den afrikanischen Kontinent in drei “Makroregionen kolonialen Einflusses” mit je eigenen sozioökonomischen System und Arbeitspraktiken unterteilt: das Afrika des Kolonialhandels oder der kleinbäuerlichen Wirtschaft, das der über Konzessionen verfügenden Konzerne und das der Arbeitskräftereserven. Wir vertreten die These, dass Mosambik alle drei “Makroregionen” in einer einzigen Kolonie verband. Wir rekonstruieren die Einnahmen aus direkten und indirekten Steuern, die dem Staat zwischen 1930 und 1973 auf der Bezirksebene entstanden sind, und konstatieren, dass es während der Kolonialzeit anhaltende Differenzen in der “Steuerkraft” der drei Regionen gab. Die Steuersysteme entwickelten sich, so argumentieren wir, in Reaktion auf die lokal gegebenen geografischen und wirtschaftlichen Bedingungen, insbesondere in Reaktion auf die jeweiligen Arbeitspraktiken. Die portugiesische Kolonialherrschaft passte sich Praktiken wie der Migration und der Zwangsarbeit an und förderte sie, um die eigenen Einnahmen zu maximieren. Inwiefern der Mangel an Integration für den postkolonialen Staat und dessen fiskalisches Versagen eine Rolle gespielt hat, sollte noch näher untersucht werden. Übersetzung: Max Henninger , Kleoniki Alexopoulou y Dácil Juif. La formación de un estado colonial sin integración: capacidad impositiva y regímenes laborales en el Mozambique Portugués (1890-1970) . En 1972 Samir Amin dividió el continente africano en tres “macroregiones de influencia colonial” con unos sistemas socioeconómicos y unas prácticas laborales distintas: el África del comercio colonial o de la economía campesina, el África de las empresas propietarias de concesiones, y el África de las reservas de trabajo. En el artículo consideramos que Mozambique abarca esos tres tipos diferentes de macroregiones en una sola colonia. En él realizamos una reconstrucción de los ingresos (tanto de los impuestos directos como de los indirectos) recaudados por el gobierno a nivel regional entre 1930 y 1973. Encontramos diferencias continuadas en la “capacidad impositiva” de las tres regiones a lo largo del periodo colonial. Consideramos que el sistema de impuestos se desarrolló en respuesta a las condiciones geográficas y económicas existentes a nivel local, particularmente en lo que se refiere a las prácticas laborales. La legislación colonial portuguesa adaptó y promovió unas determinadas prácticas de trabajo tales como la migración y el trabajo forzado para conseguir una maximización de los ingresos impositivos. Las implicaciones de esta falta de integración jugaron un papel destacado en el estado post-colonial y en su quiebra fiscal; un aspecto que deberá ser estudiado con mayor profundidad. Traducción: Vicent Sanz Rozalén
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

AGORA ELES TÊM MEDO DE NÓS! Uma colectânea de textos sobre as revoltas populares em Moçambique (2008–2012 - Brito, Luís de (IESE, 2017)
A presente colectânea reúne uma série de textos de natureza diferente, mas que tratam todos da mesma temática, as revoltas populares do final da primeira década dos anos 2000 em Moçambique. Partindo de diferentes disciplinas das ciências sociais e de abordagens teóricas diferenciadas, todos têm em comum a intenção de contribuir para a compreensão não só das causas e dos elementos desencadeadores das manifestações populares violentas, mas sobretudo do seu significado mais profundo no actual tecido económico, político e social moçambicano. Sem pretender esgotar o rico conteúdo dos capítulos, apresentamos de seguida e em forma muito parcial e resumida alguns dos aspectos que merecem destaque em cada um deles.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito

Economia, recursos naturais, pobreza e política em Moçambique: uma colectânea de textos - Brito, Luís de; Chivulele, Fernanda Massarongo (IESE, 2017)
Neste contexto, o conjunto de textos que compõem a presente colectânea apresenta material útil para a contextualização da situação actual e para o debate dos diferentes problemas que o país enfrenta. As discussões sobre eleições, descentralização, participação, dívida pública, sistema financeiro, crescimento e desenvolvimento económico, dentre outras, que fazem parte da colectânea, informam o debate a nível de praticamente todas as áreas de desafios cruciais que hoje se vivem em Moçambique. Não só são fornecidos pontos relevantes para o debate actual, mas através desta colectânea é possível também fazer um acompanhamento histórico da evolução dos diferentes assuntos e ver como temas actualmente destacados no debate nacional já eram levantados no quadro do trabalho do IESE ao longo dos últimos 9 anos. Por esta via, é igualmente possível questionar até que ponto diferentes análises são usadas e consideradas no debate e na formulação de políticas. A colectânea contém 76 boletins produzidos por investigadores permanentes do IESE e alguns investigadores associados e está subdividida em 5 temáticas. A primeira foca questões ligadas à dívida pública, sistema financeiro e mobilização de recursos. Especificamente, esta parte discute a problemática da dívida pública em Moçambique e suas implicações para a economia, assim como dinâmicas do sector financeiro e mobilização de recursos de forma mais geral. A segunda discute a estrutura e estratégia de crescimento económico e suas implicações, fontes e padrões de investimento privado e ligações económicas existentes na economia. A terceira discute três “P” fundamentais no desenvolvimento económico: pobreza, protecção social e população. A discussão sobre pobreza incide sobre a sua conceptualização e mapeamento e sobre a sua relação com crescimento e governação. Esta discussão continua com a questão da protecção social em Moçambique, tratando aspectos como a pensão universal e as estratégias de protecção social no contexto específico da economia de Moçambique, bem como os desafios demográficos que lhe estão associados. Na quarta parte, os textos tratam da questão dos recursos naturais, seu papel no desenvolvimento, relação de grandes projectos de exploração de terra com o desenvolvimento local e a eficácia dos mecanismos concebidos para reforçar a transparência na exploração de recursos naturais. A última parte discute a questão da descentralização, mecanismos de participação da sociedade civil e questões relativas aos processos eleitorais em Moçambique.
Keywords: *snowball; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; natural resources / recursos naturais; poverty / pobreza

Elite capture and the development of natural resource linkages in Mozambique - Buur, Lars; Monjane, Celso Marcos (Fairness and Justice in Natural Resource Politics, 2017)
This chapter explores these broader processes from the perspective of linkage creation in Mozambique related to mega-projects in natural resource extraction and development from a political economy perspective. From a resource fairness perspective, linkage creation is essential as it allows for a more fair distribution of opportunities for local firms to gain from large-scale natural resource investments and for learning and spillover effects to other parts of the economy. In a longer term perspective, it is a potential key source of economic transformation towards higher value added activities and more and better local employment, therefore reducing dependence on resources.
Keywords: FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources / recursos naturais

As Autoridades Tradicionais nos Processos de Governação Descentralizada em Moçambique - Campos, Luciana Martins (Universidade Federal de Pernambuco, 2017)
A partir da década de 1990 iniciou-se, em vários países da África Subsaariana, um movimento de liberalização e descentralização política com a adoção de regimes democráticos. Associado a esse processo se têm em curso reformas administrativas e legislativas que visam incorporar as autoridades comunitárias e tradicionais à administração pública local a partir do reconhecimento de sua importância social e representativa para certas comunidades rurais, onde a presença do Estado se faz menor ou de modo deficitário. No entanto, esse lugar de importância social e cultural das autoridades tradicionais, em específico, só existe enquanto herança do Estado bifurcado colonial, conduzindo à elaboração de um sistema misto de governo na atualidade, onde as autoridades tradicionais seguem desempenhando funções “administrativas” semelhantes às exercidas no período colonial na lógica do indirect rule. As relações das autoridades tradicionais com o Estado em termos de administração local expõe uma situação de hibridismo institucional em decorrência do desafio de penetração do Estado enquanto administração pública e burocrática que, portanto, coabita com lógicas informais de funcionamento da administração e da realidade jurídica.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; authority / autoridade; decentralization / descentralização; governance / governação

Policy analysis Food security, nutrition, climate change resilience, gender and the small-scale farmers Mozambique - Care; ActionAid (ActionAid and Care, 2017)
The analysis covers both national specific policies and those policies and commitments that the Government of Mozambique has signed as part of global collective efforts. The analysis aims to become a baseline to better understand the policy gaps and implementation challenges in in FNS and CCR towards women and smallholders in Mozambique. The main purpose of this analysis is to become useful source and instrument in the implementation of CARE Mozambique Advocacy Strategy, and also for the Government of Mozambique, donors and civil society organizations, to better identify the challenges for a more effective investment in gender transformative, climate resilient and nutrition smart agriculture.
Keywords: *snowball; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas

Desafios para Moçambique - 2017 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Forquilha, Salvador; Francisco, António (Instituto de Estudos Sociais e Económicos, 2017)
INTRODUÇÃO / Carlos Nuno Castel-Branco PARTE I – POLÍTICA Um Olhar para a Abstenção Eleitoral em 2014 / Luís de Brito Descentralização e Conflito em Moçambique: O desafios da construção do Estado / Salvador Forquilha Partidos Libertadores na África Austral: Reflexões sobre os desafios para Moçambioque / Zefanias Matsimbe PARTE II – ECONOMIA Contribuição para o Método de Investigação de Economia Política de Moçambique / Carlos Nuno Castel-Branco Crises Económicas e Estruturas de Acumulação de Capital em Moçambique / Carlos Nuno Castel-Branco Dependência de Megaprojectos e Desindustrialização Prematura em Moçambique / Epifânia Langa Integração da Força de Trabalho no Sistema de Acumulação de Capital / Rosimina Ali e Carlos Muianga Política Monetária e Estrutura Produtiva da Economia em Moçambique / Fernanda Massarongo Chivulele A Bolha Económica Moçambicana e o Papel da Porosidade Económica na Absorção de Recursos Externos / Oksana Mandlate Lógica Histórica do Modelo de Acumulação de Capital em Moçambique / Carlos Nuno Castel-Branco Novas Questões e Caminhos de Investigação / Carlos Nuno Castel-Branco PARTE III – SOCIEDADE “Gerontocrescimento” e Envelhecimento Populacional em África / António A. da Silva Francisco “Restauração da Dignidade do nosso Povo” De salários sectoriais a um salário mínimo nacional na África do Sul / Ruth Castel-Branco e Gilad Isaacs PARTE IV – MOÇAMBIQUE NO MUNDO Moçambique e a Crise Político-Económica Brasileira / Sérgio Chichava Um Olhar do IESE sobre Cooperação Sul-Sul Brasileira / Natalia N. Fingermann
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Desafio da articulação entre os cidadãos e os Comités de Qualidade e Humanização dos Cuidados de Saúde como órgãos de representação da comunidade - Dias, José (Centro de Aprendizagem e Capacitação da Sociedade Civil, 2017)
O Ministério da Saúde reconhece os Comités de Qualidade e Humanização dos Cuidados de Saúde nas Unidades Sanitárias como a principal forma de diálogo e ligação entre os serviços de saúde e as comunidades. Os Termos de Referência revistos, afirmam que o Comité de Qualidade e Humanização das Unidades Sanitárias constitui uma equipa de assessoria e coordenação ao processo de implementação da actividades de qualidade e humanização no âmbito da Unidade Sanitária. Destina-se a empreender uma política institucional de resgate de valores humanitários e de garantia de qualidade nos serviços de saúde, em benefício dos utentes e trabalhadores através da gestão participativa. Contudo, o sector de saúde dispõe também da Carta dos Direitos e Deveres do Doente, como instrumento que, no nosso entendimento, define o padrão da prestação de serviços, de comportamento, e concede espaço ao cidadão, individual ou colectivamente, para a exigência directa de serviços de saúde de qualidade. A este último propósito, por exemplo, cabe ressaltar que no quadro do Direito 16 (Direito a apresentar sugestões, queixas e reclamações) é estabelecido que através dos canais disponibilizados pelas Autoridades Sanitárias, os doentes têm direito a apresentar, individual ou colectivamente, petições, sugestões, reclamações ou queixas sobre a organização e o funcionamento dos serviços de saúde; e de ter as suas queixas atendidas prontamente e de maneira equitativa (MISAU, 2011). O que se apreende do exposto é que enquanto os Comités de Qualidade e Humanização funcionam numa lógica essencialmente de Democracia Representativa, a Carta dos Direitos e Deveres do Doente se insere numa abordagem de Democracia Participativa, buscando promover uma cidadania activa do doente/cidadão na sua interacção directa com as unidades sanitárias. O nosso artigo problematiza e discute as dinâmicas de representação e de participação activa do cidadão no processo da prestação de serviços de saúde. A nossa base de discussão é fundamentada em evidências de 15 distritos de actuação do Centro de Aprendizagem e Capacitação da Sociedade Civil (CESC), onde funcionam os Comités de Qualidade e Humanização, por um lado, e se implementa a abordagem de Responsabilização Social, usando ferramentas tais como Cartão de Pontuação Comunitária, por outro.
Keywords: G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; citizenship & participation / cidadania e participação; health / saúde

Anuário Estatístico - Statistical Yearbook 2016 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2017)
O Anuário Estatístico 2016 é parte da série de publicações que o Instituto Nacional de Estatística leva aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2012-2016. O ano de 2016 foi crucial no âmbito da preparação do IV Recenseamento Geral da População e Habitação 2017. Seguindo as recomendações internacionais, em Outubro teve lugar o Censo Piloto, onde foi testada toda a máquina e produzidos os devidos ajustamentos metodológicos rumo ao Censo 2017.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Estratégia Científica 2016-2015 - Instituto Nacional da Saúde - Moçambique (Instituto Nacional da Saúde - Moçambique, 2017)
A presente Estratégia Científica do Instituto Nacional de Saúde (INS) para 2016-2025 está alinhada com o Programa Quinquenal do Governo (2015-2019) e com o Plano Estratégico do Sector Saúde (PESS 2014-2019). No contexto global, a elaboração da presente Estratégia teve em conta os Objectivos de Desenvolvimento Sustentável (ODS), o Regulamento Sanitário Internacional (RSI) e a Agenda Global de Segurança Sanitária (GHSA). As principais diferenças entre a presente e anterior estratégia do INS são: 1) um horizonte temporal incrementado, sendo de 10 anos ao contrário de 5 anos na estratégia anterior; 2) uma ampliação das áreas programáticas estratégicas; 3) a inclusão de um robusto eixo estratégico de fortalecimento na área de gestão institucional. A Estratégia Científica do INS 2016-2025 está organizada em Programas e em Eixos Estratégicos. Os oito Programas desta Estratégia Científica reflectem as áreas temáticas consideradas como prioritárias. Estes Programas são: 1) Saúde e Ambiente, incluindo Saúde do Trabalhador; 2) Saúde Mental, Trauma e Violência; 3) Saúde da Mulher e da Criança; 4) Adolescente, Idoso e Outras Populações Vulneráveis; 5) Determinantes de Doenças Crónicas; 6) Doenças Transmitidas por Vectores, Negligenciadas e Zoonóticas; 7) Doenças Endémicas de Grande Impacto Sanitário; 8) Sistema de Saúde. Os cinco Eixos Estratégicos representam as funções essenciais de saúde pública. Este Eixos Estratégicos são: 1) Observatório Nacional de Saúde e Vigilância Epidemiológica; 2) Rede de Laboratórios de Referência em Saúde; 3) Pesquisa, Desenvolvimento Tecnológico e Inovação; 4) Ensino, Informação e Comunicação em Saúde; 5) Gestão e Desenvolvimento Institucional. Cada Programa e Eixo Estratégico tem um ou mais Objetivos Estratégicos e seus respectivos indicadores de impacto, cada um dos quais descreve a situação ideal que se pretende atingir a médio e longo prazo. Cada Objectivo Estratégico deve ser atingido mediante a execução de uma ou mais Acções cujo enunciado reflete num conjunto de Projectos/Actividades afins. Os Projectos são actividades com objectivos e temporalidade definidas, enquanto se denominam Actividades aquelas outras que são de carácter continuado, geralmente de gestão. Finalmente, cada Projecto/Actividade tem Produtos, Indicadores e Metas temporais e/ou quantitativas definidas. Os Projectos/Actividades temáticos encontram-se descritos em cada um dos oito programas, enquanto os Projectos/Actividades estruturantes encontram-se descritos em cada um dos cinco eixos estratégicos. A presente Estratégia Científica compreende 17 Objectivos Estratégicos, 19 Acções e 102 Projectos / Actividades.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; health - health services / serviços de saúde

O agronegócio no desenvolvimento do meio rural em Moçambique: perceção e análise das cadeias de valor de milho e da mandioca na província de Nampula - Linha, Paulo (Universidade de Lisboa, 2017)
O Agronegócio em Moçambique poderá ser um factor dinamizador da agricultura, chave para o desevolvimento económico, elemento para a equidade no desenvolvimento social e fundamental para a redução da pobreza e da fome. O estudo analisa as perceções dos atores do agronegócio do milho e da mandioca sobre o impacto destas culturas na vida económica e social no meio rural. Diante desta perspetiva, esta pesquisa teve como objetivo investigar prospectivamente as cadeias de valor das culturas do milho e da mandioca, no corredor de Nacala, com vista a identificar formas de potenciar o desenvolvimento do agronegócio como fator dinamizador da promoção do desenvolvimento socioeconómico sustentável no meio rural. Os resultados alcançados indicam que em Moçambique, de forma geral, o agronegócio do milho e da mandioca é potencial pilar dinamizador que poderá contribuir para o desenvolvimento da agricultura e impulsionar o crescimento económico e o desenvolvimento social se o Estado colocar-se na dianteira na criação, nas zonas de produção, de infraestruturas públicas para a prática de uma agricultura economicamente sustentável e uma legislação flexível e promotora de um clima propício para o agronegócio. Com as infraestruturas públicas criadas nos centros de produção deve-se optar, pelo envolvimento de todos atores do agronegócio num sistema de Integração e Coordenação Vertical, apostando na transformação da baixa renda da agricultura rural em agricultura comercial e competitiva para que efetivamente o agronegócio seja um dos pilares para o combate da fome e da pobreza no meio rural. A Integração e Coordenação Vertical, significa a existência de instituições âncoras que se dedicam a puxar a atividade do agronegócio dos produtores locais na base contratual. Esta forma promete rápida integração ao mercado, crescimento económico, inovação tecnológica, ao mesmo tempo em que protege os direitos e a autonomia do produtor sob regime de integração e coordenação. Agribusiness in Mozambique could be a driving force for agriculture, key to economic development, an element for equity in social development and fundamental to reducing poverty and hunger. The study analyzes the perceptions of corn and cassava agribusiness actors on the impact of these crops on economic and social life in rural areas. The objective of this research was to investigate prospectively the corn and cassava value chains in the Nacala corridor in order to identify ways to promote the development of agribusiness as a driving force for the promotion of sustainable socioeconomic development in the environment rural. The results indicate that, in general, corn and cassava agribusiness in Mozambique are potential pivotal factors that could contribute to the development of agriculture and boost economic growth and social development, if the government takes the initiative to build public infrastructures for an economic sustainable agriculture as well as create a flexible legislation that promotes a proper environment for agribusiness. With the public infrastructures created in the production centers, one must opt for the involvement of all agribusiness actors in a system of Integration and Vertical Coordination, betting on the transformation of low income from rural agriculture into commercial and competitive agriculture so that agribusiness is effectively a pillar to combat hunger and poverty in rural areas. Integration and Vertical Coordination means the existence of anchor institution dedicated to pull the agribusiness activity of the local producers in the contractual basis. This form promises rapid market integration, economic growth, technological innovation, while protecting the rights and autonomy of the producer under integration and coordination.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; agriculture / agricultura; private sector / setor privado

Perspectives on the coordination of multisectoral nutrition in Mozambique and an emerging framework - Michaud-Létourneau, Isabelle; Pelletier, David Louis (Food Policy, 2017)
Multisectoral approaches represent a prominent ideological consensus, inﬂuenced by historical roots and the current political, ﬁnancial and institutional landscape, to address the multi-faceted and complex causes of most nutrition, public health and food problems. However, the implementation of multisectoral approaches presents tremendous challenges; one of the most often cited problems, in the literature and by practitioners, is coordination. This study investigates the perspectives of key national leaders on a range of issues regarding the coordination of a Multisectoral Action Plan for the Reduction of Chronic Undernutrition (PAMRDC) in Mozambique. Within this policy group, the principal researcher played the role of a researcher-participant for 14 months, and used Q methodology with a total of 21 key national leaders who had been actively engaged in coordination groups at the central level. Participants sorted 54 subjective statements on a range of issues that were present in the current national discourse. The results revealed four distinct perspectives. The Implementation perspective (n = 12) prioritized concrete actions to advance the operationalization of the plan, based on a guidance-based approach from the central level to the lower administrative levels. The Advocacy perspective (n = 3) emphasized advocacy to increase politicians’ awareness of the problem and of potential solutions to enhance political commitment. The Structuralist perspective (n = 3) was concerned with the development of structures and mechanisms to facilitate coordination, funding and improving communication between the government and donors. The People-centered perspective (n = 3) focused on the importance of mobilizing individuals to compensate for the sub-optimal structures and processes for coordination. Areas of convergence across the perspectives included: low capacity and skills that limit the work; the agency in charge of coordination (SETSAN) should exercise an increased leadership to facilitate the multisectoral work; and SETSAN should advocate to mobilize politicians and donors for resources. Areas of divergence related to the type of guidance from national to sub-national levels (prescriptive or not) and the functions to be carried out by SETSAN. This study highlights lack of clarity on the meaning of coordination and on the functions of the multisectoral coordination body that appear to arise for two reasons: the lack of an explicit and shared framework for the policy process and the complex nature of coordination itself. These results are examined through the lenses of several related literatures, including governance, public policy and political economy of nutrition, leading to a three-dimensional conceptual framework for coordination that distinguishes the coordination space, forms, and instruments. Global guidance, such as provided through the SUN movement, could support countries in overcoming their coordination challenges by facilitating an analysis of their decision-making processes in order to choose the functions for the coordination body based on a shared understanding of countries’ needs, context and opportunities. This paper moves the ﬁeld beyond a broad consideration of horizontal and vertical coordination within multisectoral initiatives.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Women's Economic Empowerment in Selected MENA Countries: The Impact of Legal Frameworks in Algeria, Egypt, Jordan, Libya, Morocco and Tunisia - OECD (Competitiveness and Private Sector Development, 2017)
OECD's dissemination platform for all published content - books, serials and statistics
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Mozambique: A Political Economy Analysis - Orre, Aslak; Rønning, Helge (NUPI political economy reports, 2017)
This report uses a political economy analysis to shed light on some of the paradoxes that characterise Mozambique mid 2017: Entrenched poverty, the resuscitated armed conflict/war, the trust crisis between the Mozambican (Frelimo) government and its development partners, the spiralling debt and the party-state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; conflict / conflito; poverty / pobreza

Austerity and the “sector-wide approach” to health: The Mozambique experience - Pfeiffer, James; Gimbel, Sarah; Chilundo, Baltazar; Gloyd, Stephen; Chapman, Rachel; Sherr, Kenneth (Social Science & Medicine, 2017)
Fiscal austerity policies imposed by the IMF have reduced investments in social services, leaving postindependence nations like Mozambique struggling to recover from civil war and high disease burden. By 2000, a sector-wide approach (SWAp) was promoted to maximize aid effectiveness. ‘Like-minded’ bilateral donors, from Europe and Canada, promoted a uniﬁed approach to health sector support focusing on joint planning, common basket funding, and streamlined monitoring and evaluation to improve sector coordination, amplify country ownership, and build sustainable health systems. Notable donors e including US government and the Global Fund e did not participate in the SWAp, and increased vertical funding weakened the SWAp in favor of non-governmental organizations (NGOs). In spite of some success in harmonizing aid to the health sector, the SWAp experience in Mozambique demonstrates how continued austerity regimes that severely constrain public spending will continue to undermine health system strengthening in Africa, even in the midst of high levels of foreign aid with the ostensible purpose of strengthening those systems. The SWAp story provides a poignant illustration of how continued austerity will impede progress toward Sustainable Development Goal 3 (SDG 3); “Achieve universal health coverage, including ﬁnancial risk protection, access to quality essential health-care services and access to safe, effective, quality and affordable essential medicines and vaccines for all”. However, the SWAp continues to offer an alternative model to health system support that can provide a foundation for resistance to renewed austerity measures.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; fiscal policy / política fiscal; health / saúde

A Economia Política da Descentralização em Moçambique: Dinâmicas, Efeitos, Desafios - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
O livro aborda a questão da descentralização mediante uma abordagem multidisciplinar e multissectorial, considerando o ângulo visual de tipo político, assim como institucional, da administração pública ou da burocracia, da economia, das finanças (públicas) e da sociedade. O objectivo que se põe tem a ver com o relacionamento entre descentralização e democracia. Trata-se de um assunto conhecido e enfrentado várias vezes no debate próprio da ciência política: será que uma maior descentralização corresponde a um nível mais avançado de democracia? Moçambique é um País ainda novo, quanto à sua vida democrática. E o livro oferece um quadro claro da história da descentralização desde 1992 até hoje; entretanto, a tese de fundo é a seguinte: a classe política que sempre esteve no poder procurou sistematicamente travar ou limitar os processos de descentralização. Será que esta tese é aceitável? Será, sobretudo, que esta tese sai comprovada das evidências que o livro traz?
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

The costs of corruption to the Mozambican economy. Why it is important to fight corruption in a climate of fiscal fragility - CIP and CMI (CMI Report, 2016)
What is the price that Mozambique has to pay for the widespread corruption in the country? What is the cost of corruption for the...
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

População da Ilha de Moçambique queixa-se de cobranças ilícitas na maternidade - Televisão de Moçambique TVM (Televisão de Moçambique TVM, 2016)
Primeira sessão do dia aberto ao cidadão, uma iniciativa do conselho municipal da ilha de Moçambique para escutar as questões que atinjem os cerca de 50mil habitantes da primeira capital de Moçambique. As reuniões são realizadas nas comunidades para que de forma franca e aberta os munícipes possam apresentar os seus problemas
Keywords: G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

Relatório de Pesquisa Formativa – Educação e Saúde de Qualidade (2014) (Responsabilização Social em Moçambique, 2016)
As intervenções programadas pelo CEP enquadram-se num contexto em que Moçambique regista um progressivo aumento na disponibilidade de serviços de educação e saúde, ao mesmo tempo em que enfr…
Keywords: G - Mozambique / Moçambique; L - portuguese / português

Pobreza e Bem-Estar em Moçambique: Quarta Availação Nacional - Inquérito Ao Orçamento Familiar - Iof 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Pobreza e Bem-estar em Moçambique: Resumo da Quarta Availação Nacional - Inquérito ao Orçamento Familiar - IOF 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Country Evaluation Brief - Mozambique - CMI (Chr. Michelsens Institutt (CMI), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação

Social Movements, Agrarian Change and the Contestation of ProSAVANA in Mozambique and Brazil - Shankland, Alex; Gonçalves, Euclides; Favareto, Arilson (Future Agricultures Working 137, 2016)
In this study, we set out to examine three interrelated questions: To what extent has Brazilian cooperation in the agriculture sector contributed to agrarian transformation in Mozambique? How has Mozambican civil society, and in particular the União Nacional dos Camponeses (UNAC, National Peasants’ Union), responded to the prospect of Brazilian agribusiness investments in the Nacala Corridor? And what effects has BrazilianMozambican agricultural development cooperation had on the existing relations among Brazilian and Mozambican rural social movements, in particular UNAC and Brazil’s Movimento dos Trabalhadores Sem Terra (MST, Landless Rural Workers’ Movement) and Movimento dos Pequenos Agricultores (MPA, Movement of Small Farmers), as well as between these movements and other civil society groups?
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; Northern PEA; agriculture / agricultura; government policy / politica governamental; south-south cooperation / cooperação sul-sul

Mozambique: Report 8/2016 Country Evaluation Brief - Tvedten, Inge; Orre, Aslak (Norwegian Agency for Development Cooperation (Norad), 2016)
The purpose of this Country Evaluation Brief is to present relevant knowledge about donors’ development efforts in Mozambique. The brief systematises relevant findings from existing evaluations of development interventions in the country. The idea is to present the findings to the reader in a succinct and easily accessible format.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Government Decentralization Program in Indonesia - Nasution, Anwar (ADBI, 2016)
Without much preparation, Indonesia, in 2000, at a stroke replaced the previous system of centralized government and development planning with a wide range of decentralization programs. The reforms gave greater authority, political power, and financial resources directly to regencies and municipalities, bypassing the provinces. The powers transferred include those of executing a wide range of responsibilities in the areas of health, primary and middle-level education, public works, environment, communication, transport, agriculture, manufacturing, and other economic sectors. At the same time, the government replaced the antiquated cash-based, single-entry system of public finance with a modern double-entry accounting system that uses a single treasury account; is performance based; and has transparent management of the public treasury, tight expenditure and financial controls with performance indicators, computerized reporting, and a tightly scheduled auditing system.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found

Divisão Administrativa / A Provincia / Início - Portal do Governo da Provincia de Niassa - Governo da Província de Niassa (Governo da Província de Niassa, 2016)
SUBDIVISÕES DA PROVÍNCIA A província do Niassa está dividida em 16, os 15 distritos já existentes quando foi realizado o censo de 2007, mais o distrito de Lichinga, estabelecido em 2013 para administrar as competências do governo central, e que coincide territorialmente com o município do mesmo nome, e o distrito de Chimbonila, que é o novo nome do antigo distrito de Lichinga:
Keywords: #Map / Mapa; G - Mozambique / Moçambique; L - portuguese / português; demographics / demografia

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Secret security debts devastate economy - Africa Confidential (Africa Confidential, 2016)
As officials count the rising cost of the hidden debts, President Nyusi faces awkward questions from investors and donors. As Mozambique's mountain of dubious debts tops US$2 billion, there are growing calls for a forensic audit and an international police probe into the officials and entities involved in this massive fraud. The deals and loans arranged under President Armando Guebuza, and largely kept secret under his successor Filipe Nyusi, mean that Mozambicans now face the prospect of penury under the yoke of debt repayments on an epic scale. The role of the banks involved in the deals, whose terms were far above market rates, is also attracting regulatory interest and criticism.
Keywords: G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico

Mozambique - Map No. 3706 Rev. 6 - United Nations (United Nations, 2016)
Map Mozambique
Keywords: #Map / Mapa; G - Mozambique / Moçambique; L - english / inglês; demographics / demografia

Facilitators and obstacles to cooperation in international development networks: a network approach - Petersen, Il-haam (Development in Practice, 2016)
This paper draws attention to the value of a network approach for understanding cooperation in international development networks. The approach emphasises the impact of social interaction, and the values, ideas, and behaviours of individuals on the achievement of development goals. Social network analysis is used to analyse the social structure and dynamics of interaction in an aid-funded development network organisation that aimed to develop optometry capacity in Mozambique. The analysis shows the value of combining quantitative and qualitative methods in a complementary way to identify factors facilitating (network consciousness and social skill) and hindering (power dynamics) cooperation.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; collaboration / colaboração

Rethinking Indonesia’s Informal Sector - Rothenberg, Alexander D.; Gaduh, Arya; Burger, Nicholas E.; Chazali, Charina; Tjandraningsih, Indrasari; Radikun, Rini; Sutera, Cole; Weilant, Sarah (World Development, 2016)
This paper reviews competing theories about the causes of informality in developing countries and uses new data to determine which theory best explains the persistence and scale of Indonesia’s informal sector. Using nationally representative survey data on micro, small, and medium-sized firms, we find that most of Indonesia’s informal firms are very small, micro firms, with less than five employees. These firms pay low wages, are relatively unproductive when compared to large firms, are managed by individuals with low educational attainment, predominantly supply products to local markets, and have not recently attempted to expand their operations. From a small-scale, qualitative survey of firms, we find that many informal firms do not register their businesses either because they have no desire to expand or borrow from formal financial sources, or because they are avoiding taxes. Finally, we evaluate the impact of Indonesia’s one-stop-shops for business registration program, a large-scale program that attempted to reduce registration costs. We find both that the program had no effects on firms’ informality rates, and we also find that it did not reduce the probability that workers were informally employed. Taken together, the evidence suggests that a combination of the rational exit and the dual economy theories best explains why so many firms in Indonesia are informal.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Análise do desenvolvimento institucional do processo de descentralização em Moçambique: lógicas e dinâmicas políticas - Rosário, Domingos Manuel do (Instituto de Estudos Sociais e Económicos (IESE), 2016)
Moçambique é uma colónia portuguesa antiga, que alcançou a independência em 1975, depois da queda do regime fascista português em Abril de 1974. O sucesso militar da Frelimo contra os portugueses, deu legitimidade a este movimento para se impor como o único representante da sociedade (Cahen, 2003). Em 1977, o Comité Central da Frelimo realizou o 3° congresso que marcou oficialmente a passagem ao partido Marxista-leninista e de «Vanguarda». A partir de 1980, o campo político Moçambicano foi objecto de uma série de transformações. Em 1983 assistimos a realização do IV congresso da Frelimo que recomendou o governo a operar reformas económicas e administrativas que iniciaram em 1987. Estas reformas culminaram com a aprovação em 1990 de uma Constituição pluralista que estabeleceu “liberdades políticas”. Em 1992 o governo da Frelimo e o movimento de guerrilha da Resistência Nacional de Moçambique (Renamo) assinaram o Acordo Geral de Paz em Roma que pôs fim a uma guerra civil, que durante 16 anos (1976-1992) devastou o tecido social, económico e político do país. Em Setembro de 1994 a Assembleia popular aprovou por unanimidade a Lei 3/1994 - Programa dos órgãos locais do Estado; e finalmente a 4 de Outubro de 1994 realizaram-se as primeiras Eleições Gerais multipartidárias em Moçambique. As eleições Gerais Presidenciais e Legislativas de 1994 foram ganhas pela Frelimo (44,33%) e seu candidato Joaquim Chissano (53,30%) contra 33,73% de Afonso Dhlakama e 37,78% da Renamo (STAE, 1997). Em resultado do processo de colonização e das políticas implementadas pela Frelimo durante o período do Marxismo-leninismo foi possível observar dois fenómenos nestas eleições: A clivagem étnico-regional e a clivagem rural-urbano. A Frelimo conseguiu grandes maiorias nos centros urbanos e nas regiões sul (Maputo, Gaza e Inhambane) e no extremo Norte (Cabo Delgado). É destes meios que é oriunda a elite assimilada e intelectual (sul) e militar (Cabo Delgado). A Renamo saiu vitoriosa nas zonas rurais das províncias do Centro (Manica, Sofala e Tete), Centro Nordeste e Norte (Zambézia e Nampula respectivamente). A Frelimo conquistou 59% do total dos votos urbanos contra apenas 29% da Renamo. Por sua vez, a Renamo ganhou 41% do total dos votos rurais, contra 40% da Frelimo (Brito, 1995). Apesar do aparecimento do Movimento Democrático de Moçambique (MDM) no cenário político nacional a partir de 2009, a estrutura do voto produzida nas eleições de 1994 permanece inalterável até hoje. A Frelimo se sentindo ameaçada pela legitimidade democrática ganha pela Renamo, nas eleições de 1994 inicia um processo de reconstrução do Estado e da economia a seu favor (Sumich & Honwana, 2007). Na ausência de uma política e Estratégia de Descentralização (entretanto aprovada em 2012), a Frelimo optou por um compromisso misto de desconcentração: descentralização com eleições para as zonas urbanas/municípios - com a substituição da Lei 3/1994 pela Lei 2/97 das autarquias locais; e uma descentralização sem eleições para as lideranças dos distritos e das províncias - com a aprovação da Lei 8/2003 - Lei dos órgãos locais do Estado (LOLE). Esta descentralização foi concebida como meio para construir ligações significativas e duradouras entre o partido - Estado até então altamente centralizado e os cidadãos, ligações essas que tinham sido seriamente desafiadas, se não quebradas durante a guerra (Weimer, 2012).
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Place, Time and Experience: Barriers to Universalization Of Institutional Child Delivery in Rural Mozambique - Agadjanian, Victor; Yao, Jing; Hayford, Sarah R (International perspectives on sexual and reproductive health, 2016)
CONTEXT: Although institutional coverage of childbirth is increasing in the developing world, a substantial minority of births in rural Mozambique still occur outside of health facilities. Identifying the remaining barriers to safe professional delivery services can aid in achieving universal coverage. METHODS: Survey data collected in 2009 from 1,373 women in Gaza, Mozambique, were used in combination with spatial, meteorological and health facility data to examine patterns in place of delivery. Geographic information system-based visualization and mapping and exploratory spatial data analysis were used to outline the spatial distribution of home deliveries. Multilevel logistic regression models were constructed to identify associations between individual, spatial and other characteristics and whether women's most recent delivery took place at home. RESULTS: Spatial analysis revealed high- and low-prevalence clusters of home births. In multivariate analyses, women with a higher number of clinics within 10 kilometers of their home had a reduced likelihood of home delivery, but those living closer to urban centers had an increased likelihood. Giving birth during the rainy, high agricultural season was positively associated with home delivery, while household wealth was negatively associated with home birth. No associations were evident for measures of exposure to and experience with health institutions. CONCLUSIONS: The results suggest the need for a comprehensive approach to expansion of professional delivery services. Such an approach should complement measures facilitating physical access to health institutions for residents of harder-to-reach areas with community-based interventions aimed at improving rural women's living conditions and opportunities, while also taking into account seasonal and other variables.
Keywords: G - Mozambique / Moçambique; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Pequenas e Médias Empresas em Moçambique: Situação e Desafios - GIZ (GIZ, 2016)
O Manual sobre Pequenas e Médias Empresas é um documento de referência para este segmento empresarial, que apresenta diversos aspectos de organização, de mercado e legal relevantes para sucesso das mesmas, aliando teoria à prática. Trata-se de um tema actual, de grande relevância e que vem merecendo interesse dos autores, entidades que vem trabalhando em prol do desenvolvimento de Moçambique. Índice 1. Política Centrada nas Micro, Pequenas e Médias Empresas: Situação, Justificação e Desafios 2. A Relevância da Dimensão da Empresa para a Reforma do Ambiente Empresarial. 3. O Perfil das PMEs em Moçambique 4. Enquadramento Legal das PMEs: Regime específico das Pequenas e Médias Empreas na Legislação Moçambicana 5. Importância, Ambiente de Negócios e Competitividade das PMEs 6. Financiamento e Serviços Financeiros para PMEs 7. Temas Seleccionados 8. Visão Política: Carta Moçambicana das Pequenas e Médias Empresas: Uma Proposta para a Assembleia da Republica
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; entrepreneurship / empreendedorismo

JICA in Mozambique Brochure - Japan International Cooperation Agency (JICA) (2016)
1. What is JICA? Since joining the Colombo plan in 1954, Japan has been providing financial and technical assistance to developing countries through ODA (Official Development Assistance). JICA is the "one stop shop of Japan's bilateral ODA'', providing Technical Cooperation, ODA Loans (Concessional Loans) and Grant Aid. JICA has a network of more than 90 overseas offices. In Mozambique, JICA opened office in 2003. 3. Priority Areas in Mozambique: 1) Activation of Regional and Local Economies 2) Environment and Climate Change Action 3) Human Development & Capacity Building
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Socio-economic impacts of private land use investment on rural communities: Industrial forest plantations in Niassa, Mozambique - Bleyer, Maja; Kniivilä, Matleena; Horne, Paula; Sitoe, Almeida; Falcão, Mário Paulo (Land Use Policy, 2016)
East Africa has experienced an increase of private land use investments in the past years. Rural households have consequently faced crucial changes in their livelihoods. This paper explores the socio-economic impacts of industrial forest plantations on rural communities in Niassa, Mozambique. According to our results private forest plantations have the potential to positively impact local people’s wealth and well-being, if enough emphasis is given to minimizing the negative impacts. The household survey data of 218 observations from five villages were analyzed using binary and multinomial logistic regression analyses. The study shows that forest plantations have threatened the basis of traditional rural livelihoods by reducing the availability of natural resources and through the relocation of agricultural plots. However, investments have also supported the diversification of livelihood strategies in the communities by providing formal employment and by increasing business and trading activities. As growing population and traditional agricultural practices have led to the overexploitation of natural resources, non-natural resource-based livelihood strategies increase the resilience of a household. The majority of respondents reported plantations to have either no overall impact or a positive impact on the well-being of their household. According to our results, socio-economic household characteristics only marginally explain respondents’ perceptions of the impacts of forest plantations but perceptions differ significantly between individual villages.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Overblown expectations of the mining sector - Economist Intelligence (Economist Intelligence, 2016)
The government of Mozambique remains confident that its mining boom is set to accelerate in the coming years, despite weak sentiment in the global mining industry. Rising coal production and an eventual rebound in global prices will spur some growth in Mozambique's mining sector in 2016‑20 but we expect that, weighed down by infrastructure deficits and non-competitive policies, it will remain a relatively small contributor to GDP growth. Mozambique has untapped coal reserves estimated to be in excess of 20bn tonnes, as well as commercial quantities of aluminium, gold, titanium, graphite and gemstones. Plus, it benefits from a long coastline and geographic proximity to mineral-hungry markets in Asia. At the peak of the commodity super-cycle, investor interest in Mozambican mining soared; the contribution of the mining sector to GDP increased from 1.6% in 2009 to 3.2% in 2013, while government earnings from the sector swelled from US$40m in 2009 to over US$1bn in 2014.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; extractive industries / indústrias extractivas; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Imagining Agricultural Development in South–South Cooperation: The Contestation and Transformation of ProSAVANA - Shankland, Alex; Gonçalves, Euclides (World Development, 2016)
This paper discusses South–South cooperation by examining ProSAVANA, a flagship agricultural development program seeking to apply Brazilian experience to Mozambique. ProSAVANA is a joint Japan–Brazil–Mozambique initiative in the savannah zone of Mozambique’s Nacala Corridor region that was initially inspired by the Japan–Brazil PRODECER program in Brazil’s Cerrado region. ProSAVANA subsequently became the focus of fears about land-grabbing in the Nacala Corridor, attracting strong civil society contestation. We show how distinct imaginaries of agricultural development in Mozambique and Brazil were used to mobilize for and against ProSAVANA, thus revealing the contentious nature of the similarity claims underpinning South–South cooperation. In particular, we focus on the role of landscape imaginaries associated with the savannah and the Cerrado. We examine the use in the promotion and contestation of ProSAVANA of visual representations that draw on these imaginaries, including GIS maps of Mozambique’s savannah region made by Brazilian agribusiness consultants and an advocacy video of Brazil’s Cerrado region filmed by Mozambican land rights activists. Noting that the latest ProSAVANA planning documents differ significantly from those expressing its initial vision, we argue that the contestation of ProSAVANA has had a series of productive effects even before the program has moved to full implementation. These productive effects are visible not only in the program itself but also in the wider context of state-society relations shaping debates on South–South cooperation in Mozambique, Brazil, and beyond.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; M - ethnography / etnografia; Northern PEA; agriculture / agricultura; south-south cooperation / cooperação sul-sul

Effects of food price shocks on child malnutrition: The Mozambican experience 2008/2009 - Arndt, Channing; Hussain, M. Azhar; Salvucci, Vincenzo; Østerdal, Lars Peter (Elsevier, 2016)
A propitiously timed household survey carried out in Mozambique over the period 2008/ 2009 permits us to study the relationship between shifts in food prices and child nutrition status in a low income setting. We focus on weight-for-height and weight-for-age in different survey quarters characterized by very different food price inflation rates. Using propensity score matching techniques, we find that these nutrition measures, which are sensitive in the short run, improve significantly in the fourth quarter of the survey, when the inflation rate for basic food products is low, compared to the first semester or three quarters, when food price inflation was generally high. The prevalence of underweight, in particular, falls by about 40 percent. We conclude that the best available evidence points to food penury, driven by the food and fuel price crisis combined with a short agricultural production year, as substantially increasing malnutrition amongst under-five children in Mozambique.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde; ⛔ No DOI found

Mozambique: Growth Corridors - ARUP (Arup and Cities Alliance, 2016)
This report relates to urbanisation as it is currently happening in Mozambique. It explores the present situation of cities and the government’s planned urbanisation strategy. It also discusses how the country plans to transition to a majority urban population. The report also discusses the impact of the urbanisation strategy on the regional development of the country through the promotion of growth corridors. To discuss this message, Future Cities Africa has selected three cities along the Nacala Corridor - Tete, Nampula, and Nacala - to explore current urbanisation trends and to highlight key challenges these cities may face in the future. This report relates to urban growth corridors in Mozambique and represents one of four reports prepared for Future Cities Africa. Each report covers a specific country, its national urbanisation strategy and its specific regional planning typology. The other three reports include metropolitan cities in Ghana, secondary cities in Uganda, and regional cities in Ethiopia
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; urbanization / urbanização

Body.: Illness, Memory, and the Dynamics of Healing - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
When residents of Chimoio and Honde talk of the forceful and potentially perilous dimensions of spirits, healing, and illness, they frequently relate them to tchianhu wo atewe. Spirits, which embody various potencies and capacities, are integral to diurnal and nocturnal lives in urban and rural contexts alike. As shown previously, a wide range of spirits exhibit dynamics of re-/deterritorialization. Further, people relate to ancestral spirits, so-called vadzimu, in annual private rituals to secure the well-being of their dzindza and household, or they participate in more elaborate communal rituals led by authorities like the tchirenge, who invoke the ancestors’ protection from
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Conclusion.: Uncapturability, Dynamics, and Power - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Ethnography harbors the power of critique—political, social, and theoretical. Ultimately a capacity to destabilize, this orientation also applies when writing an account of the violence inherent to processes of state formation in Mozambique. While such critical potential may be realized in a number of ways, here I have privileged perspectives forged on the margins of the centers of power, supplemented by historical sources. But there is more to it than this: by privileging a decentering of institution-based notions of the state informed by multiple readings of Deleuze, a wholly different picture of what a state is—and might be
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Economy.: Substance, Production, and Accumulation - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
In After Kinship (2004), Janet Carsten employs “substance” to delineate important dimensions of classical understandings of kinship and personhood. She does so by reinterpreting Schneider’s (1980) studies on American kinship and revisiting Marilyn Strathern’s (1988) analyses of Trobriand kinship and in/dividuality. Based on these reinterpretations and, more generally, extensive comparisons between Indian, Melanesian, British, and American cases, Carsten specifically recontextualizes and questions the components of kinship as code and substance as argued by Schneider. Concentrating on substance, she argues that the term has a range of different connotations but is used in diverse ways, ranging from the stuff of relations
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Law.: Political Authority and Multiple Sovereignties - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Since the General Peace Agreement was signed in 1992 the legal, administrative, and political sectors of Mozambique have undergone multiple reforms that have exposed the complexity of its historical trajectories of law, violence, and authority. From the perspective of those living in the impoverished and frequently dangerous and violent urban and peri-ur-ban bairros, a great variety of agencies and authorities can be approached at times of difficulty or trouble. These range from n’angas, profetes, and police agents to government bureaucrats and Frelimo secretaries. This chapter explores the general situation in the marginalized communities making up the rural-urban continuum of Chimoio
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Sovereignty.: The Mozambican President and the Ordering of Sorcery - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
Why does the Mozambican state attempt to control uroi —a force that is seemingly incompatible with the state rationale of both the postindependence Afro-Marxist era as well as the post–civil war period of neoliberal democracy? This chapter will broach this question through untangling the problematic relations between spirit and state within the context of AMETRAMO (Associação da Medicina Tradicional de Moçambique —the Association for Traditional Medicine in Mozambique), a state-sanctioned institution organizing so-called traditional healers. I will argue that the case of AMETRAMO exemplifies a statal mechanism for capture and control of the force fields and potencies of the
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Spirit.: Chiefly Authority, Soil, and Medium - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
This vision of sovereign power hovering above the relations between natural and human elements is relevant beyond genealogical analyses of biopower, pastoral power, and govenmentality. If we go beyond Foucault’s near exclusive context and subject of enquiry, Europe, these relations move to the forefront of social and political life. In Honde, crucial interconnections between polities of chiefly rule and traditional authority, cosmologies of land and the well-being of its inhabitants, and soil are present in a number of contexts. We have seen indications of this previously through Renamo’s appropriation of the traditional field, in Ngungunyane’s problematic relations with rainmaking capacities,
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Territory.: Spatio-Historical Approaches to State Formation - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
What does the notion of territory entail for state formation? As Elden (2013) has made clear in his recent genealogy of territory, it may be seen as a spatial extension of state power. While Elden’s point is crucial, in this chapter I will entertain the idea that the colonial state form is not different in its key dynamics from later state forms, as well as certain African polities, and in this way the chapter challenges the idea of the colonial state as radically different from earlier or later state forms. While basing myself on information from Manica Province, the empirical
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Violence.: War, State, and Anthropology in Mozambique - Bertelsen, Bjørn Enge (Violent Becomings, 2016)
How is one to make sense of state formation as a predominantly violent process? More concretely, how is one, as an anthropologist, to understand one’s interlocutors’ repeated insistence on life being a sustained period of suffering ( sofrimento )? One point at which to start is with the most recent large-scale period of violence, namely the Mozambican civil war (1976–92). During this phase of violent upheaval, the traditional field was implicated in complex ways and its reality as a domain of the potential was actualized in various manners vis-à-vis state dynamics and war machine dynamics. By describing the civil war as
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Civil society organisations’ political control over Brazil and Japan’s development cooperation in Mozambique: More than a mere whim? - Chichava, Sérgio; Durán, Jimena (LSE Global South Unit, 2016)
This article aims to analyse and explain the reasons behind the CSOs’ strong criticism of the ProSavana programme. This will contribute toward: (1) understanding the role of Mozambican CSOs as actors regulating international development cooperation projects; (2) revealing the political and economic interests behind ProSavana, as a first step toward a more critical approach to trilateral cooperation; and (3) illustrating through this case how a partnership between Brazil and “traditional” donors actually works. Firstly, we will analyse the cooperation policies of Brazil and Japan in Mozambique, taking into account its evolution, actors, mechanisms and motives. Secondly, we will introduce ProSavana, examining the narratives and roles of Japan and Brazil in this programme. Thirdly, we will consider the engagement of CSOs from the three countries, their role in exerting a political check on the Brazilian and Japanese governments, investors, and companies, as well as their narratives and mechanisms of protest.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; civil society / sociedade civil; development partners / parceiros de cooperação

Porquê o conflito armado em Moçambique? Enquadramento teórico, dominância e dinâmica de recrutamento nos partidos da oposição - Cortês, Emmanuel de Oliveira (2016)
A partir de um modelo de previsões sobre dominância e a dinâmica de recrutamento nos partidos da oposição em sistemas de partido dominante, pretendeu-se perceber as dinâmicas do conflito político em Moçambique que culminaram com o agravamento da tensão militar entre as forças armadas do Governo moçambicano, e o maior partido da oposição, a RENAMO. Pode-se tomar como hipóteses que a assimetria de recursos entre o partido dominante no poder, a FRELIMO, e o maior partido da oposição, bem como os custos assimétricos de filiação à oposição, contribuiram para a radicalização da postura do maior partido da oposição, que se insurgiram militarmente para expressar a sua insatisfação. Dado ao facto dos militantes partidários que visam ocupar cargos públicos priorizarem a vitória nas eleições, valida-se a hipótese que os militantes da RENAMO que almejam tais cargos, tornaram-se mais sensíveis as vantagens dos recursos do partido FRELIMO, como denota-se em certos discursos feitos à imprensa. Mas por outro lado, se as vantagens dos recursos entre a FRELIMO e a RENAMO forem mais simétricas, os mesmos militantes da oposição poderão moderar suas posições. Devido ao facto do partido dominante possuir mais recursos que a oposição, o número de militantes da oposição, bem como da RENAMO, que almejam cargos públicos será menor. Porém, quando os recursos que os partidos dominantes possuem entram em declínio- geralmente em períodos de crises económicas, quando os Governos são coagidos a reduzir o tamanho do setor público, principal fonte de recursos para o partido dominante-, o número de militantes da oposição que almejam cargos públicos aumenta. Com o agravar da crise da dívida pública moçambicana, e consequente declínio de recursos do partido dominante, a proporção de militantes na oposição (em especial na RENAMO) que visam adquirir cargos públicos poderá aumentar. Mas como as vantagens detidas pelo partido dominante, a FRELIMO, ainda são maiores, a oposição continuará apresentando um número de votos mais baixo.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; conflict - civil war / conflito - guerra civil; conflict / conflito; ⛔ No DOI found

Desafios para Moçambique - 2016 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2016)
PARTE I – POLÍTICA Instituições Políticas e Unidade Nacional / Luís de Brito Para Onde Vamos? Dinâmicas de Paz e Conflitos em Moçambique / João C. G. Pereira Democracia e Municipalização em Moçambique: Gradualismo, participação local e serviços básicos / Salvador Forquilha PARTE II – ECONOMIA Inflação e Pobreza – Uma perspectiva macroeconómica / Marc Wuyts Estrutura da Dívida Pública em Moçambique e a sua Relação com as Dinâmicas de Acumulação / Fernanda Massarongo Chivulele Dilemas da Industrialização num Contexto Extractivo de Acumulação de Capital / Carlos Nuno Castel-Branco Desenvolvimento Centrado em PME? Problematização crítica desta abordagem / Carlos Nuno Castel-Branco Produtividade Agrícula, Planeamento e Cultura do Trabalho em Moçambique / Bridget O’Laughlin Emprego e Condições Sociais de Trabalho nas Agro-Indústria – Contradições e desafios / Rosimina Ali e Carlos Muianga PARTE III – SOCIEDADE Estratégia de Crescimento Económico em Moçambique – Desta vez é direfente? / António Francisco, Moisés Siúta e Ivan Semedo Relações Rural Urbano, Transferências Pessoais e Políticas Públicas – Uma análise a partir de populações residentes na cidade de Maputo / João Feijó e Momade Ibraimo O Desafio da Gentrificação na Cidade de Maputo – Reflexões sobre o sistema habitacional, a política social de habitação e a exclusão social / Michael Godet Sambo PARTE IV – MOÇAMBIQUE NO MUNDO A Sociedade Civil e o Pro-Savana em Moçambique / Sérgio Chichava A Grécia e Moçambique: Dilemas, lições e opções de luta / Carlos Nuno Castel-Branco
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Social protection reform in Mozambique and the new basic social security strategy - Falange, Sergio; Pellerano, Luca (IPC-IG One Pager, 2016)
In the framework of efforts to fight extreme poverty and recognising the importance and need to protect the poor and vulnerable population, in 2007 Mozambique approved Law No. 4/2007 which structured social protection into three levels, including basic social security. In 2010 the first National Basic Social Security Strategy (ENSSB I) was approved for the period 2010–2014, including a set of old (e.g. the Basic Social Security Programme—PSSB) and new (e.g. the Productive Social Action Programme—PASP) non-contributory social protection programmes, all implemented by the National Institute for Social Action (INAS) under the policy guidance of the Ministry of Gender, Child and Social Action (MGCAS).
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

Public Policies and Private Interests: An Analysis from the Nacala Corridor in Mozambique - Garcia, Ana; Kato, Karina; Garcia, Ana; Kato, Karina (Caderno CRH, 2016)
A política externa brasileira, a partir de 2003, apresentou uma notória curva em direção ao aprofundamento e à expansão das relações com outros países e regiões “do Sul global”. Nesse contexto, o continente africano ganhou importância para as relações internacionais do Brasil. O objetivo do artigo é avançar na compreensão da participação do setor empresarial na cooperação brasileira em Moçambique. Os resultados demonstram que as empresas e seus projetos privados se mesclam nos territórios. Examinaremos o caso do corredor logístico de Nacala, interseção das principais e maiores iniciativas de cooperação e de investimento de empresas brasileiras em Moçambique. O cenário construído nos mostra um tabuleiro no qual a cooperação Sul-Sul e, dentro dela, a cooperação brasileira, não podem ser compreendidas sem serem considerados sua relação com os interesses e investimentos empresariais, o jogo de poder com outros países e as políticas de instituições multilaterais como o Banco Mundial.
Keywords: G - Mozambique / Moçambique; L - english / inglês; infrastructure / infrastrutura; south-south cooperation / cooperação sul-sul

Estratégia Nacional de Segurança Social Básica 2016-2024 - Governo de Moçambique (Governo de Moçambique, 2016)
a Estratégia Nacional de segurança social Básica (ENssB) 2016-2024 visa a materialização do Programa Quinquenal do governo 2015-2019, através da implementação de acções que concorrem para a redução da pobreza e da vulnerabilidade, assegurando que os resultados do crescimento da economia moçambicana beneficiem a todos os cidadãos, sobretudo os que vivem em situação de pobreza e de vulnerabilidade. A elaboração da presente Estratégia teve como base as metas definidas na Estratégia Nacional de Desenvolvimento 2015-2035, a Agenda 2063 da União Africana, os Objectivos de Desenvolvimento Sustentável, aprovados pelas Nações Unidas que, no seu conjunto, enfatizam a abordagem dinâmica e promocional da protecção social e o potencial dos instrumentos de segurança social básica para reforçar o capital humano, produtivo e social assim como a capacidade de resiliência dos agregados familiares e indivíduos mais vulneráveis. Esta estratégia pretende continuar com as acções levadas a cabo, desde a adopção da Lei de Protecção Social em 2007, para construir um sistema eficaz e eficiente de segurança social básica e apresenta uma abordagem integral para a protecção social dos grupos mais desfavorecidas da população moçambicana, definindo as linhas orientadoras para o reforço da sua capacidade de protecção contra os riscos sociais de modo que saiam da situação de vulnerabilidade numa base sustentável a longo prazo. A ENSSB 2016-2024 foi elaborada, considerando o perfil de vulnerabilidades e de riscos no país, as funções da segurança social básica e o diagnóstico da situação actual do sistema, apresentando os seguintes objectivos: 1) Reforçar o nível de consumo e a resiliência das camadas pobres e vulneráveis da população; 2) Contribuir para o desenvolvimento do capital humano, através da melhoria de nutrição e do acesso aos serviços básicos de saúde e educação das camadas pobres e vulneráveis da população; 3) Prevenir e responder aos riscos de violência, abuso, exploração, discriminação e exclusão social, através de serviços de acção social, e 4) Desenvolver a capacidade institucional para a implementação e coordenação do subsistema de segurança social básica. Para a operacionalização destes objectivos, a ENSSB 2016-2024 estrutura-se em quatro eixos de intervenção, nomeadamente: » Eixo 1: Reforço do consumo, da autonomia e da resiliência; » Eixo 2: Melhoria da nutrição e do acesso aos serviços de saúde e de educação; » Eixo 3: Prevenção e resposta aos riscos sociais; e » Eixo 4: Desenvolvimento institucional. Eixo 1: operacionaliza o primeiro objectivo da estratégia e engloba as acções que visam reforçar, no sistema de segurança social básica, as funções de compensação devido a velhice e incapacidade funcional, a redução da pobreza e da desigualdade social e a promoção da autonomia e resiliência das camadas pobres e vulneráveis da população. Prevê-se introduzir modificações no Programa Subsídio Social Básico para estabelecer os subsídios para a pessoa idosa e de incapacidade funcional. Através deste Eixo será expandido o actual Programa de Acção Social Produtiva (PASP) e reforçado o seu papel na promoção da autonomia e graduação dos seus beneficiários em situação de pobreza. Outro aspecto incluso no presente Eixo é o fortalecimento do papel da segurança social básica na resposta a choques. Eixo 2: focaliza-se nas acções que promovem o desenvolvimento do capital humano, através da melhoria da nutrição e do acesso aos serviços de saúde e educação (objectivo 2). Neste eixo estão enquadrados os subsídios para a criança. Eixo 3: diz respeito aos Serviços de Acção Social que visam prevenir e responder aos riscos sociais que afectam principalmente crianças, mulheres, pessoas idosas, pessoas com deficiência e pessoas afectadas pelo HIV e SIDA (objectivo 3). Eixo 4: Centra-se nas acções de desenvolvimento institucional (objectivo 4) requeridas para reforçar a capacidade de implementação dos primeiros três eixos a todos os níveis (central, provincial e distrital). Estão previstas na Estratégia acções para o reforço da coordenação intersectorial e a monitoria dos resultados da implementação da ENSSB 2016-2024, através do Conselho Nacional de Acção Social (CNAS). Espera-se que com a implementação da presente Estratégia sejam alcançados 3.352.515 beneficiários directos e um total de 8.274.789 beneficiários indirectos, devendo ser alocado um orçamento correspondente a 2.23% do PIB até 2024
Keywords: #Policy Document / Documento de Política; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social security / segurança social; government policy / politica governamental; social protection / proteção social

The promotion of decentralisation and local governance in fragile contexts - Grävingholt, Jörn; von Haldenwang, Christian (Deutsches Institut für Entwicklungspolitik gGmbH, 2016)
The promotion of decentralisation and local governance has long since been an established part of bilateral and multilateral development cooperation. In the context of fragile statehood, however, this area of development cooperation is frequently faced with the general suspicion of encouraging separatism, exacerbating conflicts, and thereby promoting the disintegration of the state. At the same time, fragile contexts create demand for institutional solutions concerning the distribution of tasks, responsibilities, resources and political power between the various different levels of the state. This paper provides an overview of the challenges regarding support to decentralisation and local governance in fragile contexts. It discusses risks and opportunities, and develops suggestions on how development cooperation can better rise to the challenges surrounding the promotion of decentralisation in fragile states. Against this background the authors advocate an ambitious approach which understands the promotion of decentralisation as being a contribution to overcoming fragility and to the structural alleviation of conflict situations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização

Corporate Social Responsibility in Mozambique - Kaufmann, Friedrich; Simons-Kaufmann, Claudia (Corporate Social Responsibility in Sub-Saharan Africa: Sustainable Development in its Embryonic Form, 2016)
Mozambique is a young African country with a strong growing economy and increasing foreign direct investment. We can observe a rising number of Corporate Social Responsibility (CSR) projects and activities in the country. Nevertheless there is still no systematic approach or coordination through public authorities or the business sector itself. CSR is mainly motivated by immediate own company needs like training or health of workers. We also find philanthropy projects as well as projects supporting local communities on development priorities, mainly health, education and community development. CSR, as part of a business concept, is mainly limited to large companies and foreign investors with international experience and less to small and medium-sized enterprises (SMEs). Many national companies, especially SMEs still do not have the CSR capacity or the respective mind set. First of all it is the mega projects that have their professional CSR departments and budgets. In the mining sector a CSR component is now compulsory by law since 2014.As public institutions are weak, CSR in Mozambique is more about “CSR towards compliance” and sometimes less about “CSR beyond compliance”. Strong views are expressed by civil society that for example the enforcement of labour legislation within companies is weak and hardly controllable by the government. This fact combined with corruption issues makes CSR towards compliance of existing labour, environmental, fiscal laws and other regulation an important topic. Nevertheless it is questionable if this should be considered as CSR. CSR in general is sometimes seen as “green washing” by big investors, benefitting on the other hand from generous tax exemptions and special deals with the government. Nevertheless, CSR is of growing importance in Mozambique and as the new mining CSR law shows, government is slowly entering the CSR landscape. A better coordination and public-private dialogue about CSR is necessary in order to make it a more useful and an efficient instrument for development. Nevertheless it should be clear that CSR is voluntary and in a globalized economy with international value chains becomes more and more an international issue.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado

Barriers and facilitators to health care seeking behaviours in pregnancy in rural communities of southern Mozambique - Munguambe, Khátia; Boene, Helena; Vidler, Marianne; Bique, Cassimo; Sawchuck, Diane; Firoz, Tabassum; Makanga, Prestige Tatenda; Qureshi, Rahat; Macete, Eusébio; Menéndez, Clara; von Dadelszen, Peter; Sevene, Esperança (Reproductive Health, 2016)
Background: In countries, such as Mozambique, where maternal mortality remains high, the greatest contribution of mortality comes from the poor and vulnerable communities, who frequently reside in remote and rural areas with limited access to health care services. This study aimed to understand women’s health care seeking practices during pregnancy, taking into account the underlying social, cultural and structural barriers to accessing timely appropriate care in Maputo and Gaza Provinces, southern Mozambique. Methods: This ethnographic study collected data through in-depth interviews and focus group discussions with women of reproductive age, including pregnant women, as well as household-level decision makers (partners, mothers and mothers-in-law), traditional healers, matrons, and primary health care providers. Data was analysed thematically using NVivo 10. Results: Antenatal care was sought at the heath facility for the purpose of opening the antenatal record. Women without antenatal cards feared mistreatment during labour. Antenatal care was also sought to resolve discomforts, such as headaches, flu-like symptoms, body pain and backache. However, partners and husbands considered lower abdominal pain as the only symptom requiring care and discouraged women from revealing their pregnancy early in gestation. Health care providers for pregnant women often included those at the health facility, matrons, elders, traditional birth attendants, and community health workers. Although seeking care from traditional healers was discouraged during the antenatal period, they did provide services during pregnancy and after delivery. Besides household-level decision-makers, matrons, community health workers, and neighbours were key actors in the referral of pregnant women. The decision-making process may be delayed and particularly complex if an emergency occurs in their absence. Limited access to transport and money makes the decision-making process to seek care at the health facility even more complex.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - south / sul; GP - Gaza; GP - Maputo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

For an efficient, decentralised, transparent and inclusive health system - N'weti (N'weti, 2016)
Recommendations: 1. On planning and budgeting, greater coordination is recommended between planning (setting priorities) and budgeting (financial apportionment). Transformation of all District Health Services, Women and Social Action (SDSMAS) into Management Beneficiary Units (MBU) is necessary. 2. Stakeholders should bet more on application of national public financial management systems (PFM). The use of parallel financial systems instead of enabling the National Health System (NHS) to be more e cient hinders the enhancement of the sector’s PFM systems. 3. With regard to budgeting, zero-based budgeting implementation is recommended, replacing the incremental budgeting system. Zero-based budgeting is more realistic in so far as the health sector operation costs are concerned. 4. On the decentralisation and citizen participation component, the establishment of a national plan for decentralisation in the health sector is recommended. This plan would allow systematise local citizen participation mechanisms in the health system management and monitoring. 5. On revenue collection, the sector authorities need to explore areas of potential revenue already identified in Intellica’s 2013 research report, such as drug prescription, outpatient, medical certificate rates; and comply with the Decree 11/2007 of 30 May, which regulates tobacco consumption and sale, which has great potential to generate revenue for the health sector at the district level, by means of fines on the lawbreakers. 6. A Policy Brief drawn from the Public Expenditure Tracking Survey (PETS) in the Health Sector in Angoche, Bilene, Magude and Xai-Xai districts, and Chamanculo and José Macamo General Hospitals On expenditure performance, more and better coordination among stakeholders at district levels and Health Centres is recommended in order to avoid expenditure implementation costs in a fragmented and uncoordinated manner. 7. On procurement, accuracy improvement is recommended for the current legal framework implementation. This is to ensure that Procurement Management Units (PMUs) are practical; they can perform their tasks with independence, impartiality and professionalism. The direct award should always be treated as provided for in the law (an exception) and not deemed as the rule like what we have noticed occur in the researched cases. The document disorderliness of the Procurement Management Units portfolios can be solved with portfolio digitisation, ensuring more and better file and document handling, more control and additional transparency. 8. On transparency, recommendation to the Ministry of Health (MoH) is on the establishment of mechanisms which may ensure that sector o cials, who handle equal duties, should have the same understanding about procedures, not only in the health sector, but also in liaison with other sectors and society in general. When applying the Right to Information Act, Civil Society Organizations (CSOs) should now carry out awareness raising sessions and dialogue with sector o cials in order to reach mutual understanding on the added value that represents transparent public service management, with accountability and civil society influence, through monitoring and evaluation.
Keywords: *indexed; *non-public; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; GD - Bilene; GD - Magude; GD - Xai-Xai; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; budget / orçamento; decentralization / descentralização; health / saúde

Estrutura Geológica de Moçambique - Nogar Boca (2016)
Tema: Estrutura Geológica de Moçambique A estrutura geológica de Moçambique é resultado da interacção de vários processos, sobretudo os endógenos (internos) e exógenos (externos), que se fizeram sentir e ainda sentem-se na actual região da África Austral, onde Moçambique faz parte. Do ponto de vista geológico, Moçambique apresenta duas grandes unidades geológicas: Pré-câmbrico Fanerozóico
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; natural resources / recursos naturais

Mozambique Early Generation Seed Study - USAID (Scaling Seeds and Technologies Partnership in collaboration with The Rutgers University, 2016)
Seed systems in Mozambique There are three identified dominant seed systems in Mozambique, namely informal seed system (mainly farmer-saved seed), the intermediary (mainly administered by the NGOs and communitybased organizations) and the formal seed system that includes public sector and private sector (local and international seed companies). The farmer-saved and intermediary systems account for the bulk of seed volume transacted across the country (90%) focusing mainly on the local varieties. Although the adoption rate is relatively high for cassava, there is no vegetative seed certification system in place. There is no official sesame variety, despite an over three-fold increase in the last 12 years in terms of the total area allocated to this crop. Early generation seed systems by crop Six crops selected for the Mozambique EGS case study were maize (hybrid and OPV), rice, cowpea, groundnut, soybean and cassava
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Mapping the use of research to support strategies tackling maternal and child health inequities: evidence from six countries in Africa and Latin America - Vargas, Emily; Becerril-Montekio, Victor; Gonzalez-Block, Miguel Ángel; Akweongo, Patricia; Hazel, Cynthia N. A.; Cuembelo, Maria de Fatima; Limbani, Felix; Bernardo, Wanderley; Muñoz, Fernando (Health Research Policy and Systems, 2016)
Background: Striving to foster collaboration among countries suffering from maternal and child health (MCH) inequities, the MASCOT project mapped and analyzed the use of research in strategies tackling them in 11 low- and middle-income countries. This article aims to present the way in which research influenced MCH policies and programs in six of these countries – three in Africa and three in Latin America. Methods: Qualitative research using a thematic synthesis narrative process was used to identify and describe who is producing what kind of research, how research is funded, how inequities are approached by research and policies, the countries’ research capacities, and the type of evidence base that MCH policies and programs use. Four tools were designed for these purposes: an online survey for researchers, a semi-structured interview with decision makers, and two content analysis guides: one for policy and programs documents and one for scientific articles. Results: Three modalities of research utilization were observed in the strategies tackling MCH inequities in the six included countries – instrumental, conceptual and symbolic. Instrumental utilization directly relates the formulation and contents of the strategies with research results, and is the least used within the analyzed policies and programs. Even though research is considered as an important input to support decision making and most of the analyzed countries count five or six relevant MCH research initiatives, in most cases, the actual impact of research is not clearly identifiable. Conclusions: While MCH research is increasing in low- and middle-income countries, the impact of its outcomes on policy formulation is low. We did not identify a direct relationship between the nature of the financial support organizations and the kind of evidence utilization within the policy process. There is still a visible gap between researchers and policymakers regarding their different intentions to link evidence and decision making processes.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; government policy / politica governamental; health - maternal and child / saúde - materno-infantil; health / saúde

Política Monetária e a Agricultura Em Moçambique - Abbas, Máriam (Observatório do Meio Rural, 2015)
Este estudo pretende verificar a causalidade de curto e longo prazo entre a política monetária e a produção agrícola em Moçambique. Para esse efeito estudar-se-ão variáveis como taxas de juros, oferta monetária, inflação, taxa de câmbio e crédito agrícola.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura

Ex-Post Project Evaluation 2014 (Mozambique, Bhutan, Palestine) - JICA (Japan International Cooperation Agency (JICA), 2015)
The project’s objective was to improve access to lower secondary education, by constructing 4 schools and extending the capacity of existing schools and their facilities in the target areas of Maputo Province and Gaza Province, thereby contributing to improvement of the quality of education. The project’s objective coincides with the development policy of Mozambique, which emphasizes the expansion of access to secondary education at the time of planning and also ex-post evaluation. It also coincides with the development needs of Mozambique, because there are very strong needs for the construction of secondary schools in order to respond to the rapid increase in the number of students who wish to receive secondary education. It was also relevant to Japan’s ODA policy at the time of planning. Thus, its relevance is high. The project cost and the project period are the same as planned, thus its efficiency is high. As to the effects of the project, 4 schools and 58 classrooms were constructed as planned, the number of students enrolled at those schools exceeded the original target, and other positive effects were revealed in terms of the access to secondary education such as improvement of educational environment and reduction in commuting time to schools. Thus, its effectiveness is high. There were some negative impacts of the project; for example, the IT classrooms of some schools were not utilized as planned, and the promotion rate declined in some grades of 2 schools in Maputo Province partly because the number of students per classroom far exceeded the capacity of the classroom. On the other hand, there were some positive indirect impacts as planned; the promotion rate improved in 2 schools in Gaza Province, and the learning attitudes of students and teaching attitudes of teachers also improved. Thus, the project’s effectiveness and impact are high. As to the aspects of operation and maintenance (O&M), there were no serious problems in the technical aspect, but there were some problems in the institutional and financial aspects, as well as the O&M situations. Thus, sustainability of the project is fair. In the light of the above, this project is evaluated to be highly satisfactory.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; development partners / parceiros de cooperação; education / educação

O papel da educação para a igualdade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 2005-2015 - Lucas, Geraldo Cebola João (Revista Litteris, 2015)
Este artigo tem como objecto “o contributo da educação para a equidade de género e empoderamento da mulher em Moçambique: o caso da cidade de Lichinga, 1997-2015”. O terceiro objectivo do milénio defende que para que possa alcançar o desenvolvimento sustentável nos países em vias de desenvolvimento e mesmo os já industrializados é preciso que a questão de género seja tomada como primordial nas políticas e estratégias de desenvolvimento. E tal pressuposto requer, como se defende nos objectivos, uma equidade de género e seu paralelo empoderamento. Porque acredita-se que a questão de género é transversal. É preocupação nesta pesquisa verificar se as políticas de género em Moçambique estão em consonância com o terceiro objectivo do milénio. Em segundo lugar, verificar o grau do cumprimento do terceiro objectivo do Milénio na cidade de Lichinga. A pesquisa é norteada pela seguinte pergunta de pesquisa: “ em que medida as políticas da educação moçambicana têm contribuído para a equidade e empoderamento do género no quadro do terceiro objectivo do milénio?”.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - portuguese / português; education / educação; empowerment / empoderamento; gender / género; youth / juventude

EU & Partners' Country Roadmap for Engagement with Civil Society: 2016-2019 - Government of Canada; Government of Switzerland; UNICEF; USAID (Governments of Canada, Switzerland, UNICEF, USAID, 2015)
Study commissioned by EU and other countries on CSO engagement. The identification of priorities is based on four criteria: • The findings of the recent mapping of civil society in Mozambique commissioned by the EU and other studies; • The official EU guidance on the preparation of a civil society roadmap; • Existing and planned EU interventions and of the partners engaged in the roadmap; • The need to combine a longer term perspective with concrete actions over the next 3 years. The priorities constitute primarily a common agenda that will shape and orient discussions and collaboration between the roadmap partners. It allows situating individual interventions in a broader collective framework and as such adds a strategic dimension to programming.
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação

FIFTY YEARS OF TRADE POLICY IN INDONESIA: NEW WORLD TRADE, OLD TREATMENTS - Pangestu, Mari; Rahardja, Sjamsu; Ing, Lili Yan (Bulletin of Indonesian Economic Studies, 2015)
Indonesia's trade policy has evolved over the last 50 years. It has been influenced by the country's level of development and the conflict between openness and protectionism; external developments, such as commodity booms and busts and increased competition; and international commitments, whether multilateral or regional. As a result, trade policy has often been ambivalent and ineffective. Given that Indonesia has undergone various transformations and that the world is a different place from what it was in 1965, the country needs to take a more pragmatic and forward-looking stance. Trade policy needs to be part of a comprehensive strategy to improve competitiveness and diversify exports. If Indonesia is to be part of the new paradigm, where the production of goods and services is based on production networks and global value chains, its policy focus will need to shift from protecting and favouring sectors to promoting trade and industrial policies that encourage the flow of goods, services, and people.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Relatório do Estudo sobre a Sustentabilidade das Organizações da Sociedade Civil (versão final) - Eurosis (Eurosis, 2015)
O presente documento constitui o Relatório do Estudo de Sustentabilidade das Organizações da Sociedade Civil solicitado por 5 Organizações Não Governamentais (DIAKONIA, FHI360, HELVETAS, KEPA e OXFAM NOVIB) e realizado pela EUROSIS Consultoria e Formação em Gestão. De forma sintetizada, este estudo tinha como objectivos chave: a) mapear o entendimento que a governação e gestão das OSC têm sobre sustentabilidade e seus desafios; b) ajudar a desconstruir a percepção que limita a sustentabilidade à viabilidade económico-financeira das OSC, trazendo à superfície outras dimensões também relevantes para o efeito; c) recomendar acções para a tomada de decisão dos diversos actores que trabalham no fortalecimento das OSC. Tendo em consideração os seus objectivos, este estudo está estruturado em quatro componentes chave: • revisão de literatura internacional para identificação de factores que, de acordo com pesquisa internacional, influenciam sustentabilidade de OSC. • recolha de dados (através de questionários auto-administrados, entrevistas face-a-face e workshops) para o levantamento de percepções e opiniões de OSC com relação ao conceito de sustentabilidade, limitantes colocadas pelo contexto moçambicano à sustentabilidade de OSC, fragilidades das próprias OSC que não ajudam à sustentabilidade). Importa referenciar que para a recolha de dados: 79 representantes de 62 OSC preencheram o questionário online; foram realizadas 19 entrevistas semiestruturadas e em profundidade; e foram realizados três workshops em Maputo, Chimoio e Nampula com a participação de 69 representantes de 54 OSC. • análise e conclusões que incluiu: a) comparação dos factores mencionados em literatura internacional com os mencionados pelos respondentes no estudo para identificação de factores comuns e identificação daqueles que não parecem estar no campo das preocupações ou prioridades da maior parte das OSC respondentes; b) tendo em consideração a comparação anterior, elaboração de proposições sobre os factores que, na nossa opinião, afectam ou limitam a sustentabilidade de OSC em Moçambique. • recomendações elaboradas com base na análise e nas conclusões apresentadas
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil

PEDEC-NACALA Final Study Report Analysis Report: Strategic Master Plan on Strengthening of Nacala Corridor Region-Wide Freight Network for Agricultural and Mining Sectors - Oriental Consultants Global Co., Ltd.; RECS International Inc.; International Development Center of Japan Kokusai Kogyo Co., Ltd. (Japan International Cooperation Agency (JICA), 2015)
This document was prepared as an analysis report for sharing a study result on a particular theme as part of ‘The Project for Nacala Corridor Economic Development Strategies (PEDEC-Nacala)’ which is a technical assistance project supported by Japan International Cooperation Agency (JICA) for the Government of Mozambique. PEDEC-Nacala formulated integrated development strategies for corridor development by an integrated approach involving several sectors and also by giving consideration to environmental and social aspects. The actual strategies formulated in PEDEC-Nacala and details of the present situation of the Nacala Corridor Region are compiled into the PEDEC-Nacala Final Study Report
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura

When do relative prices matter for measuring income inequality? The case of food prices in Mozambique - Jones, Sam; Salvucci, Vincenzo; Arndt, Channing (The Journal of Economic Inequality, 2015)
Changes in relative prices of commodities consumed in different shares across income groups can be expected to alter real income differentials between these groups. Using Mozambican household budget survey and price data from 2002/03 and 2008/09, we show that once relative price increases are accounted for, inequality of real consumption increases substantially. We obtain this result by constructing a price deflator that reflects divergent price dynamics of different product categories. Since the main factors driving this result prevail in other developing countries, it is likely that inequality may be underestimated elsewhere.
Keywords: G - Mozambique / Moçambique; L - english / inglês; income inequality

Estratégia da Suécia para a cooperação para o desenvolvimento com Moçambique, 2015-2020 - Ministry for Foreign Affairs - Sweden (Ministry for Foreign Affairs - Sweden, 2015)
Within the framework of this strategy, Swedish development cooperation with Mozambique aims to make use of the increased interest and potential to utilise the country's natural resources in a socially, economically and environmentally sustainable way. It also aims to improve opportunities for people living in poverty to contribute to and benefit from economic and democratic development. The strategy is valid for the period 2015–2020 and comprises a total of SEK 4.1 billion.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; natural resources / recursos naturais

Strategy for Sweden’s development cooperation with Mozambique, 2015–2020 - Ministry for Foreign Affairs - Sweden (Ministry for Foreign Affairs - Sweden, 2015)
Within the framework of this strategy, Swedish development cooperation with Mozambique aims to make use of the increased interest and potential to utilise the country's natural resources in a socially, economically and environmentally sustainable way. It also aims to improve opportunities for people living in poverty to contribute to and benefit from economic and democratic development. The strategy is valid for the period 2015–2020 and comprises a total of SEK 4.1 billion.
Keywords: G - Mozambique / Moçambique; L - english / inglês; economic development / desenvolvimento económico; natural resources / recursos naturais

Business licensing: a key to investment climate reform - Ing, Lili Yan; Magiera, Stephen; Widiana, Anika (ERIA, 2015)
Reforming business licensing is a key starting point for improving the investment climate. Complex licensing procedures may encourage firms to remain unregistered, giving rise to difficulties later in accessing finance from formal financial institutions and constraining productivity and expansion. Across sectors, this can suppress the establishment of new firms and therefore the creation of new jobs, dragging down overall economic growth. Improving and reforming business licensing can significantly increase the number of businesses and thus help nurture employment creation. Several quick-win interventions are possible. First, there is a need to improve the quality of the business licensing website and help desk. The website and help desk should act as a frontline in dealing with investment regulations and policies for investors. Improvements should cover both hard and soft infrastructure of the website and help desk, including the skills of officials. Second, business license simplification should be continued by limiting licenses to those that serve their objective and cutting unnecessary licenses, and or consolidating licenses. Third, full implementation of electronic application and payment systems for business licenses should be fostered, together with increasing the nonfiscal incentives for firms to become registered. The registration system should also function as a nationwide database which could then be a source of reliable information both on firms and for firms, linked to government programs and grants, and business regulation updates. Fourth, a transparent system to show the progress of each business application should be set up, together with a recorded evaluation system in which users can provide feedback to improve the system. Finally, efforts in the medium term should focus on improving coordination among government agencies and clarifying the roles of central and local regulations, both horizontally and vertically.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

The land grabbers of the Nacala Corridor - UNAC (GRAIN, 2015)
A new report by Mozambique's National Farmers' Union (UNAC) and GRAIN shows there is a colonial-style scramble for Africa's farm lands under way. Politically-connected companies based in offshore tax havens have grabbed hundreds of thousands of hectares of farmland from peasants in Mozambique.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; Important; L - english / inglês; Northern PEA; law / direito

Growth, capital accumulation and economic porosity in Mozambique: social losses, private gains - Castel-Branco, Carlos Nuno (Review of African Political Economy, 2015)
The Mozambican economy has been growing at an annual average of 7.5% for the best part of two decades, and has become one of the three most attractive economies for foreign direct investment (FDI) in sub-Saharan Africa. Yet, it has been ineffective and inefficient at reducing poverty and providing a broader social and economic basis for development. It is argued here that the dominant political economy of Mozambique is focused on three fundamental and interlinked processes, namely the maximisation of inflows of foreign capital - FDI or commercial loans - without political conditionality; the development of linkages between these capital inflows and the domestic process of accumulation and the formation of national capitalist classes; and the reproduction of a labour system in which the workforce is remunerated at below its social cost of subsistence and families have to bear the responsibility for maintaining (especially feeding) the wage-earning workers by complementing their wages or trying to maintain the availability of the enormous idle reserve of labour. This article focuses on economic porosity, which, arguably, is a dominant factor in promoting the linkages between domestic and foreign capital, nurtured, supported and mediated by the state.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Accountability Through Active Citizenship: Improving Petroleum Governance in Ghana, Mozambique & Tanzania - Arregui, Chiqui (Oxfam America, 2015)
The objective of the baseline survey is to analyze and document the situation around accountability, transparency and governance of the O&G sector in the country prior to the implementation of the Oxfam project. It focuses on a selected group of indicators chosen for the country program logical framework, identified and approved in the Baseline Inception Phase. A total of 33 people were interviewed in the context of this baseline. This was accompanied by a thorough national and international literature review. It was not possible to gain access to some key Government and CSO representatives at sub-national level and any of the three O&G companies contemplated in the context of this baseline, which could affect the comprehensiveness of findings. It is expected that a similar exercise be conducted at the end of the program to gauge the changes brought about by program interventions. The fieldwork for the baseline was conducted in December 2014. Baseline findings are presented in line with program outcomes, broadly focusing on building the capacities of (i) communities (Outcome 1); (ii) CSOs and the media (Outcome 2) and (iii) Other stakeholders (Outcome 3).
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; governance / governação

A Macroeconomia e a Produção Agrícola em Moçambique - Abbas, Máriam (Observatório do Meio Rural, 2015)
Este trabalho procura verificar a relação entre variáveis macroeconómicas e a produção agrícola em Moçambique. O sector agrícola desempenha um papel fundamental no desenvolvimento da economia moçambicana. Assim sendo, torna-se importante compreender a relação entre o ambiente macroeconómico e o sector. De acordo com Ali et al. (2010) a economia agrícola mundial tem sido substancialmente sensível aos movimentos dos indicadores macroeconómicos. Vários investigadores e economistas concordam que as alterações na política macroeconómica têm, muitas vezes, um impacto significativo na economia agrícola. Sendo assim, o sector agrícola não deve ser tratado como um sector fechado às alterações estruturais no ambiente macroeconómico e à integração dramática nos mercados internacionais, Schuh (1976) em Letsoalo e Kirsten (2003).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; economic development / desenvolvimento económico

Challenges and opportunities for implementing evidence-based antenatal care in Mozambique: a qualitative study - Biza, Adriano; Jille-Traas, Ingeborg; Colomar, Mercedes; Belizan, Maria; Requejo Harris, Jennifer; Crahay, Beatrice; Merialdi, Mario; Nguyen, My Huong; Althabe, Fernando; Aleman, Alicia; Bergel, Eduardo; Carbonell, Alicia; et al. (BMC Pregnancy and Childbirth, 2015)
Background: Maternal mortality remains a daunting problem in Mozambique and many other low-resource countries. High quality antenatal care (ANC) services can improve maternal and newborn health outcomes and increase the likelihood that women will seek skilled delivery care. This study explores the factors influencing provider uptake of the recommended package of ANC interventions in Mozambique. Methods: This study used qualitative research methods including key informant interviews with stakeholders from the health sector and a total of five focus group discussions with women with experience with ANC or women from the community. Study participants were selected from three health centers located in Maputo city, Tete, and Cabo Delgado provinces in Mozambique. Staff responsible for the medicines/supply chain at national, provincial and district level were interviewed. A check list was implemented to confirm the availability of the supplies required for ANC. Deductive content analysis was conducted. Results: Three main groups of factors were identified that hinder the implementation of the ANC package in the study setting: a) system or organizational: include chronic supply chain deficiencies, failures in the continuing education system, lack of regular audits and supervision, absence of an efficient patient record system and poor environmental conditions at the health center; b) health care provider factors: such as limited awareness of current clinical guidelines and a resistant attitude to adopting new recommendations; and c) Users: challenges with accessing ANC, poor recognition amongst women about the purpose and importance of the specific interventions provided through ANC, and widespread perception of an unfriendly environment at the health center. Conclusions: The ANC package in Mozambique is not being fully implemented in the three study facilities, and a major barrier is poor functioning of the supply chain system. Recommendations for improving the implementation of antenatal interventions include ensuring clinical protocols based on the ANC model. Increasing the community understanding of the importance of ANC would improve demand for high quality ANC services. The supply chain functioning could be strengthened through the introduction of a kit system with all the necessary supplies for ANC and a simple monitoring system to track the stock levels is recommended.
Keywords: *indexed; *tagged; G - Maputo City / Cidade de Maputo; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GP - Cabo Delgado; GP - Tete; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Revoltas da fome: protestos populares em Moçambique (2008-2012) - Brito, Luís de; Chaimite, Egídio; Pereira, Crescêncio; Posse, Lúcio; Sambo, Michael; Shankland, Alex (Cadernos IESE, 2015)
Em Fevereiro de 2008 e Setembro de 2010, as cidades de Maputo e Matola foram palco de protestos violentos contra a subida do custo de vida, protagonizados por grupos de populares. Tais protestos foram logo depois replicados em algumas outras cidades do país, mas numa dimensão bem mais restrita e rapidamente controlados pelas forças policiais. Em Novembro de 2012, um novo protesto se desenhou, mas a acção repressiva imediata nos locais críticos de concentração dos populares pelas forças da polícia, que nos últimos anos tinha sido reforçada fortemente em homens e material, impediu que a violência se generalizasse, ainda que não tenha evitado a paralisia quase total da actividade no grande Maputo durante um dia e meio. Neste relatório procuramos mostrar que, se estas revoltas se enquadram num movimento mais amplo que desde 2008 tem abalado muitos países em consequência do aumento e da alta volatilidade dos preços alimentares no mercado internacional, elas exprimem sobretudo dinâmicas económicas locais e são um resultado da exclusão social e política a que são votadas as camadas sociais urbanas mais pobres em Moçambique. O relatório começa por apresentar uma breve perspectiva histórica e caracterização da natureza da economia moçambicana e da tradição política autoritária que tem sido dominante desde a proclamação da independência, ainda que coexistindo com uma profunda mudança nas alianças políticas do partido no poder, para depois abordar a questão alimentar e do custo de vida, assim como o contexto imediato dos protestos, os discursos e representações sobre os mesmos e o tipo de resposta por parte do governo.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social

A perspectiva de género no desenho dos programas de protecção social em Moçambique: o caso do programa Acção Social Produtiva - Chiboleca, Gil Tomás; Cremades, Raquel Coello (Faculdade Latino Americana de Ciências Sociais, 2015)
Este trabalho aborda uma das questões centrais no debate sobre a protecção social: género no desenho dos programas de protecção social. Neste contexto, o presente estudo analisa a integração da perspectiva de género no desenho dos programas de protecção social em Moçambique, tomando como estudo de caso – o Programa Acção Social Produtiva. Para a materialização deste trabalho, a nossa proposta de percurso metodológico, em conformidade com os objectivos propostos, o nosso quadro analítico irá guiar-se pelas variáveis centrais: (i) Objectivos gerais e específicos do programa; e (ii) Grupo-alvo (Beneficiários do programa). O estudo constatou que a integração da perspectiva de género nos programas de protecção social é complexa, limitada, e varia de acordo com as características e objectivos de cada programa de protecção social. Ademais, em alguns casos, a consideração de género nos programas é feita através da inclusão das mulheres como principais beneficiárias, ignorando a dimensão do género no seu todo. Na análise do PASP na óptica de género, o trabalho conclui que o programa não incorpora de forma explícita a perspectiva de género, e que a promoção da igualdade de género não constitui um objectivo primário na concepção do PASP. A análise dos grupos-alvo mostra que a consideração de género no PASP é feita através da inclusão da mulher como grupo-alvo prioritário. Isto acontece, como defende o presente estudo, pelo facto do PASP não ter sido desenhado/concebido com o intuito de promover a igualdade de género e empoderamento da mulher, mas para proteger os grupos vulneráveis aliviando a pobreza, e preveni-los contra a indigência e a fome.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; social protection / proteção social

An Analysis of Mozambique’s Political and Economic Networks - Chivangue, Andes; Cortez, Edson (CEsA - research center part of CSG/Research in Social Sciences and Management, 2015)
This paper analyses the social networks existing among politicians and economists in contemporary Mozambique, using the SNA-Social Networks Analysis method to identify the links between these individuals, to discern their relationships and to measure both the density and the centrality of the political-business network. Mozambique’s political and business elite is thus identified. A network sociogram is presented identifying the individual position in the network and the linkages among these individuals and several positional metrics of the individuals in the network are estimated, allowing identifying each individual and its influence in the network. As this network is resource accumulation driven, this exercise permits to identify the main political and economic individual active in Mozambique economy. President Guebuza define the major network centre and other individuals, Joaquim Chissano, the former president, and Graça Machel, the widow of another former president. Policy implications are derived and the links between them displayed, allowing for an accurate view of Mozambique’s political and business world.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Desafios para Moçambique - 2015 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2015)
PARTE I – POLÍTICA Alguns Desafios do Presindente Nyusi / Luís de Brito Os Recursos da Violência e as Lutas Pelo Poder Político em Moçambique / Victor Igreja A Sociedade Civil nas Eleições de 2014 em Moçambique – Oportunidade de Afrimação Perdida? / Sérgio Chichava e Egídio Chaimite Descentralização Sectorial e Provisão de Serviços Públicos em Moçambique – O Caso do Sector Agrário. / Salvador Forquilha Rede De Gestão De Água Em Nacala Porto Estender A Distribuição Ou A «Dominação»? / Domingos M. Rosário e Egídio P. Guambe PARTE II – ECONOMIA «Capitalizando» o capitalismo doméstico – Porosidade e Acumulação Primitiva de Capital em Moçambique / Carlos Nuno Castel-Branco Desafios da Sustentabilidade do Crescimento Económico Uma «Bolha Económica» em Moçambique? / Carlos Nuno Castel-Branco Dinâmicas Actuais de Aquisição de Terra para Investimento Em Moçambique Tendências, Escala, Factores, Actores e Questões para Análise. / Carlos Muianga «Ligações Minadas» O Caso dos Fornecedores Nacionais da Vale e da Rio Tinto em Moçambique / Epifânia Langa Capacitação das Empresas Nacionais e Conteúdo Local de Megaprojectos em Moçambique / Oksana Mandlate Processos Migratórios, Trabalho Agrícola e Integração nos Mercados Efeitos da Implementação de Grandes Projectos Sobre Comunidades Camponesas. /João Feijó e Aleia Rachide Agy PARTE III – SOCIEDADE Poupança Externa num Contexto de Crescimento Económico sem Poupança Interna / António Francisco e Moisés Siúta Porque Moçambique Ainda não Possui uma Pensão Universal para Idosos? / António Francisco e Gustavo Sugahara A Desigualdade Socioeconómica e a Transição Demografica em Moçambique / Boaventura Manuel Cau Dividendo Demografíco em Moçambique – Oportunidades e Desafios / Carlos Arnaldo e Rogers Hansine PARTE IV – MOÇAMBIQUE NO MUNDO A Controvérsia Sobre a Navegação Nos Rios Zambeze e Chire nas Relações Dipplomáticas entre Moçambique e o Malawi / Raúl Chambote Economias Emergentes e Instituições Nacionais – Debate Sobre a Presença Brasileira em Malawi e Moçambique /Carolina Milhorance
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

N’weti’s Community Scorecard Experience in Nampula: a Case Study - Franco, Erika Lopez; Dumangane, Sansão (Institute of Development Studies and N'weti, 2015)
This case study was commissioned by N’weti Comunicação para a Saúde to explore the changes emerging from the implementation of an adapted version of the Community Scorecard (CSC) tool in 11 health facilities catchment areas in Nampula. This case study discusses how N’weti has adapted the Community Scorecard (CSC) tool to better improve the quality of the participation and prospects of accountability for citizens. The case study presents evidence that the adapted CSC tool has resulted in an increased awareness of rights, an improved relationship with the service providers, a revitalisation of the health unit Co-management Committees, citizens feeling that their voice is being heard, and N’weti is recognised by people and authorities as catalyser and legitimate mediator of this voice. However, challenges also surfaced which N’weti must reflect and learn from. The first relates to the meaningful control from regular citizens (rather than NGO staff members) of the institutionalisation, follow-up of commitments and advocacy actions derived from the implementation of a CSC process. Other challenges refer to social exclusion, the lack of a deeper understanding of power dynamics, and the fact that ignoring previous histories of citizen engagement and other contextual factors can be misleading as not all change can be directly attributed to the implementation of the CSC.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Meconta; GD - Moma; GD - Rapale; GP - Nampula; Health PEA; Important; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; citizenship & participation / cidadania e participação; decentralization / descentralização; health / saúde; social inclusion & exclusion / inclusão e exclusão social

Gás para desenvolvimento ou apenas dinheiro? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
O gás de Moçambique pode ser usado para promover industrialização e desenvolvimento rural desde que, a partir de agora, sejam feitas as opções correctas. As actuais prioridades vão para os megaprojectos baseados na exportação, que prometem altos rendimentos mas que, tal como os megaprojectos anteriores, fazem pouco pela criação de empregos ou pela redução da pobreza. Os megaprojectos custando dezenas de bilhões de dólares são essenciais, mas o Conselho de Ministros pode orientar as negociações de maneira a darem a prioridade mais alta à utilização do gás para criar uma indústria nacional e empregos, mesmo que reduza as receitas a curto prazo
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Gas for development or just for money? - Hanlon, Joseph; Nuvunga, Adriano (Centro de Integridade Pública (Public Integrity Centre), 2015)
Mozambique’s gas can be used to promote industrialisation and rural development, but only if key choices are made now. Current priorities are for export based mega-projects promising high revenues, but like past mega-projects doing little to create jobs or reduce poverty. Mega-projects costing tens of billions of dollars are essential, but the Council of Ministers can instruct that negotiations give a higher priority to using the gas to create a domestic industry and jobs, even if it reduces short term income.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; rural development / desenvolvimento rural

Child Marriage and Adolescent Pregnancy in Mozambique: Policy Brief - Hodges, Anthony (UNFPA, Meninas e Não Noivas, UNICEF, 2015)
Child marriage is one of Mozambique’s most serious but largely ignored development challenges – requiring far greater attention from policy makers Child marriage rates are still very high despite a long-term decline, especially in marriage before the age of 15. Economic pressures and the incentive of bride price appear to be powerful factors driving parents to marry off their daughters at a young age. The high rates of child marriage cannot be allowed to continue without a vigorous response from the government, civil society and development partners.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

A participação dos cidadãos nos processos de responsabilização social: aprendizagens da experiência da Facilidade na Província de Nampula - Lopez-Franco, Erika (2015)
O Programa Cidadania e Participação (Citizen Engagement Programme - CEP) em Moçambique é um programa de empoderamento e responsabilização que visa melhorar a qualidade dos serviços de saúde e educação através do apoio aos cidadãos para os monitorarem. O programa ajuda os cidadãos a envolverem-se com os provedores de serviços para tratarem problemas identificados; visa também gerar evidência para a melhoria das políticas e programas aos níveis local e nacional. Para o CEP é fundamental partilhar as experiências, lições e desafios do programa com todos aqueles que estão envolvidos nele e também aqueles que têm interesse nas áreas de trabalho do CEP. Esperamos com esta partilha contribuir para um aprofundamento do conhecimento sobre as questões que tratamos no programa. Os Cadernos do CEP são uma das ategorias de publicações que produzimos com o propósito acima mencionado. Nestes cadernos apresentamos estudos de caso, análises e histórias que mostram o que o programa faz e apoia a fazer. Embora sejam publicações de carácter e interesse abrangente, pensamos que os seus conteúdos se revestem de particular relevância para quem implementa programas de esponsabilização social e especialistas nas áreas temáticas e metodologias cobertas pelo programa.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; ⛔ No DOI found

Learning from citizen participation for accountability in Nampula province - Lopez-Franco, Erika (IDS, 2015)
The Citizen Engagement Program (CEP) in Mozambique is an empowerment and accountability program aiming to improve the quality of health and education services through supporting citizens to monitor them. The program supports citizens to engage with service providers to address identified problems; it also aims to generate evidence for policy and program improvement at the local and national levels. This case study is structured in three main sections. The first section provides a background to set the context in which organizations such as Facilidade emerged across Mozambique, with reference to the ‘third generation’ of decentralization policies in Sub-Saharan Africa and the growing expectation over nearly two decades of ‘participation’ as a magic bullet to improve service-delivery and governance. As well, this section will give an overview of the methodology, some of the assumptions behind the approach and the challenges and questions that the process raised. The second section presents the findings of the research. These are structured around four themes: practices of participation; citizenship building for accountability; inclusion challenges; and other positive outcomes from the work with citizens. Finally, the third section provides conclusions and spells out questions that remain after this exercise. These questions will be useful for CEP, as well as other social accountability initiatives, to bear in mind when thinking about citizen participation for accountability.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; ⛔ No DOI found

Repositório Aberto: Insucesso escolar em Moçambique : estudo de caso na Escola Secundária Graça Machel - Macamo, Ernesto Mário (Universidade Aberta, 2015)
O insucesso escolar constitui um dos grandes problemas do sistema educativo formal, em Moçambique. Existe por várias razões, tais como o abandono da escola antes da conclusão do ciclo, as reprovações anteriores que dão lugar a grandes desníveis entre a idade cronológica do aluno e o nível escolar em que se encontra, a falta de materiais pedagógicos, os métodos usados pelos professores. Os níveis de fracasso escolar podem ser totais (em todas as disciplinas) ou parciais (numa ou duas disciplinas). Um dos objetivos do estudo é o de identificar as perceções sobre as causas do insucesso escolar. Pretendemos também saber se os factores apontados são de ordem interna ou externa à escola. A investigação utilizou o método de estudo de caso, de tipo exploratório. Para conhecermos as opiniões de alunos e professores, recorremos à utilização de inquérito por questionário. Foram ainda realizadas entrevistas semi-estruturadas ao director da escola e ao presidente do conselho da escola. Foram analisadas pela técnica análise de conteúdo. Segundo os inquiridos e os dois entrevistados, a falta de laboratórios eficientemente equipados, a prática de atividades de pastagem pelos alunos, implicando o afastamento da escola por longos períodos de tempo, os casamentos prematuros e a falta de acompanhamento pelos pais e encarregados de educação tem contribuído para o insucesso escolar. Não existe por parte dos professores nem por parte da direção pedagógica e do presidente do conselho de escola a assunção da sua responsabilidade no problema.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; education / educação

A migração internacional e o processo de desenvolvimento na região norte de Moçambique : estudo de caso da província de Nampula - Patrício, Gonçalves (2015)
Este estudo procura reflectir as causalidades e os efeitos socioeconómicos dos movimentos migratórios no processo de desenvolvimento na região norte de Moçambique, especificamente na província de Nampula, onde a entrada de estrangeiros de forma regular ou irregular é cada vez mais acentuada. Procuramos igualmente captar as motivações subjacentes, os pontos de entrada, as formas de integração, bem como o papel das instituições do Estado na reprodução dos fluxos migratórios. Neste trabalho fizemos uma combinação de métodos e técnicas usadas em ciências sociais. O procedimento de recolha e tratamento de dados baseou-se em: i) consulta bibliográfica e análise documental; ii) análise da informação estatística disponível sobre as migrações em Moçambique; iii) observação directa e entrevistas a diferentes actores institucionais e individuais. Os resultados da investigação sugerem que a localização desta província, as suas potencialidades económicas e a fragilidade das instituições do Estado no controlo das imigrações constituem factores apelativos para a entrada de imigrantes de várias partes do mundo, com especial destaque para os imigrantes africanos, que abandonaram as suas regiões de origem por razões conjunturais socioeconómicas e políticas adversas e procuram, na região acolhedora, segurança e melhores condições de vida. Constatamos que, no geral, os imigrantes são pobres, constituídos, na sua maioria, por “refugiados” que não pedem o estatuto formal dessa condição. Porque não são absorvidos no mercado de trabalho pelo sector privado e pelas instituições do Estado, desenvolvem actividades por conta própria, no sector formal e, sobretudo, no informal, como forma de aumentar os seus rendimentos e melhorar as suas condições de vida. Os empreendimentos formais e informais gerados pelos estrangeiros africanos constituem uma mais-valia socioeconómica para a província na medida em que, embora a sua maioria sejam precários, permitem a diversificação das actividades económicas, proporcionando vários serviços à população local.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; ⛔ No DOI found

Os Municípios dos “Outros”. Alternância do poder local em Moçambique? O caso de Angoche - Rosário, Domingos Manuel do (Cadernos de Estudos Africanos, 2015)
As eleições municipais de 2003 marcaram o início do exercício do poder local pela Renamo no município de Angoche. Quais são os factores explicativos desta situação eleitoral local? A partir de uma perspectiva sócio-histórica, este artigo procura compreender como é que a evolução política e administrativa destes territórios influenciou a lógica do poder local. São as relações estabelecidas entre as populações e o Estado e a forma como a municipalização foi desenhada e implementada desde 1994 pela Frelimo que não proporcionam condições favoráveis à criação de um pluralismo político, na medida em que o partido dominante consegue, através do controlo que exerce sobre o Estado central, instrumentalizar os recursos e fortificar suas bases políticas e eleitorais.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; L - portuguese / português; Northern PEA; electoral geography / geografia eleitoral

Mapping study of Civil Society Organisations in Mozambique - Topsøe-Jensen, Bente; Pisco, Alice; Salimo, Padil; Lameiras, João (ALTAIR Asesores and Agriconsulting. S.L, 2015)
The Mapping Study of Civil Society Organizations (CSOs) in Mozambique was carried out during the first half of 2015, within the context of preparation for the Roadmap of the European Union (EU), Member States and other partners for engagement with civil society. Data collection included document analysis, and interviews with CSOs, international partners and Mozambican government institutions at national, provincial, district and local level. In the first phase of the field work, nine provincial workshops were held, and in the second phase four workshops were held for verification of findings and validation of recommendations. The overall objective of the mapping study is to provide the EU and all interested parties with a comprehensive overview of the state of CSOs in Mozambique, including identification of their needs and proposals for maximizing their influence in the definition and monitoring of public policies. The study also presents recommendations on the priorities to include in the EU Roadmap for engagement with civil society, and may thus contribute to improving the strategy for support to CSOs within current programming. The specific objectives are to: - Analyse the global state of play of the civil society in Mozambique, particularly regarding the environment, structure, capacity, engagement and sustainability of its organizations; - Identify existing the gaps, the fundamental needs and the opportunities for the CSOs to get involved in and influence policy processes, to monitor implementation of state commitments, and in general to claim transparency in public processes and good governance; - Provide specific recommendations on how to better meet needs identified by suggesting priorities and actions for programmes and other civil society support interventions.
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

Natural Gas and Socio-Economic Transformation in Mozambique: Some Preliminary Evidence - Uetela, Pedro; Obeng-Odoom, Franklin (The Journal of Energy and Development, 2015)
The aim of this article is to extend the state of analysis on the impacts of gas development in Mozambique by evaluating the relationship between the gas sector, the Mozambican economy, and social change. As the resource curse framework is only limited to economic growth, this work utilizes two alternative frameworks—the Staples approach and the Linkages approach—that are melded into an institutional analysis, looking simultaneously at “benefits, costs, and uncertainties” or “blessings, uncertainties, and curses,” and used to conceptualize progress more widely to include not only growth, but other externalities and broader social change as applied to the case of Mozambique. In so doing, the evidence suggests that the natural gas industry in Mozambique has contributed to both the expansion in economic growth and social change. However, the positive experience with social change arises from direct intervention and not necessarily the result of the related economic growth. Indeed, in the process of economic growth, the production and export of natural gas in Mozambique have raised the possibility of major socio-economic and ecological dangers. Contrary to the theoretical criticism of spending windfall revenues on social services as wasteful, we argue that only strategic social and ecological expenditures of gas revenues can provide and increase the chances of the gas industry becoming transformational economically, socially, and ecologically. The article is organized as follows; the next section deals with conceptualizing the paper and describing the sources of data. This is followed by sections that present the results, a discussion of those results, and conclusions and policy implications from the study.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; ⛔ No DOI found

The land grabbers of the Nacala Corridor: A new era of struggle against colonial plantations in Northern Mozambique - UNAC; GRAIN (UNAC and GRAIN, 2015)
This report looks at the companies already setting up agribusiness operations in the Nacala Corridor, an area that the government has prioritised for agribusiness development. These companies, typically structured through offshore tax havens and often connected to Mozambican political elites, have been grabbing lands and extracting wealth in ways reminiscent of the country's colonial days.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Hunger Revolts and Citizen Strikes: Popular Protests in Mozambique, 2008-2012 - Brito, Luis de; Chaimite, Egídio; Pereira, Crescêncio; Posse, Lúcio; Sambo, Michael; Shankland, Alex (Institute of Development Studies/Instituto de Estudos Sociais e Economicos, 2014)
In February 2008 and September 2010, the cities of Maputo and Matola were the scene of violent protests against the rise in the cost of living, undertaken by groups of ordinary citizens. Immediately afterwards, these protests were replicated in some other Mozambican cities, but on a much smaller scale, and they were quickly brought under control by the police. In November 2012, a new protest was set in motion, but immediate repressive action by the police (which in recent years has been greatly strengthened in men and material) in the key places where people were gathering prevented the violence from spreading, although it did not prevent the near total paralysis of activity in greater Maputo for a day and a half.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Reformas de descentralização e serviços públicos agrários em Moçambique: Porquê os desafios persistem? - Forquilha, Salvador (IDeIAS, 2014)
Nos anos 1980, vários países da África subsaariana iniciaram um conjunto de reformas ligadas ao sector público visando, entre outros objectivos, fazer face à crise do Estado, que se manifestava essencialmente em duas dimensões, nomeadamente regulação política e provisão de serviços públicos. Desde então, assistiu-se a três gerações de reformas do sector público (Kiragu, 2002; Crook, 2010). A primeira geração vai dos meados dos anos 1980 aos meados dos anos 1990, com enfoque nos Planos de Ajustamento Estrutural; A segunda geração destacou-se nos meados dos anos 1990, com uma forte componente de assistência técnica aos programas das reformas; Finalmente, a terceira geração das reformas inicia nos finais dos anos 1990 e começos dos anos 2000, marcada pela ligação das reformas com as Estratégias de Redução da Pobreza (no caso de Moçambique os PARPAs e o PARP) e um enfoque na questão da descentralização e melhoria de serviços públicos. Que resultados estas reformas trouxeram em termos de provisão de serviços públicos?
Keywords: G - Mozambique / Moçambique; L - portuguese / português; agriculture / agricultura; decentralization / descentralização; ⛔ No DOI found

Artisanal gold mining and rural development policies in Mozambique: Perspectives for the future - Dondeyne, Stefaan; Ndunguru, Eduardo (Futures, 2014)
Despite Mozambique's great natural resource wealth and strong economic growth, rural poverty remains high countrywide. The challenge is thus finding ways to turn this wealth into development opportunities. For many rural people in central Mozambique, artisanal gold mining is the most direct source of income and this is most likely to remain so. Drawing on our personal experiences, we reflect on the future of artisanal gold mining in Mozambique. The government's strategy consists of promoting improved technologies and encouraging artisanal miners to establish themselves as businesses by creating miners associations. This has proved successful where the ore allows for sufficiently long exploitation, in practice, where reef gold occurs. The same cannot be said, however, of colluvial or alluvial deposits, where placer gold is mined. Given the variable nature of these deposits, accompanying mining activities are relatively short-lived at such sites. In these cases, local authorities and community representatives must play an expanded role in enforcing good mining practices. Doing so would be in line with the country's current decentralisation and democratisation policies in relation to rural development.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; GP - Sofala; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; rural development / desenvolvimento rural

The geographic and sectoral patterns of large-scale farmland investments in sub-Saharan Africa - Schoneveld, George Christoffel (Food Policy, 2014)
Following the food and energy price crises of the mid 2000s, sub-Saharan Africa has become one of the largest recipients for large-scale farmland investments. While much has been written on the phenomenon, scant reliable empirical evidence is available as to the precise geographic and sectoral patterns and underlying drivers. Employing strict data quality requirements, this paper addresses these knowledge gaps by analyzing 563 farmland projects that have been established between 2005 and 2013 in sub-Saharan Africa. Findings show that the investment intensity and associated risks are not geographically uniform. Moreover, the study highlights a number of popular misconceptions regarding investor origin and their sectoral interests and motives.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Guião de consulta e participação da sociedade civil e cidadãos no funcionamento dos conselhos consultivos locais - Monjane, Celso; Salimo, Padil (MASC, 2014)
O presente guião é um instrumento que tem em vista dotar as OSC e cidadãos de modo geral, de conhecimentos sobre o funcionamento dos Conselhos Consultivos Locais (CCLs) de maneira a facilitar a sua participação e a alargar as suas intervenções na área de monitoria e advocacia da governação a nível distrital. Estão apresentados neste guião, os elementos que permitem perceber a organização, a estrutura, funções, e responsabilidades dos Conselhos Consultivos Locais, como eles funcionam, as oportunidades existentes para a participação das OSC e cidadãos de um modo geral na articulação com os Conselhos Locais por forma a estimular diálogo e contribuir na melhoria da sua influência na tomada de decisões e na melhorias na prestação de serviços às comunidades a nível dos distritos pelos governos distritais. O guião está estruturado em cinco secções. A primeira secção, apresenta o contexto, objectivos e a metodologia usada na sua elaboração; a segunda secção, procura explicar os principais elementos sobre a participação e consulta comunitárias, as formas de organização das comunidades locais para a participação comunitária, e a importância da participação e consulta comunitária, bem como uma explicação sobre como a consulta e a participação é feita a nível distrital. A terceira secção, apresenta detalhadamente aspectos sobre funcionamento, tarefas e estratégias de trabalho, bem como formas de prestação de contas. A quarta secção, fala sobre os mecanismos de escolha dos membros dos Conselhos Consultivos Locais, número de membros e direitos e deveres que eles possuem. A quinta secção, fornece algumas bases sobre como a sociedade civil e cidadãos podem contribuir para o fortalecimento dos CCLs, bem como, as estratégias para incrementar mecanismos de monitoria e advocacia.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação; collaboration / colaboração; governance / governação; government policy / politica governamental

Displacement and Dispossession Through Land Grabbing in Mozambique: The Limits of International and National Legal Instruments - Twomey, Hannah (Refugee Studies Centre (RSC), 2014)
This working paper examines the limitations of international and national law to address displacement and dispossession from land grabs within the case study of Mozambique. The main question that I seek to answer is: What limits international and national law in addressing displacement and dispossession due to land grabs in Mozambique? I will argue that the limits of law to address displacement and dispossession are not due to a lack of institutionalising international good governance norms into domestic-level legal frameworks. Nor can the limits be attributed to state incapacity. Rather, the limits of law lie within the norm implementation process, wherein norms are conditioned by the local Mozambican governance context to serve domestic interests
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; Law - Rule of Law / Law - Estado de Direito; governance / governação; land governance / gestão de terra

Guião de Consultas Comunitárias - Tankar, Issufo (Centro Terra Viva (CTV), 2014)
Em 2009, o Centro Terra Viva (CTV) publicou o Guião de Consultas Comunitárias, como parte do seu esforço em melhorar a aplicação da legislação sobre terras e outros recursos naturais. O guião resultou de várias pesquisas de campo realizadas pelo CTV e outras organizações que trabalham na área de Terras. No entanto, a aprovação do Decreto n° 43/2012 de 10 de Outubro, seguida do Diploma Ministerial n° 158/2011 de 15 de Junho, uma parte significativa do Guião ficou ultrapassada. Por outro lado, foram aprovadas directrizes pelo Fórum de Consulta sobre a Terra que são relacionadas a este tema. Deste modo, e como forma de facilitar a interpretação e aplicação do quadro legal sobre consultas comunitárias, o Centro Terra Viva, produziu este guião de consultas comunitárias destinado às comunidades, técnicos do Estado, técnicos de ONG’s e todos actores que trabalham na área de Terras.
Keywords: *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Brief presentation of the geological resources of Mozambique - Vasconcelos, Lopo (2014)
This paper aims at giving a general overview on the geology of Mozambique, and its mineral and geological resources associated to the different geological units. The geology of Mozambique covers almost all periods of the Earth’s history. Tectonically speaking, Precambrian is found in three Gondwana blocks – E, W and S -, each one of them with its geostructural characteristics, and separated from each other by great structural features. For Phanerozoic, reference is made to the Karoo Supergroup (Upper Carboniferous to Early Jurassic), and to the East- Africa Rift System (Jurassic to the present), with origin linked to the Gondwana fragmentation and the opening of the Mozambique Channel, where the great sedimentary basins of Rovuma (N) and Mozambique (center-S) can be distinguished, both world-wide known for the discoveries of hydrocarbons. A general presentation of the geological resources and their location. © 2014, LNEG – Laboratório Nacional de Geologia e Energia IP.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources / recursos naturais

Desafios para Moçambique - 2014 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2014)
PARTE I – POLÍTICA Uma Reflexão Sobre o Desafio da Paz em Moçambique / Luís de Brito Cultura Política e Cidadania em Moçambique: Uma Relação Conflituosa / Elísio Macamo Do discurso da “história de sucesso ” às dinâmicas políticas internas:O desafio da transição política em Moçambique / Salvador Forquilha Das revoltas às marchas:emergência de um repertório de acção colectiva em Moçambique / Egídio Chaimite PARTE II – ECONOMIA O Crescimento da Cultura do Tabaco em Moçambique: Questões e Desafios para um Sector em Transformação/ Helena Pérez-Niño Grupos de Poupança e Crédito Rurais como Opção para a Inclusão Financeira: Uma Análise Crítica / Rosimina Ali, Yasfir Ibraimo, Fernanda Massarongo e Nelsa Massingue Oportunidades e condicionalismos da agricultura no Regadio do Chókwè/ Ana Sofia Ganho e Phil Woodhouse O caminho pela frente: desenvolvimento actual e perspectivas futuras do sector do transporte rodoviário de mercadorias em Moçambique: um estudo de caso no coredor da Beira / Helena Pérez-Niño Indústria extractiva e desenvolvimento local:O papel da responsabilidade social empresarial / Epifânia Langa e Nelsa Massingue PARTE III – SOCIEDADE Caminhos Moçambicanos para a Construção da Democracia em Moçambique: Notas de uma leitura psicanalítica / Bóia Efraime Júnior Para além do Espaço Fiscal:A Protecção social no Contexto da Transição Demográfica Moçambicana / António Francisco e Gustavo Sugahara O Nascimento da Poupança Doméstica Moçambicana:Evidências e Significado /António Francisco e Moisés Siúta Alguns Desafios do Ensino Superior em Moçambique: Do conhecimento experiencial à necesidade de produção de conhecimento científico / Patrício Vitorino Langa PARTE IV – MOÇAMBIQUE NO MUNDO Juventude, Waithood e Protestos Sociais em África / Alcinda Honwana Acumulação num contexto de lógicas e dinâmicas neo-patrimoniais: O caso da ARPONE em Xai-Xai / Sérgio Chichava
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Juventude, Waithood e Protestos Sociais em África - Honwana, Alcinda (Desafios para Moçambique 2014, 2014)
Este artigo tem como tema principal as experiências de muitos jovens africanos que se debatem com os problemas de desemprego, dificuldade de encontrar meios de subsistência sustentáveis, marginalização e ausência de liberdades civis. A instabilidade política, a má governação e políticas sociais e económicas desajustadas têm agravado os problemas existentes em muitas sociedades africanas e têm também reduzido consideravelmente a capacidade de os jovens se tornarem cidadãos “responsáveis” e independentes. Muitos jovens são hoje incapazes de atingir os pré‑requisitos da idade adulta. No plano global, a onda de movimentos sociais de protesto protagonizados por jovens nos últimos anos enquadra‑se no contexto da luta desta geração pela sua emancipação económica, social e política.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; youth / juventude

Indústria extractiva e desenvolvimento local: O papel da responsabilidade social empresarial - Langa, Epifânia; Massingue, Nelsa (Desafios para Moçambique, 2014)
A entrada de grandes investimentos de capitais estrangeiros na área de recursos minerais e energia, nos últimos anos, tem levantado várias questões sobre o papel dos mega ‑projectos no desenvolvimento económico e social em Moçambique, gerando um debate sem consenso. Uma das temáticas do debate é a responsabilidade social empresarial (RSE). Acções de RSE como a construção de infra ‑estruturas sociais para a educação e a saúde, a geração de emprego, entre outras são muitas vezes referenciadas em muitos discursos, principalmente políticos e de empresas, como aspectos positivos que complementam as acções do governo, devendo por isso ser promovidas e valorizadas.1 Entretanto, estes discursos muitas vezes negligenciam componentes não menos importantes como a intenção das empresas ao desen‑ volver iniciativas sociais, o risco das comunidades se tornarem dependentes destes mega ‑projectos e a possibilidade de fragilização do papel do Estado (Schroeder & Schroeder, 2004).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; extractive industries / indústrias extractivas; natural resources / recursos naturais; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado

Mozambique land policy development case study - Locke, Anna (Overseas Development Institute, 2014)
This case study has been produced in response to a request made to the Evidence on Demand Helpdesk. The objective of the request was to provide a detailed case study on the evolution of land policy in Mozambique and provide the reader with insights into what is viewed as one of Africa’s most progressive land laws, recognising multiple forms of tenure. Mozambique has experienced accelerated rates of growth over the past decade, averaging 7.2% per year, with projected growth rates of over 8%. However, this high growth rate has failed to translate into significant reductions in poverty and inequality has increased in almost all parts of the country. While growth has been driven by capital-intensive projects, mainly in the extractives sector, agriculture is seen as an important foundation for economic development and there has been a high level of interest in acquiring large tracts of land for investment over the past six years. Mozambique is one the most land-abundant countries in Africa, with around 80 million hectares (has). Currently, only five million hectares are cultivated, mainly by smallholders under rain-fed, traditional systems, and only 3-5% of landholdings are formally registered.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra

Abordagens para promover responsabilização social: revisão de algumas experiências - McGee, Rosie; Wanjiku Kelbert, Alexandra (Laboratório de Inovação do CEP - CEP - Cidadania e Participação, 2014)
O Programa Cidadania e Participação (CEP) (2013-2018) apoia os cidadãos na monitoria da qualidade de prestação de serviços de saúde e de educação em quatro províncias de Moçambique, assim como a advogar para a melhoria da qualidade desses serviços nos níveis distrital, provincial e nacional. O CEP pretende contribuir para: uma maior disponibilidade de informação relevante de modo a que os cidadãos tenham um melhor acesso e benefício dos serviços prestados pelo sector público; melhorar as capacidades dos cidadãos de avaliar a prestação de serviços e de se envolverem com os provedores de serviços de modo a melhorar a qualidade dos serviços de saúde e educação aos níveis primário e secundário; apoiar as organizações da sociedade civil a impulsionarem essas constatações nos processos de tomada de decisões a níveis mais altos.Este programa facilitará o diálogo entre cidadãos e comunidade por um lado, e os provedores de serviços por outro lado, para melhorar a qualidade dos serviços. Esta análise constitui uma parte da contribuição do IDS para o Output 5 do CEP (Output 5: ‘Aprendizagem e metodologias compartilhadas e aplicadas por outros actores do desenvolvimento’). Esta fornece uma visão geral de algumas das mais inovadoras experiências de responsabilização social e práticas de envolvimento dos cidadãos de vários contextos africanos, bem como internacionais, como forma de ajudar a aumentar o nível geral de interesse e consciencialização sobre práticas inovadoras de envolvimento dos cidadãos em Moçambique.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação

Perfil Do Distrito De Macomia Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Macomia; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação

Perfil Do Distrito De Pemba Metuge Província De Cabo Delgado - Ministério de Administração Estatal (Ministério de Administração Estatal, 2014)
O Ministério de Administração Estatal elaborou e procede a publicação da versão actualizada dos Perfis dos 128 Distritos de Moçambique. Estamos certo de que este produto apetrecherá as várias instituições públicas e privadas, nacionais ou internacionais, com o conhecimento de todo o país, que potencia o prosseguimento coordenado das acções de combate a probreza de Moçambique
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Pemba Metuge; GP - Cabo Delgado; L - portuguese / português; demographics / demografia; governance / governação; poverty / pobreza

O caminho pela frente: desenvolvimento actual e perspectivas futuras do sector do transporte rodoviário de mercadorias em Moçambique: um estudo de caso no corredor da beira - Pérez-Niño, Helena (Desafios para Moçambique 2014, 2014)
A economia moçambicana conhece atualmente uma fase de transição que se reflecte nos diferentes sectores produtivos. Esta transformação é tanto qualitativa – em termos da variedade de actividades levadas a cabo e a diversidade de ligações criadas – quanto quantitativa – em termos dos volumes de produtos e serviços comercializados. Em particular, a transformação tem igualmente efeitos e implicações distintos para diferentes grupos em Moçambique. O sector dos transportes é tanto o veículo condutor da economia produtiva como o barómetro da magnitude e qualidade da atual transformação, e, como tal, oferece um ângulo de análise de onde é possível observar as mudanças no sistema e reflectir sobre os desafios e as oportunidades emergentes. Não obstante as suas limitações e períodos de interrupção, a economia moçambicana tem sido historicamente direccionada para a provisão de serviços de transporte que não só ligam o vasto território nacional como servem de porta de entrada para os vários Estados e regiões interiores. O sistema de transporte moçambicano e as redes de transporte ligadas aos corredores de desenvolvimento têm atraído alguma atenção da parte de instituições de investigação e académicos. No entanto, a investigação no sector dos transportes tem‑se concentrado no desenvolvimento e funcionamento dos caminhos‑de‑ferro e da infraestrutura física das estradas. Em termos comparativos, com pequenas excepções, os operadores do transporte rodoviário de mercadorias ainda não foram estudados de forma sistemática. Não obstante vários esforços no sentido de desenvolver a intermodalidade dos transportes, o transporte rodoviário de mercadorias é ainda central para o funcionamento da economia moçambicana, como será discutido em baixo. As empresas de transporte rodoviário de mercadorias respondem às necessidades mais imediatas e de um maior número de sectores do que qualquer outra forma de transporte de carga em Moçambique. Apesar de as transportadoras rodoviárias de carga serem actores‑chave do desenvolvimento do sector de extracção mineral, estas servem essencialmente os sectores não‑mineiros e são, consequentemente, um elemento crucial na avaliação das perspectivas de desenvolvimento de uma base produtiva diversificada e equilibrada e no entendimento das ligações entre os sectores extractivos e não‑extractivos da economia.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; ⛔ No DOI found

Mozambique rising: building a new tomorrow - Ross, Doris C. (International Monetary Fund, African Department, 2014)
This publication highlights Mozambique's remarkably strong growth over the two decades since the end of the civil war in 1992, as well as the major challenges that remain for the country to rise out of poverty and further its economic development. Chapters explore such topics as the role of megaprojects and their relationship to jobs and growth; infrastructure and public investment; Mozambique's quest for inclusive growth; developing the agricultural sector; and building a social protection floor
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; Social Protection PEA; agriculture / agricultura; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo; infrastructure / infrastrutura; social protection / proteção social

The Importance of Microfinance for Development of MSMEs in ASEAN: Evidence from Indonesia - Tambunan, Tulus (Journal of ASEAN Studies, 2014)
Despite studies on microfinance (MF) or development of microfinance institutions (MFIs) in Asia developing countries, including countries as member states of the Association of Southeast Asian Nation (ASEAN), are growing, not so much attention have been given to the role of MF in financing micro, small and medium enterprises (MSMEs). Based on a key literaturestudy and analysis of secondary/national data, the main aim of this study is to fill this gap. It shows that in many ASEAN member states (AMS) MF has developed to some significant degree, although the rate of growth (e.g. number of MFIs, number of depositors and debtors, total loans allocated, etc.) as well as the market structure of MF vary across member states. From the Indonesian case this study comes with two most interesting facts. First, majority of MSMEs do not have access to credit from banks and/or other formal non-bank financial institutions. Second, MF services or MFIs are growing fast, and the most popular MF program so far is Kredit Usaha Rakyat (KUR), or people business credit (i.e. a credit scheme without collateral), introduced during the SBY period
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Orientacoes superiores: Time and bureaucratic authority in Mozambique - Gonçalves, Euclides (African Affairs, 2013)
This article examines the production, circulation, and interpretation of regulatory documents in contemporary Mozambique in order to highlight their central importance to processes of governance. The empirical focus is on orientações superiores – written and oral documents issued by ﬁgures and institutions of authority with the intention of advising on procedures for policy formulation and implementation. By producing orientações superiores in a way that leaves their intent ambiguous and their status provisional, party and state ofﬁcials shift the focus of policy making from substance to process. In this way, bureaucratic authority is produced and reinforced through the manipulation of the timing of policy implementation. This perspective expands current understandings of African governance that on the whole have been limited to the analysis of the effectiveness of African institutions and policies, leaving the tactical effects of ambiguity, timing, and provisionality in policy implementation undertheorized.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - ethnography / etnografia; authority / autoridade

Joint Assessment of the Mozambican Health Sector Strategic Plan (PESS, 2014-2019) - JANS - Joint Assessment of National Strategies (International Health Partnership, 2013)
Since independence in 1975, development in Mozambique has been guided by a sequence of Five Year Plans, (Planos Quinquenais de Desenvolvimento). In 2002 the Government of Mozambique (GOM) initiated a series of reforms in all development sectors, aiming to start a process of decentralisation and bringing management closer to the lower levels of state organisation (Provinces and Districts). For the Municipalities, a devolution model was chosen that is currently in the process of being rolled out to all municipalities in the country. It is within this context that the health sector initiated its Five Year Strategic Plans (Plano Estrategico do Sector da Saúde - PESS) in 2000 with the aim to gradually improve the health status of the people. The current PESS is the third of its kind (PESS III), representing a continuation of this good management practice in the country, aiming to improve access and quality of current services (Pilar 1), while at the same time continuing a series of Reforms within the health sector that aim to improve effectiveness and efficiency in overall service provision at all levels (Pilar 2). The health sector distinguishes four levels of service provision, going from Health Posts and Health Centres at the level of villages and sub-districts to District Hospitals to Provincial Hospitals and finally to the Central / Specialised Hospitals at the top of the health pyramid.
Keywords: G - Mozambique / Moçambique; Health PEA; L - english / inglês; decentralization / descentralização; health / saúde

“What is a House without Food?”: Mozambique’s Coal Mining Boom and Resettlements (Human Rights Watch, 2013)
“What is a House without Food?” Mozambique’s Coal Mining Boom and Resettlements
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Measuring Coverage in MNCH: Testing the Validity of Women's Self-Report of Key Maternal and Newborn Health Interventions during the Peripartum Period in Mozambique - Stanton, Cynthia K.; Rawlins, Barbara; Drake, Mary; dos Anjos, Matias; Cantor, David; Chongo, Lidia; Chavane, Leonardo; da Luz Vaz, Maria; Ricca, Jim (PLoS ONE, 2013)
Background: As low-income countries strive to meet targets for Millennium Development Goals 4 and 5, there is growing need to track coverage and quality of high-impact peripartum interventions. At present, nationally representative household surveys conducted in low-income settings primarily measure contact with the health system, shedding little light on content or quality of care. The objective of this study is to validate the ability of women in Mozambique to report on facility-based care they and their newborns received during labor and one hour postpartum. Methods and Findings: The study involved household interviews with women in Mozambique whose births were observed eight to ten months previously as part of a survey of the quality of maternal and newborn care at government health facilities. Of 487 women whose births were observed and who agreed to a follow-up interview, 304 were interviewed (62.4%). The validity of 34 indicators was tested using two measures: area under receiver operator characteristic curve (AUC) and inflation factor (IF); 27 indicators had sufficient numbers for robust analysis, of which four met acceptability criteria for both (AUC .0.6 and 0.75,IF,1.25). Two of these indicators are considered high demand and are recommended for incorporation into international survey programs: presence of a support person during labor/delivery and placement of the newborn skin to skin against the mother. Nine indicators met acceptability criteria for one of the validity measures. All 13 indicators are recommended for use in in-depth maternal/newborn health surveys. Conclusions: Women are able to report on some aspects of peripartum care. Larger studies may be able to validate some indicators that this study could not assess due to the sample size. Future qualitative research may assist in improving question formulation for some indicators. Studies of similar design in other low-income settings are needed to confirm these results.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Facing the forest entrepreneurs - Healy, Hazel (New Internationalist, 2013)
Communities are scrambling to protect their lands from the tree plantations multiplying across Mozambique.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra

A Rede de Negocios da Frelimo no Norte - , Erik (Verdade - A verdade a cada palavra, 2013)
O investimento em energias e infra-estruturas pode transformar o negligenciado norte e afectar a sucessão presidencial. Andarko e outras companhias petrolíferas prevêem que o gás descoberto em Cabo Delgado pode duplicar o produto interno bruto anual. Por enquanto acredita-se que as vastas reservas de carvão se encontram na província do Niassa. O centro de gravidade de oportunidades económicas de Moçambique parecem se transladar para o norte. O governo está a atrair investidores estrangeiros para ajudarem na transformação desses recursos naturais em rendimentos públicos para o que era até agora um dos países mais pobres do mundo.
Keywords: #Reporting & Media / Reportagem & Mídia; G - north / norte; GP - Cabo Delgado; infrastructure - energy / infrastrutura - energia; natural resources / recursos naturais

Peril dos dados básicos das cidades de Moçambique. Edição preliminar. - Ventura, Albert Gerard; Pazero, Renata; Hoelich, Sara; Bennaton, Alessa; Llop, Josep Maria (ASF - Catalunya/Secretariado Mundial CGLU / Cátedra UNESCO - Red CIMES, 2013)
O projeto que tem previsto uma duração de 28 meses e foi iniciado em janeiro de 2013, prevê a melhoria da capacidade de gestão do desenvolvimento de oito municípios em Moçambique e seis no Brasil, assim como de duas associações de autoridades locais (Associação Nacional de Municípios de Moçambique - ANAMM - e Frente Nacional de Prefeitos do Brasil -FNP), mediante ações de intercâmbio de boas práticas, capacitação institucional e articulação em rede das AL. O projeto é coordenado por Cidades e Governos Locais Unidos (CGLU), juntamente com Arquitectos sem Fronteiras (ASF) e Cátedra UNESCO / Rede-CIMES. Conecta-se com os processos de descentralização e fortalecimento dos governos locais. No Brasil, cuja trajetória é mais larga, estes vêm marcados principalmente pelas políticas do Ministério das Cidades e do Estatuto da Cidade (2001), que desenvolveu o Plano Diretor como a peça central do desenvolvimento deinido na Constituição de 1988, além de outros instrumentos de gestão urbana. De um modo similar mais recente, em Moçambique se está desenvolvendo uma política de descentralização da gestão urbana municipal. Usando instrumentos similares de planejamento, deinidos na Lei de Ordenamento do Território, a Política Nacional de Habitação reconhece a acesso à habitação adequada como um direito e vetor de inclusão social e deine as ferramentas para a sua implementação. No entanto, estas políticas ainda não tem uma dotação orçamentária deinida. A ação propõe os seguintes objetivos especíicos: 1. Melhorar as capacidades institucionais de gestão do desenvolvimento das Autoridades Locais (AL), consolidando-as como agentes de desenvolvimento em nível local e como atores de desenvolvimento em nível nacional e internacional no âmbito da cooperação descentralizada Sul-Sul. 2. Consolidar a articulação em rede de Autoridades Locais em Associações de Autoridades Locais (AAL), possibilitando a sua projeção como atores em cooperação, a criação de sinergias entre Autoridades Locais e fomentando a sua interação com outros atores descentralizados Concretamente, o projeto inclui o desenvolvimento, a adaptação local, a gestão e conhecimento de três ferramentas: o Planejamento Base, o Cadastro Inclusivo e o Plano de Orçamento Participativo / Business Plan mediante a troca de experiências entre as cidades dos dois países.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; south-south cooperation / cooperação sul-sul

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo; , Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra

Moçambique Inquérito Demográfico e de Saúde 2011 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2013)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Abraçando a participação local: A construção da democracia na África a partir dos territórios - de Oliveira, Osmany Porto (Osmany Porto, 2013)
Desenvolvida na cidade de Porto Alegre no Brasil em 1989 e consagrada como “boa prática” pela ONU em 1996, o Orçamento Participativo vem ganhando força na África. Na América Latina os efeitos do Orçamento Participativo estão associados ao estímulo à participação política e ao controle social, a inversão de prioridades nas políticas públicas, o aumento da transparência política e a promoção de justiça social. Na África Sub-sahariana esta política de governança participativa se enraíza a partir de 2003 quando municípios do Senegal e dos Camarões passaram a desenvolvê-la. A expansão do Orçamento Participativo no continente se traduz numa forma de construir a democracia, a partir da base dos Estados: os governos locais.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - portuguese / português; budget / orçamento; citizenship & participation / cidadania e participação

How active citizens can make a difference to improving service delivery in Mozambique: Phase 1: mapping citizen engagement programmes, initiatives and experiences - Programme, Citizen Engagement (2013)
The Citizen Engagement Program (CEP) supports citizens to monitor the quality of health and education service delivery in 4 of the 11 provinces of Mozambique, as well as to advocate for the improvement of the quality of those services at the district, provincial and national levels. The CEP aims at contributing towards the increased availability of relevant information for citizens to better access and benefit from services delivered by the public sector; improving citizens' capacity to assess service delivery and engage with service providers to improve the quality of health and education services at the primary and secondary levels; and supporting civil society organizations to leverage those findings within decision-making processes at higher levels. The programme will facilitate the dialogue between citizens / communities and service providers to improve the quality of services. The programme supports capacity-building, learning and experimentation, and will develop a robust system of monitoring and evaluation. The CEP will also analyse and build on experiences of service monitoring carried out by other actors and programmes, including other DFID and Irish Aid funded activities.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; citizenship & participation / cidadania e participação; decentralization / descentralização; gender / género; health / saúde; ⛔ No DOI found

Mid-Term Review of the AGIR Programme. Final report. - Kelpin; Johnsen, Vibe; Macuane, José Jaime; Christoplos, Ian; Rothman, Jessica (Decentralised Evaluation, 2013)
This mid-term review report of the ‘Action Programme for Inclusive and Responsible Governance’ (AGIR) in Mozambique was carried out from August 2012 to its completion at the end of October 2012 by a three-member review team fielded by Indevelop. A presentation of the preliminary findings was made on October 24th, 2012 to AGIR intermediaries and AGIR CSO partners. Subsequent to this presentation, the review team was provided with the just-completed 2012 semi-annual report, which was written and submitted jointly by AGIR intermediary organisations. AGIR has duration of five years beginning in 2010 and ending in 2014. Sweden is the only core donor, with Denmark and the Netherlands also providing support to participating INGOs (International Non-Governmental Organisations). The programme works with both national partners and with organisations in the provinces. In an effort to strengthen civil society and civil society organisations within Mozambique, the Swedish Embassy initiated the AGIR programme in 2010. The objective of AGIR is to: Support Mozambican civil society organisations, strengthening their capacity for and impact on improving transparency, accountability, citizen’s participation, access to information, respect for human rights, and gender equality. In line with the Paris Declaration and the Accra Agenda for Action, AGIR is structured to provide “good donor-ship” through support given for CSO ‘core funding’ that is aligned with the “strategic direction of the organisation” and to support and facilitate linkages and knowledge sharing between Mozambican CSOs.2 The main support modality for this capacity strengthening of CSOs is to “work through a limited number of qualified intermediary organisations within the following four clusters of support: i) Participation, social and legal accountability, including monitoring of respect for human rights; ii) Social accountability in management of natural resources and community land rights; iii) Transparency, financial and political accountability; and, iv) Promotion of access to information.”
Keywords: G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil

Support to Civil Society Engagement in Policy Dialogue - Ministry of Foreign Affairs of Denmark (Joint Evaluation, 2013)
This evaluation, the ‘Joint Evaluation of Support to Civil Society Engagement in Policy Dialogue’ was initiated by the Donor Group on Civil Society and Aid Effectiveness. Specifically it was commissioned by three Development Partners (DPs), ADC/Austria, Danida/Denmark and Sida/Sweden, which form the Management Group. A larger group of bilateral DPs support the evaluation through their participation as the international Reference Group. The evaluation took place between June 2011 and September 2012. The Evaluation Team was drawn from the consulting firm ITAD Ltd in the UK (lead firm), together with experts from COWI (Denmark) and experts from each of the three countries selected for the fieldwork, Bangladesh, Mozambique and Uganda. The purpose of this evaluation is lesson learning, to help DPs gain a better understanding of how best to support Civil Society Organisations (CSOs) in the area of policy dialogue. The findings will also have direct relevance to the CSOs in the three countries and the wider CSO community, as well as the Governments and local authorities interacting with Civil Society (CS) representatives. The evaluation focuses on: 1. How CSOs engage in policy dialogue and the relevance and effectiveness of their policy work; 2. the enabling environment, that is the enablers and barriers to CSO engagement; and 3. how different DP support strategies may influence CSOs’ ability to engage in policy dialogue, and how best the DPs might support CSO policy dialogue in the future.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; citizenship & participation / cidadania e participação; civil society / sociedade civil

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude

Desafios para Moçambique - 2013 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2013)
PARTE I – POLÍTICA BREVE REFLEXÃO SOBRE AUTARQUIAS, ELEIÇÕES E DEMOCRATIZAÇÃO / Luís de Brito POLÍTICA DE ELEIÇÕES EM MOÇAMBIQUE: AS EXPERIÊNCIAS DE ANGOCHE E NICOADALA / Adriano Nuvunga O TEMPO DAS VISITAS DA GOVERNAÇÃO ABERTA EM MOÇAMBIQUE / Euclides Gonçalves PARTE II – ECONOMIA REFLECTINDO SOBRE ACUMULAÇÃO, POROSIDADE E INDUSTRIALIZAÇÃO EM CONTEXTO DE ECONOMIA EXTRACTIVA/ Carlos Nuno Castel-Branco TENDÊNCIAS E PADRÕES DE INVESTIMENTO PRIVADO EM MOÇAMBIQUE: QUESTÕES PARA ANÁLISE / Nelsa Massingue | Carlos Muianga PORQUE É QUE OS BANCOS COMERCIAIS NÃO RESPONDEM À REDUÇÃO DAS TAXAS DE REFERÊNCIA DO BANCO DE MOÇAMBIQUE? REFLEXÕES / Fernanda Massarongo QUESTÕES À VOLTA DE LIGAÇÕES A MONTANTE COM A MOZAL /Epifânia Langa | Oksana Mandlate MERCADOS DE TRABALHO RURAIS: PORQUE SÃO NEGLIGENCIADOS NAS POLÍTICAS DE EMPREGO, REDUÇÃO DE POBREZA E DESENVOLVIMENTO EM MOÇAMBIQUE/ Rosimina Ali MULHERES NO PROCESSAMENTO DA CASTANHA DE CAJU: REFLEXÕES SOBRE AS SOCIEDADES AGRÁRIAS, TRABALHO E GÉNERO NA PROVÍNCIA DE CABO DELGADO / Sara Stevano EXPANSÃO DA PRODUÇÃO DE PRODUTOS PRIMÁRIOS, EMPREGO E POBREZA / Yasfir Ibraimo AGRO-INVESTIMENTOS PRIVADOS E SEUS REFLEXOS NA REGULAMENTAÇÃO FUNDIÁRIA E HÍDRICA EM DOIS REGADIOS ESTATAIS EM GAZA / Ana Sofia Ganho PARTE III – SOCIEDADE A FORMALIZAÇÃO DO TRABALHO DOMÉSTICO NA CIDADE DE MAPUTO: DESAFIOS PARA O ESTADO E ORGANIZAÇÕES LABORAIS / Ruth Kélia Castel-Branco “NÃO BASTA INTRODUZIR REFORMAS PARA SE TER MELHORES SERVIÇOS PÚBLICOS”: SUBSÍDIOS PARA UMA ANÁLISE DOS RESULTADOS DAS REFORMAS NO SUBSECTOR DE ÁGUA RURAL EM MOÇAMBIQUE / Salvador Forquilha “ACÇÃO SOCIAL PRODUTIVA” EM MOÇAMBIQUE: UMA FALSA SOLUÇÃO PARA UM PROBLEMA REAL /António Francisco PARTE IV – MOÇAMBIQUE NO MUNDO O BRASIL NA AGRICULTURA MOÇAMBICANA: PARCEIRO DE DESENVOLVIMENTO OU USURPADOR DE TERRA? / Jimena Dúran | Sérgio Chichava DISCURSOS E NARRATIVAS SOBRE O ENGAJAMENTO BRASILEIRO E CHINÊS NA AGRICULTURA MOÇAMBICANA / Sérgio Chichava | Jimena Dúran | Lídia Cabral | Alex Shankland | Lila Buckley | Tang Lixia | Zhang Yue
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Políticas Públicas e Relações internacionais: Elementos endógenos e exógenos nas transferências do Orçamento Participativo na África - de Oliveira, Osmany Porto (Seminário Internacional Participação, Democracia e Políticas Públicas: aproximando agendas e agentes, 2013)
Estudo da difusão internacional de Políticas Públicas (Análise de PP e estudo das RI) Caso: Orçamento Participativo Estratégia de análise: missões de pesquisa de campo in loco, observação participante em eventos, entrevistas e análise de documentos (100 entrivistas)
Keywords: *non-public; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - portuguese / português; budget / orçamento

Indirect Dispossession: Domestic Power Imbalances and Foreign Access to Land in Mozambique - Fairbairn, Madeleine (Development and Change, 2013)
Rather than treating the global land grab as a top-down phenomenon driven by global markets or foreign states, this article instead highlights the crucial mediating role played by the host state and domestic elites through a case study of Mozambique. I first introduce the domestic institutional framework, particularly the national Land Law and the institutions that determine the economic value of land. I then argue for an analysis of large-scale land acquisitions that brings into focus the effects of domestic power imbalances on determining the outcomes of foreign demand for land. I examine the ways in which domestic inequality may shape foreign land acquisitions through a typology of the sources of power that give domestic elites a privileged role in relation to foreign investors. The five sources of domestic power considered are: traditional authority, bureaucratic influence, historical accumulation, locally-based business knowledge and networks, and control over the development agenda. Finally, I conclude that the emphasis placed on the actions of the foreigner by both opponents (via framings of land acquisitions as neocolonialism or imperialism) and proponents (via solutions rooted in corporate codes of conduct) may obscure the ways in which pre-existing domestic inequality conditions the outcomes of these deals.
Keywords: G - Mozambique / Moçambique; L - english / inglês

“Não basta introduzir reformas para se ter melhores serviços públicos”: subsídio para uma análise dos resultados das reformas no subsector de água rural em Moçambique - Forquilha, Salvador (Desafios para Moçambique 2013, 2013)
Em Setembro de 2012, o Governo de Moçambique anunciou a mudança de critérios para o cálculo das taxas de cobertura de abastecimento de água nas zonas rurais. Com efeito, de 500 pessoas para um poço ou furo equipado com uma bomba manual, num raio de 500 metros, passou -se para 300 pessoas para um poço ou furo equipado com uma bomba manual. Esta mudança de critérios acontece mais de 15 anos depois da aprovação da Política Nacional de Águas (PNA) e resulta da constatação de que, em muitos casos, os números oficiais estão longe de reflectir o que realmente se passa no terreno em termos de taxas de cobertura. Uma das consequências imediatas desta medida é, provavelmente, a revisão em baixa das taxas de cobertura de abastecimento de água rural, o que vai reforçar a ideia de que, à semelhança do que acontece com outros serviços públicos, o abastecimento de água rural ainda está longe de satisfazer as reais necessidades das populações.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; health - WASH / saúde - água, higiene e saneamento; rural development / desenvolvimento rural; ⛔ No DOI found

"Acção social produtiva" em Moçambique: Uma falsa solução para o problema real - Francisco, António (Desafios para Moçambique 2013, 2013)
O artigo está organizado em quatro secções. A primeira secção aborda a seguinte questão: “Qual é a essência do real problema que o conteúdo e a operacionalização da ASP não identifica correctamente?” Esta questão é respondida em dois momentos ou subcapítulos. Inicia-se por sublinhar a importância da distinção entre os principais meios de aquisição da riqueza para a identificação do problema real da sociedade moçambicana e relevante para o debate sobre a pobreza. De seguida, apresenta-se um breve enquadramento da protecção social formal moçambicana, com destaque para o quadro da actual ortodoxia oficial sobre a natureza e as causas da pobreza. A segunda secção reúne um conjunto de dados e relações empíricas, caracterizadoras da dimensão demográfica, económica e social do problema real da população moçambicana. Chama a atenção para a natureza das mudanças em curso na estrutura etária, manifestada no aumento da dependência infantil. Uma dependência que a população tenta compensar, através da participação activa em actividades económicas de todas as gerações: crianças-adolescentes, jovens/adultos e idosos. A terceira secção toma como referência a análise das secções anteriores, para demonstrar que uma solução errada para um problema errado é, por definição, duplamente errada e gratuita. De forma resumida, apresenta os objectivos, o que é e qual é o alcance da iniciativa ASP em curso; argumenta, de seguida, que a ASP não é social nem produtiva. A quarta secção contém algumas considerações finais e a conclusão. Explica porque não tem sentido fazer acompanhar a análise crítica da iniciativa ASP de uma proposta alternativa, visando convertê-la numa acção alegadamente mais produtiva do que tem sido. Respondendo à questão “Justifica-se a ASP?”, o artigo defende que a resposta depende da perspectiva de protecção social seguida; identifica algumas das respostas que têm sido dadas, desde a resposta do Governo, a qual se inspira ou está alinhada com a do Banco Mundial, até à do próprio autor deste texto. Após mostrar que a ASP oferece uma falsa solução para um problema real, o artigo termina identificando duas implicações desta constatação: uma política e outra social
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; social action / ação social; social protection / proteção social

Youth Social Exclusion and Lessons from Youth Work: Evidence from literature and surveys - Paolini, Giulia; Brel, Patrice; Vanandruel, Colette (European Commission Education, Audiovisual and Culture Executive Agency (EACEA), 2013)
It is widely recognised that social exclusion produces deep and long-term damage to the living conditions, social and economic participation, emotional life, and health status of young people. It also contributes to the intergenerational transmission of poverty. In turn, insecurity in living standards, political and social isolation, feelings of estrangement and unhealthy lifestyles aggravate pre-existing conditions of social exclusion. This results in a vicious circle where socially excluded young people are in even more danger of suffering from additional material deprivation, social and emotional marginalisation, and health issues, which in turn expose them to more serious risks of exclusion. Almost one out of three young persons between the ages of 18 and 24 is at risk of poverty or social exclusion in the European Union. Youth work can offer opportunities for preventing and remedying this vicious circle. By offering young people targeted support, opportunities for non-formal learning, information on health and wellbeing, and opportunities for positive integration into the local community, youth workers are able to reduce the risks of further social exclusion linked to deteriorating living conditions and unhealthy life styles. The EU Youth Strategy recognises the relevance of youth work to mitigating the effects of social exclusion amongst young people. Reaffirming this concept, the Council Resolution on Youth Work of 2010 invited Member States and the Commission to support the development of youth work at local, regional, national and European level. The relation between youth work and social inclusion also touches upon the priorities established by the 2012 EU Youth Report. A general overview of the fundamental threats to social inclusion experienced by young people can be found in the dedicated chapter of the Youth Report. The benefits coming from youth work to the inclusion of young people, and in particular of those with a migrant background, has been recognised in the Conclusions of the Council of 27 November 2012. To address the risks of exclusion run by many young individuals, the Social Investment Package adopted by the European Commission seeks to improve the situation of young people by tackling childhood disadvantage, improving access to quality education and support services, helping young people develop skills relevant to the labour market, and ensuring work experience and on-the-job training and helping young people find a first good job (European Commission, 2013a). This paper aims at offering evidence about the situation of social exclusion suffered by young people in the European Union, and the positive effects that youth work initiatives produce in fostering their (re)inclusion. Looking at factual information on the main conditions of exclusion is essential to have an accurate understanding of the threats encountered by young people. Available data and research literature illustrate the major reasons behind the marginalisation of young Europeans, and pave the way to the development of effective policy strategies to prevent it.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Brazil’s cooperation in African agricultural development and food security - Patriota, Thomas Cooper; Pierri, Francesca Maria (Agricultural development and food security in Africa: The impact of Chinese, Indian and Brazilian investments, 2013)
Brazil’s agricultural cooperation in Africa is shifting from small localised projects to more structured ventures capable of having larger and more durable impacts on African rural development. Nonetheless, it still suffers from in adequate coordination between relevant ministries and other governmental bodies. However, the coexistence of two agricultural development paradigms in Brazil’s cooperation should not be seen as incoherent. Rather, it is a direct reflection of the twotiered structure of Brazil’s agricultural policy framework, with support for agribusiness provided by the Ministry of Agriculture, Livestock and Food Supply (Ministério da Agricultura, Pecuária e Abastecimento) and for family farming by MDA. Consequently, the Brazilian government has attempted to present both as part of the Brazil–Africa Dialogue to enable African ministers to learn about the wide range of policies implemented in Brazil. Combined with demanddriven horizontal cooperation, the approach has enabled African countries to choose between (and sometimes combine) approaches to promoting their agriculture.
Keywords: G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural; south-south cooperation / cooperação sul-sul

Políticas Públicas e Relações internacionais: Elementos endógenos e exógenos nas transferências do Orçamento Participativo na África - Porto de Oliveira, Osmany (Encontro Internacional: Participação, Democracia e Políticas Públicas: aproximando agendas e agentes, 2013)
Com cerca de 2500 casos no mundo, o Orçamento Participativo (OP) é um exemplo emblemático da proliferação em escala global das políticas de governança participativa. A literatura sobre o assunto avançou nas dinâmicas internas das experiências de OP. Todavia, ainda se conhece pouco sobre sua dimensão transnacional e as dinâmicas de circulação deste dispositivo de governança participativa. Este artigo se vale do estudo das relações internacionais e das análise de políticas públicas para preencher um vácuo na literatura. O objeto de pesquisa é a difusão do OP na África subsaariana, analisada à partir de suas dinâmicas regionais e de três casos representativos de transferência do OP na região. Este trabalho se fundamenta em informações coletadas in loco no Moçambique, na África do Sul e no Senegal.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - portuguese / português; budget / orçamento; ⛔ No DOI found

Brazil, biofuels, and food security in Mozambique - Thali, Kai (Agricultural development and food security in Africa: The impact of Chinese, Indian and Brazilian investments, 2013)
This chapter, therefore, explores the role of agriculture in Brazilian develop ment assistance programmes and direct investment in Africa, focusing on the potential tensions between biofuel feedstock and food production. After a brief overview of the history of Brazil’s own agricultural development and the country’s relations with Africa, the chapter delves into an examination of Brazilian engagement in the conjoined agricultural and energy sectors of Mozambique, a country that possesses large tracts of arable land and is considered a prime site for biofuel production. The chapter critiques Brazil’s development assistance and investment model and presents ways to improve its effectiveness in order to generate greater benefits for the Mozambican people.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; agriculture / agricultura

Algumas cartas abertas ao Presidente da República e da FRELIMO - Various, Paulo (2013)
A collection of open letters to the president of the Republic and FRELIMO
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português

Translating the Idea of the eGovernment One-Stop-Shop in Indonesia - Wahid, Fathul (Springer, 2013)
This study aims to understand how the idea of an eGovernment one-stop-shop (OSS) has been translated into a new setting. Since the beginning of 2000, this idea has been implemented in a variety of ways by Indonesian local governments. Using an interpretive case study in the city of Yogyakarta, the study revealed that the specificity of each setting influences the translation process of the idea of OSS during its institutionalization. It also identified a set of editing rules used during the translation process. These include the editing rules concerning context (e.g., internal readiness); logic (e.g., corruption eradication); and formulation (e.g., standardized processes). The study also found that the idea translation was not a single round process.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Programa de Acção Social Produtiva (PASP) - Documento Base - INAS - Instituto Nacional de Acção Social (Ministério da Mulher e da Acção Social, República de Moçambique, 2012)
O presente documento surge assim como um instrumento de operacionalização do PASP visando clarificar as intervenções deste programa que é mais uma contribuição da segurança social básica para os esforços do Governo no combate à pobreza, alinhando-se com outras intervenções em curso, como por exemplo, o Programa Estratégico de Redução da Pobreza Urbana (PERPU), o Fundo de Desenvolvimento Distrital (FDD) e o Programa Nacional de insumos Agrícolas. O PASP procura contribuir para a superação da insegurança alimentar crónica agravada pelos choques e riscos estruturais e impactos das mudanças ambientais, como as secas, desemprego, permitindo que os agregados familiares abrangidos tenham estabilidade económica e social. O PASP toma como alvo de intervenção os Agregados Familiares (AF) com pelo menos um elemento com capacidade para o trabalho, enfrentando altos níveis de vulnerabilidade, com prioridade para os agregados chefiados por mulheres, por pessoas com deficiências e com crianças com problemas de desnutrição, que estejam localizados nas zonas urbanas e rurais, a partir do envolvimento destes em trabalhos públicos como principal veículo para a disponibilização de transferências sociais monetárias que lhes permitam estabilizar o seu rendimento e consumo. Os mesmos agregados familiares são encorajados em seguida a se envolverem em iniciativas de geração de rendimentos através de um conjunto de acções enquadradas num processo de preparação social para a graduação. O presente documento desenvolve o modelo de intervenções do PASP, os seus objectivos, componentes, nomeadamente, trabalhos públicos com o uso da mão-de-obra intensiva e apoio ao desenvolvimento de iniciativas de geração de rendimentos, as ligações necessárias entre este. Programa e outros processos no âmbito do combate à pobreza, bem como os mecanismos de implementação, financiamento e os factores críticos de sucesso do Programa.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; social protection / proteção social

Promoting SME development in Indonesia - Mourougane, Annabelle (OECD Economics Department Working Papers, 2012)
Micro, small and medium-sized firms (MSMEs) are a key source of employment and economic growth in Indonesia. They contributed to the country’s economic resilience during the 2008-09 financial crisis. But many suffer from low productivity, curbing their role in boosting living standards. There are several ways to spur MSME productivity growth over the medium term. The first route would be to encourage the formalisation of small firms. Lessening red tape through simplification of the licensing process and lower tax compliance costs would help. Avoiding excessive rises in the minimum wage in provinces where it is already at a reasonable level would also be important. Looking forward, it would be useful to remove rigidities in the formal labour markets, while moving to some form of unemployment benefit system to insure workers against job-loss risks. The second route would be to boost investment. Clarifying property rights for real estate, and making the information collected by the credit bureau available to all financial institutions would ease access to finance. At the same time, the development of financing alternatives such as venture capital, leasing or micro-finance would enhance credit supply. The poor state of infrastructure, in particular in the transportation and electricity sectors, is also perceived as an important impediment to investment and could be remedied by increasing public infrastructure spending on cost-effective projects. The third route would be to enhance the quality of human resources. The country suffers from a lack of skilled workers, and policies should aim both at increasing the pool of workers and making education and training institutions more responsive to evolving labour-market demand. Indonesia has a long tradition of supporting MSMEs. But responsibilities between the different levels of government and within the central government need to be clarified to minimise overlap and inefficiencies. A rigorous assessment of existing programmes would allow schemes to be consolidated and scarce public funds to be directed to their most cost-effective uses.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Avaliação Conjunta do: Apoio à Participação da Sociedade Civil no Diálogo sobre Políticas - ITAD; COWI (ITAD/COWI, 2012)
Estudo de Caso 1. Planificação Distrital e Monitoria do Orçamento Planificação Distrital e Monitoria do Orçamento são processos interligados mas distintos. A Planificação Distrital é um processo de política ao abrigo da LOLE1, segundo a qual a participação das comunidades locais é um princípio básico na governação local e gestão de bens públicos. A planificação distrital é um processo simples, no qual a sociedade civil (SC) local é representada através dos Conselhos Consultivos Locais. O processo de planificação é muitas vezes uma “lista de compras”, sem ligação com a definição de prioridades do orçamento, que é feita ao nível do governo central ou provincial, muitas vezes depois de a planificação ter sido feita a nível distrital. A monitoria sistemática do orçamento é um exercício recente em Moçambique, embora tenha já sido feita sob os auspícios de várias projectos apoiados por Organizações Internacionais da Sociedade Civil (OISCs). Baseia-se na experiência da SC em vários mecanismos de diálogo sobre políticas (por exemplo, Observatórios de Desenvolvimento (ODs)). Estudo de Caso 2. Legislação sobre Violência Doméstica A violência contra a mulher (VCM), em geral, e a violência doméstica contra as mulheres, em particular, constituem um problema global. Em Moçambique, é uma prática generalizada e, infelizmente, largamente aceite, que assenta em sólidos papéis tradicionais de género. Isto é testemunhado por estudos e casos documentados recolhidos por OSCs (WLSA, Le Musica), e por estatísticas dos Gabinetes de Atendimento para mulheres vítimas de violência37. Os casos de violência doméstica contra as mulheres eram, porém, vistos como pertencendo à esfera doméstica (privada) e, assim sendo, não eram considerados uma questão pública; e, até recentemente, não havia nenhum enquadramento jurídico da questão.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; civil society / sociedade civil; gender / género

The Human Rights Impacts of Tree Plantations in Niassa Province, Mozambique - Seufert, Philip; Santos, Ricardo (FIAN International, 2012)
This study investigates the impairing of the rights of peasant communities through the establishment of tree plantations in Niassa province, Mozambique. More particularly, it looks at the impacts of the operations of Chikweti Forests of Niassa on the local population in the districts of Lago, Lichinga and Sanga. In order to do so, it presents an introductory chapter on the general context of Mozambique and the legal framework. This legal framework will serve as a basis on the analysis of the findings of this study using a human rights approach. It contains an overview of national and international provisions relevant to the case. This includes Mozambican national legislation and policies, as well as standards under international human rights law. Regarding the latter, it puts a particular focus on extraterritorial obligations (ETOs), recently clarified by the Maastricht Principles on Extraterritorial Obligations, and includes provisions related to access to land and related resources, as contained in the Voluntary Guidelines on the Responsible Governance of Tenure of Land, Fisheries and Forests.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; rural development / desenvolvimento rural

Saúde Para O Povo? Para Um Entendimento Da Economia Política E Das Dinâmicas Da Descentralização No Sector Da Saúde Em Moçambique - Weimer, Bernhard (Moçambique: Descentralizar o Centralismo? Economia Política, Recursos E Resultados, 2012)
Houve em 2011 três acontecimentos que revelaram as dimensões dos desafios que se colocam à gestão do Sistema Nacional de Saúde moçambicano em geral e ao Ministério de Saúde (MISAU) em particular. O primeiro foi uma auditoria externa das contas de 2009 do PROSAUDE II e do Fundo Global, realizada pela empresa de auditoria KPMG e entregue ao governo e aos seus parceiros internacionais em Junho de 2011. Esta auditoria revelou fraquezas consideráveis, nomeadamente em relação à auditoria interna e uma substancial diferença final não reconciliada entre os valores recebidos e os pagamentos efectuados. O segundo foi a crise de abastecimento de medicamentos, amplamente divulgada dos produtos farmacêuticos, quando os meios de comunicação noticiaram, num período de Março a Julho, que, no armazém farmacêutico central do MISAU, o CMAM,49 em Maputo, havia medicamentos no valor de pelo menos 2 milhões de USD que estavam fora de prazo; que os medicamentos se tinham esgotado nos hospitais públicos na Zambézia; e que grandes quantidades de medicamentos tinham desaparecido da farmácia do Hospital Central de Nampula.50 Os doadores recusaram um pedido de um montante adicional de 25 milhões de dólares para reabastecimento de medicamentos, feito pelo Ministro da Saúde em Março de 2011, argumentando que o governo teria que abordar e resolver as questões pendentes dos resultados da auditoria de 2009, antes de os doadores do PROSAUDE assumirem quaisquer compromissos de financiamento adicionais.51 Em terceiro lugar, pouco antes do fim do ano, o pessoal da saúde na Cidade de Nampula, incluindo os médicos, ameaçaram fazer greve, se não lhes fossem pagos os salários, três meses atrasados. Estes acontecimentos põem em relevo, em síntese, alguns dos principais desafios com que a gestão do sector da saúde se debate em Moçambique. Não se sabe até que ponto estes acontecimentos e o que eles revelam sobre a gestão de recursos no sector da saúde afectaram o funcionamento das unidades de saúde nas províncias e distritos, e o impacto sobre a saúde das pessoas doentes e da população em geral. Estas unidades dependem crucialmente de recursos (pessoal, financiamento e medicamentos) para o cumprimento da sua missão de controlar a doença e salvar vidas humanas, ou seja, para produzir os resultados de saúde que lhes compete alcançar, muitas vezes medidos com o indicador DALY.52 Neste artigo, não tentaremos avaliar o impacto das práticas de gestão no sector da saúde e os seus resultados em termos de vidas humanas. Tentaremos antes entender as dinâmicas políticas, económicas e institucionais que influenciam os resultados de saúde e o desempenho das unidades de saúde ao nível subnacional em Moçambique. O nosso argumento é que estas variáveis são determinadas não apenas por factores endógenos ao sector de saúde, como sejam as suas políticas e quadro regulamentar, a sua estrutura institucional, o grau de descentralização, e ainda os recursos que lhe são atribuídos e as suas capacidades de gestão. Também há factoresexógenos, como as decisões orçamentais do Ministério das Finanças, a Ajuda ao Desenvolvimento da Saúde (ADS)53 por parte dos doadores e as suas políticas e mecanismos de atribuição de fundos, como a abordagem sectorial integrada (SWAp)54 e o financiamento conjunto, bem como a mudança social e económica e as formas de governar um país, que produzem impactos decisivos no sistema de saúde e nos seus resultados. No que diz respeito à temática da descentralização da saúde, partimos, em primeiro lugar, do princípio que os ‘objectivos gerais da descentralização e a abordagem sectorial não são incompatíveis’, uma vez que tanto os primeiros como a segunda ‘têm por objectivo aumentar a eficiência técnica; incentivam uma maior participação; e põem a tónica na transparência e prestação de contas’ (Hutton, 2002: 3. Original em inglês). Em segundo lugar, chamamos a atenção para a necessidade de reconhecer um papel forte e normativo do Estado central nas políticas de saúde, na sua gestão, supervisão e questões de equilíbrio social, especialmente em matéria de cuidados de saúde primários, uma vez que a descentralização pode levar à diferenciação e à diversidade e não ao reforço da justiça social nos padrões e no acesso às unidades de saúde (Collins & Green, 1994). Como Booth sugeriu, o papel do Estado central é fundamental, nomeadamente em institucionalizar e supervisionar, do topo para a base, a disciplina de desempenho eficaz na componente de recursos humanos e na produção de serviços de qualidade a nível local (Booth, 2010: 34). Para este artigo, optámos por usar um quadro da análise político-económica para examinar alguns dos determinantes endógenos e exógenos. Do ponto de vista conceptual, a análise da economia política e da descentralização no sector da saúde pode ser estruturada de várias maneiras. Uma, é analisando as mudanças de epidemiologia, de características biomédicas dos corpos humanos e de ocorrênciaschave nos ciclos da vida humana (por exemplo, a fertilidade, a morbilidade ou mortalidade) como resultantes de intervenções por parte das instituições do sector da saúde, em condições sociais, económicas, ambientais e culturais em mudança. Esta abordagem é muitas vezes centrada na pobreza e assenta no pressuposto de que as mudanças institucionais, como a descentralização da prestação de serviços de saúde, conduzem a um aumento do bem-estar e a uma melhoria da saúde nas sociedades, se as intervenções institucionais (planos, programas, prestadores de serviços, etc.) forem ‘correctos’ e dispuserem de suficientes recursos financeiros e humanos, e capacidades, bem como de um quadro adequado de políticas. Dessa forma, julga-se que as taxas de fertilidade e mortalidade acabarão por diminuir, que as doenças infecciosas serão controladas e podem ser alcançados outros progressos no combate à pobreza e à doença (O’ Laughlin, 2010: 7).
Keywords: G - Mozambique / Moçambique; L - portuguese / português; decentralization / descentralização; health / saúde

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

Promoting Respectful Maternity Care in Mozambique - Reis, Veronica (USAID, 2012)
The objective of this document is to share the results of work undertaken in Mozambique to promote respectful health care, particularly in maternal and neonatal care. With its origins in “humanization of care” efforts in Latin America, this approach centers on the woman and her family and is grounded by principles of ethics and respect for human rights. The approach recognizes a client’s cultural background, and views the client as a person with values and expectations that should be respected during the provision of health care. Respectful maternity care (RMC) emphasizes the fundamental rights of the mother, newborn, and family, and recognizes that childbirth is a deeply personal experience for each woman and her family. In addition, RMC ensures that the client has timely access to health information, privacy, and evidence-based care. Promoting RMC can result in many benefits, including increased service utilization and better health outcomes. It is known that women refuse care from health providers who treat them poorly, even if these providers are capable of preventing or managing obstetric or newborn complications. In countries where a large proportion of births occur outside health facilities, RMC can contribute to increased uptake of maternal and newborn health (MNH) services.
Keywords: G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; gender / género; health - dignified care / saúde - atendimento humanizado / mau atendimento; health - maternal and child / saúde - materno-infantil; health / saúde

O contexto de REDD+ em Moçambique: Causas, actores e instituições - Sitoe, Almeida; Salomão, Alda; Wertz-Kanounnikoff, Sheila (CIFOR, 2012)
Desde 2009, o CIFOR iniciou o Estudo Comparativo Global de REDD+ (GCS-REDD) em novo países: Bolívia, Brasil, Peru, República dos Camarões, República Democrática do Congo, Tanzânia, Indonésia, Nepal e Vietname. Uma analise parcial é feito em três países: Papua Nova Guiné, Moçambique e Burkina Faso. Depois de analisar políticas nacionais e estratégias emergentes de REDD+, os pesquisadores do CIFOR desenvolveram cinco áreas de trabalho para cada país. Essas áreas incluem um perfil do país, análise de mídia, análise da rede de políticas, análise de conteúdo politico, e uma quinta área de estudos. de políticas específicas, a ser determinada pelos resultados de pesquisas emergentes. Este estudo fornece uma visão geral do contexto de REDD+ em Moçambique através de uma síntese do conhecimento actual das principais causas da mudança de carbono florestal, uma revisão do quadro legal e institucional, e uma descrição do processo político actual de REDD+. O objectivo é reunir dados e informações pertinentes, e oferecer uma análise preliminar dos aspectos fundamentais a ter em conta para políticas de REDD+ eficazes, eficientes e equitativas. Especificamente, este estudo constata que entre os maiores problemas encontra-se a falta de dados sobre o desmatamento e a degradação florestal, fraquezas institucionais (na fiscalização e nos direitos de propriedade) e lacunas na capacidade técnica e humana para enfrentar as exigências ligadas a REDD+. Assim, os resultados eficazes dependerão do grau em que as políticas de REDD+ forem orientadas à mitigação real das fontes de mudança de carbono florestal. Em Moçambique, estas tendem a se originar de fora do sector madeireiro. O custo-eficácia dos resultados dependerá de se as causas fundamentais da mudança de carbono florestal são identificadas e tratadas com opções políticas mais viáveis de REDD+; da capacidade do governo de responder às exigências de REDD+, sobretudo a nível subnacional, mas também da capacidade da sociedade civil e outras instituições; e da força do quadro institucional. O grau de sucesso dos resultados equitativos e a geração de co-benefícios dependerá se os processos são inclusivos e realmente apropriados nacionalmente; se aqueles que suportam os custos de REDD+ também estão sendo compensados; e da definição sobre os direitos do carbono e dos serviços ambientais em geral
Keywords: G - Mozambique / Moçambique; L - portuguese / português

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - MAP Consult (2012)
The powerpoint has the same objective as the article (see related section). ------- The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; G - Mozambique / Moçambique; Health PEA; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; health / saúde

The White Gold: The Role of Government and State in Rehabilitating the Sugar Industry in Mozambique - Buur, Lars; Mondlane Tembe, Carlota; Baloi, Obede (The Journal of Development Studies, 2012)
This article examines the rehabilitation of the sugar industry in Mozambique after the General Peace Accord in 1992, engaging primarily and critically with certain aspects of the business-state literature. It explains why the sugar sector was rehabilitated from the perspectives of Mozambican state, government and industry actors. The article argues that support for the industry cannot be identified in singular and one-dimensional terms, but must include a variety of attributes of support that emerged from a post-independence fusion of industry, state and government officials' historical experiences of success and failure in the industry, and pragmatic as well as longer-term ideological stances. This, it is argued, created a ‘mediating bureaucracy’ that could broker between the diverse interests and aspirations of state/government and industry.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Political economy of the health sector in Mozambique: Towards an understanding of its features, dynamics and challenges - Weimer, Bernhard; Cumbi, Amelia J.; Macuane, José Jaime (MAP Consult, 2012)
The present study was commissioned by the Department for International Development (DFID) in Mozambique. As a piece of independent research on the political economy of the health sector, it is considered to inform DFID’s health sector support programme for the period 2012-2016 and to lead to more in-depth inquiries of Mozambique’s health sector. The latter has witnessed a number of institutional, management, financial and governance challenges in the past few years, including a change in leadership considered important for the sector. The objective of this consultancy is to inform the development of a health sector support programme for the Government of Mozambique and to highlight particular political economy challenges and opportunities that DFID Mozambique should take into account in supporting PROSAUDE.
Keywords: *non-public; *tagged; G - Mozambique / Moçambique; L - english / inglês; decentralization / descentralização; health / saúde

Gender Disparity in Laws and Female Employment - Amin, Mohammad (Mimeograph, 2012)
Berkeley Electronic Press Selected Works, In a large sample of firms in 66 developing countries, it is shown that gender specific disparity in the laws favoring males over females tends to lower the employment of females relative to males at the firm level. However, this relationship between gender disparity in laws and employment is driven by small and medium firms, and it does not hold for the sample of large firms. However, the relationship holds equally in rich vs. poor countries, small vs. large cities within countries and among firms with and without female owners. We also confirm a sharp negative effect of gender disparity in the laws on the absolute level of employment of females. In short, in the presence of gender disparity in the laws, suitable reforms or policy measures promoting female employment may be required to achieve greater employment of women and greater gender parity in employment.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Effects of food price shocks on child malnutrition: the Mozambican experience 2008/09 - Arndt, Channing; Hussain, M. Azhar; Østerdal, Lars Peter (World Institute for Development Economics Research (WIDER), 2012)
A propitiously timed household survey carried out in Mozambique over the period 2008-09 permits us to evaluate the short-to-medium run relationship between sudden shocks to food prices and child nutrition status. We link local price inflation with child malnutrition status. We find that the prevalence of underweight amongst children rises in response to a higher inflation rate for basic food products. Stunting and wasting malnutrition measures are mostly insensitive to the inflation rate. The very high food inflation during 2008/09 was responsible for an extra 39,000 moderately underweight and 24,000 severely underweight children.
Keywords: G - Mozambique / Moçambique; L - english / inglês; health / saúde

Mozambique’s Coming Natural Resource Boom Expectations, Vulnerabilities, and Policies for Successful Management - Biggs, Tyler (USAID, 2012)
Mozambique is set to become a world-class natural resource exporter with projections indicating that it will experience rapid increases in windfall revenues over the next several decades and well beyond. While this is welcome news for a low-income country with a substantial proportion of the population below the poverty line, it foreshadows some economic management problems ahead. The main concern is the poor economic record of many other lowincome countries with large natural resource endowments. It is remarkable how often these countries have experienced inferior rates of growth compared with countries lacking such endowments. This pattern, known as the ―natural resource curse,‖ has been documented in empirical research across a wide sample of nations.
Keywords: *indexed; *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; extractive industries / indústrias extractivas; natural disasters / desastres naturais

Afrobarometer Round 5. Summary of Results for Mozambique, 2012 - Centro de Pesquisas de Governação e Desenvolvimento (CPGD) (Centro de Pesquisas de Governação e Desenvolvimento (CPGD), 2012)
The Afrobarometer is a comparative series of public attitude surveys that will be covering up to 35 African countries in Round 5 (2011-2013). Based on representative national samples, the surveys assess citizen attitudes to democracy and governance, markets, and civil society, among other topics. The first round of surveys was conducted between 1999-2001 and covered seven Southern African countries (Botswana, Lesotho, Malawi, Namibia, South Africa, Zambia and Zimbabwe), three countries in West Africa (Ghana, Nigeria and Mali) and two in East Africa (Uganda and Tanzania). Round 2 surveys were completed by November 2003 with four new countries added: Kenya, Senegal, Cape Verde and Mozambique. Round 3 surveys were conducted from March 2005 to February 2006 in the same countries, plus Benin and Madagascar. The 4th Round of surveys covered 20 countries between 2008 and 2009, with the addition of Burkina Faso and Liberia.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; civil society / sociedade civil; governance / governação

Desafios para Moçambique - 2012 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2012)
PARTE I – POLÍTICA POBREZA, “PARPAS” EGOVERNAÇÃO / Luís de Brito A DESCENTRALIZAÇÃO AJUDA A REDUZIR A POBREZAPOLÍTICA EM MOÇAMBIQUE? / Joao C.G. Pereira APRENDIZADO DE POLÍTICAS PÚBLICAS NO CONTEXTO DO PARP:ABORDAGEM BASEADA NAS REDES / José Jaime Macuane UNIVERSIDADES MOÇAMBICANAS E O FUTURO DE MOÇAMBIQUE / Lourenço do Rosário PARTE II – ECONOMIA PARP 2011-2014: CONTRADIÇÕES, TENSÕES E DILEMAS/ Carlos Nuno Castel-Branco DA ECONOMIA EXTRACTIVA À DIVERSIFICAÇÃO DA BASE PRODUTIVA:O QUE PODE O PARP UTILIZAR DA ANÁLISE DO MODO DE ACUMULAÇÃO EM MOÇAMBIQUE? / Carlos Nuno Castel-Branco | Oksana Mandlate SERÁ A ITIEM RELEVANTE PARA MELHORAR A GESTÃO DOS RECURSOS MINERAIS?UMA ANÁLISE CRÍTICA DA EXPERIÊNCIA / Rogério Ossemane AGRICULTURA, POBREZA E A RECEITA DO PARP /Philip Woodhouse POLÍTICA MONETÁRIA E REDUÇÃO DA POBREZA EM MOÇAMBIQUE: DISCUSSÃO CRÍTICA / Carlos Nuno Castel-Branco | Rogério Ossemane DESAFIOS DE DESENVOLVIMENTO DA BASE PRODUTIVA: UM OLHAR A PARTIR DO PARP 2011-2014 / Carlos Muianga OPÇÕES DE FINANCIAMENTO DO INVESTIMENTO PÚBLICO: UM OLHAR CRÍTICO SOBRE O PARP 2012-14 / Sofia Amarcy MEGA-PROJECTOS NO MEIO RURAL, DESENVOLVIMENTO DO TERRITÓRIO E POBREZA: O CASO DE TETE / João Mosca | Tomás Selemane PARTE III – SOCIEDADE POLÍTICA PÚBLICA E INTERVENCIONISMO: PORQUE EXISTE O PARP EM MOÇAMBIQUE? / António Francisco IDOSOS EM MOÇAMBIQUE: ROMPER A CONSPIRAÇÃO DO SILÊNCIO / Gustavo Sugahara | António Francisco O DESAFIO DA SAÚDE RURAL / Bridget O’Laughlin REFLEXÕES SOBRE EMPREGO E REDUÇÃO DA POBREZA NO PARP: DESAFIOS PARA UMA ABORDAGEM ALTERNATIVA / Yasfir Ibraimo PARTE IV – MOÇAMBIQUE NO MUNDO CRISE GLOBAL, CRESCIMENTO E DESAFIOS PARA MOÇAMBIQUE E SUA ESTRATÉGIA DE DESENVOLVIMENTO / Carlos Oya INVESTIMENTO DIRECTO ESTRANGEIRO E O COMBATE À POBREZA EM MOÇAMBIQUE: UMA LEITURA A PARTIR DO INVESTIMENTO CHINÊS NA AGRICULTURA / Sérgio Chichava
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Mozambique Social Protection Assessment - Review of Social Assistance Programs and Social Protection Expenditures - Marques, José Silvério (World Bank, 2012)
This assessment shows that Mozambique social protection system is developing. While programs to address most of the risks identified exist, there are still major gaps. Poor families with children are not adequately supported, there is no significant youth program, and subsistence farmers and other workers are not properly protected against recurrent shocks. The government spends a considerable amount of its resources on social protection but most are absorbed by untargeted subsidies and pensions that benefit only a few. This assessment suggests that it will be necessary to address three mutually complimentary issues: developing effective mechanisms to maximize the impact of social protection on reducing poverty; rationalizing public expenditures while filling existing program gaps; and strengthening institutional arrangements. In order to address the multiple challenges Mozambique faces to support particularly vulnerable groups and reduce extreme poverty and food insecurity, the report proposes a gradual approach framed in the existing social protection strategy approved by the Government in 2010.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; social protection / proteção social

From Negligence to Populism: An Analysis of Mozambique’s Agricultural Political Economy - Rosário, Domingos Manuel do (2012)
The paper analyses the changing configuration of the political system since the Rome Peace Agreement of 1992. It discusses how the “political settlement” underlying the Peace Agreement and the outcomes of multiparty elections thereafter have shaped governance, including policy-making concerning the agriculture sector and the rural economy. The paper argues that private interests and electoral objectives have been important drivers of policy decisions taken by the governing elites concerning the agriculture sector and local governance, with precedence over donor influence. By contrasting the political choices and governance approaches adopted by the two different presidential administrations in office since the first multiparty elections were held in 1994, it is argued that one (led by Joaquim Chissano) is marked by features of “neopatrimonialism”, whereas the other (led by Armando Guebuza) is showing signs of electoral “populism”. The former is characterised by significant rent distribution by the governing elite to a narrow “selectorate”. The latter is manifested by a paternalistic and politically mobilising discourse emanating directly from the President and appealing to the broader electorate, particularly the rural population of the central and Northern region of the country, who has been traditionally opposed to the ruling party
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura

Transforming Cash Transfers: Beneficiary and community perspectives of the Basic Social Subsidy Programme in Mozambique - Selvester, Kerry; Fidalgo, Lourdes; Tambo, Neila (Overseas Development Institute (ODI), 2012)
The increasing recognition that social protection programmes in developing countries can play an important role in inclusive and transformative development is welcomed by analysts as a step towards supporting extremely poor households in these countries. In Mozambique, the national cash transfer programme, the Basic Social Subsidy Programme (Programa de Subsídio Social Básico or PSSB), which began in 1992, provides a relatively low value of 130 MTn (approx. $4.5) to 380 MTn (approx. $13), narrowly targeted transfer to nearly 300,000 extremely vulnerable households. The programme has clear political commitment to sustainability, using state funds. The PSSB is not an isolated intervention; rather, it is part of a broader social protection platform that includes providing support to households that temporarily find themselves unable to overcome a specific shock or event, along with social assistance delivered through the health and education sectors. The social protection system in Mozambique is in the process of being reformed and modernised, which should result in a more transparent and accountable system. One of the key reforms involves the development of a management information system (MIS) that will provide an integrated technical platform for the management of the social assistance programmes. The key research objectives of this study are:  to explore the views, experiences and perceptions of cash transfer programme beneficiaries and other community members (non-beneficiaries) in order to ensure that they are better reflected in policy and programming  to gather perceptions and experiences from programme implementers  to provide examples of best practice on how to involve beneficiaries and communities in participatory monitoring and evaluation (M&E) of cash transfer programmes  to build the capacity of national researchers in qualitative and participatory data collection and analysis. The research report presents background information on cash transfers in Mozambique in order to frame the detailed qualitative and participative study conducted in two districts in the southern province of Gaza, Chokwe and Chibuto. The research focuses on people with disabilities who receive the cash transfer. Currently, of the 286,176 people with disabilities living in poverty), less than 14,000 households with disabled members are receiving the government cash transfer. The fieldwork for the research was preceded by a demand generation consultation (DGC) exercise that provided valuable insights into stakeholders’ concerns in terms of the delivery and impact of the PSSB on beneficiaries’ lives, particularly on households headed by people with disabilities. Stakeholders were concerned that the research examined the extent to which beneficiaries are aware of their rights, the procedures and regulations of the PSSB, and whether there was any transparency, at local level, in the selection of beneficiaries. The research team used a wide variety of qualitative data collection tools with a view to collecting in-depth information about the impact of the cash transfer on beneficiaries’ lives and perceptions of all stakeholders (including beneficiaries) about the extent to which the PSSB was a transparent and accountable mechanism. All of the fieldwork tools were pre-tested in the peri-urban area of BairroAreoporto, Maputo city. There was unanimous agreement among all stakeholders interviewed that the value of the transfer was too low to be considered a transformative measure and is rather perceived as a minimum welfare payment to reduce the possibility of vulnerable households becoming destitute. Advocacy is needed to increase the real value of the transfer in order to strengthen resilience of the most vulnerable households. The Mozambique Government’s implementing agency, the National Institute for Social Action (INAS), recognises that the fiscal space for the programme is still relatively constrained, whic vi means there is a lack of sustainable financial capacity to address the problems of all vulnerable groups that fall within its mandate. Improving beneficiary management and outsourcing payments to private sector providers are the main pillars of change currently proposed by INAS to begin to address this issue. Our research highlighted the need for coordinated and harmonised support to the sector by development cooperation partners to ensure that reform efforts build an integrated social protection system rather than creating unsustainable ad hoc programmes that satisfy the short-term goals of individual donor agencies. The research clearly identified how little information was available about the PSSB at all levels of the system, leading to a lack of transparency, and ultimately a lack of accountability to beneficiaries. The report recommends that there is a need for a comprehensive communication and education strategy to reach all the stakeholders, including the use of media (particularly radio), capacity-building and refresher training for staff and community liaison agents, and the production and dissemination of simple printed materials describing key elements of the programme. There was a clear indication in the research that people with disabilities are under-represented in the programme, and more importantly do not feel that they have a right to complain about any aspects of it. A lack of understanding (on the part of the implementing agency and staff) about the needs of the programme’s target groups has led to people feeling that the cash transfer was solely a pension provided to older people, those who are unable to work and those who are chronically poor. Physical access to the people who fill in the application forms1 was considered less of a barrier than feelings of lack of entitlement by extremely poor people living with a disability. Making targeting mechanisms and criteria more transparent (easily understood) through clear and well-disseminated information would reduce the bias against applicants with disabilities. Our research also found that demand for accountability from beneficiaries was low, as they generally have few expectations of the government institutions or other agencies that provide assistance ‘system’; creating a demand for transparency is a challenge that will require considerable political will, information campaigns and engagement of multiple stakeholders. With the aforementioned modernisation of the social protection system, there are openings to improve transparency that could lead to greater accountability at all levels. These include the development of an effective grievance system to increase and improve communication between beneficiaries and INAS, which, over time, could create a sense of mutual accountability and trust. In addition, there were calls from INAS officials, local leaders and beneficiaries for independent, participatory monitoring of the programme. The recently formed Civil Society Platform for Social Protection is designing a community-based monitoring system for social assistance programmes, which will be piloted in 2013. Government actors as well as non-government actors in Mozambique recognise that there is a lack of structured and institutionalised coordination and collaboration between entities working in the social protection sector. This leads to duplication of efforts in some areas and glaring service gaps in others. Mechanisms need to be set up at local level to bring these entities together to share information and establish simple working guidelines for collaboration. Each district should establish locally specific mechanisms based on guiding principles of openness, collaboration and transparency of action. There are deep concerns about the human resource capacity of INAS to fulfil its wide mandate of not only providing social assistance transfers but moving towards case management of beneficiaries and the delivery of a transparent and accountable social protection system. Throughout the report, the voice of programme beneficiaries is clearly presented, indicating above all the urgency required to deliver more effective and efficient social protection programmes that will give the most disenfranchised people an opportunity to participate socially and economically in society.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; government policy / politica governamental; social protection / proteção social

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

How do female entrepreneurs perform? Evidence from three developing regions - Bardasi, Elena; Sabarwal, Shwetlena; Terrell, Katherine (Small Business Economics, 2011)
Using the World Bank Enterprise Survey data, we analyze performance gaps between male- and female-owned companies in three regions—Eastern Europe and Central Asia (ECA), Latin America (LA), and Sub-Saharan Africa (SSA). Among our findings are significant gender gaps between male- and female-owned companies in terms of firm size, but much smaller gaps in terms of firm efficiency and growth (except in LA). Part of the reason women run smaller firms is that they tend to concentrate in sectors in which firms are smaller and less efficient (in ECA and SSA). By contrast, we find no evidence of gender discrimination in access to formal finance in any of the three regions, although in ECA women are less likely than men to seek formal finance. Finally, while female entrepreneurs receive smaller loans than their male counterparts, the returns from each dollar they receive is no lower in terms of overall sales revenue.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Gender and the Business Environment for New Firm Creation - Klapper, Leora F.; Parker, Simon C. (The World Bank Research Observer, 2011)
Abstract. The authors summarize the extant literature on the relationship between gender and entrepreneurship. They note significant quantitative gender differ
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

The Preparatory Survey on Nacala Port Development Project in the Republic of Mozambique Final Report - JICA (Japan International Cooperation Agency (JICA), 2011)
Japan International Cooperation Agency (JICA) decided to conduct the preparatory survey on Nacala Port Development Project in the Republic of Mozambique, and organized a survey team headed by Dr. Kobune of Ides and consists of OCDI, Oriental Consultants, ECOH CORPORATION, and Ides between June, 2010 and April, 2011. The survey team held a series of discussions with the officials concerned of the Government of the Republic of Mozambique, and conducted field investigations. As a result of further studies in Japan, the present report was finalized. I hope that this report will contribute to the promotion of the project and to the enhancement of friendly relations between our two countries. The Study Team compiled this report, which proposed the Medium and Long-term Development Plan of Nacala Port with the target year of 2030 and the Short-term Development Plan, and selected the Urgent Rehabilitation Project through close consultations with officials of the Mozambique Government, in particular, Ministry of Transport and Communications (MTC), Portos e Caminhos de Ferro de Mocambique E.P. (CFM), as well as the Management of Corredor de Desenvolvimento do Norte (CDN), and authorities concerned.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Prioritising PPCR Investments in Mozambique: The Politics of ‘Country Ownership’ and ‘Stakeholder Participation’ - Shankland, Alex; Chambote, Raul (2011)
Mozambique is both one of the poorest countries and one with the highest level of vulnerability to multiple potential consequences of climate change, including drought, flood, sea level rise and increased frequency and severity of tropical cyclones – making it a natural candidate for inclusion in the Pilot Program for Climate Resilience (PPCR), which aims to help poorer countries to integrate climate change response into their national development processes. This article examines the process of prioritising investments under the PPCR in Mozambique, and asks to what extent this process has demonstrated the ‘country ownership’ and ‘broad participation’ which the PPCR claims to promote. It particularly focuses on the coastal cities component of the programme, and the question of whether the opposition-controlled port city of Beira should receive priority in PPCR investments.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP)

Desafios para Moçambique - 2011 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2011)
PARTE I – POLÍTICA ESTADO, DESCENTRALIZAÇÃO E CIDADANIA – EQUAÇÃO POSSÍVEL OU IMPERATIVA? / José Óscar Monteiro “TRANSFORMAÇÕES SEM MUDANÇAS?” OS CONSELHOS LOCAIS E O DESAFIO DA INSTITUCIONALIZAÇÃO DEMOCRÁTICA EM MOÇAMBIQUE / Salvador Cadete Forquilha | Aslak Orre DESCENTRALIZAÇÃO EM CONTEXTO DE PARTIDO “DOMINANTE” – O CASO DO MUNICÍPIO DE NACALA PORTO / Domingos do Rosário REVISÃO DA LEGISLAÇÃO ELEITORAL – ALGUMAS PROPOSTAS PARA O DEBATE / Luís de Brito PARTE II – ECONOMIA DESAFIOS DA MOBILIZAÇÃO DE RECURSOS DOMÉSTICOS – REVISÃO CRÍTICA DO DEBATE / Carlos Nuno Castel-Branco DESAFIOS DE EXPANSÃO DAS RECEITAS FISCAIS EM MOÇAMBIQUE / Rogério Ossemane FINANCIAMENTO DO ESTADO COM RECURSO À DÍVIDA – PROBLEMAS E DESAFIOS / Fernanda Massarongo | Carlos Muianga DESAFIOS DA EXPANSÃO DE SERVIÇOS FINANCEIROS EM MOÇAMBIQUE / Sofia Amarcy | Nelsa Massingue “7 MILHÕES” – REVISÃO DO DEBATE E DESAFIOS PARA DIVERSIFICAÇÃO DA BASE PRODUTIVA / Zaqueo Sande PARTE III – SOCIEDADE TER MUITOS FILHOS, PRINCIPAL FORMA DE PROTECÇÃO SOCIAL NUMA TRANSIÇÃO DEMOGRÁFICA INCIPIENTE – O CASO DE MOÇAMBIQUE / António Francisco PROTECÇÃO SOCIAL FINANCEIRA E DEMOGRÁFICA – DESAFIOS PARA UMA SEGURANÇA HUMANA DIGNA EM MOÇAMBIQUE / António Francisco | Rosimina Ali | Yasfir Ibraimo POLÍTICAS DE HIV E SIDA E DINÂMICAS SOCIOCULTURAIS EM MOÇAMBIQUE – NOTAS PARA REFLEXÃO /Sandra Manuel PARTE IV – MOÇAMBIQUE NO MUNDO SADC – COOPERAÇÃO E SEGURANÇA PÚBLICA / João Paulo Borges Coelho AS ECONOMIAS “EMERGENTES” NO SECTOR AGRÍCOLA MOÇAMBICANO – LEITURAS, IMPLICAÇÕES E DESAFIOS / Sérgio Chichava DEPENDÊNCIA DE AJUDA EXTERNA, ACUMULAÇÃO E OWNERSHIP – CONTRIBUIÇÃO PARA UM DEBATE DE ECONOMIA POLÍTICA / Carlos Nuno Castel-Branco
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Ten years of single window implementation: lessons learned for the future - Koh, Jonathan (Global Trade Facilitation Conference 2011, 2011)
This paper examines the Single Window concept and its developments in practice over the last 10 years and provides an analysis of its development over time. An overview of the emerging information technology that would impact its future development is also presented. The paper also examines regional trends in Single Window implementation, based on a survey of tenders documents issued by various countries in the recent years. Finally, it offers an outlook on its future development and provides a number of recommendations.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; ⛔ No DOI found

Accountability Through Dialogue: The Presidencîa Aberta E Inclusiva In Mozambique - Leininger, Julia (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Accountability is a central feature of democracy. Governments must explain what they are doing, justify why they are doing certain things and not others. Moreover, accountability increases the likelihood of the improvement of public services if citizens have the political scope to hold politicians and administrators accountable, and potentially sanction them. Consequently, developing countries as well as the OECD-donor community have committed themselves to working towards the improvement of domestic accountability in developing countries. In many developing countries, accountability is exercised through both formal and informal institutions. This paper summarises the results of an empirical study on accountability in Mozambique. It focuses on the Presidência Aberta e Inclusiva (PAI, Open and Inclusive Presidency), a legally not codified institution for accountability introduced by President Armando E. Guebuza. It provides a public forum for the president to engage in a dialogue with the population and the local administrations, in combination with an ongoing process of decentralisation. This study shows that the interaction between formal and more informal institutions has a mixed influence on policymaking and democracy. Overall, there is an untapped potential to improve the PAI as an institution for accountability that strengthens formal institutions.
Keywords: G - Mozambique / Moçambique; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação

Abastecimento De Água Nas Zonas Rurais: Avaliação Dos Progressos Para a Prestação De Serviços Sustentáveis - Munguambe, Carlos Gideon José; Jesus, Vitória Afonso Langa de (IRC International Water and Sanitation Centre, 2011)
This study presents an analytical ‘picture’ of the rural water sub-sector in Mozambique, describing the legal framework, mechanisms for coordination, harmonisation, funding, accountability, participation and supervision. The study was commissioned for the Sustainable Services at Scale, or Triple-S, initiative, which aims to contribute to improving the sustainability of global rural water supply. According to the general population census carried out in 2007, Mozambique had a total population of 20,226,296, 70.2% of whom live in rural areas, with a water coverage rate of only 54%.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; health - WASH / saúde - água, higiene e saneamento; health / saúde

Decentralization and Economic Performance in Indonesia - Pepinsky, Thomas B.; Wihardja, Maria M. (Journal of East Asian Studies, 2011)
Indonesia's 1999 decentralization law gave local governments in Indonesia an unprecedented opportunity to adopt prodevelopment policies. In this article, we study whether decentralization has in fact generated improved economic performance in Indonesia. Using a synthetic case control methodology, we argue that Indonesian decentralization has had no discernable effect on the country's national-level economic performance. To explain why not, we use subnational data to probe two political economy mechanisms-interjurisdictional competition and democratic accountability-that underlie all theories linking decentralization to better economic outcomes. Our findings suggest that extreme heterogeneity in endowments, factor immobility, and the endogenous deterioration of local governance institutions can each undermine the supposed development-enhancing promises of decentralized government in emerging economies such as Indonesia.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Examining and Exploring Indonesia Small and Medium Enterprise Performance: An Empirical Study - Pribadi, Henry; Kanai, Kazuyori; Kanai, Kazuyori (Asian Journal of Business Management, 2011)
Abstract: This study attempts to explore and examining about Indonesia Small and Medium Enterprise (SME) performance through relationship with strategic management theory. We apply strategic management model into our research to explain the relationship of firm performance with firm determinants. Firm strategy, external environment factors and internal resource factors of firm will be used as determinant of firm performance. Samples from Indonesia SME are collected and statistical analysis is applied to produce valid results. Result shows direct positive relationship of firm strategy and internal factors of firm with firm performance. Direct positive relationship of external and internal factors of firm with firm strategy also recorded. Our finding shows that high perform firms of Indonesia SME tend to use differentiation strategy, emphasize on organization assets and human resource capabilities, and focus more on customer needs.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo

Local economic governance: a survey of business operators in 245 districts/municipalities in Indonesia, 2011 - The Asia Foundation; Regional Autonomy Watch (Local Economic Governance, 2011)
Decentralization has been underway in Indonesia for more than ten years, but recently many have challenged the how effectively decentralization – and even democratization – is being implemented. Deterioration in the quality of public services, the many corruption cases involving local governments, and low economic growth rates in some regions have prompted discourse about whether the country is making a reversal away from decentralization and democratization. We recognize that the move toward regional autonomy has not been without its faults. Nevertheless, a choice was made to strengthen democracy and move towards local autonomy based on the problems created by the centralistic, authoritarian system of the previous regime. Yet it is unfair to judge regional autonomy a failure after it has been implemented for such a short time, and under a somewhat inconsistent policy framework. Since 2001, the Regional Autonomy Watch (KPPOD) and The Asia Foundation have aimed to present a clear picture of the quality of regional economic governance from the perspective of business owners. Our studies provide input to government at the central, provincial and regional/municipal levels, as well as information to other stakeholders regarding efforts that can be undertaken to promote improve economic growth under regional autonomy. This year’s study finds significant variation among regions in the quality of economic governance. This indicates that despite many limitations, some regions have used the opportunities provided by autonomy to foster good governance while others have not. It is hoped that this present study, and the awards presented to regencies and municipalities with the best performance, will promote a healthy competition among regional leaders. It is also envisioned that local governments whose performance is still low can learn from their neighbors who are doing better, and be inspired to improve. We recognize that improving economic governance requires a strong commitment and hard work, not only from the heads of regions but from all ranks of government officials, politicians, business owners and other stakeholders. This study can help set priorities for reform of local economic governance, identifying areas for immediate improvement that are relatively easy to achieve but have the potential of significant impact. Other aspects may need more time for improvement.
Keywords: G - Rest of the World / Resto do Mundo; L - english / inglês; M - survey / inquérito; Northern PEA; decentralization / descentralização

Health Commodity Security Project - World Bank (World Bank, 2010)
Information document about the Health Commodity Security Project. It is divided in the sections below: - Country and Sector Background - Objectives - Rationale for Bank Involvement - Description - Financing - Implementation - Sustainability - Lessons Learned from Past Operations in the Country/Sector - Safeguard Policies (including public consultation) - List of Factual Technical Documents - Contact point - For more information contact
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; health / saúde

“All I Eat Is ARVs:” The Paradox of AIDS Treatment Interventions in Central Mozambique - Kalofonos, Ippolytos Andreas (Medical Anthropology Quarterly, 2010)
The number of people on antiretroviral treatment in Mozambique has increased by over 1,500 percent since it first became free and publicly available in 2004. The rising count of “lives saved” seems to portray a success story of high-tech treatment being provided in one of the poorest contexts in the world, as people with AIDS experience dramatic recoveries and live longer. The “scale-up” has had significant social effects, however, as it unfolds in a region with a complicated history and persistent problems related to poverty. Hunger is the principal complaint of people on antiretroviral treatment. The inability of current interventions to adequately address this issue leads to intense competition among people living with HIV/AIDS for the scarce resources available, undermining social solidarity and the potential for further community action around HIV/AIDS issues. Discourses of hunger serve as a critique of these shortcomings, and of the wider political economy underlying the HIV/AIDS epidemic.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; Health PEA; L - english / inglês; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Astill-Brown_Weimer_Moz_conflict_por.pdf - Astill-Brown, Jeremy; Weimer, Markus (Chatham House, 2010)
Este documento foi comissionado pelo Departamento de Desenvolvimento Internacional do Reino Unido (DfID) com o objectivo de ajudar a desenvolver, em todo o governo britânico, uma melhor compreensão dos desafios à paz e à segurança em Moçambique. O documento foi concebido principalmente para contribuir para o desenvolvimento da política do governo britânico (e correspondente estratégia de influência) em relação a Moçambique, bem como para aprofundar a consciência dos riscos potenciais inerentes às abordagens adoptadas pelo governo britânico para a prestação de assistência no sector de desenvolvimento. Embora o documento se baseie, em grande parte, na Análise Estratégica de Conflitos de 2006 – e embora muitas das suas conclusões sejam semelhantes – a verdade é que tem um âmbito muito mais extenso. O documento contém uma análise de vários aspectos do conflito embora conste, de uma maneira geral, de uma análise de riscos políticos focalizando um ambiente político e económico variável. Como tal, cobre assuntos de interesse para a comunidade governamental britânica em geral, propondo ainda sinergias entre esta e o programa de desenvolvimento. O documento cobre apenas as principais questões estratégicas e proporciona um ponto de partida para discussões intra-governamentais sobre linhas de acção que sejam tanto possíveis como apropriadas. Esta investigação teve início em Fevereiro de 2010, com um período de revisão da literatura. A seguir, em Março do mesmo ano, os autores visitaram Moçambique, onde entrevistaram doadores, funcionários do governo, membros de partidos políticos e de organizações da sociedade civil, académicos e outros interessados, à procura não de dados mas sim de impressões e perspectivas. As suas conclusões preliminares foram apresentadas em Maputo, em Maio de 2010. As investigações foram lideradas por Jeremy Astill-Brown e Markus Weimer, com a ajuda de Carolina Hunguana e Alex Vines.
Keywords: G - Mozambique / Moçambique; L - english / inglês; conflict / conflito; security / segurança

Ex-Post Evaluation Report of Grant Aid Projects 2009 (Mozambique) - JICA (Japan International Cooperation Agency (JICA), 2010)
Ex-post evaluation of ODA projects has been in place since 1975 and since then the coverage of evaluation has expanded. Japan’s ODA charter revised in 2003 shows Japan’s commitment to ODA evaluation, clearly stating under the section “Enhancement of Evaluation” that in order to measure, analyze and objectively evaluate the outcome of ODA, third-party evaluations conducted by experts will be enhanced. This volume shows the results of the ex-post evaluation of Grant Aid projects that were mainly completed in fiscal year 2006. The ex-post evaluation was entrusted to external evaluators to ensure objective analysis of the projects’ effects and to draw lessons and recommendations to be utilized in similar projects.
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Final Report 1 of 3 Summary - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part I-II - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-IV - JICA (Japan International Cooperation Agency (JICA), 2010)
The Study Road (N13: Cuamba – Mandimba – Lichinga), as part of the two Mozambican corridors (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors), provides a strategic link to the Malawi Border at Mandimba with the ports of Nacala and Pemba, in Nampula and Cabo Delgado Provinces respectively. Although the Study Road has much potential for stimulating development and reducing poverty throughout the entire northern area of Mozambique by enabling efficient connection, the section concerned is the only unpaved section. The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-V - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors)
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part VI: Environmental and Social Considerations - JICA (Japan International Cooperation Agency (JICA), 2010)
In response to the request from the Government of the Republic of Mozambique, the Government of Japan decided to conduct the Preparatory Survey on Road Improvement Plan in Nacala Development Corridor (N13: Cuamba-Mandimba-Lichinga) and entrusted the study to the Japan International Cooperation Agency (JICA). Objectives of the study: (1) The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. (2) Formulation and recommendation of the “Regional Development Program” intended for Niassa Province is also the objective of the Study.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part IV Economic Feasibility Study - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter1 Existing Traffic Flow Patterns This chapter aims to analyze traffic flow patterns on the Study Road based on various information in order to conduct the appropriate traffic demand forecast. Chapter 2 International Goods Transportation Though Nacala Corridor This chapter aims to discuss the current condition of international goods transportation through Nacala Corridor in order to estimate future traffic demand on the Study Road. Chapter 3 Traffic Demand Forecast 3.1 Macro-Economic Background 3.2 Forecasting Methods 3.3 Traffic Demand Forecast 3.4 Results of Traffic Forecast Chapter 4 Economic and Financial Analysis (Cuamba-Mandimba Section) The Study objective is “to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing earth/ gravel roads in the rural areas to paved roads.” For the purpose of the economic evaluation, it is important to first define the existing state of the Project road for the base case, and then to define the alternatives to be analyzed, and finally the structure of the analysis.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part V Cross-Border Facilities - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter 1 Mozambique-Malawi Border Control and Facilities 1.1 Current Condition of Cross-Border Traffic between Mozambique and Malawi 1.2 Border Facilities between Mozambique and Malawi 1.3 Border Control System and Border Facilities Chapter 2 Mandimba Border Control and Facilities 2.1 Characteristics of Mandimba Border Area 2.2 Cross-Border Traffic and Cargo 2.3 Mandimba Border Post and Facilities 2.4 Chiponde Border Post and Facilities Chapter 3 Strategy for Upgrading Border Control and Facilities 3.1 SADC-COMESA Regional Strategy 3.2 One Stop Border Posts 3.3 Mozambique-Malawi Bilateral Strategy Chapter 4 Implementation Approach for Upgrading Mandimba Border Facilities 4.1 Needs Assessment and Proposed Approach for Implementation 4.2 Methodology for OSBP Phased Introduction 4.3 Challenges to OSBP Introduction Chapter 5 Border Development Strategy for Upgrading Mandimba Border Facilities 5.1 Traffic Demand Forecast at Mandimba-Chiponde Border 5.2 Proposed Implementation Policy 5.3 Proposed Facility Planning for Phased Introduction of OSBP
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Nationalism, urban poverty and identity in Maputo, Mozambique - Sumich, Jason (2010)
This paper examines the changing perceptions of Frelimo's nationalist project amongst members of the middle class in Maputo, Mozambique's capital. I argue that nationalism in Mozambique created a system of meaning and new forms of identity that are especially relevant for more privileged urbanites. However, growing urban poverty and inequality has had an effect throughout the social spectrum in Mozambique. The self-same set of nationalist values provides a critique for the failings of the regime as everyday life continually conflicts with the government's message of unity and progress for all and this is causing a loss of support even among the regime's beneficiaries.
Keywords: G - Mozambique / Moçambique; L - english / inglês; urbanization / urbanização

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

Economia extractiva e desafios de industrialização em Moçambique - Castel-Branco, Carlos Nuno (Cadernos IESE, 2010)
A experiência económica de Moçambique é frequentemente apresentada como um exemplo de sucesso na promoção de rápido crescimento com estabilização e redução da pobreza. Paradoxalmente, a economia nacional mantém anormalmente elevadas taxas de dependência em relação a fluxos externos de capitais, tanto oficiais (ajuda externa) como privados (investimento directo estrangeiro e empréstimos no sistema bancário internacional). Como é que este nível de dependência é consistente com a história de sucesso? Se o investimento privado é tão dependente de fluxos externos de capitais, e se estes fluxos reflectem sobretudo os interesses globais dos grandes investidores multinacionais interessados em explorar os recursos naturais (terra, florestas, minerais e energéticos) de Moçambique, que padrão de produção e comércio está sendo criado? Não será, a continuação desta dependência profunda, um indicador da fragilidade estrutural da base produtiva, comercial e fiscal da economia? Ao longo da última década e meia, a eficácia do crescimento da economia em reduzir pobreza, medida pela elasticidade da redução da percentagem da população que vive abaixo da linha da pobreza em relação à taxa de crescimento do Produto Interno Bruto (PIB), tem vindo a reduzir. Até que ponto é que a redução da eficácia do crescimento económico a reduzir pobreza reflecte os padrões de acumulação, crescimento e distribuição gerados pela dependência da economia em relação ao investimento privado estrangeiro (concentrado em grandes projectos de recursos naturais)? Até que ponto seria esta eficácia ainda pior na ausência de ajuda externa para financiar o investimento público? Este artigo concentra-se da discussão das causas estruturais das fraquezas dos padrões de acumulação económica em Moçambique. O artigo desenvolve o conceito de economia extractiva e relaciona-o com a história e a economia política do padrão de acumulação, distribuição e reprodução. Esta discussão é realizada revisitando as análises históricas e os dados oficiais da economia moçambicana e, nesse processo, explorando duas vertentes relacionadas: a composição do crescimento económico e o seu impacto na estabilidade estrutural da macroeconomia de Moçambique. Finalmente, o artigo discute alguns desafios fundamentais para a transformação destes padrões e, por conseguinte, para o processo de industrialização.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

Desafios para Moçambique - 2010 - de Brito, Luís; Castel-Branco, Carlos Nuno; Chichava, Sérgio; Francisco, António (Instituto de Estudos Sociais e Económicos, 2010)
PARTE I – POLÍTICA – DESAFIOS DA CONSTRUÇÃO DEMOCRÁTICA O SISTEMA ELEITORAL: UMA DIMENSÃO CRÍTICA DA REPRESENTAÇÃO POLÍTICA EM MOÇAMBIQUE / Luís de Brito GOVERNAÇÃO DISTRITAL NO CONTEXTO DAS REFORMAS DE DESCENTRALIZAÇÃO ADMINISTRATIVA EM MOÇAMBIQUE LÓGICAS, DINÂMICAS E DESAFIOS / Salvador Cadete Forquilha SOCIEDADE CIVIL EM MOÇAMBIQUE EXPECTATIVAS E DESAFIOS / António Francisco DESAFIOS DA GESTÃO MUNICIPAL DE UMA LÓGICA ADMINISTRATIVA E INSTITUCIONAL PARA UMA LÓGICA DE DESENVOLVIMENTO ORGANIZACIONAL E SUSTENTABILIDADE / João Noronha | Lídia Brito UMA BREVE ANÁLISE DA IMPRENSA MOÇAMBICANA / Sérgio Chichava | Jonas Pohlmann PARTE II – ECONOMIA – DESAFIOS DA CONSTRUÇÃO DE UMA ECONOMIA SUSTENTÁVEL CRISES CÍCLICAS E DESAFIOS DA TRANSFORMAÇÃO DO PADRÃO DE CRESCIMENTO ECONÓMICO EM MOÇAMBIQUE / Carlos Nuno Castel-Branco | Rogério Ossemane DESAFIOS DO DESENVOLVIMENTO RURAL EM MOÇAMBIQUE / Carlos Nuno Castel-Branco | Nelsa Massingue | Rosimina Ali A TERRA NO CONTEXTO DO DESENVOLVIMENTO DA INDÚSTRIA MINEIRA PRESSÕES E CONFLITOS EM TORNO DOS DUATS / Virgílio Cambaza FINANCIAR O DESENVOLVIMENTO / Abdul Magid Osman PARTE III – SOCIEDADE – DESAFIOS DE CIDADANIA, EDUCAÇÃO E URBANIZAÇÃO CONSTITUIÇÃO E REFORMA DA JUSTIÇA UM PROJECTO POR REALIZAR / João Carlos Trindade OS DESAFIOS DA LEITURA / Miguel Buendía EDUCAÇÃO, FORMAÇÃO PROFISSIONAL E PODER / Roland Brouwer | Lídia Brito | Zélia Menete DESAFIOS DO ENSINO SUPERIOR / Narciso Matos | João Mosca DESAFIOS NO DOMÍNIO DA HABITAÇÃO / Júlio Carrilho | Luís Lage PARTE IV – MOÇAMBIQUE NO MUNDO – DESAFIOS DE INTEGRAÇÃO E COOPERAÇÃO MOÇAMBIQUE NO MUNDO A COMPETIÇÃO SUBTIL / Abdul Magid Osman | Nelson Saúte MOÇAMBIQUE NA ROTA DA CHINA UMA OPORTUNIDADE PARA O DESENVOLVIMENTO? / Sérgio Chichava
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; politics / política; society / sociedade

Small and Medium Enterprises (smes) Access to Finance in Selected East Asian Economies - Harvie, Charles; Oum, Sothea; Narjoko, Dionisius A (ERIA - Economic Research Institute for ASEAN and East Asia, 2010)
Findings from ERIA’s SME research project in FY 2009 confirms that access to finance is amongst the most critical factors determining the competitive readiness of regional SMEs and their ability to fully exploit and participate in the global economy and business opportunities from regional economic integration and, in particular, participation in regional production networks. Well recognized in the literature, access to funding is the lifeblood of any enterprise, enabling it to grow, and to generate more output and employment. There is considerable evidence to support the contention that SMEs, in particular, face a number of obstacles and problems in accessing finance, mainly related to their limited resources and perceived risk by lenders. This is particularly problematic and worrisome for policy makers, given that SMEs and entrepreneurship are widely recognized as being the key sources of dynamism, innovation, and flexibility in advanced industrialized, emerging market and developing economies, and are major net job creators in these economies. Without access to finance, SMEs are unable to invest, impairing their capacity to: improve productivity; raise competitiveness; promote innovation; generate employment; and contribute to economic growth and development.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; ⛔ No DOI found

The Expansion of Tree Monocultures in Mozambique. Impacts on Local Peasant Communities in the Province of Niassa - Overbeek, Winfridus (Movimento Mundial pelas Florestas Tropicais, 2010)
This publication is the result of a visit to Mozambique in November 2009 by two activists involved in the struggle against tree monocultures in the Brazilian state of Espírito Santo. This visit was made possible by the World Rainforest Movement (WRM) with the goal of exchanging experiences about large-scale tree monocultures. With more than 40 years of dealing with monoculture plantations and expansion, Brazil has a lot of experience in this area. At the same time, affected communities and supporting organizations in the country have led several struggles and acts of resistance and formed alliances, which nearly ten years ago resulted in the foundation of the Alert against the Green Desert Network (Rede Alerta contra o Deserto Verde). In the past few years, WRM has been made aware of the fact that more and more tree monocultures are being planted in Mozambique. Since Brazil and Mozambique have in common Portuguese as their official language, the idea arose to promote the exchange between the two countries so as to: − exchange experiences with the affected communities about the impacts; − better understand the current situation of the introduction and expansion of tree monocultures in Mozambique; and, − identify organizations involved or interested in the subject. This visit would not have been possible without the invaluable help of our friends at UNAC (União Nacional de Camponeses - National Peasant Union) in Mozambique, and UCA (União dos Camponeses e Associações de Lichinga - Union of Peasant and Associations of Lichinga), who volunteered to receive and accompany the Brazilian delegation and organized the visits to the communities. We also want to thank Via Campesina Brasil for their support in this initiative.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; rural development / desenvolvimento rural

Gender and poverty in Mozambique - Tvedten, Inge (CMI Brief, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found

Género e pobreza em Moçambique - Tvedten, Inge (CMI, 2010)
A igualdade de género e o empoderamento das mulheres estão no centro das agendas do governo e dos doadores na África Sub-Sahariana, mas no geral não conseguiram ter impacto. Mais do que a ‘integração’ do género, é necessária mais atenção às variações da posição das mulheres. Numa série de três estudos sobre políticas de género e feminização da pobreza em Moçambique, foram encontradas diferenças significativas entre o norte e o sul, bem como entre as áreas rural e urbana. É essencial que se compreendam estas variações para se desenhar políticas e intervenções relevantes para a melhoria das condições das mulheres no país.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; empowerment / empoderamento; gender / género; poverty / pobreza

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

'Não fica bem que uma mulher seja chefe quando existem homens'. Género e Pobreza no Sul de Mocambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2010)
Este relatório final é o terceiro da série "Políticas de Género e Feminização da...
Keywords: G - Mozambique / Moçambique; G - south / sul; L - portuguese / português

Relatório para o Governo da Província de Cabo Delgado e Agência Espanhola de Cooperação Internacional para o Desenvolvimento (AECID) - Umarji, Mariam; Makda, Sadya; Paulo, Arsénio; Lalá, Aly (SAL & Caldeira, 2009)
O relatório que se segue retrata a avaliação conduzida ao Sistema de Gestão de Finanças Públicas da Província de Cabo Delgado considerando o ciclo orçamental do ano de 2008, considerando a informação de contabilidade, reporte e auditoria relacionada com este ano mas produzida em 2007 e em 2009. A avaliação teve como base a Metodologia PEFA – Despesa Pública e Responsabilidade Financeira – devidamente adaptada ao nível subnacional (província) de acordo com as orientações metodológicas emanadas pelo Secretariado PEFA. Foram utilizados um total de 25 indicadores para a avaliação. Os indicadores reflectem a situação actual do sistema e fornecem um ponto de comparação para avaliações ou seguimentos futuros dos progressos esperados nos processos de planificação, orçamentação, contabilidade, reporte e auditoria da província. Esta Avaliação Sumária apresenta as constatações finais da equipa de consultores sendo fruto do trabalho de campo realizado para inquérito e recolha de evidência combinada com a revisão documental de informação recebida e disponibilizada de forma a se poder realizar a avaliação dos diferentes indicadores.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; budget / orçamento; fiscal policy / política fiscal

Relatório Final da Pesquisa sobre o Impacto da Descentralização dos Fundos Sectoriais de Estradas, Águas e de Construção Acelerada de Salas de Aulas nas Províncias, nos Distritos e nas Autarquias Locais - Kulipossa, Fidelx Pius; Nguenha, Eduardo Jossias (The Open University consultancy, 2009)
A 17a Sessão Ordinária do Conselho de Ministros realizada em 2007 tomou a corajosa decisão de descentralizar os fundos dos sectores de estradas, águas, agricultura, e infra-estruturas de educação e saúde para garantir a implementação efectiva da Lei 8/2003 sobre os Órgãos Locais do Estado e materializar os objectivos estratégicos definidos no PARPA II e no Plano Quinquenal do Governo. Tal decisão, em parte, reconhece que a pobreza absoluta que flagela muitos cidadãos está estreitamente ligada à falta de acesso aos serviços básicos tais estradas, água potável, infra-estruturas escolares e de saúde e outros serviços úteis para a sobrevivência e sustentabilidade da vida humana. Com efeito, presumia-se que ao se descentralizar estes fundos sectoriais para os níveis provinciais e distritais, as instituições locais teriam maior capacidade de resposta às demandas da população em termos de prestação de melhores serviços, de maneira que ela estivesse mais satisfeita e participasse activamente na vida política e económica do país. Em termos de produção legislativa, regista-se avanço significativo na descentralização de fundos sectoriais. Porém, sendo essa legislação muito recente e em fase primária de sua implementação, constatam-se algumas reservas na implementação efectiva da mesma. Por exemplo, os progressos sectoriais na descentralização de fundos são diferenciados. No sector de estradas, os fundos são geridas e os pagamentos efectuados a partir do nível central através da Administração Nacional de Estradas (ANE). Relativamente aos sectores de água e de educação (construção acelerada de salas de aulas) os fundos são geridos a nível provincial e os pagamentos feitos nos dois níveis: provincial e distrital. A leitura do processo, e com respeito às constatações feitas nas províncias de Nampula e Gaza, onde decorreu o trabalho de campo, revelou diferenças peculiares nos avanços e na forma de abordagem da descentralização nas duas províncias, particularmente nos aspectos referentes a critérios de planificação, definição de prioridades, alocação de recursos e fluxos financeiros. As diferenças verificadas para as duas províncias, que podem ser explicadas, em parte, pela diferença de maturidade na condução dos processos de descentralização entre Nampula e Gaza, sendo a primeira mais experiente, não inibem concluir que, em termos gerais: (1) a descentralização de fundos sectoriais ainda não é efectiva; (2) o envolvimento das instituições de planificação e consulta comunitária é efectivo; (3) o sistema de prestação de contas é complexo, moroso e contraproducente; (4) o sistema de monitoria e avaliação ao nível distrital pode ainda ser melhorado; (5) a capacidade de manutenção ao nível distrital precisa de fortalecimento; (6) há fraco envolvimento do sector privado na prestação de alguns serviços; (7) há desarticulação institucional na aplicação de alguma legislação; (8) os critérios de atribuição de fundos sectoriais são inconsistentes e pouco divulgados; e (9) há, nos distritos, falta de uma perspectiva multisectorial e sistemática de planificação. Face aos problemas identificados, este Relatório Final propõe algumas recomendações: nova abordagem sobre os fundos sectoriais, particularmente a sua integração nos PESOD; alinhamento dos instrumentos de planificação estratégicos locais com os nacionais; regulação em legislação própria dos critérios de alocação de fundos, capacitação institucional entre outras acções.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - portuguese / português; access to services / acesso a serviços; decentralization / descentralização; education / educação; infrastructure - roads / infrastructura - estradas

Muslims of northern Mozambique and the liberation movements - Bonate, Liazzat J. K. (Social Dynamics, 2009)
Despite the fact that the liberation war occurred in northern Mozambique, where a considerable number of Muslims lived, their contribution to the independence struggle has been little studied. This paper focusses on their participation in two nationalist liberation movements, Mozambican African National Union (MANU) and Frente de Libertação de Moçambique (FRELIMO), and demonstrates that the prevailing idea in scholarship about Muslims’ aloofness from the liberation struggle is unjustified. It argues that Muslim support and participation in the liberation movements stemmed primarily from grassroots African nationalism. Like most Africans, Muslims wished to end colonialism and recover their land from the Portuguese. African Muslims of northern Mozambique were well suited to support these movements, because Islam and chieftainship were linked to each other. Chiefs were believed to be the ‘owners’ and ‘stewards’ of the land, and a majority of Muslim leaders, whether traditional chiefs (régulos, in Portuguese) or Sufi leaders (tariqa khulafa’, in Arabic), were from the chiefly clans. Most importantly, Muslims of northern Mozambique had close historical and cultural ties to Tanganyika and Zanzibar, especially through Islamic and kinship networks. The involvement of Muslims in the liberation movements of those regions, in particular in Tanganyika African National Union (TANU), inspired and encouraged the Muslims of northern Mozambique to support MANU and FRELIMO, especially since these two movements were launched in Tanganyika and Zanzibar with TANU backing and the participation of Muslim immigrants from northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

PARPA II – Relatório de Avaliação de Impacto Pesquisa Sobre o Combate À Corrupção - CS Advocacia, Consultoria e Serviços (Republica de Moçambique: Ministério da Planificação e Desenvolvimento, 2009)
Este estudo enquadra‐se no âmbito dos Mecanismos e Instrumentos de Monitoria e Avaliação do Plano de Acção para a Redução da Pobreza Absoluta 2006‐2009 (PARPA II), que preconizam a preparação de um Relatório de Avaliação de Impacto (RAI). O RAI tem como objectivo sintetizar informação sobre a pobreza e a evolução de indicadores socioeconómicos e analisar esta informação com uma visão particular para atribuir causa e efeito. Como parte das prioridades do PARPA II, o combate à corrupção é um dos temas a ser abordado no RAI. Neste âmbito, o presente estudo tem como objectivo geral, avaliar o impacto das medidas adoptadas no âmbito do combate à corrupção, com enfoque nos mecanismos de controlo interno (inspecções e auditorias), relacionando com a quantidade e qualidade dos recursos humanos existentes, o desempenho e impacto do Gabinete Central de Combate à Corrupção (GCCC).
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - portuguese / português; corruption / corrupção; government policy / politica governamental

Country Review Report: Republic of Mozambique - African Peer Review Mechanism (African Peer Review Mechanism, 2009)
The report is divided into seven chapters. This introductory chapter is followed by Chapter Two, which provides an overview of Mozambique as a backdrop to the report. Chapters Three to Six evaluate developments and challenges in the four APRM focus areas (Democracy and Political Governance; Economic Governance and Management; Corporate Governance; and Socio-Economic Development) respectively. Each of these chapters has two sections: the first analyses the codes and standards of the APRM, while the second assesses the APRM‘s objectives for that thematic area. Each section begins with a summary of the CSAR, followed by the findings of the CRM and, finally, the APR Panel‘s recommendations on the identified challenges. Effort has also been made to highlight areas of best practice in boxes. Chapter Seven discusses the cross-cutting issues considered critical due to their wider impact on governance and thus require holistic, immediate and urgent attention. These salient issues are the following: Poverty and Inequality; Party/government/business dichotomy; Land; High levels of illiteracy; Eliminating aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. The Chapter also highlights three special issues of interest to Mozambique and the Mission - the Environment, land mines and Beira city. The NPOA received from Mozambique and the comments of the government are annexed to the report, as mandated by the APRM rules.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico; governance / governação

Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

APRM Country Review Report Mozambique - República de Moçambique (República de Moçambique, 2009)
The major cross-cutting issues which featured prominently in all the thematic areas are highlighted below. A comprehensive approach is needed to address these issues as they have wider ramification for the various dimensions of governance in Mozambique. The following are the major thirteen crosscutting issues emerging from this report: Poverty and Inequality; Party/government/business dichotomy; HIV/AIDs; Land Ownership; High levels of illiteracy; High aid dependency; Information flow and paucity of data; Inclusivity; Crime, safety and Security; Domestic violence; Capacity constraints and implementation challenge; Elections; and, Corruption. CONCLUSION: The remarkable recovery that Mozambique has made since the end of the civil war in 1992 should make the people proud of their accomplishments. Over the last two decades, Mozambicans has made considerable progress in rebuilding its political, economic and social institutions, with noticeable progress. There is no doubt that Mozambicans can build on the successes highlighted in this report, while addressing the challenges in a vigorous manner, in order for the country to rapidly move forward. With its abundant natural resources, Mozambicans can exploit these resources for the benefit of the majority of its people. But this will be difficult to achieve without pragmatic and innovative solutions to the challenges arising from both the thematic and cross-cutting issues identified by this report.
Keywords: *non-public; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; governance / governação; health / saúde; natural resources / recursos naturais; poverty / pobreza

Moçambique: de uma economia de serviços a uma economia de renda - Brito, Luís de (IDeIAS, 2009)
A periodização que se segue tem como objectivo dar uma visão geral da evolução da economia moçambicana e situar a indústria no contexto desse desenvolvimento histórico. Uma das conclusões que se pode tirar desta visão panorâmica é que, mais de um século depois da partilha de África na Conferência de Berlim e de 35 anos de independência, a economia moçambicana apresenta ainda um padrão de tipo colonial, tendo como traço dominante a exportação de matérias-primas e recursos naturais.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; ⛔ No DOI found

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Youth exclusion, violence, conflict and fragile states - Hilker, Lyndsay McLean; Fraser, Erika (Social Development Direct, 2009)
This report forms part of a portfolio of work on youth focussed on two interconnected thematic areas: youth, jobs and growth and on youth exclusion, fragile states and conflict and complements work being conducted to develop a Youth Participation Guide for DFID staff. It is intended to inform a DFID Policy Briefing and a practical Guidance Note on addressing youth exclusion and unemployment. The objectives of the study are: (i) To scope out existing evidence and analysis on the links between youth exclusion, violence, conflict and fragile states and distil this information to enable DFID (and partners) to better understand the implications for poverty elimination, state and community-building, peace-building, Disarmament, Demobilisation and Reintegration (DDR) and conflict prevention, in order to address the issues more effectively in policy and programmes; (ii) To develop a conceptual framework that renders this information manageable while still reflecting the many dimensions of this issue. The study involved a desk-based literature review and consultations with a small number of key informants from DFID, other donors, academia and youth groups. This study focuses mainly on people aged 15-24, but conceptualises “youth” as a transitional stage in life between childhood and adulthood rather than as a rigid construct based on age. It recognises the diversity of youth by gender, class, ethnicity and focuses on the multiple dimensions of exclusion that systematically disadvantage youth. It also takes a holistic approach to violence – recognising that in practice different forms of violence (e.g. political, criminal, interpersonal, extremism) may overlap and that some of the same structural and proximate factors may drive youth engagement in different forms of violence.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Social Protection in Mozambique: A new imperative? - Waterhouse, Dr Rachel; Lauriciano, Gil (IESE Conference ‘Poverty Dynamics and Patterns of Accumulation in Mozambique, 2009)
Even before the impact of a global economic crisis kicks in, there is renewed thinking in Mozambique about a wider role for the state in social protection. Proponents are still struggling to convince others of the economic and social value of a broader investment in social protection. This is against the backdrop of institutional resistance borne of Mozambique’s political and economic history. The government attitude to social protection has been influenced by colonial experience of an extractive rather than protective state and the legacy of post-Independence events and processes. After Independence in 1975, initial social service expansion was heavily undermined by war-time destruction and economic collapse in the 1980s. Post war, the Government’s top priorities were to re-establish security and rebuild infrastructure. However, political and economic liberalisation in the 1990s saw tight caps on state spending. Poverty was so widespread and deep that there seemed to be little scope for special consideration of the ‘poorest of the poor’... except for ad hoc initiatives, such as the food subsidy programme for the poor and unable to work. In the last 15 years, Mozambique has experienced impressive economic growth and poverty reduction. Nonetheless Mozambique continues to rank amongst the world’s poorest countries. Government is becoming more aware of chronic poverty and that large population groups are currently unable to escape the poverty trap. This raises debate about what can be done ... and promotes renewed thinking on social protection. There are still many obstacles to a coherent and comprehensive approach to social protection. These include: analytical limitations around the causes, consequences and extent of vulnerability as well as the potential social and economic benefits of social protection; institutional barriers; budgetary limitations; and perceived political risk. However, there is also a growing acceptance of the relevance and importance of social protection to reduce vulnerability, build resilience and contribute to poverty reduction. These issues need to be addressed at policy and practical level, if Mozambique is to effectively address the growing challenge of chronic poverty.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; poverty / pobreza; social protection / proteção social

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

Doing Business with the Ladies: Gender, Legal Reform, and Entrepreneurship in the International Finance Corporation - Bedford, Kate (Labour, Capital and Society / Travail, capital et société, 2009)
Since 2007 the World Bank's gender approach has moved away from the Wolfensohn-era emphasis on gender as central to social development concerns, towards a business case model that involves a far greater role for the private sector in efforts to reduce poverty and achieve gender equity. Using a case study of the International Finance Corporation (IFC) and its project, 'Doing Business', to promote the ease of doing business across the world, I ask what this new direction entails for the Bank's gender and development efforts, and examine the new links being forged between gender empowerment and free market reform. The article focuses on three themes in this regard: first, how attention to gender within the 'Doing Business' project helps promote labour market deregulation; second, the contested way in which free markets, legal reform, and gender equality are linked together; and third, the regional reconfigurations of Gender and Development (GAD) evident in the project's report on Women in Africa, wherein women entrepreneurs are celebrated and new networb of GAD specialists are drawn together.
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; entrepreneurship / empreendedorismo; gender / género; law / direito; ⛔ No DOI found

Jovens e associações em Moçambique: motivações e dinâmicas actuais [Youths and associations in Mozambique: motivations and current dynamics] - Biza, Adriano Mateus (Saúde e Sociedade, 2009)
O presente artigo é uma reflexão sobre dinâmicas associativas de jovens no Moçambique pós colonial. O objectivo desta reflexão foi identificar e analisar as motivações de engajamento dos jovens nesses agrupamentos. Baseando-se em aproximações empíricas feitas a duas associações de jovens - Associação Aro Juvenil e Associação Positiva Juvenil - a análise demonstra que dinamica associativa de jovens mete em evidência relações complexas entre identidade, contexto, o privado, o público e o afectivo. Embora haja múltiplas motivações, a adesão dos jovens em associações associa trajectórias e expectativas individualizadas. A nível discursivo, a entrada na vida associativa representa uma forma de legitimação sóciopolítica em resposta a um discurso que considera os jovens passivos e pouco intervenientes na solução dos problemas que lhes afecta em particular e à sociedade no geral. A nível das práticas associativas quotidianas, os jovens reintrepretam e dão outro sentido às motivações do seu engajamento: para lá dos objectivos formais, pretensamente desenvolvimentistas, altruistas e humanitários, o associativismo é uma estratégia de vida e de realização de projectos individuais. Criar uma associação e/ou nela aderir pode significar maiores possibilidades de aceder e controlar recursos e capitais diversificados como emprego/profissão, dinheiro, trabalho, poder, reconhecimento e prestigio, formações entre outros que de outra forma não seria possível. en: This article reflects on youth associations dynamics in Postcolonial Mozambique. The aim is to identify and analyze motivations for young people's involvement in such groups. Based on empirical work with two youth associations - namely "Associação Aro Juvenil" and "Associação Positiva Juvenil" - the assessment finds that youth associations dynamics highlights intricate relationships involving identity, context, private, public and affective milieus. Although there are multiple motivations, young people's adherence to associations is combined with individual life stories and expectations. At the discourse level, entrance to the associative life represents a form of socio-political legitimation in response to other narratives that consider young people very passive and less intervening in finding solutions to their own problems, and society's in general. At the level of day-to-day practices, young people re-interpret and give a different sense to their motivations and commitment: beyond formal objectives - arguably development-oriented, altruistic and humanistic - associations are a life strategy for the accomplishment of individual achievements. To create an association and/or take part in one may imply greater possibilities of accessing and controlling diversified resources and capitals, such as a job/occupation, money, work, power, recognition, prestige, and training, among others, which would be otherwise impossible.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

The politics of gradualismo: popular participation and decentralised governance in Mozambique - Buur, Lars (Rethinking Popular Representation., 2009)
The question of how to proceed with democratic decentralisation has been of political concern in Mozambique over the past decade. In accordance with post-war constitutional commitments to démocratisation after the country’s post-independence flirtation with socialism and a high degree of centralism, the process of decentralisation has taken two forms. First, a system of locally elected governments in the form of municipalities (municipios) for the urban and semi-urban areas was approved in 1997 to cover the devolution of direct although limited powers and functions to autonomous elected bodies. The Municipal Law (2/1997) made provision for locally elected municipalities (autarquias locais) in 33 urban or peri-urban settings.1 Second, for the rest of the population (roughly .70 percent) and the local state administration, the process of decentralisation has taken the general form of de-concentration and a transfer of responsibility to lower level bodies within the state sector combined with different forms of participatory mechanisms for representation and consultation. These participatory mechanisms are grounded in community- based organisations claiming representative status on the basis of identity, interest, community, and similar factors.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; governance / governação

Programas de saúde materno-infantil em Moçambique: marcos evolutivos e a inserção da enfermagem (Programs of maternal and infant health in Mozambique: gradual landmarks and the insertion of nursing) - Lourenço, Maria Acácia Ernesto; Tyrrell, Maria Antonieta Rubio (Escola Anna Nery, 2009)
See english abstract below. Pesquisa centrada nas políticas públicas do governo moçambicano para o setor da saúde, com foco voltado para programas de assistência à saúde materno-infantil. Tem o propósito de apresentar contextos básicos para a reflexão sobre a filosofia da implantação e implementação dos programas e a inserção da Enfermagem, mostrando seus marcos evolutivos. Constatou-se que, na década 70, o Sistema Nacional de Saúde adotou o Programa de Proteção Materno-Infantil, que na década de 80 ficou concebido como Programa de Saúde Materno-Infantil e, posteriormente, na década 90, ficou inserido no Programa Nacional Integrado de Saúde Materno-Infantil e Planejamento Familiar, Programa Alargado de Vacinação, Saúde Escolar e do Adolescente, incluindo Saúde Sexual e Reprodutiva. A inserção da Enfermagem foi evidenciada na implementação das ações assistenciais. Os marcos evolutivos foram: a introdução dos cursos específicos de Enfermagem em saúde materno-infantil do nível básico ao superior e abrangência dos serviços do Programa Nacional Integrado. ABSTRACT For the interest to know about the public Policies of Mozambican government to the Health sector, this research put much emphasis on the process of implantation and implementation of assistance programs to maternal health looking at reflection about the philosophy of including nursing through ever-changing world or marked changes. Established in the 1970s, the National Health System came up with a maternal health protection program which in the 1980s was drawn into Maternal Health Program. This, in the 1990s was included in the National integrated program of maternal health and family planning, integrating a broad vaccination program, school health and adolescent sexual reproductive health. The inclusion of nursing in the implementation of integrated program became as the evidence through action assistances. The evolutional signs were the introduction of specific courses of Maternal and Infant Health Nursing from basic to superior levels, including the service of National Integrated Program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - portuguese / português; access to services / acesso a serviços; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Gender and Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Tuominen, Minna (Chr. Michelsen Institute, 2009)
The main objective of this report is to capture the local configurations of gender relations in Nampula, by focussing on one rural and one urban area in the province. The former is the coastal and rural district of Mossuril, which is considered one of the most deprived districts in the province, both in terms of material poverty and human development (MAE 2005). The urban areas are Muatala and Namutequeliua, which are two of the most populous bairros in the city of Nampula and largely inhabited by migrants from the coast and hence share historical and sociocultural roots with Mossuril.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mossuril; GP - Nampula; Health PEA; L - english / inglês; education / educação; employment / emprego; gender / género; health / saúde; poverty / pobreza

Monitoring and Evaluating Mozambique’s Poverty Reduction Strategy PARPA 2006-2008. A Synopsis of Three Qualitative Studies on Rural and Urban Poverty. - Tvedten, Inge; Rosário, Carmeliza; Paulo, Margarida (Chr. Michelsen Institute:, 2009)
The purpose of this synopsis is to facilitate discussions between the government, civil society organisations, donors and other stakeholders in Mozambique’s efforts to reduce poverty and, more specifically, to contribute to the Impact Assessment Report (Relatótio de Avaliação de Impacto, RAI) which is to be carried out in 2009. We will focus on our main findings and preliminary conclusions, and will to the extent possible avoid repeating data found in the original reports to ease accessibility. The discussions related the synopsis will also be used to further identify the most relevant topics and approaches for the final three studies, in order to secure their maximum utility for the government’s monitoring and evaluation programme. The synopsis will be divided into six parts following this Introduction. In Chapter 2 we briefly account for the analytical framework and methodological approaches of the studies. In Chapter 3 we present what we have identified as aspects of Mozambique’s political economy with particular impacts on the situation in local communities. In Chapter 4 we analyse the main features of the political context at the level of districts through which poverty reduction is implemented. In Chapter 5 we present the main findings from the adapted surveys we have carried out, with a focus on the similarities and differences between the three areas of study. In Chapter 6 we assess the outcome of our qualitative and participatory approaches to our analyses. And finally, in Chapter 7, we present preliminary conclusions and recommendations from the first three studies and outline the approach of the three follow-up studies.
Keywords: G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural

Contexto Politico e institucional da protecao social em Mocambique - Waterhouse, Rachel; Lauriciano, Gil (Protecção Social: Abordagens, Desafios e Experiências para Moçambique, 2009)
Mesmo antes de se fazer sentir o impacto duma crise económica global, há um pensamento renovado em Moçambique sobre um papel mais amplo do Estado na protecção social. Os proponentes lutam de modo a convencer os outros do valor económico e social dum investimento mais alargado na protecção social. Isto vai contra o pano de fundo da resistência institucional, que a história política e económica de Moçambique acarreta. Moçambique já era unido como uma nação sob o regime colonial português, desde o princípio do século XX. O governo colonial praticou um regime altamente extractivo, fornecendo pouco para o bem-estar social ou a para a protecção social. Um breve período de políticas marxistas-leninistas após a independência nacional em 1975 –quando o governo da Frelimo tentou ampliar os serviços sociais básicos em todo o país– foi rapidamente superado pelo colapso económico e pela guerra, seguido por um rígido exercício de poder pelo estado sob ajustamento estrutural. Um pensamento renovado coerente e abrangente sobre um papel mais amplo do Estado no fornecimento duma Protecção social dos seus cidadãos é ainda emergente e controverso. Este artigo apresenta uma breve panorâmica do contexto político e institucional em que este debate está a ganhar importância.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; social protection / proteção social

Higher fuel and food prices: impacts and responses for Mozambique - Arndt, Channing; Maximiano, Nelson; Thurlow, James T.; Nucifora, Antonio M. D. (Agricultural Economics, 2008)
Rising world prices for fuel and food represent a negative terms-of-trade shock for Mozambique. The impacts of these price rises are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short-run net benefit ratio analysis indicates that urban households and households in the southern region are more vulnerable to food price increases. Rural households, particularly in the North and Center, often benefit from being in a net seller position. Longer-term analysis using a computable general equilibrium (CGE) model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Again, negative impacts are larger in urban areas. The importance of agricultural production response in general and export response in particular is highlighted. Policy analysis reveals difficult trade-offs between short-run mitigation and long-run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Crónicas dos Motins - Granjo, Paulo (Anropocoiso - Blog de Paulo Granjo, 2008)
Mensagens correspondentes à consulta "Crónicas dos Motins".
Keywords: *non-public; G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito

Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais

The Environment for Women's Entrepreneurship in the Middle East and North Africa - Chamlou, Nadereh (Orientations in Development, 2008)
This report is about how women entrepreneurs can contribute more to the quality and direction of economic and social development in the Middle East and North Africa (MENA) region. Economic growth in the Middle East has been remarkable since 2004, mainly because of higher oil prices. Rapid job growth has followed, driven mainly by the private sector. Yet the region still faces two important challenges: the first is to create better jobs for an increasingly educated young workforce; the second is to diversify its economies away from the traditional sectors of agriculture, natural resources, construction, and public works and into sectors that can provide more and better jobs for young people— sectors that are more export oriented, labor intensive, and knowledge driven. These goals can be achieved only by more innovative and diverse investors. In this, the private sector must play an even bigger role than in the past. This report is different. Its objective is to provide a better understanding of barriers to investment and doing business that may be common to all investors and those that affect women entrepreneurs disproportionately. The report examines newly available data from more than 4,800 surveyed firms in the formal sector in eight Middle East and North African countries (the Arab Republic of Egypt, Jordan, Lebanon, Morocco, Saudi Arabia, the Syrian Arab Republic, Gaza and the West Bank, and the Republic of Yemen). These surveys detail firm characteristics and the responses of male- and female- owned firms to questions about perceived barriers along 18 categories of the investment climate. The purpose of the report is threefold: • to provide an overview of the characteristics of female- owned firms in the region; • to analyze gender- specific barriers that exist across the region or within countries; and • to identify other factors outside the business environment that might affect women’s entrepreneurship. The report finishes with policy recommendations on how to reduce the identified barriers and create a level playing field for women entrepreneurs. The report acknowledges limitations resulting from the availability and depth of data. It does not attempt to answer every question about women’s entrepreneurship in MENA. Indeed, it may raise more questions than it answers. The hope is to spur greater interest in the topic among researchers and policy makers.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Mineral Resources Potential in Mozambique - Lehto, Tapio; Gonçalves, Reinaldo (Geological Survey of Finland, 2008)
The metallic mineral, industrial mineral and construction material resources in Mozambique have been mapped as part of the Mineral Resources Management Capacity Building Project, financed by a grant provided by the Nordic Development Fund. A database covering the location and characteristics of more than 600 mineral indications, showings and deposits within the geographical contract area assigned to the GTK Consortium was created. A total of 140 mineral occurrences were selected for field surveys and assessments that were mainly carried out during May-November 2003, 2004 and 2005. All available data in the report archives of the client, the National Directorate of Geology (DNG), was collected and transferred to the mineral occurrence database, which was then updated with information from field surveys and with new data published by exploration and mining companies on the Internet. New mineral resources maps at the scales 1:50 000 (part of contract area), 1:250 000 and 1:1 million were prepared with the corresponding symbols for various commodities plotted. Favourability maps showing zones with high potential for selected commodities were compiled at the 1:250 000 scale. The mineral resources in Mozambique were described in the four map explanation volumes and summarized in the final reports for the projects Geological Mapping LOT 2 and Geological Mapping LOT 3. As a consequence of increased geological knowledge, facilitated by the activities of the GTK Consortium, investments in Mozambique’s mineral potential by leading international and regional mining companies is already increasing. Currently, global mining houses are investing in exploration for energy minerals (hydrocarbons, coal and uranium), for titanium and zirconium in heavy mineral sands, for gold and gemstones, for the agricultural minerals lime and phosphate and for tantalum, fluorite and other industrial minerals.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; ⛔ No DOI found

Doing Business: Women in Africa - World Bank (Doing Business, 2008)
Women in Africa
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Mozambique - Lloyd, Robert B. (Countries at the Crossroads 2007: A Survey of Democratic Governance, 2007)
Countries at the Crossroads is an annual survey of government performance in 30 key countries worldwide that are at a critical crossroads in determining their political future. Crossroads provides a unique comparative tool for assessing government performance in the areas of accountability and public voice, civil liberties, rule of law, and anticorruption and transparency. The countries evaluated in Crossroads represent a range of governments: traditional or constitutional monarchies, one-party states or outright dictatorships, failed states, states where reforms have stalled or lagged behind, and states that suffer from insurgencies. The survey provides a comparative, in-depth assessment of democratic governance intended to help government officials, scholars, educators, nongovernmental organizations, and the media identify areas of progress and highlight points of concern. For the international community, the survey helps target diplomatic efforts and reform assistance. The narratives and scores clearly highlight the problems and successes of each government, and separate recommendations sections prioritize the steps that should be taken by the countries in question to remedy deficiencies in governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; governance / governação

Exploring Natural Resources in Mozambique: Will it be a Blessing or a Curse? - Bacuane, Aurélio; Mulder, Peter (Instituto de Estudos Sociais e Económicos (IESE), 2007)
Mozambique has considerable quantity of natural resources, of which the major part is yet to be explored. The Government of Mozambique is determined to extract and export its natural resource potential as soon as possible, supposing that this will positively contribute to economic growth and poverty reduction. However, any resources rich countries are among the poorest nations in the world, in spite of decennia-long exploration of their natural wealth. This so colled 'paradox of plenty' or 'resource curse' raises the question whether the foreseen exploration of natural resources in Mozambique will pose a serious threat rather than a blessing to its economic development. In this paper we first estimate the potential resource wealth of Mozambique in comparison to other countries. Next, we briefly review the rowing body of literature on the existence and determinants of a natural resource curse. Then we evaluate the risk of a resource curse to occur in Mozambique in the (near) future. Finally, we try to come up with suggestions to avert a Mozambican resource curse.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); extractive industries / indústrias extractivas; institutions / instituições; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais; transparency / transparência

A Green Revolution in Southern Niassa? A field study from a small farmer perspective about possibilities and obstacles for a Green Revolution. - Karin Gatu; Sofia Rodman (Växjö University, 2007)
The aim of this field study was to analyze, by taking into consideration the small farmers’ perspective, the possibilities and obstacles for an implementation of a Green Revolution in southern Niassa, Northern Mozambique. The authors also ask: in what sense are the findings in Asia, presented by Djurfeldt, relevant for thesituation in southern Niassa?
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura

Adverse incorporation, social exclusion and chronic poverty - Hickey, Samuel; Andries du Toit (Institute for Development Policy and Management, School of Environment and Development, University of Manchester, 2007)
There are a number of compelling reasons to focus on the ways in which the processes and relations of adverse incorporation and social exclusion (AISE) underpin chronic poverty. In particular, AISE research draws attention to the causal processes that lead poverty to persist, and to the politics and political economy of these processes and associated relationships over time. Specific dimensions of AISE are explored in relation to chronic poverty – namely political, economic, socio-cultural and spatial – and are found to relate closely to long-term historical processes, particularly concerning the nature and forms of capitalism, different stages and types of state formation, and institutionalised patterns of social norms and attitudes. However, it is also stressed that much of the promise of AISE research lies in its capacity to cross analytical boundaries and capture the multi-dimensional and interlocking character of long-term deprivation. This analysis suggests a number of fruitful areas for research, most of which are currently under-explored in poverty research. In methodological terms, there are benefits to adopting integrated qualitative-quantitative approaches when investigating AISE, although it is argued that (a) the relational nature of AISE and the limitations of quantitative data may dictate that qualitative work should take priority here and (b) that more historical and theoretically oriented forms of research are particularly appropriate in studying AISE. To think about challenging AISE involves shifting the frame from policy to politics and from specific anti-poverty interventions to longer-term development strategies, particularly in terms of industrialisation and labour market restructuring, moves towards developmental states and supporting shifts from clientelism to citizenship. However, a range of more immediate development policy interventions may also be able to make headway in challenging the forms of AISE that perpetuate poverty.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Niassa Agricultural Development Project (NADP): Completion Evaluation - International Fund for Agricultural Development (International Fund for Agricultural Development, 2007)
Evaluation report of IFAD's Niassa Agricultural Development Project (NADP).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Lichinga; GP - Niassa; L - english / inglês; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; poverty / pobreza

Sex, Food and Female Power: Discussion of Data Material from Northern Mozambique - Arnfred, Signe (Sexualities, 2007)
Issues of sex and food are often inscribed in male/female relationships. Frequently in a western context sex is perceived as a site of male power and female subordination, while food and cooking are seen as female domains, but still sites of subordination, as elements of women's household chores. In this article, looking at issues of sex and food in a rural matrilineal setting, power aspects of male/female relationships as mediated through sex and food emerge somewhat differently. Sexual proficiency is here a woman's art, mastered by old women and transmitted to the young. Also, in a setting where daily life is largely based on subsistence production, food and cooking become domains of power, again with old women in control. Based on fieldwork in northern Mozambique and with reference to African feminist conceptualizations of male/female power relationships, the article makes a case for rurality and ‘tradition’ not necessarily being adverse to female power in social relationships.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; gender / género; youth / juventude

Gender, Entrepreneurship, and Competitiveness in Africa - Bardasi, Elena; Blackden, Mark C.; Guzman, Juan (World Bank, 2007)
This chapter aims to shed light on the nature of men’s and women’s enterprises in Africa, to assess the extent to which the constraints and obstacles faced by women and men entrepreneurs may differ, and to address whether the constraints and obstacles entrepreneurs face affect the productivity and performance of men’s and women’s businesses differently.We begin with a brief overview of gender in the economy, followed by a more detailed analysis of available Enterprise Survey data where key characteristics of businesses can be disaggregated by the sex of the business owner.1 This allows us to look at various characteristics of men’s and women’s businesses, including perceptions of obstacles and constraints, and to assess productivity differences.After briefly placing this analysis in a wider context, the chapter concludes with some recommended actions to address the gender dimensions of entrepreneurship more systematically in policy and programs aimed at supporting private-sector development, along with suggestions for further data collection and analysis.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; entrepreneurship / empreendedorismo; gender / género

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

Traditions and transitions : Islam and chiefship in Northern Mozambique, ca. 1850-1974 - Bonate, Liazzat J K (2007)
This thesis is based on the archival and fieldwork research, and sheds light on the area which has been little studied or reflected in scholarly literature: Islam in Northern Mozambique. Its particular focus is on African Muslim leadership in Northern Mozambique, which has historically incorporated Islamic authority and chiefship. The link between Islam and the chiefly clans existed since the eight century when Islam made inroads into the northern Mozambican coast and became associated with the Shirazi ruling elites. With the involvement of the region in the international slave trade during the nineteenth century, the Shirazi clans secured alliances with the most powerful mainland chiefs through conquest and kinship relations in order to access supplies of slaves from the mainland. This process was accompanied by a massive expansion of Islam from the coast into the hinterland. The alliances between the Shirazi at the coast and the chiefdoms further into the interior resulted in a network of paramount chiefs and their subordinates making up the bulk of Muslim slave-raiders, who established the limits between themselves (the Maca, Muslims and 'civilized') and those to be enslaved (the Makua and Lomwe, derogatory terms, meaning savagery, i.e., 'non-Muslims' and 'uncivilized')
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Governance, Security and Development, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Consultoria sobre a Abolição das Taxas aos Utilizadores do Serviço Nacional de Saúde (SNS) em Moçambique - Cabral, Antonio Jorge Rodrigues (Instituto de Higiene e Medicina Tropical da Universidade Nova de Lisboa, 2007)
Existem actualmente taxas de utente cobradas em grande parte dos serviços de saúde públicos, em Moçambique. No entanto, historicamente, o partido no poder, a FRELIMO, tem sido bastante favorável a uma situação de serviços básicos de saúde gratuitos, e considera que a eliminação de barreiras de acesso à educação e saúde básicas constituem elementos fundamentais da estratégia de redução de Pobreza e de êxito nas Metas de Desenvolvimento do Milénio. O Governo de Moçambique considera ainda que a permanência das taxas mantém aberta a porta para a cobrança de taxas ilegais. A experiência de países vizinhos e a eliminação das taxas de matrícula no Ensino Básico em Moçambique constituíram motivações adicionais aos responsáveis do sector para que a viabilidade da remoção das taxas fosse avaliada. Esperava-se desta consultoria: i) uma avaliação da aplicação actual das taxas de utente; ii) uma síntese sobre o provável impacto esperado da abolição das taxas de utente nos serviços básicos de saúde em Moçambique, em especial na carga de trabalho dos funcionários da saúde e nos custos recorrentes no Sector da Saúde; iii) uma síntese dos pontos de vista da população em relação as condições de acesso aos cuidados de saúde, e dos pontos de vista de outros intervenientes em relação as taxas de utente no sector da saúde.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; health - dignified care / saúde - atendimento humanizado / mau atendimento; health / saúde

Gender and economic growthin Kenya: unleashing the power of women - Ellis, Amanda; Cultura, Jozefina; Dione, Nouma; Gillson, Ian; Manuel, Clare; Thongori, Judy (The World Bank, 2007)
This report examines the legal, administrative, and regulatory barriers that are preventing women in Kenya from contributing fully to the Kenyan economy. Building on the 2004 Foreign Investment and Advisory Service (FIAS) report, “Improving the Commercial Legal Framework and Removing Administrative and Regulatory Barriers to Investment,” this study looks at the bureaucratic barriers facing women in Kenya through a gender lens. The report makes specific recommendations to address gender-related barriers in the context of ongoing government and donor initiatives to encourage private sector development as the key driver of poverty reduction and economic growth, in line with Kenya’s Economic Recovery Strategy for Wealth and Employment Creation 2003–2007 (ERS). Addressing these constraints will not only allow women to make a full contribution to the economy but also improve their livelihoods and those of their families and help create a more enabling environment for all businesses in Kenya.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; gender / género; justice / justiça

Mozambican Civil Society Within: Evaluation, Challenges, Opportunities and Action - Fundação para o Desenvolvimento da Comunidade (FDC) (Fundação para o Desenvolvimento da Comunidade (FDC), 2007)
This section presents the main results of the CIVICUS Civil Society Index (CSI) research project in Mozambique conducted between March and December 2007. The project was implemented by the Community Development Foundation (FDC) in close collaboration with CIVICUS (World Alliance for citizen participation) and with financial support from the United Nations Development Programme (UNDP), the Aga Kahn Foundation and the European Union. The CSI project is an integrated research effort involving multiple sources, quantitative and qualitative methods and broad participation by actors and stakeholders in evaluating the state of civil society throughout the world. In line with the CIVICUS CSI methodology, the FDC established a National Index Team (NIT) and a National Advisory Group (NAG). The entire implementation process was monitored and supported by the CIVICUS team but totally implemented by the team of national researchers, and advised by NAG. The technical team met, systematised and analyzed information from a variety of sources, both secondary and primary. At different stages of the research the data and results were subject to ample discussion and critical analysis, especially in meetings of the NAG that validated the final score for the 80 indicators that make up the Civil Society Index (CSI). Consultations and data collection covered the whole country and involved two original primary surveys. One was a Community Sample Research (INC07) based on a statistically representative sample of 4015 people. The other was a national survey of 477 civil society organisations (INOSC07) based on a sample taken from the database of INE (2006) that conducted a census of almost 5000 non-profit organisations in 2003. The CSI is an international comparative project that has to date involved some 60 countries using the same CIVICUS methodology. The CSI was conceived with two main objectives: 1) to provide up-to-date and useful knowledge about civil society; 2) to strengthen stakeholder commitment to strengthening and expanding civil society. The final report, on which this Extended Summary is based, has three main chapters. Chapter 3 contains the main analysis and is structured according to the logic of the four CSI subdimensions. This summary describes the main results, including a brief historical overview, the main debate on the civil society concept in the specific case of Mozambique, the results of the four dimensions of the CSI diamond (Structure, Environment, Values and Impact) and finally the strengths and weaknesses of the current state of Mozambican civil society. The data and analysis summarised here are the result of considerable discussion and debate by the NAG and in a three-day national workshop held in Maputo during 4 to 6 December 2007.
Keywords: G - Mozambique / Moçambique; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil

Indonesia After the Asian Crisis* - Hill, Hal; Shiraishi, Takashi (Asian Economic Policy Review, 2007)
Indonesia was deeply affected by the 1997–1998 crisis, more so than its East Asian neighbors. Its economic contraction was deeper and more prolonged. It was the only one to experience a (temporary) loss of macroeconomic control. It also suffered “twin crises,” in the sense that its serious economic and financial problems were accompanied by regime collapse. Consequently, recovery was a slow and complex process, as new institutions had to be created, and old ones reformed under successive short-lived administrations. But this process is largely over. The directly elected president with a strong popular mandate is in power. The new institutional framework for economic policy-making is in place. Macroeconomic stability has been restored. Although growth has yet to return to pre-crisis levels, by 2004 per capita income and poverty incidence had recovered to levels prevailing in the mid-1990s, and in the circumstances economic recovery has arguably proceeded about as quickly as could reasonably have been expected.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; economic development / desenvolvimento económico

Proposta de regulamento sobre organização e funcionamento os conselhos consultivos locais - Ministério de Administração Estatal (2007)
O presente Regulamento estabelece as formas de organização e funcionamento dos Conselhos Consultivos Locais, com vista a cumprir eficazmente com a sua função de articipação das comunidades locais na concepção e implementação e programas e planos económicos, sociais e culturais, em prol do desenvolvimento local.
Keywords: *non-public

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde

"Xiculungo" - Social relations of urban poverty in Maputo, Mozambique - Paulo, Margarida; Rosário, Carmeliza; Tvedten, Inge; Chr. Michelsen Institute (CMI Report, 2007)
This is the second in a series of six participatory and qualitative studies of poverty in Mozambique, done with the objective of supporting the government in monitoring and evaluating the ongoing Action Plan for the Reduction of Absolute Poverty, PARPA II (GdM 2005). The first report looked into social relations of rural poverty in northern Mozambique, with special reference to the District of Murrupula in the Nampula province (Tvedten, Paulo and Rosário 2006). This report will analyse social relations of urban poverty, with special reference to four settlement areas (bairros) in Mozambique’s capital Maputo (see Terms of Reference, Annex 1). The Government of Mozambique and donors have invested considerable effort and resources in economic development and the reduction of poverty. While this has led to improvements in terms of an economic growth of 8 percent per annum over the past ten years (Arndt et al. 2006) and a reduction in the proportion of Mozambicans living in poverty from 69 to 54 percent (INE 2004), key socio-economic indicators are still very serious: GDP per capita is USD 1,117, the adult literacy rate is 46.5 percent, and life expectancy at birth is 41.9 years (World Bank 2006; UNICEF 2007). This places Mozambique at number 172 of 177 countries in UNDP’s Human Development Index, which makes it the least developed country in Southern Africa (UNDP 2007). Research-based information about poverty is recognised as important for Mozambique’s poverty reduction strategies, as these are expressed in the Government’s Five Year Plan (GoM 2005) and the related PARPA II (GdM 2005). Key data for the monitoring and evaluation of poverty in Mozambique stem from the National Census (INE 1997 and forthcoming 2008), the National Household Survey IAF (INE 1997 and 2004) and the National Demographic and Health Survey (MdS 2005), as well as a number of analyses by the Government of Mozambique based on these data (see e.g. DNPO 2004; Chiconela 2004; Maximiano et al. 2005). In addition, international organisations have commissioned several studies on their own, of which those undertaken by UNDP (2006), UNICEF (2007) and the World Bank (2007) are the most recent and comprehensive
Keywords: G - Mozambique / Moçambique; Important; L - english / inglês; M - evaluation / avaliação; poverty / pobreza; urbanization / urbanização

Business licensing and one stop shops in Indonesia - Steer, Liesbet (The Asia Foundation, 2006)
In 2001, Indonesia embarked on a decentralization process that has had a dramatic impact on the local political landscape, especially in relation to taxation and administrative processes. Rules and procedures that govern licensing, registration, some taxes and user charges have largely been devolved to local governments. A significant number of new licenses and charges have been created at the local level, and most licenses are issued through a complicated system of procedures and agencies. Licensing has become one of the most important barriers to business formalization and growth in Indonesia. The local licensing framework in Indonesia has three key problems, raising transactions costs and inefficiencies. Licensing reform through One Stop Shops (OSS). The Asia Foundation OSS technical assistance program. The methodology has proven to be highly effective.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; decentralization / descentralização

Impacto da Economia Informal na Protecção Social, Pobreza e Exclusão: A Dimensão Oculta da Informalidade em Moçambique - Francisco, António A da Silva; Paulo, Margarida (CRUZEIRO DO SUL – INSTITUTO DE INVESTIGAÇÃO PARA O DESENVOLVIMENTO JOSÉ NEGRÃO, 2006)
O trabalho anunciado no título desta monografia analisa a economia informal e a protecção social, bem como os seus impactos, directos e indirectos, no desenvolvimento económico e humano, na pobreza e na exclusão social em Moçambique. A resposta e os resultados que a monografia encontrou para as questões principais de pesquisa revelaram-se, de algum modo, surpreendentes, tanto para os promotores do estudo como para os organizadores e os próprios autores. A surpresa não é por causa da revelação que a informalidade domina a sociedade moçambicana. Afinal de contas, os números aqui reunidos, segundo os quais a economia informal domina 90% da economia de Moçambique, apenas confirmam o que as pessoas sentem e vivem na sua vida quotidiana. As surpresas reveladas neste trabalho têm a ver com os mitos e falácias em que as pesquisas sobre economia informal em Moçambique têm acreditado. Do ponto de vista analítico e prático, a presente monografia levanta um duplo desafio, um relacionado directamente com a economia informal e o outro com a protecção social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social Protection PEA; economic development / desenvolvimento económico; employment / emprego; informality / informalidade; poverty / pobreza; social protection / proteção social

Plano De Acção Para a Redução Da Pobreza Absoluta: 2006-09 (PARPA II) - República de Moçambique (República de Moçambique, 2006)
O Plano de Acçãoo para a Redução da Pobreza Absoluta para 2006-2009 (PARPA II) do Governo de MoÁambique tem em vista alcanÁar o objectivo de diminuir a incidÍncia da pobreza de 54% em 2003 para 45% em 2009. Este documento sucede ao PARPA I de 2001-2005 (Governo de MoÁambique, 2001), mantendo em comum as prioridades em ·reas do desenvolvimento do capital humano na educaÁ„o e sa˙de, da melhoria na governaÁ„o, do desenvolvimento das infra-estruturas b·sicas e da agricultura, do desenvolvimento rural, e de melhoria na gestão macro-económica e financeira. O presente PARPA distingue-se do anterior por incluir nas suas prioridades uma maior integração da economia nacional e o aumento da produtividade. Em particular, focaliza a atenção no desenvolvimento de base ao nÌvel distrital, na criação de um ambiente favorável ao crescimento do sector produtivo nacional, melhoria do sistema financeiro, ao florescimento das pequenas e mÈdias empresas enquadradas no sector formal, e a desenvolver ambos os sistemas de arrecadaÁ„o de receitas internas e de afectação dos recursos orçamentais.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; government policy / politica governamental; poverty / pobreza

War and reconstruction in northern Mozambique - Brück, Tilman (The Economics of Peace and Security Journal, 2006)
The article discusses some of the economic effects of war in northern Mozambique. It indicates how the historical and structural features of the economy of northern Mozambique restricted post-war reconstruction and post-war poverty alleviation. These features include the dominance of only a few cash crops for export, the absence of much rural trading, poor communication infrastructure, and weak political and state institutions. The specific nature of the internal war further weakened the state through the collapse of tax revenue and export earnings and the massive growth of debt and aid, of which little reached rural northern Mozambique. The article also summarizes key aspects of the geography, climate, markets, and social institutions of northern Mozambique, which define the potential production opportunities for peasant households. Finally, the article suggests how post-war reconstruction could have been more effective in achieving faster post-war poverty alleviation in northern Mozambique.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; access to services / acesso a serviços; conflict - civil war / conflito - guerra civil; health / saúde

PPFD/PRODER Joint Review and Strategy Proposal for the National PPFD Program Architecture - Final report - Ministry of Planning and Development - Mozambique (MÉTIER, Consultoria e Desenvolvimento, Lda, 2006)
The present report integrates the main conclusions of the three PPFD projects evaluation: PPFDNorth, PPFD-Centre and PRODER, establishing the articulation with the evolution of the political and administrative evolution and relevant for the decentralization process. Based on this analysis the report proposes the architecture of a single National PPFD Program and its main components. This report is based on the main conclusions of an extensive field work covering various provinces and districts and of the various workshops with participation of representatives of the Government at different levels, of the partners and national and international staff from the projects. It constitutes an important basis for the work of the commissions created to start the program formulations. This final report is complemented by other four partial reports: Evaluation report of the PPFD North; Evaluation report of the PPFD Centre; Evaluation report of the PRODER; and Phases 2 and 3 Report: Strategy for a single national PPFD
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - evaluation / avaliação; government policy / politica governamental

National Governance and Local Chieftaincy : A Multi-level Power Assessment of Mozambique from Niassa's Perspective - Nilsson, Anders; Åkesson, Gunilla (Sida, 2006)
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Campos de batalha da cidadania no Norte de Moçambique - Temudo, Marina Padrão (Cadernos de Estudos Africanos, 2005)
Durante muitos anos, a ideia de que a guerra civil que assolou Moçambique era conduzida por um exército mercenário ao serviço de interesses externos foi considerada inquestionável, desconhecendo-se que a Renamo possuía uma base social de apoio rural e que a produção agrícola constituía uma das fontes de financiamento da guerra. Após a independência, o partido-Estado Frelimo provocou uma desestruturação social, económica, política e cultural das sociedades rurais, conduzindo um projecto de desenvolvimento e de construção da nação autoritário e centralizado, que pôs em causa direitos fundamentais de cidadania. A adesão à guerra de parte da população pode assim ser interpretada como uma tentativa de conquista desses direitos. Neste trabalho, através de dois estudos de caso contrastantes, pretende-se revelar as estratégias de reprodução social e económica que permitiram a sobrevivência das populações durante o conflito e a posterior reconstrução, mas também as múltiplas formas que a afirmação dos direitos de cidadania pode encobrir.
Keywords: G - Mozambique / Moçambique; L - portuguese / português; conflict / conflito; electoral geography / geografia eleitoral

Moçambique Inquérito Demográfico e de Saúde 2003 - Ministerio da Saude - MISAU/Moçambique; Instituto Nacional de Estatística - INE/Moçambique; ICF International (MISA/Moçambique, INE/Moçambique and ICF International, 2005)
O Inquérito Demográfico e de Saúde (IDS) em Moçambique faze parte dum programa internacional de inquéritos (MEASURE DHS) desenvolvido pelo ICF International através de um contrato com a USAID, com o propósito de apoiar aos governos e instituições privadas dos países em desenvolvimento na realização de inquéritos nacionais por amostragem, nas áreas de população e saúde. O Programa MEASURE DHS tem por objectivo: • Subsidiar a formulação de políticas e implementação de programas nas áreas de população e saúde; • Aumentar a base internacional de dados sobre população e saúde para acompanhamento e avaliação; • Aprimorar metodologia de inquérito por amostragem, e • Consolidar, na área de inquérito, a capacidade técnica da instituição executora no país participante do Programa. O Programa DHS teve início em 1984 e, desde então, já foram realizados inquéritos em mais de 70 países da América Latina, Caribe, África, Ásia e Leste Europeu.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Investigação sobre Mulher e Género no Centro de Estudos Africanos - Casimiro, Isabel Maria; Adrare, Ximena (Estudos Moçambicanos, 2005)
Os estudos sobre as relações sociais entre homens e mulheres - das relações de Género - começaram a ganhar corpo a partir de finais da década de 60 os países de língua inglesa - onde foi onstruída a categoria de Género (Gender) - mas depressa se expandiram pelo mundo. Género como categoria análitica, foi e continua a ser o resultado duma interrogação feminista no sentido de esclarecer a subalternidade e subordinação das mulheres no mundo. Trata-se de uma procura que caminhou que continua a caminhar no sentido de interrogações. Não pretendem as suas criadoras feministas o esclarecimento contemplativo por si acerca da discriminação das mulheres. Moveu-as e move-as o desejo de alterar as relações desiguais entre mulheres e homens, no âmbito de construções identitárias que marcam a discriminação entre os seres humanos baseada num poder hierárquico característico do mundo em que vivemos, com o propósito de o transformar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; gender / género; institutions / instituições; ⛔ No DOI found

Neo-liberal Reforms and Illiberal Consolidations: The Indonesian Paradox - Hadiz, Vedi; Robison, Richard (Journal of Development Studies, 2005)
Market-oriented policy agendas have enjoyed a remarkable influence in Indonesia for almost four decades. Yet, attempts to impose these agendas in any systematic fashion have proven uncertain and inconclusive. This is not simply a case of successful resistance to reform by entrenched interests. Rather, the deepening of market capitalism and global integration has, in many instances, appeared to consolidate authoritarian politics and predatory economic relationships. Even in the wake of economic crisis and dramatic political change, these basic frameworks of power remain largely intact. Such paradoxes raise important questions about the relationships between markets, institutions and political and social power. We examine how market reforms have been resisted and even hijacked to consolidate predatory state and private oligarchies. We look at the way such entrenched interests have been reorganised in the face of fundamental institutional changes, including the collapse of authoritarian rule and the decentralisation of political authority.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; decentralization / descentralização; institutions / instituições

Chains of fortune: linking women producers and workers with global markets - Commonwealth Secretariat; Carr, Marilyn (2004)
Globalisation opens up new economic opportunities if poor women producers and workers are enabled to take advantage of them. The need for assistance differs between independent producers on the one hand and wage workers in export industries on the other. In the former case, the need mainly is for increased access to global markets. In the latter case, the need mainly is for better organising so as to bargain for better wages and working conditions. This edited volume brings together six case studies. Three link local producers with global markets: a cocoa cooperative in Ghana; an organic coconut oil producer in Samoa; and small enterprises in Mozambique. Three focus on improving the working conditions of wage workers in global value chains: those in the fruit exporting industry in South Africa; those in the garment export industry in Bangladesh; and those in the newly created call centres in India. Each case study is written by a team of international and national researchers and aims to present decision makers with concrete examples which can spread the gains of globalisation to the working poor through shifting the balance of access, power and returns within global value chains.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Eight Years of Multiparty Democracy in Mozambique: The Public’s View - João Pereira; Ines Raimundo; Annie Chikwanha; Alda Saute; Robert Mattes (Afrobarometer Working Papers, 2003)
Since its emergence from a brutal, 17-year civil war, Mozambique’s process of political reform has faced a number of challenges. The first has been to empower ordinary Mozambicans by allowing them to participate in a democratic system and enabling them to voice their demands to the state and hold it accountable. The second has been to rebuild a state with the capacity to respond to citizen demands effectively. And given the long history of violent division, a third challenge has been to build a state that enjoys broad legitimacy – a legitimacy that spans the bitter partisan divides of the past, enabling the formation of a strong, authoritative state with the ability to enforce the rule of law, but also the discipline to rule through transparent procedures. Perhaps the best evidence by which to judge the success of the process of political reform are the opinions of ordinary Mozambicans. Rather than looking to expert judgments or to measures of formal constitutional rights, we believe that the views of ordinary citizens – as the ultimate consumers of what democratic governments supply – can offer perhaps the most conclusive assessment of the quality of governance. What do they say? Through its partner in Mozambique, the Public Opinion Service of the Centre for Population Studies at the University of Eduardo Mondlane, the Afrobarometer surveyed a nationally representative sample of 1425 Mozambicans citizens, aged 18 years and older, using a multi-stage, area-stratified, clustered sample designed by the National Institute for Statistics. The survey was carried out between August and October 2002 in all 10 provinces of the Republic of Mozambique. At a confidence level of 95 percent, a sample of this size allows a confidence interval, or margin of error, of plus or minus 2.5 percent. This means that, had we interviewed every Mozambican, 19 times out of 20 the results would differ from those of this survey by no more than 2.5 percent. The evidence from this survey suggests that although Mozambique is plagued by what appear to be insurmountable problems, in general the country appears to be on the right path as an emerging democracy. While the society faces vast challenges of building human and social capital to empower citizens further and increase the capacity of the state, the democratization that has occurred since Mozambique opened its political space has gone a long way in propelling democracy forward.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; M - survey / inquérito; accountability / responsabilização; civil society / sociedade civil

Endangering safe motherhood in Mozambique: prenatal care as pregnancy risk - Chapman, Rachel R. (Social Science & Medicine, 2003)
Despite high infant and maternal mortality rates, many Mozambican women with access to prenatal services delay prenatal clinic consultations, limiting opportunity for prevention and treatment of preventable pregnancy complications. Ethnographic research, interviews with health providers and longitudinal pregnancy case studies with 83 women were conducted in Central Mozambique to examine pregnant women's underutilization of clinic-based prenatal services. The study found that pregnancy beliefs and prenatal practices reflect women's attempts to influence reproduction under conditions of vulnerability at multiple levels. Women reported high maternal reproductive morbidity, frequent pregnancy wastage, and immense pressure to bear children throughout their reproductive years. Reproductive vulnerability is intensified by poverty and an intense burden placed on poor, peri-urban women farmers for family subsistence and continuous fertility in a period of economic austerity, land shortages, and increasing social conflict and inequality. In this environment of economic insecurity exacerbated by congested living conditions, women report competing for scarce resources, including male support and income. This vulnerability heightens women's perceptions that they and their unborn infants will be targets of witchcraft or sorcery by jealous neighbors and kin. They respond by hiding pregnancy and delaying prenatal care. Within the context of women's perceived reproductive risks, delayed prenatal care can be seen as a strategy to protect pregnancy from purposeful human and spirit harm. Women mobilized limited resources to acquire prenatal care outside the formal clinic setting. It is concluded that provision of clinical prenatal services is insufficient to reduce reproductive risks for the most socially and economically marginal since it is their vulnerability that prevents women from using available services. Confidential maternity services and social safety nets for greater economic security are recommended.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil

Malonda – The Private Sector Support related to Agriculture in Niassa - Carlsson, Lars (SIDA - The Swedish International Development Cooperation Agency, 2003)
Information on the Swedish support to the private sector related to agriculture in Niassa, Mozambique 2003.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; poverty / pobreza; private sector / setor privado

A gender analysis of the impact of indirect taxes on small and medium enterprises in Vietnam - Akram-Lodhi, A Haroon; van Staveren, Irene (Institute of Social Studies, 2003)
This paper brings together gender analysis, small scale enterprise analysis, and gender budget analysis in a development context. The paper demonstrates that gender matters not only to the ownership of an SME, but also to its most likely principal activity, the stock of the assets that it possesses, the labour that it utilizes, the costs that it faces, the revenues that it generates, and the profits that it earns. In particular, lower earnings for female-owned SMEs can be attributed to the different input cost structures facing female and male-owned SMEs, which in turn are influenced by the indirect tax system. In this context, the paper identifies five gender biases in Vietnam’s VAT system. These biases help explain the higher costs and lower profits of female-owned SMEs in Vietnam. This explanation is different from the more common explanation given for lower performance of female owned enterprises in developing countries, which is the gender segregation of sectors. Although this also plays a role, we argue that gender biases in costs and earnings, partly caused by the tax system, are the more dominant factor.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; budget / orçamento; gender / género

Indústria e industrialização em Moçambique: análise da situação actual e linhas estratégicas de desenvolvimento - Castel-Branco, Carlos (Quaderni della Cooperazione Italiana, 2003)
Published as part of the working paper series of the Italian Cooperation. Discusses the dynamics of industrialization in the early stages of large FDI boom in Mozambique, as well as challenges ahead,
Keywords: G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA

New Rules, New Roles: Does PSP Benefit the Poor? Small-Scale Private Sector Participation in Niassa, Mozambique - Jose Atanasio David; Lindsey Breslin (Estamos organização comunitária, 2003)
This case study has attempted to show that the implementation of a policy mechanism like PSP in water and sanitation in a context like Niassa is highly unlikely to achieve the development impacts intended. It appears that the concept “PSP” itself is erroneous; it assumes that there is a private sector wishing to participate, and that public sector delivery is the key obstacle to private involvement. Equally erroneous is the idea that the private sector can just emerge from market mechanisms that are assumed to be existent. The market itself, and he relationships that typically exist within it, need to be constructed first. Niassa is an example of an extremely impoverished area where the cashpoor local economy and damaged social institutions currently could not support and sustain the emergence of a viable private sector.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; health - WASH / saúde - água, higiene e saneamento; health / saúde; private sector / setor privado

Indonesia: Managing Decentralization - Ahmad, Ehtisham; Mansoor, Ali M. (International Monetary Fund, 2002)
The process of decentralization in Indonesia was initiated after a long period of autocratic rule. Despite the political imperatives, there is a need to carefully sequence the fiscal decentralization to ensure that financing follows the assignment of functions. The functions should be commensurate with the capacity to provide public services. The paper argues for the proper sequencing to avoid jeopardizing macroeconomic stability or the effective delivery of public services.
Keywords: G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA

Agricultural supply response and poverty in Mozambique - Heltberg, R.; Tarp, F. (Food Policy, 2002)
This paper identifies key causal factors behind farmers’ marketing decisions in Mozambique. A two-step decision making process is outlined. Farmers decide, first, whether or not to participate in the market. Next, they decide how much to sell. The model is estimated using a Heckman switching regression approach. The key importance of non-price factors such as risk, technology and transport infrastructure come out clearly. Marginal effects are calculated for poor and nonpoor households and broken down into a market participation and a quantity (sales value) component. The marginal effects for the poor are not substantially different from those of the nonpoor. This suggests that differences in area-based characteristics (especially risk and technology) are more influential in the commercialization process than differences in how the poor and the nonpoor respond to incentives. Moreover, interventions to promote market access are likely to solicit a greater volume of additional supply from peasants entering the market for the first time than from existing market participants stepping up their production and sales. To achieve pro-poor rural growth it is essential to address explicitly the conditions of high-risk, low productivity and low capital endowments of poor farmers.
Keywords: G - Mozambique / Moçambique; L - english / inglês

Discovering normality in health and the reproductive body : proceedings of a workshop held at the Program of African Studies Norhtwestern University - Bledsoe, Caroline; LaRay, Denzer; Glassman, Jonathon; Schoenbrun, David; Ebeling, Mary F. E.; Hansen, Karen Tranberg (Pas, 2002)
The papers and discussions included in this collection are the product of a workshop, “Discovering Normality in Health and the Reproductive Body,” held in March, 2001 at Northwestern University's Program of African Studies. The idea for the workshop stemmed from a history of collaborations among Caroline Bledsoe, Jane Guyer, and Kuate Defo Barthélemy on topics of fertility, health, and research methodology. The workshop itself grew out of a commitment to continue that conversation and to expand it to a wider range of people and disciplines. The disciplines represented were wideranging indeed. They included sociocultural anthropology, biological anthropology, history, reproductive biology, history of medicine, public health, and obstetric medicine. The focus of the workshop was Africa, but we also included important comparative cases on South Asia and the Netherlands. In addition we have included those of the discussants' excellent and provocative comments that were available, some of the rapporteurs' notes, and a full list of the participants.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; ⛔ No DOI found

Improving Health for the Poor in Mozambique: The Fight Continues - Chao, Shiyan; Kostermans, Kees (International Bank for Reconstruction and Development / The World Bank, 2002)
The health sector in Mozambique has made significant progress in terms of increasing coverage of services. However, health remains a major concern in the area of poverty reduction. The study describes the health status of the population, especially of the poor, and how the sector responds to the needs. Huge inequalities continue to exist with regards to resource allocation, deployment of staff and availability of services among various geographic areas, between the urban and rural population, and between the poor and the non-poor. The study builds upon the existing studies on health and consolidates the sector knowledge. Based on the analysis, the study makes various recommendations on how the health sector reforms can be made more pro-poor by focusing on certain interventions, by targeting certain areas and population groups, by designing new delivery models that would bring the services closer to the population, and by improving financial management to serve the poor more effectively.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; access to services / acesso a serviços; health / saúde; poverty / pobreza

From ‘Abaixo’ to ‘chiefs of production’: Agrarian change in Nampula province, mozambique, 1975–87 - Dinerman, Alice (The Journal of Peasant Studies, 2001)
This article reconstructs key aspects of the evolving relationship between state institutions and former regulos (Portuguese‐appointed chiefs), in Nampula Province, Mozambique during the first 12 years of independence. In doing so, it simultaneously draws on and critiques two opposing interpretations of revolution and counterrevolution which have dominated scholarly production on post‐independence Mozambique and have polarized Mozambican studies in recent years. Against both sets of literature, my study finds that state socialism did not always and everywhere bring major disruptions to grassroots structures of authority; rather, many families who had been recognized by the Portuguese as royals were able, through a variety of strategies, to maintain their grip on local power. Secondly, I argue that the provincial government's enlistment of former regulos to serve as ‘chiefs of production’ was but one aspect of an attempt on the part of officialdom to recreate the most salient aspects of the colonial cotton regime rather than a war‐induced genuflection by the Frelimo regime to Renamo on the question of chiefly rule, as has been claimed by what I call ‘revisionist’ scholarship. Frelimo's refusal to acknowledge the role of villagization in agricultural decline throughout the country, a point raised and highlighted by revisionist writing is, however, crucial to understanding the ideological practices that helped justify and legitimate the return to Portuguese precedent on matters relating to rural labour. The reasons why Nampula was the site of these initiatives are explored.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; agriculture / agricultura; authority / autoridade

A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde

The Indonesian Financial Crisis: From Banking Crisis to Financial Sector Reforms, 1997-2000 - Sharma, Shalendra D. (Cornell University Press, 2001)
In mid-1998, a World Bank study grimly noted that "Indonesia is in deep economic crisis. A country that achieved decades of rapid growth, stability, and poverty reduction is now near economic collapse . . . no country in recent history, let alone one the size of Indonesia, has ever suffered such a dramatic reversal of fortune." There is bitter irony in Indonesia's fall from grace. Long hailed as a model of successful economic development, it was widely predicted to escape the fate of Thailand. Between June-August 1997, as Thailand's economy unraveled and the virulent Asian flu sent shock waves through the region, the Indonesian economy remained relatively stable—a veritable rock in the stormy sea. Even the World Bank remained upbeat about the short-term outlook, believing that a widening of the intervention band would be sufficient to ward off contagion.4 The Indonesian government, which received much praise for its swift and decisive response to the crisis, went to great lengths to assure jittery investors "that Indonesia was not Thailand." Then the unthinkable happened. Indonesia suddenly succumbed to the contagion, and, measured by the magnitude of currency depreciation and contraction of economic activity, it emerged as the most serious casualty of Asia's financial crisis. What happened? Why did Indonesia (and the other high-performing Asian economies) collapse like hollow dominoes? In the numerous post-mortems that have followed, analysts have identified a number of related factors behind the region's dramatic reversal of fortune. In the case of Indonesia, the variable that soon acquired particular salience was "crony capitalism." Initially popularized by the Economist, the term quickly took a life of its own. Soon thereafter, the distinguished MIT economist, Paul Krugman, would argue that crony capitalism lay the root of Indonesia's—and indeed, East Asia's—financial woes. Krugman describes the innerworkings and manifestations of the insidious crony capitalism in evocative prose.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; economic development / desenvolvimento económico